3.9 day orbital modulation in the TeV γ-ray flux and spectrum from the X-ray binary LS 5039 - van Eldik, Christopher; Funk, Stefan; et al. (Astronomy & Astrophysics, 2006)
Aims. LS 5039 is a High Mass X-ray Binary (HMXRB) comprising a compact object in an eccentric 3.9 day orbit around a massive O6.SV star. Observations at energies above 0.1 TeV (10 eV) by the High Energy Stereoscopic System (HESS) in 2004 revealed that LS 5039 is a source of Very High Energy (VHE) γ-rays and hence, is able to accelerate particles to multi-TeV energies. Deeper observations by HESS were carried out in 2005 in an effort to probe further the high energy astrophysics taking place. In particular, we have searched for orbital modulation of the VHE γ-ray flux, which if detected, would yield new information about the complex variation in γ-ray absorption and production within X-ray binary systems. Methods. Observations at energies above 0.1 TeV (10 eV), were carried out with the High Energy Stereoscopic System (HESS) of Cherenkov Telescopes in 2005. A timing analysis was performed on the dataset employing the Lomb-Scargle and Normalised Rayleigh statistics, and orbital phase-resolved energy spectra were obtained. Results. The timing analysis reveals a highly significant (post-trial chance probability <10 ) peak in the TeV emission periodogram at a frequency matching that of the 3.9 day orbital motion of the compact object around the massive stellar companion. This is the first time in γ-ray astronomy that orbital modulation has been observed, and periodicity clearly established using ground-based γ-ray detectors. The γ-ray emission is largely confined to half of the orbit, peaking around the inferior conjunction epoch of the compact object. Around this epoch, there is also a hardening of the energy spectrum in the energy range between 0.2 TeV and a few TeV. Conclusions. The γ-ray flux vs. orbital phase profile suggests the presence of γ-ray absorption via pair production, which would imply that a large fraction of the γ-ray production region is situated within ∼1 AU of the compact object. This source size constraint can be compared to the collimated outflows or jets observed in LS 5039 resolved down to scales of a few AU. The spectral hardening is however not explained exclusively by the absorption effect, indicating that other effects are present, perhaps related to the γ-ray production mechanism(s). If the γ-ray emission arises from accelerated electrons, the hardening may arise from variations with phase in the maximum electron energies, the dominant radiative mechanism, and/or the angular dependence in the inverse-Compton scattering cross-section. Overall, these results provide new insights into the competing γ-ray absorption and production processes in X-ray binaries. © ESO 2006.
Keywords: Acceleration of particles; Block hole physics; Gamma rays: observations; Stars: binaries: close

Acceleration of petaelectronvolt protons in the Galactic Centre - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, M.; Balzer, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; Bernhard, S.; Bernloehr, K.; et al. (Nature, 2016)
Galactic cosmic rays reach energies of at least a few petaelectronvolts(1) (of the order of 1015 electronvolts). This implies that our Galaxy contains petaelectronvolt accelerators ('PeVatrons'), but all proposed models of Galactic cosmic-ray accelerators encounter difficulties at exactly these energies(2). Dozens of Galactic accelerators capable of accelerating particles to energies of tens of teraelectronvolts (of the order of 10(13) electronvolts) were inferred from recent gamma-ray observations(3). However, none of the currently known accelerators-not even the handful of shell-type supernova remnants commonly believed to supply most Galactic cosmic rays-has shown the characteristic tracers of petaelectronvolt particles, namely, power-law spectra of.-rays extending without a cut-off or a spectral break to tens of teraelectronvolts(4). Here we report deep.-ray observations with arcminute angular resolution of the region surrounding the Galactic Centre, which show the expected tracer of the presence of petaelectronvolt protons within the central 10 parsecs of the Galaxy. We propose that the supermassive black hole Sagittarius A* is linked to this PeVatron. Sagittarius A* went through active phases in the past, as demonstrated by X-ray outbursts(5) and an outflow from the Galactic Centre(6). Although its current rate of particle acceleration is not sufficient to provide a substantial contribution to Galactic cosmic rays, Sagittarius A* could have plausibly been more active over the last 10(6)-10(7) years, and therefore should be considered as a viable alternative to supernova remnants as a source of petaelectronvolt Galactic cosmic rays.

A convolutional neural network based cascade reconstruction for the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Journal of Instrumentation, 2021)
Continued improvements on existing reconstruction methods are vital to the success of high-energy physics experiments, such as the IceCube Neutrino Observatory. In IceCube, further challenges arise as the detector is situated at the geographic South Pole where computational resources are limited. However, to perform real-time analyses and to issue alerts to telescopes around the world, powerful and fast reconstruction methods are desired. Deep neural networks can be extremely powerful, and their usage is computationally inexpensive once the networks are trained. These characteristics make a deep learning-based approach an excellent candidate for the application in IceCube. A reconstruction method based on convolutional architectures and hexagonally shaped kernels is presented. The presented method is robust towards systematic uncertainties in the simulation and has been tested on experimental data. In comparison to standard reconstruction methods in IceCube, it can improve upon the reconstruction accuracy, while reducing the time necessary to run the reconstruction by two to three orders of magnitude.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Calibration; Cluster finding; Data analysis; Fitting methods; Neutrino detectors; Pattern recognition

Active Personal Eye Lens Dosimetry with the Hybrid Pixelated Dosepix Detector - Beiser, Florian; Haag, Dennis; Ballabriga, Rafael; Behrens, Rolf; Campbell, Michael; Fuhg, Christian; Hufschmidt, Patrick; Hupe, Oliver; Kupillas, Carolin; Llopart, Xavier; Roth, Jurgen; Schmidt, Sebastian; et al. (IEEE Transactions on Radiation and Plasma Medical Sciences, 2023)
Eye lens dosimetry has been an important field of research in the last decade. Dose measurements with a prototype of an active personal eye lens dosemeter based on the Dosepix detector are presented. The personal dose equivalent at 3 mm depth of soft tissue, Hp(3), was measured in the center front of a water-filled cylinder phantom with a height and diameter of 20 cm. The energy dependence of the normalized response is investigated for mean photon energies between 12.4 keV and 248 keV for continuous reference radiation fields (N-series) according to ISO 4037. The response normalized to N-60 (E=47.9 keV) at 0∘ angle of irradiation stays within the approval limits of IEC 61526 for angles of incidence between -75∘ and +75∘. Performance in pulsed photon fields was tested for varying dose rates from 0.1 Svh up to 1000 Svh and pulse durations from 1 ms up to 10 s. The dose measurement works well within the approval limits (acc. to IEC 61526) up to 1 Svh. No significant influence of the pulse duration on the measured dose is found. Reproducibility measurements yield a coefficient of variation which does not exceed 1 % for two tested eye lens dosemeter prototypes.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Active personal dosemeter; Detectors; Dosepix; Dosimetry; dosimetry for interventional procedures; dosimetry for radiation based medical applications; eye lens dosimetry; Histograms; Lenses; Phantoms; Photonics; Prototypes; pulsed x-ray fields; radiation detectors for medical applications: semiconductors

(untitled) - van Eldik, Christopher; et al.
Aims. We present results from deep observations of the Galactic shell-type supernova remnant (SNR) RX J1713.7-3946 (also known as 0347.3-0.5) conducted with the complete HESS array in 2004. Methods. Detailed morphological and spatially resolved spectral studies reveal the very-high-energy (VHE - Energies E > 100 GeV) gamma-ray aspects of this object with unprecedented precision. Since this is the first in-depth analysis of an extended VHE gamma-ray source, we present a thorough discussion of our methodology and investigations of possible sources of systematic errors. Results. Gamma rays are detected throughout the whole SNR. The emission is found to resemble a shell structure with increased fluxes from the western and northwestern parts. The differential gamma-ray spectrum of the whole SNR is measured over more than two orders of magnitude, from 190 GeV to 40 TeV, and is rather hard with indications for a deviation from a pure power law at high energies. Spectra have also been determined for spatially separated regions of RX J1713.7-3946. The flux values vary by more than a factor of two, but no significant change in spectral shape is found. There is a striking correlation between the X-ray and the gamma-ray image. Radial profiles in both wavelength regimes reveal the same shape almost everywhere in the region of the SNR. Conclusions. The VHE gamma-ray emission of RX J1713.7-3946 is phenomenologically discussed for two scenarios, one where the gamma rays are produced by VHE electrons via Inverse Compton scattering and one where the gamma rays are due to neutral pion decay from proton-proton interactions. In conjunction with multi-wavelength considerations, the latter case is favoured. However, no decisive conclusions can yet be drawn regarding the parent particle population dominantly responsible for the gamma-ray emission from RX J1713.7-3946. © ESO 2006.

A first search for coincident gravitational waves and high energy neutrinos using LIGO, Virgo and ANTARES data from 2007 - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
We present the results of the first search for gravitational wave bursts associated with high energy neutrinos. Together, these messengers could reveal new, hidden sources that are not observed by conventional photon astronomy, particularly at high energy. Our search uses neutrinos detected by the underwater neutrino telescope ANTARES in its 5 line configuration during the period January - September 2007, which coincided with the fifth and first science runs of LIGO and Virgo, respectively. The LIGO-Virgo data were analysed for candidate gravitational-wave signals coincident in time and direction with the neutrino events. No significant coincident events were observed. We place limits on the density of joint high energy neutrino - gravitational wave emission events in the local universe, and compare them with densities of merger and core-collapse events.
Keywords: gravitational waves / experiments; neutrino astronomy

All-flavor constraints on nonstandard neutrino interactions and generalized matter potential with three years of IceCube DeepCore data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Physical Review D, 2021)
We report constraints on nonstandard neutrino interactions (NSI) from the observation of atmospheric neutrinos with IceCube, limiting all individual coupling strengths from a single dataset. Furthermore, IceCube is the first experiment to constrain flavor-violating and nonuniversal couplings simultaneously. Hypothetical NSI are generically expected to arise due to the exchange of a new heavy mediator particle. Neutrinos propagating in matter scatter off fermions in the forward direction with negligible momentum transfer. Hence the study of the matter effect on neutrinos propagating in the Earth is sensitive to NSI independently of the energy scale of new physics. We present constraints on NSI obtained with an all-flavor event sample of atmospheric neutrinos based on three years of IceCube DeepCore data. The analysis uses neutrinos arriving from all directions, with reconstructed energies between 5.6 GeV and 100 GeV. We report constraints on the individual NSI coupling strengths considered singly, allowing for complex phases in the case of flavor-violating couplings. This demonstrates that IceCube is sensitive to the full NSI flavor structure at a level competitive with limits from the global analysis of all other experiments. In addition, we investigate a generalized matter potential, whose overall scale and flavor structure are also constrained.
CRIS-Team Scopus Importer:2021-10-29

All-flavor Search for a Diffuse Flux of Cosmic Neutrinos with Nine Years of ANTARES Data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The ANTARES detector is at present the most sensitive neutrino telescope in the northern hemisphere. The highly significant cosmic neutrino excess observed by the Antarctic IceCube detector can be studied with ANTARES, exploiting its complementing field of view, exposure, and lower energy threshold. Searches for an all-flavor diffuse neutrino signal, covering nine years of ANTARES data taking, are presented in this Letter. Upward-going events are used to reduce the atmospheric muon background. This work includes for the first time in ANTARES both track-like (mainly nu mu) and shower-like (mainly nu(e)) events in this kind of analysis. Track-like events allow for an increase of the effective volume of the detector thanks to the long path traveled by muons in rock and/ or sea water. Shower-like events are well reconstructed only when the neutrino interaction vertex is close to, or inside, the instrumented volume. A mild excess of high-energy events over the expected background is observed in nine years of ANTARES data in both samples. The best fit for a single power-law cosmic neutrino spectrum, in terms of perflavor flux at 100 TeV, is Phi(1f)(0) (100 TeV) = (1.7 +/- 1.0) x 10(-18) GeV-1 cm(-2) s(-1) sr(-1) with spectral index Gamma = 2.4(-0.4)(+0.5) .The null cosmic flux assumption is rejected with a significance of 1.6 sigma .
Keywords: astroparticle physics; neutrinos

All-sky Measurement of the Anisotropy of Cosmic Rays at 10 TeV and Mapping of the Local Interstellar Magnetic Field - Abeysekara, A. U.; Alfaro, R.; Alvarez, C.; Arceo, R.; Arteaga-Velazquez, J. C.; Avila Rojas, D.; Belmont-Moreno, E.; Benzvi, S. Y.; Brisbois, C.; Capistran, T.; Carramiana, A.; Casanova, S.; et al. (Astrophysical Journal, 2019)
We present the first full-sky analysis of the cosmic ray arrival direction distribution with data collected by the High-Altitude Water Cherenkov and IceCube observatories in the northern and southern hemispheres at the same median primary particle energy of 10 TeV. The combined sky map and angular power spectrum largely eliminate biases that result from partial sky coverage and present a key to probe into the propagation properties of TeV cosmic rays through our local interstellar medium and the interaction between the interstellar and heliospheric magnetic fields. From the map, we determine the horizontal dipole components of the anisotropy δ 0h = 9.16 ×10 -4 and δ 6h = 7.25 ×10 -4 (±0.04 × 10 -4 ). In addition, we infer the direction (229.°2 ± 3.°5 R.A., 11.°4 ± 3.°0 decl.) of the interstellar magnetic field from the boundary between large-scale excess and deficit regions from which we estimate the missing corresponding vertical dipole component of the large-scale anisotropy to be δN ∼ -3.97 +1.0 -2.0 × 10 -4 .
CRIS-Team Scopus Importer:2019-05-02
Keywords: astroparticle physics; cosmic rays; ISM: magnetic fields

All-sky search for high-energy neutrinos from gravitational wave event GW170104 with the Antares neutrino telescope: The ANTARES Collaboration - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (European Physical Journal C, 2017)
Advanced LIGO detected a significant gravitational wave signal (GW170104) originating from the coalescence of two black holes during the second observation run on January 4th, 2017. Anall-sky high-energy neutrino follow-up search has been made using data from the Antares neutrino telescope, including both upgoing and downgoing events in two separate analyses. No neutrino candidates were found within +/- 500 s around the GW event time nor any time clustering of events over an extended time window of +/- 3 months. The non-detection is used to constrain isotropic-equivalent high-energy neutrino emission from GW170104 to less than similar to 1.2 x 10(55) erg for a E-2 spectrum. This constraint is valid in the energy range corresponding to the 5-95% quantiles of the neutrino flux [3.2 TeV; 3.6 PeV], if the GW emitter was below the Antares horizon at the alert time.

A low level of extragalactic background light as revealed by γ-rays from blazars - van Eldik, Christopher; et al. (Nature, 2006)
The diffuse extragalactic background light consists of the sum of the starlight emitted by galaxies through the history of the Universe, and it could also have an important contribution from the 'first stars', which may have formed before galaxy formation began. Direct measurements are difficult and not yet conclusive, owing to the large uncertainties caused by the bright foreground emission associated with zodiacal light. An alternative approach is to study the absorption features imprinted on the γ-ray spectra of distant extragalactic objects by interactions of those photons with the background light photons. Here we report the discovery of γ-ray emission from the blazars H 2356-309 and 1ES 1101-232, at redshifts z = 0.165 and z = 0.186, respectively. Their unexpectedly hard spectra provide an upper limit on the background light at optical/near-infrared wavelengths that appears to be very close to the lower limit given by the integrated light of resolved galaxies. The background flux at these wavelengths accordingly seems to be strongly dominated by the direct starlight from galaxies, thus excluding a large contribution from other sources - in particular from the first stars formed. This result also indicates that intergalactic space is more transparent to γ-rays than previously thought. © 2006 Nature Publishing Group.

A measurement of the ψ′ to J/ψ production ratio in 920 GeV proton-nucleus interactions - van Eldik, Christopher; et al. (European Physical Journal C, 2007)
Ratios of the ψ′ over the J/ψ production cross sections in the dilepton channel for C, Ti and W targets have been measured in 920 GeV proton-nucleus interactions with the HERA-B detector at the HERA storage ring. The ψ′ and J/ψ states were reconstructed in both the μμ and the ee decay modes. The measurements covered the kinematic range -0.35≤x≤0.1 with transverse momentum p≤4.5 GeV/c. The angular dependence of the ratio has been used to measure the difference of the ψ′ and J/ψ polarization. All results for the muon and electron decay channels are in good agreement: their ratio, averaged over all events, is R (μ)/R(e)=1.00±0. 08±0.04. This result constitutes a new, direct experimental constraint on the double ratio of branching fractions, (B′(μ)B(e))/(B(μ) B′(e)), of ψ′ and J/ψ in the two channels. The ψ′ to J/ψ production ratio is almost constant in the covered x range and shows a slow increase with p. © Springer-Verlag Berlin Heidelberg 2007.

A MeerKAT, e-MERLIN, HESS, and Swift search for persistent and transient emission associated with three localized FRBs - Chibueze, J. O.; Caleb, M.; Spitler, L.; Ashkar, H.; Schussler, F.; Stappers, B. W.; Venter, C.; Heywood,; Richards, A. M. S.; Williams, D. R. A.; Kramer, M.; Beswick, R.; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
We report on a search for persistent radio emission from the one-off fast radio burst (11(B) 20190714A, as well as from two repeating FRBs, 20190711A and 20171019A, using the MeerKAT radio telescope. For FRB 20171019A, we also conducted simultaneous observations with the High-Energy Stereoscopic System (H.E.S.S.) in very high-energy gamma rays and searched for signals in the ultraviolet, optical, and X-ray bands. For this FRB, we obtain a UV flux upper limit of 1.39 x 10(-16) erg cm(-2) s(-1) angstrom(-1), X-ray limit of similar to 6.6 x 10(-14) erg cm(-2) s(-1) and a limit on the very high energy gamma-ray flux Phi(E > 120 GeV) < 1.7 x 10(-12) erg cm(-2) S-1. We obtain a radio upper limit of similar to 15 mu Jy beam(-1) for persistent emission at the locations of both FRBs 20190711A and 20171019A with MeerKAT. However, we detected an almost unresolved (ratio of integrated flux to peak flux is similar to 1.7 beam) radio emission, where the synthesized beam size was similar to 8 arcsec size with a peak brightness of similar to 53 mu Jy beam(-1) at MeerKAT and similar to 86 mu Jy beam(-1) at e-MERLIN, possibly associated with FRB 20190714A at z = 0.2365. This represents the first detection of persistent continuum radio emission potentially associated with a (as-yet) non- repeating FRB. If the association is confirmed, one of the strongest remaining distinction between repeaters and non-repeaters would no longer be applicable. A parallel search for repeat bursts from these FRBs revealed no new detections down to a fluence of 0.08 Jy ms for a 1 ms duration burst.
CRIS-Team WoS Importer:2022-08-05

A method for detection of muon induced electromagnetic showers with the ANTARES detector - Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Auberth, J. J.; Baret, B.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2012)
The primary aim of ANTARES is neutrino astronomy with upward going muons created in charged current muon neutrino interactions in the detector and its surroundings. Downward going muons are background for neutrino searches. These muons are the decay products of cosmic-ray collisions in the Earth's atmosphere far above the detector. This paper presents a method to identify and count electromagnetic showers induced along atmospheric muon tracks with the ANTARES detector. The method is applied to both cosmic muon data and simulations and its applicability to the reconstruction of muon event energies is demonstrated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Electromagnetic shower identification; High energy muons; Energy reconstruction

A method to stabilise the performance of negatively fed KM3NeT photomultipliers - Adrián-Martínez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of Instrumentation, 2016)
The KM3NeT research infrastructure, currently under construction in the Mediterranean Sea, will host neutrino telescopes for the identification of neutrino sources in the Universe and for studies of the neutrino mass hierarchy. These telescopes will house hundreds of thousands of photomultiplier tubes that will have to be operated in a stable and reliable fashion. In this context, the stability of the dark counts has been investigated for photomultiplier tubes with negative high voltage on the photocathode and held in insulating support structures made of 3D printed nylon material. Small gaps between the rigid support structure and the photomultiplier tubes in the presence of electric fields can lead to discharges that produce dark count rates that are highly variable. A solution was found by applying the same insulating varnish as used for the high voltage bases directly to the outside of the photomultiplier tubes. This transparent conformal coating provides a convenient and inexpensive method of insulation.
Keywords: Instrument optimization; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (gas) (gas-photocathodes; solid-photocathodes)

A multi-PMT optical module for the IceCube upgrade - Dorn, Christian; Kossatz, M.; Kretzschmann, A.; Ortjohann, H. W.; Reubelt, Jonas; Sulanke, K. H.; Weigel, Robert; Classen, Lew; Kappes, Alexander; Karg, Timo (Proceedings of Science, 2019)
Following the first observation of an astrophysical high-energy neutrino flux with the IceCube Neutrino Observatory in 2013 and the identification of a first cosmic high-energy neutrino source in 2017, the detector will be upgraded with about 700 new advanced optical sensors. This will expand IceCube's capabilities both at low and high neutrino energies. A large fraction of the upgrade modules will be multi-PMT Digital Optical Modules, mDOMs, each featuring 24 three-inch class photomultiplier tubes (PMTs) pointing uniformly in all directions, thereby providing an almost homogeneous angular coverage. The signal from each PMT is digitized individually, providing directional information for the incident photons. Together, the 24 PMTs provide an effective photosensitive area more than twice than that of the current IceCube optical module. The main mDOM design challenges arise from the constraints on the module size and power needed for the 24-channel high-voltage and readout systems. This contribution presents an mDOM design that meets these challenges and discusses the sensitivities expected from these modules.
CRIS-Team Scopus Importer:2021-04-20

A muon-track reconstruction exploiting stochastic losses for large-scale Cherenkov detectors - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Journal of Instrumentation, 2021)
IceCube is a cubic-kilometer Cherenkov telescope operating at the South Pole. The main goal of IceCube is the detection of astrophysical neutrinos and the identification of their sources. High-energy muon neutrinos are observed via the secondary muons produced in charge current interactions with nuclei in the ice. Currently, the best performing muon track directional reconstruction is based on a maximum likelihood method using the arrival time distribution of Cherenkov photons registered by the experiment's photomultipliers. A known systematic shortcoming of the prevailing method is to assume a continuous energy loss along the muon track. However at energies >1 TeV the light yield from muons is dominated by stochastic showers. This paper discusses a generalized ansatz where the expected arrival time distribution is parametrized by a stochastic muon energy loss pattern. This more realistic parametrization of the loss profile leads to an improvement of the muon angular resolution of up to 20% for through-going tracks and up to a factor 2 for starting tracks over existing algorithms. Additionally, the procedure to estimate the directional reconstruction uncertainty has been improved to be more robust against numerical errors.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Cherenkov detectors; Data analysis; Neutrino detectors

An algorithm for the reconstruction of high-energy neutrino-induced particle showers and its application to the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (European Physical Journal C, 2017)
A novel algorithm to reconstruct neutrino-induced particle showers within the ANTARES neutrino telescope is presented. The method achieves a median angular resolution of 6. for shower energies below 100TeV. Applying this algorithm to 6 years of data taken with theANTARES detector, 8 events with reconstructed shower energies above 10TeV are observed. This is consistent with the expectation of about 5 events from atmospheric backgrounds, but also compatible with diffuse astrophysical flux measurements by the IceCube collaboration, from which 2-4 additional events are expected. A 90% C.L. upper limit on the diffuse astrophysical neutrino flux with a value per neutrino flavour of E-2.Phi(90%) = 4.9 . 10(-8) GeV.cm(-2).s(-1).sr(-1) is set, applicable to the energy range from 23TeV to 7.8PeV, assuming an unbroken E-2 spectrum and neutrino flavour equipartition at Earth.

An Algorithm for the Reconstruction of Neutrino-induced Showers in the ANTARES Neutrino Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astronomical Journal, 2017)
Muons created by nu(mu) charged current (CC) interactions in the water surrounding the ANTARES neutrino telescope have been almost exclusively used so far in searches for cosmic neutrino sources. Due to their long range, highly energetic muons inducing Cherenkov radiation in the water are reconstructed with dedicated algorithms that allow for the determination of the parent neutrino direction with a median angular resolution of about 0 degrees.4 for an E-2 neutrino spectrum. In this paper, an algorithm optimized for accurate reconstruction of energy and direction of shower events in the ANTARES detector is presented. Hadronic showers of electrically charged particles are produced by the disintegration of the nucleus both in CC and neutral current interactions of neutrinos in water. In addition, electromagnetic showers result from the CC interactions of electron neutrinos while the decay of a tau lepton produced in nu(tau) CC interactions will, in most cases, lead to either a hadronic or an electromagnetic shower. A shower can be approximated as a point source of photons. With the presented method, the shower position is reconstructed with a precision of about 1 m; the neutrino direction is reconstructed with a median angular resolution between 2 degrees and 3 degrees in the energy range of 1-1000 TeV. In this energy interval, the uncertainty on the reconstructed neutrino energy is about 5%-10%. The increase in the detector sensitivity due to the use of additional information from shower events in the searches for a cosmic neutrino flux is also presented.
Keywords: neutrinos; telescopes

Analysis of the angular dependence of time delay in gravitational lensing - Domi, Alba; et al. (Symmetry, 2018)
Keywords: Classical general relativity; Gravitational lenses; Time delay

Analysis of the HESS public data release with ctools - Knodlseder, J.; Tibaldo, L.; Tiziani, Domenico; Specovius, Andreas; Cardenzana, J.; Mayer, M.; Kelley-Hoskins, N.; Di Venere, L.; Bonnefoy, S.; Ziegler, A.; Eschbach, Stefan; Martin, P.; et al. (Astronomy & Astrophysics, 2019)
The ctools open-source software package was developed for the scientific analysis of astronomical data from Imaging Air Cherenkov Telescopes (IACTs), such as H.E.S.S., VERITAS, MAGIC, and the future Cherenkov Telescope Array (CTA). To date, the software has been mainly tested using simulated CTA data; however, upon the public release of a small set of H.E.S.S. observations of the Crab nebula, MSH 15-52, RX J1713.7-3946, and PKS 2155-304 validation using real data is now possible. We analysed the data of the H.E.S.S. public data release using ctools version 1.6 and compared our results to those published by the H.E.S.S. Collaboration for the respective sources. We developed a parametric background model that satisfactorily describes the expected background rate as a function of reconstructed energy and direction for each observation. We used that model, and tested all analysis methods that are supported by ctools, including novel unbinned and joint or stacked binned analyses of the measured event energies and reconstructed directions, and classical On-Off analysis methods that are comparable to those used by the H.E.S.S. Collaboration. For all analysis methods, we found a good agreement between the ctools results and the H.E.S.S. Collaboration publications considering that they are not always directly comparable due to differences in the datatsets and event processing software. We also performed a joint analysis of H.E.S.S. and Fermi-LAT data of the Crab nebula, illustrating the multi-wavelength capacity of ctools. The joint Crab nebula spectrum is compatible with published literature values within the systematic uncertainties. We conclude that the ctools software is mature for the analysis of data from existing IACTs, as well as from the upcoming CTA.
CRIS-Team WoS Importer:2020-01-03

A new SNR with TeV shell-type morphology: HESS J1731-347 - Abramowski, A.; Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2011)
Aims. The recent discovery of the radio shell-type supernova remnant (SNR), G353.6-0.7, in spatial coincidence with the unidentified TeV source HESS J1731-347 has motivated further observations of the source with the High Energy Stereoscopic System (HESS) Cherenkov telescope array to test a possible association of the γ-ray emission with the SNR. Methods. With a total of 59 h of observation, representing about four times the initial exposure available in the discovery paper of HESS J1731-347, the γ-ray morphology is investigated and compared with the radio morphology. An estimate of the distance is derived by comparing the interstellar absorption derived from X-rays and the one obtained from CO and HI observations. Results. The deeper γ-ray observation of the source has revealed a large shell-type structure with similar position and extension (r ∼ 0.25°) as the radio SNR, thus confirming their association. By accounting for the HESS angular resolution and projection effects within a simple shell model, the radial profile is compatible with a thin, spatially unresolved, rim. Together with RX J1713.7-3946, RX J0852.0-4622 and SN 1006, HESS J1731-347 is now the fourth SNR with a significant shell morphology at TeV energies. The derived lower limit on the distance of the SNR of 3.2 kpc is used together with radio and X-ray data to discuss the possible origin of the γ-ray emission, either via inverse Compton scattering of electrons or the decay of neutral pions resulting from proton-proton interaction. © 2011 ESO.
Keywords: Astroparticle physics; Cosmic rays; ISM: supernova remnants

An exceptional very high energy gamma-ray flare of PKS 2155-304 - van Eldik, Christopher; Funk, Stefan; et al. (Astrophysical Journal, 2007)
The high-frequency peaked BL Lac PKS 2155-304 at redshift z = 0.116 is a well-known VHE (>100 GeV) γ-ray emitter. Since 2002 its VHE flux has been monitored using the H.E.S.S. stereoscopic array of imaging atmospheric Cerenkov telescopes in Namibia. During the 2006 July dark period, the average VHE flux was measured to be more than 10 times typical values observed from the object. This article focuses solely on an extreme γ-ray outburst detected in the early hours of 2006 July 28 (MJD 53,944). The average flux observed during this outburst is I(>200 GeV) = (1.72 ± 0.05 ±0.34) × 10 cm s , corresponding to ∼7 times the flux, I(>200 GeV), observed from the Crab Nebula. Peak fluxes are measured with 1 minute timescale resolution at more than twice this average value. Variability is seen up to ∼600 s in the Fourier power spectrum, and well-resolved bursts varying on timescales of ∼200 s are observed. There are no strong indications for spectral variability within the data. Assuming the emission region has a size comparable to the Schwarzschild radius of a ∼10 M black hole, Doppler factors greater than 100 are required to accommodate the observed variability timescales. © 2007. The American Astronomical Society. All rights reserved.
Keywords: BL lacertae objects: individual (PKS 2155-304); Galaxies: active; Gamma rays: observations

A next-generation optical sensor for IceCube-Gen2 - Ishihara, Aya; Shimizu, Nobuhiro; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; et al. (Proceedings of Science, 2022)
For the in-ice component of the next generation neutrino observatory at the South Pole, IceCubeGen2, a new sensor module is being developed, which is an evolution of the D-Egg and mDOM sensors developed for the IceCube Upgrade. The sensor design features up to 18 4-inch PMTs distributed homogeneously in a borosilicate glass pressure vessel. Challenges arise for the mechanical design from the tight constraints on the bore hole diameter (which will be 2 inches smaller than for IceCube Upgrade) and from the close packing of the PMTs. The electronics design must meet the space constraints posed by the mechanical design as well as the power consumption and cost considerations from over 10,000 optical modules being deployed. This contribution presents forward-looking solutions to these design considerations. Prototype modules will be installed and integrated in the IceCube Upgrade.
CRIS-Team Scopus Importer:2023-08-15

Angular distributions of leptons from J/ψ's produced in 920 GeV fixed-target proton-nucleus collisions - Abt, I.; Adams, M.; Agari, M.; Albrecht, H.; Aleksandrov, A.; Amaral, Vasco; Amorim, Antonio; Aplin, S. J.; Aushev, Volodymyr; Bagaturia, Y.; Balagura, V.; Bargiotti, M.; et al. (European Physical Journal C, 2009)
A study of the angular distributions of leptons from decays of J/ψ's produced in p-C and p-W collisions at sqrts=41.6∼GeV has been performed in the J/ψ Feynman-x region -0.341 GeV/c a significant dependence on the reference frame is found: the polar anisotropy is more pronounced in the Collins-Soper frame and almost vanishes in the helicity frame, where, instead, a significant azimuthal anisotropy arises. © 2009 Springer-Verlag / Società Italiana di Fisica.

An improved muon track reconstruction for IceCube - Bradascio, Federica; Glüsenkamp, Thorsten (Proceedings of Science, 2019)
IceCube is a cubic-kilometer Cherenkov telescope operating at the South Pole. One of its main objectives is to detect astrophysical neutrinos and identify their sources. High-energy muon neutrinos are identified through the secondary muons produced via charge current interactions with the ice. The present best-performing directional reconstruction of the muon track is a maximum likelihood method which uses the arrival time distribution of Cherenkov photons registered by the experiment's photomultipliers. A known systematic shortcoming of the prevailing method is to assume a continuous energy loss along the muon track. This contribution discusses a generalized Ansatz where the expected arrival time distribution is parametrized by a stochastic muon energy loss pattern. This more realistic parametrization of the muon energy loss profile leads to an improvement of about 20% to the muon angular resolution of IceCube.
CRIS-Team Scopus Importer:2021-04-20

ANTARES constrains a blazar origin of two IceCube PeV neutrino events - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astronomy & Astrophysics, 2015)
Results. Both blazars predicted to be the most neutrino-bright in the TANAMI sample (1653-329 and 1714-336) have a signal flux fitted by the likelihood analysis corresponding to approximately one event. This observation is consistent with the blazar-origin hypothesis of the IceCube event IC 14 for a broad range of blazar spectra, although an atmospheric origin cannot be excluded. No ANTARES events are observed from any of the other four blazars, including the three associated with IceCube event IC20. This excludes at a 90% confidence level the possibility that this event was produced by these blazars unless the neutrino spectrum is flatter than -2.4.
Keywords: neutrinos; galaxies: active; quasars: general

ANTARES Neutrino Search for Time and Space Correlations with IceCube High-energy Neutrino Events - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal, 2019)
In past years the IceCube Collaboration has reported the observation of astrophysical high-energy neutrino events in several analyses. Despite compelling evidence for the first identification of a neutrino source, TXS 0506+056, the origin of the majority of these events is still unknown. In this paper, we search for a possible transient origin of the IceCube astrophysical events using neutrino events detected by the ANTARES telescope. The arrival time and direction of 6894 track-like and 160 shower-like events detected over 2346 days of livetime are examined to search for coincidences with 54 IceCube high-energy track-like neutrino events, by means of a maximum likelihood method. No significant correlation is observed and upper limits on the one-flavor neutrino fluence from the direction of the IceCube candidates are derived. The nonobservation of time and space correlation within the time window of 0.1 days with the two most energetic IceCube events constrains the spectral index of a possible point-like transient neutrino source to be harder than -2.3 and -2.4 for each event, respectively.
CRIS-Team WoS Importer:2019-07-26

ANTARES Search for Point Sources of Neutrinos Using Astrophysical Catalogs: A Likelihood Analysis - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal, 2021)
A search for astrophysical pointlike neutrino sources using the data collected by the ANTARES detector between 2007 January 29 and 2017 December 31 is presented. A likelihood method is used to assess the significance of an excess of muon neutrinos inducing track-like events in correlation with the location of a list of possible sources. Different sets of objects are tested in the analysis: (a) a subsample of the Fermi 3LAC catalog of blazars, (b) a jet-obscured population of active galactic nuclei, (c) a sample of hard X-ray selected radio galaxies, (d) a star-forming galaxy catalog, and (e) a public sample of 56 very-high-energy track events from the IceCube experiment. None of the tested sources shows a significant association with the sample of neutrinos detected by ANTARES. The smallest p-value is obtained for the catalog of radio galaxies with an equal-weights hypothesis, with a pre-trial p-value equivalent to a 2.8 sigma excess, which is equivalent to 1.6 sigma post-trial. In addition, the results of a dedicated analysis for the blazar MG3 J225517+2409 are also reported: this source is found to be the most significant within the Fermi 3LAC sample, with five ANTARES events located less than one degree from the source. This blazar showed evidence of flaring activity in Fermi data, in spacetime coincidence with a high-energy track detected by IceCube. An a posteriori significance of 2.6 sigma for the combination of ANTARES and IceCube data is reported.
CRIS-Team WoS Importer:2021-04-30

ANTARES upper limits on the multi-TeV neutrino emission from the GRBs detected by IACTs - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
The first gamma-ray burst detections by Imaging Atmospheric Cherenkov Telescopes have been recently announced: GRB 190114C, detected by MAGIC, GRB 180720B and GRB 190829A, observed by H.E.S.S. A dedicated search for neutrinos in space and time coincidence with the gamma-ray emission observed by IACTs has been performed using ANTARES data. The search covers both the prompt and afterglow phases, yielding no neutrinos in coincidence with the three GRBs studied. Upper limits on the energetics of the neutrino emission are inferred. The resulting upper limits are several orders of magnitude above the observed gamma-ray emission, and they do not allow to constrain the available models.
CRIS-Team Scopus Importer:2021-04-16

A phase-sampling method for an X-ray Talbot-Lau scanner with continuous grating movement - Ludwig, Veronika; Akstaller, Bernhard; Schuster, Max; Seifert, Maria; Wolf, Andreas; Michel, Thilo; Anton, Gisela (Journal of Instrumentation, 2020)
A Talbot-Lau scanner enables fast grating-based X-ray phase-contrast and dark-field imaging of large samples. We present a fast and robust scanning method based on continuous phase-sampling during the usual scan process. For that purpose the source grating is moved back and forth during the whole image acquisition procedure. The scanning method needs no specific detuning of the interferometer. The acquired images are compared to the results of a standard phase-stepping procedure. We show that high quality images are obtained by this continuous phase-sampling scanning method. One main advantage of the method is its independence of the occurring moir'e pattern shape, thus enabling an optimal alignment of the interferometer. Furthermore, the method works with a priori unknown phase-step positions. To our knowledge, this is the first time a grating is moved continuously back and forth while also the sample is in linear motion during a continuous image acquisition in Talbot-Lau imaging.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Data acquisition concepts; Inspection with x-rays; X-ray radiography and digital radiography (DR)

A pointing solution for the medium size telescopes for the Cherenkov telescope array - Tiziani, Domenico; Garczarczyk, M.; Oakes, L.; Schwanke, U.; van Eldik, Christopher (6th International Symposium on High Energy Gamma-Ray Astronomy, 2017)
An important aspect of the calibration of the Cherenkov Telescope Array is the pointing, which enables an exact alignment of each telescope and therefore allows to transform a position in the sky to a point in the plane of the Cherenkov camera and vice versa. The favoured approach for the pointing calibration of the medium size telescopes (MST) is the installation of an optical CCD-camera in the dish of the telescope that captures the position of the Cherenkov camera and of the stars in the night sky simultaneously during data taking. The adaption of this approach is presented in this proceeding.

A polarized fast radio burst at low Galactic latitude - Petroff, E.; Burke-Spolaor, S.; Keane, E. F.; Mclaughlin, M. A.; Miller, R.; Andreoni, I.; Bailes, Matthew; Barr, E. D.; Bernard, S. R.; Bhandari, S.; Bhat, N. D. R.; Burgay, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the discovery of a new fast radio burst (FRB), FRB 150215, with the Parkes radio telescope on 2015 February 15. The burst was detected in real time with a dispersion measure (DM) of 1105.6 +/- 0.8 pc cm(-3), a pulse duration of 2.8(-0.5)(+1.2) ms, and a measured peak flux density assuming that the burst was at beam centre of 0.7(-0.1)(+0.2) Jy. The FRB originated at a Galactic longitude and latitude of 24.66 degrees, 5.28 degrees and 25 degrees away from the Galactic Center. The burst was found to be 43 +/- 5 per cent linearly polarized with a rotation measure (RM) in the range -9 < RM < 12 rad m(-2) (95 per cent confidence level), consistent with zero. The burst was followed up with 11 telescopes to search for radio, optical, X-ray, gamma-ray and neutrino emission. Neither transient nor variable emission was found to be associated with the burst and no repeat pulses have been observed in 17.25 h of observing. The sightline to the burst is close to the Galactic plane and the observed physical properties of FRB 150215 demonstrate the existence of sight lines of anomalously low RM for a given electron column density. The Galactic RM foreground may approach a null value due to magnetic field reversals along the line of sight, a decreased total electron column density from the Milky Way, or some combination of these effects. A lower Galactic DM contribution might explain why this burst was detectable whereas previous searches at low latitude have had lower detection rates than those out of the plane.
Keywords: polarization; methods: data analysis; surveys; ISM: structure

Architecture and performance of the KM3NeT front-end firmware - Aiello, Sebastiano; Domi, Alba; Albert, Arnauld; Garre, Sergio Alves; Aly, Zineb; Ameli, Fabrizio; Andre, Michel; Androulakis, Giorgos; Anghinolfi, Marco; Anguita, Mancia; Anton, Gisela; Ardid, Miquel; et al. (Journal of Astronomical Telescopes, Instruments, and Systems, 2021)
The KM3NeT infrastructure consists of two deep-sea neutrino telescopes being deployed in the Mediterranean Sea. The telescopes will detect extraterrestrial and atmospheric neutrinos by means of the incident photons induced by the passage of relativistic charged particles through the seawater as a consequence of a neutrino interaction. The telescopes are configured in a three-dimensional grid of digital optical modules, each hosting 31 photomultipliers. The photomultiplier signals produced by the incident Cherenkov photons are converted into digital information consisting of the integrated pulse duration and the time at which it surpasses a chosen threshold. The digitization is done by means of time to digital converters (TDCs) embedded in the field programmable gate array of the central logic board. Subsequently, a state machine formats the acquired data for its transmission to shore. We present the architecture and performance of the front-end firmware consisting of the TDCs and the state machine.
CRIS-Team Scopus Importer:2021-04-16
Keywords: acquisition firmware; KM3NeT; neutrino telescope; time to digital converters

A search for a dark matter annihilation signal toward the Canis major overdensity with H.E.S.S. - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, V.; Borrel, V.; Braun, Isabel V; Brion, E.; et al. (Astrophysical Journal, 2009)
A search for a dark matter (DM) annihilation signal into γ-rays toward the direction of the Canis Major (CMa) overdensity is presented. The nature of CMa is still controversial and one scenario represents it as a dwarf galaxy, making it an interesting candidate for DM annihilation searches. A total of 9.6 hr of high-quality data were collected with the H.E.S.S. array of Imaging Atmospheric Cherenkov Telescopes, and no evidence for a very high energy γ-ray signal is found. Upper limits on the CMa dwarf galaxy mass of the order of 10 M are derived at the 95% confidence level (CL) assuming neutralino masses in the range 500 GeV-10 TeV and relatively large annihilation cross sections. Constraints on the velocity-weighted annihilation cross section 〈σv〉 are calculated for specific weakly interacting massive-particle scenarios, using a Navarro-Frenk-White model for the DM halo profile and taking advantage of numerical simulations of hierarchical structure formation. Assuming a total halo mass of 3 × 10 M, 95% CL exclusion limits of the order of 5 × 10 cm s are reached in the 500 GeV-10 TeV DM particle mass interval. © 2009. The American Astronomical Society. All rights reserved..
Keywords: dark matter; galaxies: dwarf; gamma rays: observations

A Search for Cosmic Neutrino and Gamma-Ray Emitting Transients in 7.3 yr of ANTARES and Fermi LAT Data - Solares, H. A. Ayala; Cowen, D. F.; Delaunay, J. J.; Fox, D. B.; Keivani, A.; Mostafa, M.; Murase, K.; Turley, C. F.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; et al. (Astrophysical Journal, 2019)
We analyze 7.3 yr of ANTARES high-energy neutrino and Fermi Large Area Telescope (LAT) gamma-ray data in search of cosmic neutrino + gamma-ray (nu + gamma) transient sources or source populations. Our analysis has the potential to detect either individual nu + gamma transient sources (durations delta t less than or similar to 1000 s), if they exhibit sufficient gamma-ray or neutrino multiplicity, or a statistical excess of nu + gamma transients of individually lower multiplicities. Individual high gamma-ray multiplicity events could be produced, for example, by a single ANTARES neutrino in coincidence with a LAT-detected gamma-ray burst. Treating ANTARES track and cascade event types separately, we establish detection thresholds by Monte Carlo scrambling of the neutrino data, and determine our analysis sensitivity by signal injection against these scrambled data sets. We find our analysis is sensitive to nu + gamma transient populations responsible for >5% of the observed gamma-coincident neutrinos in the track data at 90% confidence. Applying our analysis to the unscrambled data reveals no individual nu + gamma events of high significance; two ANTARES track + Fermi gamma-ray events are identified that exceed a once per decade false alarm rate threshold (p = 17%). No evidence for subthreshold nu + gamma source populations is found among the track (p = 39%) or cascade (p = 60%) events. Exploring a possible correlation of high-energy neutrino directions with Fermi gamma-ray sky brightness identified in previous work yields no added support for this correlation. While TXS.0506+056, a blazar and variable (nontransient) Fermi gamma-ray source, has recently been identified as the first source of high-energy neutrinos, the challenges in reconciling observations of the Fermi gamma-ray sky, the IceCube high-energy cosmic neutrinos, and ultrahigh-energy cosmic rays using only blazars suggest a significant contribution by other source populations. Searches for transient sources of high-energy neutrinos thus remain interesting, with the potential for either neutrino clustering or multimessenger coincidence searches to lead to discovery of the first nu + gamma transients.
CRIS-Team WoS Importer:2020-01-03

A search for cosmogenic neutrinos with the ARIANNA test bed using 4.5 years of data - Anker, A.; Barwick, S. W.; Bernhoff, H.; Besson, D. Z.; Bingefors, N.; Garcia-Fernandez, D.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hanson, J. C.; Klein, S. R.; Kleinfelder, S. A.; et al. (Journal of Cosmology and Astroparticle Physics, 2020)
The primary mission of the ARIANNA ultra-high energy neutrino telescope is to uncover astrophysical sources of neutrinos with energies greater than 1016 eV. A pilot array, consisting of seven ARIANNA stations located on the surface of the Ross Ice Shelf in Antarctica, was commissioned in November 2014. We report on the search for astrophysical neutrinos using data collected between November 2014 and February 2019. A straight-forward template matching analysis yielded no neutrino candidates, with a signal efficiency of 79%. We find a 90% confidence upper limit on the diffuse neutrino flux of E2Φ=1.7× 10-6 GeV cm-2s-1sr-1 for a decade wide logarithmic bin centered at a neutrino energy of 1018,eV, which is an order of magnitude improvement compared to the previous limit reported by the ARIANNA collaboration. The ARIANNA stations, including purpose built cosmic-ray stations at the Moore's Bay site and demonstrator stations at the South Pole, have operated reliably. Sustained operation at two distinct sites confirms that the flexible and adaptable architecture can be deployed in any deep ice, radio quiet environment. We show that the scientific capabilities, technical innovations, and logistical requirements of ARIANNA are sufficiently well understood to serve as the basis for large area radio-based neutrino telescope with a wide field-of-view.
CRIS-Team Scopus Importer:2020-05-12

A Search for IceCube Events in the Direction of ANITA Neutrino Candidates - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguëlles, C.; et al. (Astrophysical Journal, 2020)
During the first three flights of the Antarctic Impulsive Transient Antenna (ANITA) experiment, the collaboration detected several neutrino candidates. Two of these candidate events were consistent with an ultra-high-energy upgoing air shower and compatible with a tau neutrino interpretation. A third neutrino candidate event was detected in a search for Askaryan radiation in the Antarctic ice, although it is also consistent with the background expectation. The inferred emergence angle of the first two events is in tension with IceCube and ANITA limits on isotropic cosmogenic neutrino fluxes. Here we test the hypothesis that these events are astrophysical in origin, possibly caused by a point source in the reconstructed direction. Given that any ultra-high-energy tau neutrino flux traversing the Earth should be accompanied by a secondary flux in the TeV-PeV range, we search for these secondary counterparts in 7 yr of IceCube data using three complementary approaches. In the absence of any significant detection, we set upper limits on the neutrino flux from potential point sources. We compare these limits to ANITA's sensitivity in the same direction and show that an astrophysical explanation of these anomalous events under standard model assumptions is severely constrained regardless of source spectrum.
CRIS-Team Scopus Importer:2020-05-15

A search for neutrino emission from the Fermi bubbles with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Barrios-Marti, J.; Basa, S.; et al. (European Physical Journal C, 2014)
Analysis of the Fermi-LAT data has revealed two extended structures above and below the Galactic Centre emitting gamma rays with a hard spectrum, the so-called Fermi bubbles. Hadronic models attempting to explain the origin of the Fermi bubbles predict the emission of high-energy neutrinos and gamma rays with similar fluxes. The ANTARES detector, a neutrino telescope located in the Mediterranean Sea, has a good visibility to the Fermi bubble regions. Using data collected from 2008 to 2011 no statistically significant excess of events is observed and therefore upper limits on the neutrino flux in TeV range from the Fermi bubbles are derived for various assumed energy cutoffs of the source.

A search for neutrino point-source populations in 7 yr of icecube data with neutrino-count statistics - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Astrophysical Journal, 2020)
The presence of a population of point sources in a data set modifies the underlying neutrino-count statistics from the Poisson distribution. This deviation can be exactly quantified using the non-Poissonian template fitting technique, and in this work we present the first application of this approach to the IceCube high-energy neutrino data set. Using this method, we search in 7 yr of IceCube data for point-source populations correlated with the disk of the Milky Way, the Fermi bubbles, the Schlegel, Finkbeiner, and Davis dust map, or with the isotropic extragalactic sky. No evidence for such a population is found in the data using this technique, and in the absence of a signal, we establish constraints on population models with source-count distribution functions that can be described by a power law with a single break. The derived limits can be interpreted in the context of many possible source classes. In order to enhance the flexibility of the results, we publish the full posterior from our analysis, which can be used to establish limits on specific population models that would contribute to the observed IceCube neutrino flux.
CRIS-Team Scopus Importer:2020-06-02

A search for new supernova remnant shells in the Galactic plane with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
A search for new supernova remnants (SNRs) has been conducted using TeV gamma-ray data from the H.E.S.S. Galactic plane survey. As an identification criterion, shell morphologies that are characteristic for known resolved TeV SNRs have been used. Three new SNR candidates were identified in the H.E.S.S. data set with this method. Extensive multiwavelength searches for counterparts were conducted. A radio SNR candidate has been identified to be a counterpart to HESS J1534-571. The TeV source is therefore classified as a SNR. For the other two sources, HESS J1614-518 and HESS J1912 + 101, no identifying counterparts have been found, thus they remain SNR candidates for the time being. TeV-emitting SNRs are key objects in the context of identifying the accelerators of Galactic cosmic rays. The TeV emission of the relativistic particles in the new sources is examined in view of possible leptonic and hadronic emission scenarios, taking the current multiwavelength knowledge into account.
CRIS-Team WoS Importer:2020-01-15

A search for Secluded Dark Matter in the Sun with the ANTARES neutrino telescope - Adrián-Martínez, S.; Albert, A.; André, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
A search for Secluded Dark Matter annihilation in the Sun using 2007-2012 data of the ANTARES neutrino telescope is presented. Three different cases are considered: a) detection of dimuons that result from the decay of the mediator, or neutrino detection from: b) mediator that decays into a dimuon and, in turn, into neutrinos, and c) mediator that decays directly into neutrinos. As no significant excess over background is observed, constraints are derived on the dark matter mass and the lifetime of the mediator.
Keywords: dark matter detectors; dark matter experiments; neutrino astronomy; neutrino detectors

Atmospheric neutrinos detected with the first KM3Net detection units of ARCA and ORCA - Coniglione, Rosa; Hofestädt, Jannik; Sinopoulou, Anna; Tzamariudaki, Ekaterini; Zaborov, Dmitry (Proceedings of Science, 2019)
KM3NeT is constructing two next-generation underwater Cherenkov detectors in the deep Mediterranean Sea. The ARCA detector is optimised for TeV-PeV neutrino astronomy, and the smaller and more-densely instrumented ORCA detector is optimised for oscillation research with few-GeV atmospheric neutrinos. The first detection units of both ARCA as well as ORCA have been deployed and are taking data. In this contribution, an analysis to detect atmospheric neutrinos in the first data of a single detection unit of ORCA and two detection units of ARCA is presented. With ORCA, a sample of 77 neutrino candidates in 125.3 days of livetime is extracted. A good agreement with expectations from Monte-Carlo simulations is found. With ARCA, 6 neutrino candidates are identified in 53.2 days of livetime.
CRIS-Team Scopus Importer:2021-04-20

A unified perspective on modified Poisson likelihoods for limited Monte Carlo data - Glüsenkamp, Thorsten (Journal of Instrumentation, 2020)
Counting experiments often rely on Monte Carlo simulations for predictions of Poisson expectations. The accompanying uncertainty from the finite Monte Carlo sample size can be incorporated into parameter estimation by modifying the Poisson likelihood. We first review previous frequentist methods of this type by Barlow et al, Bohm et al, and Chirkin, as well as recently proposed probabilistic methods by the author and Argüelles et al. We show that all these approaches can be understood in a unified way: they all approximate the underlying probability distribution of the sum of weights in a given bin, the compound Poisson distribution (CPD). The Probabilistic methods marginalize the Poisson mean with a distribution that approximates the CPD, while the frequentist counterparts optimize the same integrand treating the mean as a nuisance parameter. With this viewpoint we can motivate three new probabilistic likelihoods based on generalized gamma-Poisson mixture distributions which we derive in analytic form. Afterwards, we test old and new formulas in different parameter estimation settings consisting of a "background" and "signal" dataset. The probablistic counterpart to the Ansatz by Barlow et al. outperforms all other existing approaches in various scenarios. We further find a surprising outcome: usage of the exact CPD is actually bad for parameter estimation. A continuous approximation performs much better and in principle allows to perform bias-free inference at any level of simulated livetime if the first two moments of the CPD of each dataset are known exactly. Finally, we also discuss the situation where new Monte Carlo simulation is produced for a given parameter choice which leads to fluctuations in the computed likelihood value. Two of the new formulas allow to include this Poisson uncertainty directly into the likelihood which substantially decreases these fluctuations.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Analysis and statistical methods; Data analysis; Data Processing

A very-high-energy component deep in the γ-ray burst afterglow - Abdalla, H.; Adam, R.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Barnard, M.; et al. (Nature, 2019)
Gamma-ray bursts (GRBs) are brief flashes of γ-rays and are considered to be the most energetic explosive phenomena in the Universe1. The emission from GRBs comprises a short (typically tens of seconds) and bright prompt emission, followed by a much longer afterglow phase. During the afterglow phase, the shocked outflow—produced by the interaction between the ejected matter and the circumburst medium—slows down, and a gradual decrease in brightness is observed2. GRBs typically emit most of their energy via γ-rays with energies in the kiloelectronvolt-to-megaelectronvolt range, but a few photons with energies of tens of gigaelectronvolts have been detected by space-based instruments3. However, the origins of such high-energy (above one gigaelectronvolt) photons and the presence of very-high-energy (more than 100 gigaelectronvolts) emission have remained elusive4. Here we report observations of very-high-energy emission in the bright GRB 180720B deep in the GRB afterglow—ten hours after the end of the prompt emission phase, when the X-ray flux had already decayed by four orders of magnitude. Two possible explanations exist for the observed radiation: inverse Compton emission and synchrotron emission of ultrarelativistic electrons. Our observations show that the energy fluxes in the X-ray and γ-ray range and their photon indices remain comparable to each other throughout the afterglow. This discovery places distinct constraints on the GRB environment for both emission mechanisms, with the inverse Compton explanation alleviating the particle energy requirements for the emission observed at late times. The late timing of this detection has consequences for the future observations of GRBs at the highest energies.
CRIS-Team Scopus Importer:2019-12-03

Best Licensing Practices - Grange, Yan; Juerges, Thomas; Schnabel, Jutta; Lorente, Nuria; Füßling, Matthias (2022)

Bottom production cross section from double muonic decays of b-flavoured hadrons in 920 GeV proton-nucleus collisions - van Eldik, Christopher; et al. (Physics Letters B, 2007)
The b over(b, ̄) production cross section in 920 GeV proton-nucleus fixed target collisions is measured by observing double muonic decays of b-flavoured hadrons in the kinematic region - 0.3 < x (μ) < 0.15. A total number of 83 ± 12 b over(b, ̄) events is obtained with a likelihood fit of the signal and background simulated events to the data. The resulting cross section is σ = 17.5 ± 2.6 ± 3.3 nb / nucleon, or, when combined with a previous HERA-B measurement of similar precision, σ = 15.8 ± 1.7 ± 1.3 ± 2.0 nb / nucleon, which is consistent with recent NLO calculations. © 2007.

Calibration of the Cherenkov Telescope Array - Gaug, Markus; Daniel, Michael; Berge, David; De Los Reyes, Raquel; Doro, Michele; Foerster, Andreas; Maccarone, Maria Concetta; Parsons, Dan; van Eldik, Christopher (34th International Cosmic Ray Conference (ICRC2015), 2015)
The construction of the Cherenkov Telescope Array, consisting of two observatories designed to observe the very high energy gamma-ray sky with unprecedented sensitivity and precision, is expected to start soon. We will present the baseline methods and their extensions currently foreseen to calibrate the observatory. These are bound to achieve the strong requirements on allowed systematic uncertainties for the reconstructed gamma-ray energy and flux scales, as well as on the pointing resolution, and on the overall duty cycle of the observatory. Onsite calibration activities are designed to include a robust and efficient calibration of the telescope cameras, and various methods and instruments to achieve calibration of the overall optical throughput of each telescope, leading to both inter-telescope calibration and an absolute calibration of the entire observatory. One important aspect of the onsite calibration is a correct understanding of the atmosphere above the telescopes, which constitutes the calorimeter of this detection technique. It is planned to be constantly monitored with state-of-the-art instruments to obtain a full molecular and aerosol profile up to the stratosphere. In order to guarantee the best use of the observation time, in terms of usable data, an intelligent scheduling system is required, which gives preference to those sources and observation programs that can cope with the given atmospheric conditions, especially if the sky is partially covered by clouds, or slightly contaminated by dust. Ceilometers in combination with all-sky-cameras are plannned to provide the observatory with a fast, online and full-sky knowledge of the expected conditions for each pointing direction. For a precise characterization of the adopted observing direction, wide-field optical telescopes and Raman Lidars are planned to provide information about the height-resolved and wavelength-dependent atmospheric extinction, throughout the field-of-view of the cameras.
Keywords: Astrophysics - Instrumentation and Methods for Astrophysics

Calibration strategies for the Cherenkov Telescope Array - Gaug, Markus; Berge, David; Daniel, Michael; Doro, Michele; Foerster, Andreas; Hofmann, Werner; Maccarone, Maria Concetta; Parsons, Dan; Lopez, Raquel De Los Reyes; van Eldik, Christopher (Observatory Operations: Strategies, Processes, and Systems V, 2014)
The Central Calibration Facilities workpackage of the Cherenkov Telescope Array (CTA) observatory for very high energy gamma ray astronomy defines the overall calibration strategy of the array, develops dedicated hardware and software for the overall array calibration and coordinates the calibration efforts of the different telescopes. The latter include LED-based light pulsers, and various methods and instruments to achieve a calibration of the overall optical throughput. On the array level, methods for the inter-telescope calibration and the absolute calibration of the entire observatory are being developed. Additionally, the atmosphere above the telescopes, used as a calorimeter, will be monitored constantly with state-of-the-art instruments to obtain a full molecular and aerosol profile up to the stratosphere. The aim is to provide a maximal uncertainty of 10% on the reconstructed energy-scale, obtained through various independent methods. Different types of LIDAR in combination with all-sky-cameras will provide the observatory with an online, intelligent scheduling system, which, if the sky is partially covered by clouds, gives preference to sources observable under good atmospheric conditions. Wide-field optical telescopes and Raman Lidars will provide online information about the height-resolved atmospheric extinction, throughout the field-of-view of the cameras, allowing for the correction of the reconstructed energy of each gamma-ray event. The aim is to maximize the duty cycle of the observatory, in terms of usable data, while reducing the dead time introduced by calibration activities to an absolute minimum.
Keywords: Calibration; CTA; Gamma-ray astronomy

Capability of Cherenkov telescopes to observe ultra-fast optical flares - Deil, C.; Domainko, W.; Hermann, G.; Clapson, A. C.; Foerster, A.; van Eldik, Christopher; Hofmann, W. (Astroparticle Physics, 2009)
The large optical reflector (∼100 m) of a H.E.S.S. Cherenkov telescope was used to search for very fast optical transients of astrophysical origin. Forty-three hours of observations targeting stellar-mass black holes and neutron stars were obtained using a dedicated photometer with microsecond time-resolution. The photometer consists of seven photomultiplier tube pixels: a central one to monitor the target and a surrounding ring of six pixels to veto background events. The light curves of all pixels were recorded continuously and were searched offline with a matched-filtering technique for flares with a duration of 2 μs-100 ms. As expected, many unresolved (<3 μs) and many long (>500 μs) background events originating in the earth's atmosphere were detected. In the time range 3-500 μs the measurement is essentially background-free, with only eight events detected in 43 h; five from lightning and three presumably from a piece of space debris. The detection of flashes of brightness ∼0.1 Jy and only 20 μs duration from the space debris shows the potential of this setup to find rare optical flares on timescales of tens of microseconds. This timescale corresponds to the light crossing time of stellar-mass black holes and neutron stars. © 2008 Elsevier B.V. All rights reserved.
Keywords: Cherenkov telescope; Ultra-fast optical photometry

Chandra and HESS observations of the supernova remnant CTB 37B - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Borrel, V.; Braun, Isabel; et al. (Astronomy & Astrophysics, 2008)
We discovered the > 100 GeV γ-ray source, HESS J1713-381, apparently associated with the shell-type supernova remnant (SNR) CTB 37B, using HESS in 2006. In 2007 we performed X-ray follow-up observations with Chandra with the aim of identifying a synchrotron counterpart to the TeV source and/or thermal emission from the SNR shell. These new Chandra data, together with additional TeV data, allow us to investigate the nature of this object in much greater detail than was previously possible. The new X-ray data reveal thermal emission from a ∼4′ region in close proximity to the radio shell of CTB 37B. The temperature of this emission implies an age for the remnant of ∼5000 years and an ambient gas density of ∼0.5 cm. Both these estimates are considerably uncertain due to the asymmetry of the SNR and possible modifications of the kinematics due to efficient cosmic ray (CR) acceleration. A bright (≈7 × 10 erg cm s) and unresolved (<1″) source (CXOUJ17.1405.7-381031), with a soft (Γ ≈ 3.3) non-thermal spectrum is also detected in coincidence with the radio shell. Absorption indicates a column density consistent with the thermal emission from the shell, suggesting a genuine association rather than a chance alignment. The observed TeV morphology is consistent with an origin in the complete shell of CTB 37B. The lack of diffuse non-thermal X-ray emission suggests an origin of the γ-ray emission via the decay of neutral pions produced in interactions of protons and nuclei, rather than inverse Compton (IC) emission from relativistic electrons. © ESO 2008.
Keywords: Gamma rays: observations; ISM: supernova remnants; X-rays: individuals: G348.7+0.3

Characterisation of PMTs for KM3NeT - Herold, Björn; Kalekin, Oleg (31st International Cosmic Ray Conference, ICRC 2009, 2009)
Keywords: Photomultiplier; KM3NeT; Quantum efficiency

Characterisation of the Hamamatsu photomultipliers for the KM3NeT Neutrino Telescope - Aiello, S.; Akrame, S. E.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Baars, M.; et al. (Journal of Instrumentation, 2018)
The Hamamatsu R12199-023-inch photomultiplier tube is the photodetector chosen for the first phase of the KM3NeT neutrino telescope. About 7000 photomultipliers have been characterised for dark count rate, timing spread and spurious pulses. The quantum efficiency, the gain and the peak-to-valley ratio have also been measured for a sub-sample in order to determine parameter values needed as input to numerical simulations of the detector.
Keywords: Cherenkov detectors; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (vacuum)

Characterisation of the Hamamatsu R12199-01 HA MOD photomultiplier tube for low temperature applications - Elorrieta, M. A. Unland; Classen, L.; Reubelt, Jonas; Schmiemann, S.; Schneider, Jonas; Kappes, A. (Journal of Instrumentation, 2019)
We present a detailed characterisation of the new Hamamatsu R12199-01 HA MOD 3-inch photomultiplier tube (PMT) which is under consideration for the use in segmented optical modules of deep-ice neutrino detectors at the South Pole. Because of the significantly lower operation-temperature range compared to standard applications, a focus of our studies lies on the investigation of the temperature dependence of background characteristics (dark count rate, probability of correlated pulses), timing properties, gain and peak-to-valley ratio of this PMT type. In addition, the performance of the "HA coating" intended for background reduction was tested, as well as the influence of conductive objects near the photocathode like reflectors on the PMT noise rate. A low background rate is of particular importance as the deep ice at the South Pole features negligible optical background. We find that the new PMT type is well suited for the intended applications.
CRIS-Team WoS Importer:2019-04-16

Characterising the VHE diffuse emission in the central 200 parsecs of our Galaxy with H.E.S.S. - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
The diffuse very high-energy (VHE; > 100 GeV) gamma-ray emission observed in the central 200 pc of the Milky Way by H.E.S.S. was found to follow dense matter distribution in the central molecular zone (CMZ) up to a longitudinal distance of about 130 pc to the Galactic centre (GC), where the flux rapidly decreases. This was initially interpreted as the result of a burst-like injection of energetic particles 104 yr ago, but a recent more sensitive H.E.S.S. analysis revealed that the cosmic-ray (CR) density profile drops with the distance to the centre, making data compatible with a steady cosmic PeVatron at the GC. In this paper, we extend this analysis to obtain, for the first time, a detailed characterisation of the correlation with matter and to search for additional features and individual gamma-ray sources in the inner 200 pc. Taking advantage of 250 h of H.E.S.S. data and improved analysis techniques, we perform a detailed morphology study of the diffuse VHE emission observed from the GC ridge and reconstruct its total spectrum. To test the various contributions to the total gamma-ray emission, we used an iterative 2D maximum-likelihood approach that allows us to build a phenomenological model of the emission by summing a number of different spatial components. We show that the emission correlated with dense matter covers the full CMZ and that its flux is about half the total diffuse emission flux. We also detect some emission at higher latitude that is likely produced by hadronic collisions of CRs in less dense regions of the GC interstellar medium. We detect an additional emission component centred on the GC and extending over about 15 pc that is consistent with the existence of a strong CR density gradient and confirms the presence of a CR accelerator at the very centre of our Galaxy. We show that the spectrum of full ridge diffuse emission is compatible with that previously derived from the central regions, suggesting that a single population of particles fills the entire CMZ. Finally, we report the discovery of a VHE gamma-ray source near the GC radio arc and argue that it is produced by the pulsar wind nebula candidate G0.13-0.11.
Keywords: gamma rays: general; gamma rays: ISM; Galaxy: center; cosmic rays

Characteristics of the Diffuse Astrophysical Electron and Tau Neutrino Flux with Six Years of IceCube High Energy Cascade Data - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau,; Anton, Gisela; Arguelles, C.; et al. (Physical Review Letters, 2020)
We report on the first measurement of the astrophysical neutrino flux using particle showers (cascades) in IceCube data from 2010-2015. Assuming standard oscillations, the astrophysical neutrinos in this dedicated cascade sample are dominated (similar to 90%) by electron and tau flavors. The flux, observed in the sensitive energy range from 16 TeV to 2.6 PeV, is consistent with a single power-law model as expected from Fermi-type acceleration of high energy particles at astrophysical sources. We find the flux spectral index to be gamma = 2.53 +/- 0.07 and a flux normalization for each neutrino flavor of phi(astro) = 1.66(-0.27)(+0.25) at E-0 = 100 TeV, in agreement with IceCube's complementary muon neutrino results and with all-neutrino flavor fit results. In the measured energy range we reject spectral indices gamma <= 2.28 at >= 3 sigma significance level. Because of high neutrino energy resolution and low atmospheric neutrino backgrounds, this analysis provides the most detailed characterization of the neutrino flux at energies below similar to 100 TeV compared to previous IceCube results. Results from fits assuming more complex neutrino flux models suggest a flux softening at high energies and a flux hardening at low energies (p value >= 0.06). The sizable and smooth flux measured below similar to 100 TeV remains a puzzle. In order to not violate the isotropic diffuse gamma-ray background as measured by the Fermi Large Area Telescope, it suggests the existence of astrophysical neutrino sources characterized by dense environments which are opaque to gamma rays.
CRIS-Team WoS Importer:2020-10-02

Characterization of two PMT models for the IceCube upgrade MDOM - van Eijk, D.; Schneider, Jonas; Unland, M. (Proceedings of Science, 2019)
The IceCube Upgrade will expand the IceCube Neutrino Observatory with nearly 800 new optical modules. A large fraction of these will be multi-PMT optical modules (mDOMs), featuring 24 PMTs pointing uniformly in all directions, providing an almost homogeneous angular coverage and providing an effective photosensitive area more than twice that of current IceCube optical modules. Two PMT models from different manufacturers are currently considered for use in the mDOM: a 3.5 inch PMT from HZC Photonics and a 3 inch PMT from Hamamatsu. Both PMTs have been characterized in terms of gain, timing, quantum efficiency and dark noise rate as a function of temperature. The obtained characterization results are presented here.
CRIS-Team Scopus Importer:2021-04-20

Characterizing the γ-ray long-term variability of PKS 2155 - 304 with H.E.S.S. and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Astronomy & Astrophysics, 2017)
Studying the temporal variability of BL Lac objects at the highest energies provides unique insights into the extreme physical processes occurring in relativistic jets and in the vicinity of super-massive black holes. To this end, the long-term variability of the BL Lac object PKS 2155 304 is analyzed in the high (HE, 100MeV < E < 300 GeV) and very high energy (VHE, E > 200 GeV) gamma-ray domain. Over the course of similar to 9 yr of H. E. S. S. observations the VHE light curve in the quiescent state is consistent with a log-normal behavior. The VHE variability in this state is well described by flicker noise (power-spectral-density index beta(VHE) = 1 .10(+ 0 : 10) (0 : 13)) on timescales larger than one day. An analysis of similar to 5.5 yr of HE Fermi-LAT data gives consistent results (beta(HE) = 1 : 20(+ 0 : 21) (0 : 23), on timescales larger than 10 days) compatible with the VHE findings. The HE and VHE power spectral densities show a scale invariance across the probed time ranges. A direct linear correlation between the VHE and HE fluxes could neither be excluded nor firmly established. These long-term-variability properties are discussed and compared to the red noise behavior (beta similar to 2) seen on shorter timescales during VHE-flaring states. The difference in power spectral noise behavior at VHE energies during quiescent and flaring states provides evidence that these states are influenced by different physical processes, while the compatibility of the HE and VHE long-term results is suggestive of a common physical link as it might be introduced by an underlying jet-disk connection.
Keywords: BL Lacertae objects: individual: PKS 2155-304; Galaxies: active; Galaxies: jets; Galaxies: nuclei; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Cherenkov light imaging in astroparticle physics - Katz, Uli (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
Cherenkov light induced by fast charged particles in transparent dielectric media such as air or water is exploited by a variety of experimental techniques to detect and measure extraterrestrial particles impinging on Earth. A selection of detection principles is discussed and corresponding experiments are presented together with breakthrough-results they achieved. Some future developments are highlighted.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Astroparticle physics; Cherenkov detectors; Cosmic-ray detectors; Gamma-ray telescopes; Neutrino telescopes

Coincidence of a high-fluence blazar outburst with a PeV-energy neutrino event - Kadler, Matthias; Krauss, Felicia; Mannheim, K.; Ojha, R.; Mueller, C.; Schulz, R.; Anton, Gisela; Baumgartner, W.; Beuchert, T.; Buson, S.; Carpenter, B.; Eberl, Thomas; et al. (Nature Physics, 2016)
The astrophysical sources of the extraterrestrial, very high-energy neutrinos detected by the IceCube collaboration remain to be identified. Gamma-ray (3-ray) blazars have been predicted to yield a cumulative neutrino signal exceeding the atmospheric background above energies of 100 TeV, assuming that both the neutrinos and the 3-ray photons are produced by accelerated protons in relativistic jets. As the background spectrum falls steeply with increasing energy, the individual events with the clearest signature of being of extraterrestrial origin are those at petaelectronvolt energies. Inside the large positional-uncertainty fields of the first two petaelectronvolt neutrinos detected by IceCube, the integrated emission of the blazar population has a sufficiently high electromagnetic flux to explain the detected IceCube events, but fluences of individual objects are too low to make an unambiguous source association. Here, we report that a major outburst of the blazar PKS B1424-418 occurred in temporal and positional coincidence with a third petaelectronvolt-energy neutrino event (HESE-35) detected by IceCube. On the basis of an analysis of the full sample of 3-ray blazars in the HESE-35 field, we show that the long-term average 3-ray emission of blazars as a class is in agreement with both the measured all-sky flux of petaelectronvolt neutrinos and the spectral slope of the IceCube signal. The outburst of PKS B1424-418 provides an energy output high enough to explain the observed petaelectronvolt event, suggestive of a direct physical association.

Combined search for neutrinos from dark matter self-annihilation in the Galactic Center with ANTARES and IceCube - Albert, A.; Andre, M.; Domi, Alba; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, Simone; et al. (Physical Review D, 2020)
We present the results of the first combined dark matter search targeting the Galactic Center using the ANTARES and IceCube neutrino telescopes. For dark matter particles with masses from 50 to 1000 GeV, the sensitivities on the self-annihilation cross section set by ANTARES and IceCube are comparable, making this mass range particularly interesting for a joint analysis. Dark matter self-annihilation through the tau(+)tau(-) , mu(+)mu(-) , b (b) over bar, and W+W- channels is considered for both the Navarro-Frenk-White and Burkert halo profiles. In the combination of 2101.6 days of ANTARES data and 1007 days of IceCube data, no excess over the expected background is observed. Limits on the thermally averaged dark matter annihilation cross section are set. These limits present an improvement of up to a factor of 2 in the studied dark matter mass range with respect to the individual limits published by both collaborations. When considering dark matter particles with a mass of 200 GeV annihilating through the tau(+)tau(-)channel, the value obtained for the limit is 7.44 x 10(-24) cm(3) s(-1 )for the Navarro-Frenk-White halo profile. For the purpose of this joint analysis, the model parameters and the likelihood are unified, providing a benchmark for forthcoming dark matter searches performed by neutrino telescopes.
CRIS-Team WoS Importer:2020-11-13

Commissioning and improvements of the instrumentation and launch of the scientific exploitation of OARPAF, the Regional Astronomical Observatory of the Antola Park - Domi, Alba; et al. (Journal of Astronomical Telescopes, Instruments, and Systems, 2021)
Keywords: Telescopes; Spectroscopy; Photometry; Commissioning; Échelle spectroscopy

Competition between Dehydrogenative Organometallic Bonding and Covalent Coupling of an Unfunctionalized Porphyrin on Cu(111) - Xiang, Feifei; Gemeinhardt, Anja; Schneider, M. Alexander (Acs Nano, 2018)
We studied the formation of linked porphyrin oligomers from 5,15-diphenylporphyrin (2H-DPP) by thermal, substrate-assisted organometallic and dehydrogenation coupling on Cu(111) by scanning tunneling microscopy. In the range of 300-620 K, we find three distinct stages, at 300 K, the intact 2H-DPP molecules self-assemble into linear structures held together by van der Waals forces. Increasing the substrate temperature, self-metalation and intramolecular ring-closing reactions result in planar and isolated DPP species on the surface. By C-H cleavage, porphyrin oligomers bonded by organometallic and covalent bonds between the modified DPP are formed. The amount of covalently bonded DPP oligomers increases strongly with annealing time and temperature, and they become the dominant species at 570 K. In contrast, the number of organometallically bonded DPP oligomers increases moderately even up to 620 K, indicating that in this case the organometallic bond is no precursor of the covalent bond.
Keywords: scanning tunneling microscopy; on-surface synthesis; polymerization; molecular wire; metalation

Computational techniques for the analysis of small signals in high-statistics neutrino oscillation experiments - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
The current and upcoming generation of Very Large Volume Neutrino Telescopes – collecting unprecedented quantities of neutrino events – can be used to explore subtle effects in oscillation physics, such as (but not restricted to) the neutrino mass ordering. The sensitivity of an experiment to these effects can be estimated from Monte Carlo simulations. With the high number of events that will be collected, there is a trade-off between the computational expense of running such simulations and the inherent statistical uncertainty in the determined values. In such a scenario, it becomes impractical to produce and use adequately-sized sets of simulated events with traditional methods, such as Monte Carlo weighting. In this work we present a staged approach to the generation of expected distributions of observables in order to overcome these challenges. By combining multiple integration and smoothing techniques which address limited statistics from simulation it arrives at reliable analysis results using modest computational resources.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Data analysis; Detector; KDE; MC; Monte Carlo; Neutrino; Neutrino mass ordering; Smoothing; Statistics; VLVνT

Computing in the KM3NeT Research Infrastructure - Hofestädt, Jannik (VERY LARGE VOLUME NEUTRINO TELESCOPES (VLVNT-2018), 2019)
CRIS-Team WoS Importer:2020-02-04

Concept Study of a Radio Array Embedded in a Deep Gen2-like Optical Array - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory has discovered a diffuse astrophysical flux up to 10 PeV and is now planning a large extension with IceCube-Gen2, including an optical array and a large radio array at shallow depth [1]. Neutrino searches for energies >100 PeV are best done with such shallow radio detectors like the Askaryan Radio Array (ARA) or similar (buried as deep as 200 meters below the surface) as they are cheaper to deploy. This poster explores the potential of opportunistically burying radio antennas within the planned IceCube-Gen2 detector volume (between 1350 meters and 2600 meters below the surface). A hybrid detection of events in optical and radio could substantially improve the uncertainty of neutrino cascade direction as radio signals do not scatter in ice. We show the first results of simulating neutrinos from an astrophysical and a cosmogenic flux interacting with 9760 ARA-style vertically polarized radio antennas distributed evenly across 122 strings.
CRIS-Team Scopus Importer:2023-08-15

Concluding remarks - A personal view - - Katz, Uli (VERY LARGE VOLUME NEUTRINO TELESCOPES (VLVNT-2018), 2019)
CRIS-Team WoS Importer:2020-02-04

Constraining the contribution of Gamma-Ray Bursts to the high-energy diffuse neutrino flux with 10 yr of ANTARES data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, S.; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
Addressing the origin of the astrophysical neutrino flux observed by IceCube is of paramount importance. Gamma-Ray Bursts (GRBs) are among the few astrophysical sources capable of achieving the required energy to contribute to such neutrino flux through p gamma interactions. In this work, ANTARFS data have been used to search for upward going muon neutrinos in spatial and temporal coincidence with 784 GRBs occurred from 2007 to 2017. For each GRB, the expected neutrino flux has been calculated in the framework of the internal shock model and the impact of the lack of knowledge on the majority of source redshifts and on other intrinsic parameters of the emission mechanism has been quantified. It is found that the model parameters that set the radial distance where shock collisions occur have the largest impact on neutrino flux expectations. In particular, the bulk Lorentz factor of the source ejecta and the minimum variability time-scale are found to contribute significantly to the GRB-neutrino flux uncertainty. For the selected sources, ANTARES data have been analysed by maximizing the discovery probability of the stacking sample through an extended maximum-likelihood strategy. Since no neutrino event passed the quality cuts set by the optimization procedure, 90 per cent confidence level upper limits (with their uncertainty) on the total expected diffuse neutrino flux have been derived, according to the model. The GRB contribution to the observed diffuse astrophysical neutrino flux around 100 TeV is constrained to be less than 10 percent.
CRIS-Team WoS Importer:2021-01-29

Constraining the neutrino emission of gravitationally lensed Flat-Spectrum Radio Quasars with ANTARES data - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagii, S.; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper proposes to exploit gravitational lensing effects to improve the sensitivity of neutrino telescopes to the intrinsic neutrino emission of distant blazar populations. This strategy is illustrated with a search for cosmic neutrinos in the direction of four distant and gravitationally lensed Flat-Spectrum Radio Quasars. The magnification factor is estimated for each system assuming a singular isothermal profile for the lens. Based on data collected from 2007 to 2012 by the ANTARES neutrino telescope, the strongest constraint is obtained from the lensed quasar B0218+357, providing a limit on the total neutrino luminosity of this source of 1.08 x 10(46) erg s(-1) This limit is about one order of magnitude lower than those previously obtained in the ANTARES standard point source searches with non-lensed Flat-Spectrum Radio Quasars.
Keywords: gravitational lensing; neutrino astronomy

Constraints on an annihilation signal from a core of constant dark matter density around the milky way center with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review Letters, 2015)

Constraints on axionlike particles with H.E.S.S. from the irregularity of the PKS 2155-304 energy spectrum - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2013)
Axionlike particles (ALPs) are hypothetical light (sub-eV) bosons predicted in some extensions of the Standard Model of particle physics. In astrophysical environments comprising high-energy gamma rays and turbulent magnetic fields, the existence of ALPs can modify the energy spectrum of the gamma rays for a sufficiently large coupling between ALPs and photons. This modification would take the form of an irregular behavior of the energy spectrum in a limited energy range. Data from the H.E.S.S. observations of the distant BL Lac object PKS 2155-304 (z=0.116) are used to derive upper limits at the 95% C.L. on the strength of the ALP coupling to photons, g<2. 1×1011 GeV1 for an ALP mass between 15 and 60 neV. The results depend on assumptions on the magnetic field around the source, which are chosen conservatively. The derived constraints apply to both light pseudoscalar and scalar bosons that couple to the electromagnetic field. © 2013 American Physical Society.

Constraints on Minute-Scale Transient Astrophysical Neutrino Sources - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Al Samarai, I.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; et al. (Physical Review Letters, 2019)
High-energy neutrino emission has been predicted for several short-lived astrophysical transients including gamma-ray bursts (GRBs), core-collapse supernovae with choked jets, and neutron star mergers. IceCube's optical and x-ray follow-up program searches for such transient sources by looking for two or more muon neutrino candidates in directional coincidence and arriving within 100 s. The measured rate of neutrino alerts is consistent with the expected rate of chance coincidences of atmospheric background events and no likely electromagnetic counterparts have been identified in Swift follow-up observations. Here, we calculate generic bounds on the neutrino flux of short-lived transient sources. Assuming an E-2.5 neutrino spectrum, we find that the neutrino flux of rare sources, like long gamma-ray bursts, is constrained to < 5% of the detected astrophysical flux and the energy released in neutrinos (100 GeV to 10 PeV) by a median bright GRB-like source is < 10(52.5) erg. For a harder E-2.13 neutrino spectrum up to 30% of the flux could be produced by GRBs and the allowed median source energy is < 10(52) erg. A hypothetical population of transient sources has to be more common than 10(-5) Mpc(-3) yr(-1) (5 x 10(-8) Mpc(-3) yr(-1) for the E-2.13 spectrum) to account for the complete astrophysical neutrino flux.
CRIS-Team WoS Importer:2019-02-21

Constraints on Populations of Neutrino Sources from Searches in the Directions of IceCube Neutrino Alerts - Abbasi, R.; Ackermann, M.; Adams, J.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Astrophysical Journal, 2023)
Beginning in 2016, the IceCube Neutrino Observatory has sent out alerts in real time containing the information of high-energy (E ≳ 100 TeV) neutrino candidate events with moderate to high (≳30%) probability of astrophysical origin. In this work, we use a recent catalog of such alert events, which, in addition to events announced in real time, includes events that were identified retroactively and covers the time period of 2011-2020. We also search for additional, lower-energy neutrinos from the arrival directions of these IceCube alerts. We show how performing such an analysis can constrain the contribution of rare populations of cosmic neutrino sources to the diffuse astrophysical neutrino flux. After searching for neutrino emission coincident with these alert events on various timescales, we find no significant evidence of either minute-scale or day-scale transient neutrino emission or of steady neutrino emission in the direction of these alert events. This study also shows how numerous a population of neutrino sources has to be to account for the complete astrophysical neutrino flux. Assuming that sources have the same luminosity, an E −2.5 neutrino spectrum, and number densities that follow star formation rates, the population of sources has to be more numerous than 7 × 10−9 Mpc−3. This number changes to 3 × 10−7 Mpc−3 if number densities instead have no cosmic evolution.
CRIS-Team Scopus Importer:2023-07-21

Constraints on the emission region of 3C 279 during strong flares in 2014 and 2015 through VHE γ -ray observations with H.E.S.S. - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2019)
The flat spectrum radio quasar 3C 279 is known to exhibit pronounced variability in the high-energy (100MeV < E < 100 GeV) gamma-ray band, which is continuously monitored with Fermi-LAT. During two periods of high activity in April 2014 and June 2015 target-of-opportunity observations were undertaken with the High Energy Stereoscopic System (H.E.S.S.) in the very-high-energy (VHE, E > 100 GeV) gamma-ray domain. While the observation in 2014 provides an upper limit, the observation in 2015 results in a signal with 8 : 7 sigma significance above an energy threshold of 66 GeV. No VHE variability was detected during the 2015 observations. The VHE photon spectrum is soft and described by a power-law index of 4.2 +/- 0.3. The H.E.S.S. data along with a detailed and contemporaneous multiwavelength data set provide constraints on the physical parameters of the emission region. The minimum distance of the emission region from the central black hole was estimated using two plausible geometries of the broad-line region and three potential intrinsic spectra. The emission region is confidently placed at r greater than or similar to 1 : 7 X 1017 cm from the black hole, that is beyond the assumed distance of the broad-line region. Time-dependent leptonic and lepto-hadronic one-zone models were used to describe the evolution of the 2015 flare. Neither model can fully reproduce the observations, despite testing various parameter sets. Furthermore, the H.E.S.S. data were used to derive constraints on Lorentz invariance violation given the large redshift of 3C 279.
CRIS-Team WoS Importer:2019-07-30
Keywords: Galaxies: active; Quasars: individual: 3C 279; Radiation mechanisms: non-thermal; Relativistic processes

Constraints on the gamma-ray emission from the cluster-scale AGN outburst in the Hydra A galaxy cluster - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
Context. In some galaxy clusters, powerful active galactic nuclei (AGN) have blown bubbles with cluster scale extent into the ambient medium. The main pressure support of these bubbles is not known to date, but cosmic rays are a viable possibility. For such a scenario copious gamma-ray emission is expected as a tracer of cosmic rays from these systems. Aims. Hydra A, the closest galaxy cluster hosting a cluster scale AGN outburst, located at a redshift of 0.0538, is investigated for being a gamma-ray emitter with the High Energy Stereoscopic System (H.E.S.S.) array and the Fermi Large Area Telescope (Fermi-LAT). Methods. Data obtained in 20.2 h of dedicated H.E.S.S. observations and 38 months of Fermi-LAT data, gathered by its usual all-sky scanning mode, have been analyzed to search for a gamma-ray signal. Results. No signal has been found in either data set. Upper limits on the gamma-ray flux are derived and are compared to models. These are the first limits on gamma-ray emission ever presented for galaxy clusters hosting cluster scale AGN outbursts. Conclusions. The non-detection of Hydra A in gamma-rays has important implications on the particle populations and physical conditions inside the bubbles in this system. For the case of bubbles mainly supported by hadronic cosmic rays, the most favorable scenario, which involves full mixing between cosmic rays and embedding medium, can be excluded. However, hadronic cosmic rays still remain a viable pressure support agent to sustain the bubbles against the thermal pressure of the ambient medium. The largest population of highly-energetic electrons, which are relevant for inverse-Compton gamma-ray production is found in the youngest inner lobes of Hydra A. The limit on the inverse-Compton gamma-ray flux excludes a magnetic field below half of the equipartition value of 16 μG in the inner lobes. © 2012 ESO.
Keywords: Galaxies: active; Galaxies: clusters: individual: Hydra A; Gamma rays: galaxies: clusters

Constraints on the Intergalactic Magnetic Field Using Fermi-LAT and H.E.S.S. Blazar Observations - Aharonian, F.; Aschersleben, J.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bi, B.; Bouyahiaoui, M.; Breuhaus, M.; Brose, R.; Brun, F.; et al. (Astrophysical Journal Letters, 2023)

Constraints on the multi-TeV particle population in the Coma galaxy cluster with HESS observations - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Brion, E.; et al. (Astronomy & Astrophysics, 2009)
Alms. Galaxy clusters are key targets in the search for ultra high energy particle accelerators. The Coma cluster represents one of the best candidates for such a search owing to its high mass, proximity, and the established non-thermal radio emission centred on the cluster core. Methods. The HESS (High Energy Stereoscopic System) telescopes observed Coma for ∼8 h in a search for γ-ray emission at energies >1 TeV. The large 3.5° FWHM field of view of HESS is ideal for viewing a range of targets at various sizes including the Coma cluster core, the radio-relic (1253+275) and merger/infall (NGC 4839) regions to the southwest, and features greater than 1° away. Results. No evidence for point-like nor extended TeV γ-ray emission was found and upper limits to the TeV flux F(E) for E > 1, >5, and > 10 TeV were set for the Coma core and other regions. Converting these limits to an energy flux E F(E) the lowest or most constraining is the E > 5 TeV upper limit for the Coma core (0.2° radius) at ∼8% Crab flux units or ∼10 ph cm s . Conclusions. The upper limits for the Coma core were compared with a prediction for the γ-ray emission from proton-proton interactions, the level of which ultimately scales with the mass of the Coma cluster. A direct constraint using our most stringent limit for E > 5 TeV, on the total energy content in non-thermal protons with injection energy spectrum αE and spatial distribution following the thermal gas in the cluster, is found to be ∼0.2 times the thermal energy, or ∼10 erg. The E > 5 TeV γ-ray threshold in this case corresponds to cosmic- ray proton energies ≳50 TeV. Our upper limits rule out the most optimistic theoretical models for gamma ray emission from clusters and complement radio observations which constrain the cosmic ray content in clusters at significantly lower proton energies, subject to assumptions on the magnetic field strength. ©ESO 2009.
Keywords: Galaxies: Clusters: Individual: Coma (ACO 1656); Gamma rays: Observations

Constraints on the neutrino emission from the Galactic Ridge with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physics Letters B, 2016)
A highly significant excess of high-energy astrophysical neutrinos has been reported by the IceCube Collaboration. Some features of the energy and declination distributions of IceCube events hint at a North/South asymmetry of the neutrino flux. This could be due to the presence of the bulk of our Galaxy in the Southern hemisphere. The ANTARES neutrino telescope, located in the Mediterranean Sea, has been taking data since 2007. It offers the best sensitivity to muon neutrinos produced by galactic cosmic ray interactions in this region of the sky. In this letter a search for an extended neutrino flux from the Galactic Ridge region is presented. Different models of neutrino production by cosmic ray propagation are tested. No excess of events is observed and upper limits for different neutrino flux spectral indices Γ are set. For Γ=2.4 the 90% confidence level flux upper limit at 100 TeV for one neutrino flavour corresponds to Φ (100 TeV)=2.0⋅10 GeVcmssr. Under this assumption, at most two events of the IceCube cosmic candidates can originate from the Galactic Ridge. A simple power-law extrapolation of the Fermi-LAT flux to account for IceCube High Energy Starting Events is excluded at 90% confidence level.
Keywords: ANTARES; Diffuse muon neutrino flux; Neutrino telescope

Correction to: A new benchmark of soft X-ray transition energies of Ne, CO2, and SF6: paving a pathway towards ppm accuracy (The European Physical Journal D, (2022), 76, 3, (38), 10.1140/epjd/s10053-022-00355-0) - Stierhof, Jakob; Kuehn, S.; Winter, Michael; Micke, Peter; Steinbruegge, R.; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (European Physical Journal D, 2022)
CRIS-Team Scopus Importer:2022-11-11

Cosmic ray electrons and Galactic centre observations with H.E.S.S. - van Eldik, Christopher (TeV Particle Astrophysics 2009, 2009)

Cosmic ray spectrum and composition from PeV to EeV using 3 years of data from IceTop and IceCube - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau,; Anton, Gisela; Arguelles, C.; et al. (Physical Review D, 2019)
We report on measurements of the all-particle cosmic ray energy spectrum and composition in the PeV to EeV energy range using 3 years of data from the IceCube Neutrino Observatory. The IceTop detector measures cosmic ray induced air showers on the surface of the ice, from which the energy spectrum of cosmic rays is determined by making additional assumptions about the mass composition. A separate measurement is performed when IceTop data are analyzed in coincidence with the high-energy muon energy loss information from the deep in-ice IceCube detector. In this measurement, both the spectrum and the mass composition of the primary cosmic rays are simultaneously reconstructed using a neural network trained on observables from both detectors. The performance and relative advantages of these two distinct analyses are discussed, including the systematic uncertainties and the dependence on the hadronic interaction models, and both all-particle spectra as well as individual spectra for elemental groups are presented.
CRIS-Team WoS Importer:2019-11-05

Dark matter gamma-ray line searches toward the Galactic Center halo with H.E.S.S. I - Rinchiuso, Lucia; Moulin, Emmanuel; Viana, Aion; van Eldik, Christopher; Veh, Johannes (Proceedings of Science, 2017)
The presence of dark matter is nowadays widely supported by a large body of astronomical and cosmological observations. A large amount of dark matter is expected to be present in the central region of the Milky Way. Very-high-energy (>100 GeV) γ-rays can be produced in the annihilation of dark matter particles. The H.E.S.S. array of Imaging Atmospheric Cherenkov Telescopes is a powerful tools to observe the Galactic Centre trying to detect γ-rays from dark matter annihilation. A new search for a dark matter signal has been carried out on the full H.E.S.S.-I data set of 2004-2014 observations. A 2D-binned likelihood method has been applied to exploit the spectral and spatial properties of signal and background. Updated constraints are derived on the velocity-weighted annihilation cross section for signals from prompt annihilation of dark matter particles into two photons. The larger statistics from the 10-year Galactic Center dataset of H.E.S.S.-I together with the 2D-analysis technique allows to significantly improve the previous limits.
CRIS-Team Scopus Importer:2024-02-15

Data and software preservation through containerisation in KM3NeT - Gál, Tamás (Proceedings of Science, 2019)
In this contribution we discuss of how we implemented procedures for maintaining and developing software and preserving data processing pipelines in KM3NeT using containerisation technologies and continuous integration.
CRIS-Team Scopus Importer:2021-04-20

Deeper HESS observations of Vela Junior (RX J0852.0-4622): Morphology studies and resolved spectroscopy - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
Aims. We study gamma-ray emission from the shell-type supernova remnant (SNR) RXJ0852.0-4622 to better characterize its spectral properties and its distribution over the SNR.Methods. The analysis of an extended High Energy Spectroscopic System (H.E.S.S.) data set at very high energies (E > 100 GeV) permits detailed studies, as well as spatially resolved spectroscopy, of the morphology and spectrum of the whole RXJ0852.0-4622 region. The H.E.S.S. data are combined with archival data from other wavebands and interpreted in the framework of leptonic and hadronic models. The joint Fermi-LAT-H.E.S.S. spectrum allows the direct determination of the spectral characteristics of the parent particle population in leptonic and hadronic scenarios using only GeV-TeV data.Results. An updated analysis of the H.E.S.S. data shows that the spectrum of the entire SNR connects smoothly to the high-energy spectrum measured by Fermi-LAT. The increased data set makes it possible to demonstrate that the H.E.S.S. spectrum deviates significantly from a power law and is well described by both a curved power law and a power law with an exponential cutoff at an energy of E-cut = (6.7 +/- 1.2(stat) +/- 1.2(syst)) TeV. The joint Fermi-LAT-H.E.S.S. spectrum allows the unambiguous identification of the spectral shape as a power law with an exponential cutoff. No significant evidence is found for a variation of the spectral parameters across the SNR, suggesting similar conditions of particle acceleration across the remnant. A simple modeling using one particle population to model the SNR emission demonstrates that both leptonic and hadronic emission scenarios remain plausible. It is also shown that at least a part of the shell emission is likely due to the presence of a pulsar wind nebula around PSR J0855-4644.
Keywords: astroparticle physics; gamma rays: general; acceleration of particles; cosmic rays; ISM: supernova remnants

Deep learning reconstruction in ANTARES - García-Méndez, J.; Geißelbrecht, Nicole; Eberl, Thomas; Ardid, M.; Ardid, S. (Journal of Instrumentation, 2021)
ANTARES is currently the largest undersea neutrino telescope, located in the Mediterranean Sea and taking data since 2007. It consists of a 3D array of photo sensors, instrumenting about 10Mt of seawater to detect Cherenkov light induced by secondary particles from neutrino interactions. The event reconstruction and background discrimination is challenging and machine-learning techniques are explored to improve the performance. In this contribution, two case studies using deep convolutional neural networks are presented. In the first one, this approach is used to improve the direction reconstruction of low-energy single-line events, for which the reconstruction of the azimuth angle of the incoming neutrino is particularly difficult. We observe a promising improvement in resolution over classical reconstruction techniques and expect to at least double our sensitivity in the low-energy range, important for dark matter searches. The second study employs deep learning to reconstruct the visible energy of neutrino interactions of all flavors and for the multi-line setup of the full detector.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Analysis and statistical methods; Data processing methods; Neutrino detectors; Pattern recognition; cluster finding; calibration and fitting methods

Deep-Sea Bioluminescence Blooms after Dense Water Formation at the Ocean Surface - Tamburini, Christian; Canals, Miquel; Houpert, Loic; Lefevre, Dominique; Martini, Verine; D'Ortenzio, Fabrizio; Robert, Anne; Testor, Pierre; Aguilar, Juan Antonio; Al Samarai, Imen; Albert, Arnaud; Andre, Michel; et al. (PLoS ONE, 2013)
The deep ocean is the largest and least known ecosystem on Earth. It hosts numerous pelagic organisms, most of which are able to emit light. Here we present a unique data set consisting of a 2.5-year long record of light emission by deep-sea pelagic organisms, measured from December 2007 to June 2010 at the ANTARES underwater neutrino telescope in the deep NW Mediterranean Sea, jointly with synchronous hydrological records. This is the longest continuous time-series of deep-sea bioluminescence ever recorded. Our record reveals several weeks long, seasonal bioluminescence blooms with light intensity up to two orders of magnitude higher than background values, which correlate to changes in the properties of deep waters. Such changes are triggered by the winter cooling and evaporation experienced by the upper ocean layer in the Gulf of Lion that leads to the formation and subsequent sinking of dense water through a process known as "open-sea convection". It episodically renews the deep water of the study area and conveys fresh organic matter that fuels the deep ecosystems. Luminous bacteria most likely are the main contributors to the observed deep-sea bioluminescence blooms. Our observations demonstrate a consistent and rapid connection between deep open-sea convection and bathypelagic biological activity, as expressed by bioluminescence. In a setting where dense water formation events are likely to decline under global warming scenarios enhancing ocean stratification, in situ observatories become essential as environmental sentinels for the monitoring and understanding of deep-sea ecosystem shifts.

Deep-sea deployment of the KM3NeT neutrino telescope detection units by self-unrolling - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (Journal of Instrumentation, 2020)
KM3NeT is a research infrastructure being installed in the deep Mediterranean Sea. It will house a neutrino telescope comprising hundreds of networked moorings - detection units or strings - equipped with optical instrumentation to detect the Cherenkov radiation generated by charged particles from neutrino-induced collisions in its vicinity. In comparison to moorings typically used for oceanography, several key features of the KM3NeT string are different: the instrumentation is contained in transparent and thus unprotected glass spheres; two thin Dyneema (R) ropes are used as strength members; and a thin delicate backbone tube with fibre-optics and copper wires for data and power transmission, respectively, runs along the full length of the mooring. Also, compared to other neutrino telescopes such as ANTARES in the Mediterranean Sea and GVD in Lake Baikal, the KM3NeT strings are more slender to minimise the amount of material used for support of the optical sensors. Moreover, the rate of deploying a large number of strings in a period of a few years is unprecedented. For all these reasons, for the installation of the KM3NeT strings, a custom-made, fast deployment method was designed. Despite the length of several hundreds of metres, the slim design of the string allows it to be compacted into a small, re-usable spherical launching vehicle instead of deploying the mooring weight down from a surface vessel. After being lowered to the seafloor, the string unfurls to its full length with the buoyant launching vehicle rolling along the two ropes. The design of the vehicle, the loading with a string, and its underwater self-unrolling are detailed in this paper.
CRIS-Team WoS Importer:2020-12-18

Deep sea tests of a prototype of the KM3NeT digital optical module - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; De Asmundis, R.; et al. (European Physical Journal C, 2014)
The first prototype of a photo-detection unit of the future KM3NeT neutrino telescope has been deployed in the deepwaters of the Mediterranean Sea. This digital optical module has a novel design with a very large photocathode area segmented by the use of 31 three inch photomultiplier tubes. It has been integrated in the ANTARES detector for in-situ testing and validation. This paper reports on the first months of data taking and rate measurements. The analysis results highlight the capabilities of the new module design in terms of background suppression and signal recognition. The directionality of the optical module enables the recognition of multiple Cherenkov photons from the same (40)Kdecay and the localisation of bioluminescent activity in the neighbourhood. The single unit can cleanly identify atmospheric muons and provide sensitivity to the muon arrival directions.

Deflectometric measurement of large mirrors - Olesch, Evelyn; Häusler, Gerd; Wörnlein, André; Stinzing, Friedrich; van Eldik, Christopher (Advanced Optical Technologies, 2014)
We discuss the inspection of large-sized, spherical mirror tiles by 'Phase Measuring Deflectometry' (PMD). About 10 000 of such mirror tiles, each satisfying strict requirements regarding the spatial extent of the point-spreadfunction (PSF), are planned to be installed on the Cherenkov Telescope Array (CTA), a future ground-based instrument to observe the sky in very high energy gamma-rays. Owing to their large radii of curvature of up to 60 m, a direct PSF measurement of these mirrors with concentric geometry requires large space. We present a PMD sensor with a footprint of only 5 ?2 ?1.2 m3 that overcomes this limitation. The sensor intrinsically acquires the surface slope; the shape data are calculated by integration. In this way, the PSF can be calculated for real case scenarios, e.g., when the light source is close to infinity and off-axis. The major challenge is the calibration of the PMD sensor, specifically because the PSF data have to be reconstructed from different camera views. The calibration of the setup is described, and measurements presented and compared to results obtained with the direct approach.
Keywords: 3D-metrology; Deflectometry; Interferometry; Optical testing; Telescope

Density of GeV muons in air showers measured with IceTop - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Physical Review D, 2022)
We present a measurement of the density of GeV muons in near-vertical air showers using three years of data recorded by the IceTop array at the South Pole. Depending on the shower size, the muon densities have been measured at lateral distances between 200 and 1000 m. From these lateral distributions, we derive the muon densities as functions of energy at reference distances of 600 and 800 m for primary energies between 2.5 and 40 PeV and between 9 and 120 PeV, respectively. The muon densities are determined using, as a baseline, the hadronic interaction model Sibyll 2.1 together with various composition models. The measurements are consistent with the predicted muon densities within these baseline interaction and composition models. The measured muon densities have also been compared to simulations using the post-LHC models EPOS-LHC and QGSJet-II.04. The result of this comparison is that the post-LHC models together with any given composition model yield higher muon densities than observed. This is in contrast to the observations above 1 EeV where all model simulations yield for any mass composition lower muon densities than the measured ones. The post-LHC models in general feature higher muon densities so that the agreement with experimental data at the highest energies is improved but the muon densities are not correct in the energy range between 2.5 and about 100 PeV.
CRIS-Team Scopus Importer:2022-09-02

Dependence of atmospheric muon flux on seawater depth measured with the first KM3NeT detection units: The KM3NeT Collaboration - Ageron, M.; Aiello, S.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Bagatelas, C.; Barbarino, G.; Baret, B.; et al. (European Physical Journal C: Particles and Fields, 2020)
KM3NeT is a research infrastructure located in the Mediterranean Sea, that will consist of two deep-sea Cherenkov neutrino detectors. With one detector (ARCA), the KM3NeT Collaboration aims at identifying and studying TeV–PeV astrophysical neutrino sources. With the other detector (ORCA), the neutrino mass ordering will be determined by studying GeV-scale atmospheric neutrino oscillations. The first KM3NeT detection units were deployed at the Italian and French sites between 2015 and 2017. In this paper, a description of the detector is presented, together with a summary of the procedures used to calibrate the detector in-situ. Finally, the measurement of the atmospheric muon flux between 2232–3386 m seawater depth is obtained.
CRIS-Team Scopus Importer:2020-02-18

Design and performance of the first IceAct demonstrator at the South Pole - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Journal of Instrumentation, 2020)
In this paper we describe the first results of IceAct, a compact imaging air-Cherenkov telescope operating in coincidence with the IceCube Neutrino Observatory (IceCube) at the geographic South Pole. An array of IceAct telescopes (referred to as the IceAct project) is under consideration as part of the IceCube-Gen2 extension to IceCube. Surface detectors in general will be a powerful tool in IceCube-Gen2 for distinguishing astrophysical neutrinos from the dominant backgrounds of cosmic-ray induced atmospheric muons and neutrinos: the IceTop array is already in place as part of IceCube, but has a high energy threshold. Although the duty cycle will be lower for the IceAct telescopes than the present IceTop tanks, the IceAct telescopes may prove to be more effective at lowering the detection threshold for air showers. Additionally, small imaging air-Cherenkov telescopes in combination with IceTop, the deep IceCube detector or other future detector systems might improve measurements of the composition of the cosmic ray energy spectrum. In this paper we present measurements of a first 7-pixel imaging air Cherenkov telescope demonstrator, proving the capability of this technology to measure air showers at the South Pole in coincidence with IceTop and the deep IceCube detector.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Cherenkov detectors; Gamma telescopes; Large detector systems for particle and astroparticle physics; Neutrino detectors

Design and sensitivity of the Radio Neutrino Observatory in Greenland (RNO-G) - Aguilar, J. A.; Allison, P.; Beatty, J. J.; Bernhoff, H.; Besson, D.; Bingefors, N.; Botner, O.; Buitink, S.; Carter, K.; Clark, B. A.; Connolly, A.; Dasgupta, P.; et al. (Journal of Instrumentation, 2021)
This article presents the design of the Radio Neutrino Observatory Greenland (RNO-G) and discusses its scientific prospects. Using an array of radio sensors, RNO-G seeks to measure neutrinos above 10 PeV by exploiting the Askaryan effect in neutrino-induced cascades in ice. We discuss the experimental considerations that drive the design of RNO-G, present first measurements of the hardware that is to be deployed and discuss the projected sensitivity of the instrument. RNO-G will be the first production-scale radio detector for in-ice neutrino signals.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Large detector systems for particle and astroparticle physics; Neutrino detectors

Detailed spectral and morphological analysis of the shell type SNR RCW 86 - Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Angüner, E. O.; Backes, M.; Balzer, A.; Becherini, Y.; Becker Tjus, J.; Berge, D.; Bernhard, S.; Bernlöhr, K.; et al. (Astronomy & Astrophysics, 2018)
Aims. We aim for an understanding of the morphological and spectral properties of the supernova remnant RCW 86 and for insights into the production mechanism leading to the RCW 86 very high-energy gamma-ray emission.Methods. We analyzed High Energy Spectroscopic System (H.E.S.S.) data that had increased sensitivity compared to the observations presented in the RCW 86 H.E.S.S. discovery publication. Studies of the morphological correlation between the 0.5-1 keV X-ray band, the 2-5 keV X-ray band, radio, and gamma-ray emissions have been performed as well as broadband modeling of the spectral energy distribution with two different emission models.Results. We present the first conclusive evidence that the TeV gamma-ray emission region is shell-like based on our morphological studies. The comparison with 2-5 keV X-ray data reveals a correlation with the 0.4-50 TeV gamma-ray emission. The spectrum of RCW 86 is best described by a power law with an exponential cutoff at E-cut = (3.5 +/- 1.2(stat)) TeV and a spectral index of Gamma approximate to 1.6 +/- 0.2. A static leptonic one-zone model adequately describes the measured spectral energy distribution of RCW 86, with the resultant total kinetic energy of the electrons above 1 GeV being equivalent to similar to 0.1% of the initial kinetic energy of a Type Ia supernova explosion (10(51) erg). When using a hadronic model, a magnetic field of B approximate to 100 mu G is needed to represent the measured data. Although this is comparable to formerly published estimates, a standard E-2 spectrum for the proton distribution cannot describe the gamma-ray data. Instead, a spectral index of Gamma(p) approximate to 1.7 would be required, which implies that similar to 7 x 10(49)/n(cm-3) erg has been transferred into high-energy protons with the effective density n(cm-3) = n/1 cm(-3). This is about 10% of the kinetic energy of a typical Type Ia supernova under the assumption of a density of 1 cm(-3).
Keywords: astroparticle physics; gamma rays: general; ISM: supernova remnants; cosmic rays

Detecting cosmic rays with the LOFAR radio telescope - Schellart, Pim; Nelles, Anna; Buitink, Stijn; Corstanje, A.; Enriquez, J. E.; Falcke, H.; Frieswijk, W.; Horandel, J. R.; Horneffer, A.; James, Clancy; Krause, Maria; Mevius, M.; et al. (Astronomy & Astrophysics, 2013)
The low frequency array (LOFAR), is the first radio telescope designed with the capability to measure radio emission from cosmic-ray induced air showers in parallel with interferometric observations. In the first similar to 2 years of observing, 405 cosmic-ray events in the energy range of 10(16)-10(18) eV have been detected in the band from 30-80 MHz. Each of these air showers is registered with up to similar to 1000 independent antennas resulting in measurements of the radio emission with unprecedented detail. This article describes the dataset, as well as the analysis pipeline, and serves as a reference for future papers based on these data. All steps necessary to achieve a full reconstruction of the electric field at every antenna position are explained, including removal of radio frequency interference, correcting for the antenna response and identification of the pulsed signal.
Keywords: astroparticle physics; methods: data analysis; instrumentation: interferometers

Detection of a particle shower at the Glashow resonance with IceCube - Aartsen, M. G.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Amin, N. M.; Andeen, K.; Anderson, T.; Ansseau, I.; et al. (Nature, 2021)
The Glashow resonance describes the resonant formation of a W- boson during the interaction of a high-energy electron antineutrino with an electron(1), peaking at an antineutrino energy of 6.3 petaelectronvolts (PeV) in the rest frame of the electron. Whereas this energy scale is out of reach for currently operating and future planned particle accelerators, natural astrophysical phenomena are expected to produce antineutrinos with energies beyond the PeV scale. Here we report the detection by the IceCube neutrino observatory of a cascade of high-energy particles (a particle shower) consistent with being created at the Glashow resonance. A shower with an energy of 6.05 +/- 0.72 PeV (determined from Cherenkov radiation in the Antarctic Ice Sheet) was measured. Features consistent with the production of secondary muons in the particle shower indicate the hadronic decay of a resonant W- boson, confirm that the source is astrophysical and provide improved directional localization. The evidence of the Glashow resonance suggests the presence of electron antineutrinos in the astrophysical flux, while also providing further validation of the standard model of particle physics. Its unique signature indicates a method of distinguishing neutrinos from antineutrinos, thus providing a way to identify astronomical accelerators that produce neutrinos via hadronuclear or photohadronic interactions, with or without strong magnetic fields. As such, knowledge of both the flavour (that is, electron, muon or tau neutrinos) and charge (neutrino or antineutrino) will facilitate the advancement of neutrino astronomy.
CRIS-Team WoS Importer:2021-03-19

(untitled) - van Eldik, Christopher; et al.

Detection of extended γ -ray emission around the Geminga pulsar with H.E.S.S. - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Bi, B.; Böttcher, M.; et al. (Astronomy & Astrophysics, 2023)
Geminga is an enigmatic radio-quiet γ-ray pulsar located at a mere 250 pc distance from Earth. Extended very-high-energy γ-ray emission around the pulsar was discovered by Milagro and later confirmed by HAWC, which are both water Cherenkov detector-based experiments. However, evidence for the Geminga pulsar wind nebula in gamma rays has long evaded detection by imaging atmospheric Cherenkov telescopes (IACTs) despite targeted observations. The detection of γ-ray emission on angular scales ≳2° poses a considerable challenge for the background estimation in IACT data analysis. With recent developments in understanding the complementary background estimation techniques of water Cherenkov and atmospheric Cherenkov instruments, the H.E.S.S. IACT array can now confirm the detection of highly extended γ-ray emission around the Geminga pulsar with a radius of at least 3° in the energy range 0.5-40 TeV. We find no indications for statistically significant asymmetries or energy-dependent morphology. A flux normalisation of (2.8 ± 0.7)×10-12 cm-2 s-1 TeV-1 at 1 TeV is obtained within a 1° radius region around the pulsar. To investigate the particle transport within the halo of energetic leptons around the pulsar, we fitted an electron diffusion model to the data. The normalisation of the diffusion coefficient obtained of D0 = 7.6-1.2+1.5×1027 cm2 s-1, at an electron energy of 100 TeV, is compatible with values previously reported for the pulsar halo around Geminga, which is considerably below the Galactic average.
CRIS-Team Scopus Importer:2023-06-16
Keywords: Acceleration of particles; Diffusion; Gamma rays: general; Pulsars: general

Detection of gamma rays from a starburst galaxy - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Science, 2009)
Starburst galaxies exhibit in their central regions a highly increased rate of supernovae, the remnants of which are thought to accelerate energetic cosmic rays up to energies of -10 electron volts. We report the detection of gamma rays-tracers of such cosmic rays-from the starburst galaxy NGC 253 using the High Energy Stereoscopic System (H.E.S.S.) array of imaging atmospheric Cherenkov telescopes. The gamma-ray flux above 220 billion electron volts is F = (5.5 = 1.0 ± 2.8) x 10 cm s, implying a cosmic-ray density about three orders of magnitude larger than that in the center of the Milky Way. The fraction of cosmic-ray energy channeled into gamma rays in this starburst environment is five times as large as that in our Galaxy.

Detection of the Temporal Variation of the Sun's Cosmic Ray Shadow with the IceCube Detector - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Astrophysical Journal, 2019)
We report on the observation of a deficit in the cosmic ray flux from the directions of the Moon and Sun with five years of data taken by the IceCube Neutrino Observatory. Between 2010 May and 2011 May the IceCube detector operated with 79 strings deployed in the glacial ice at the South Pole, and with 86 strings between 2011 May and 2015 May. A binned analysis is used to measure the relative deficit and significance of the cosmic ray shadows. Both the cosmic ray Moon and Sun shadows are detected with high statistical significance (> 10 sigma) for each year. The results for the Moon shadow are consistent with previous analyses and verify the stability of the IceCube detector over time. This work represents the first observation of the Sun shadow with the IceCube detector. We show that the cosmic ray shadow of the Sun varies with time. These results make it possible to study cosmic ray transport near the Sun with future data from IceCube.
CRIS-Team WoS Importer:2019-03-06

Detection of variable VHE gamma-ray emission from the extra-galactic gamma-ray binary LMC P3 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, Michael; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Context. Recently, the high-energy (HE, 0.1-100 GeV) gamma-ray emission from the object LMC P3 in the Large Magellanic Cloud (LMC) has been discovered to be modulated with a 10.3-day period, making it the first extra-galactic gamma-ray binary.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Binaries: general; Stars: massive

Detection of very high energy radiation from HESS J1908+063 confirms the Milagro unidentified source MGRO J1908+06 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, Wystan; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Aims. Detection of a γ-ray source above 300 GeV is reported, confirming the unidentified source MGRO J1908+06, discovered by the Milagro collaboration at a median energy of 20 TeV. Methods. The source was observed during 27 h as part of the extension of the HESS Galactic plane survey to longitudes >30°. Results. HESS J108+063 is detected at a significance level of 10.9σ with an integral flux above 1 TeV of (3.76 ± 0.29 ph cm s, and a spectral photon index Γ = 2.10 ± 0.07 ± 0.2. The positions and fluxes of HESS J1908+063 and MGRO J1908+06 are in good agreement. Possible counterparts at other wavelengths and the origin of the γ-ray emission are discussed. The nearby unidentified GeV source, GRO J1908+0556 (GeV) which also remains unidentified and the new Fermi pulsar 0FGL J1907.5+0617, may be connected to the TeV source. © ESO 2009.
Keywords: Gamma rays; Observations

Detection potential of the KM3NeT detector for high-energy neutrinos from the Fermi bubbles - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Astroparticle Physics, 2013)
A recent analysis of the Fermi Large Area Telescope data provided evidence for a high-intensity emission of high-energy gamma rays with a E-2 spectrum from two large areas, spanning 50 above and below the Galactic centre (the "Fermi bubbles"). A hadronic mechanism was proposed for this gamma-ray emission making the Fermi bubbles promising source candidates of high-energy neutrino emission. In this work Monte Carlo simulations regarding the detectability of high-energy neutrinos from the Fermi bubbles with the future multi-km(3) neutrino telescope KM3NeT in the Mediterranean Sea are presented. Under the hypothesis that the gamma-ray emission is completely due to hadronic processes, the results indicate that neutrinos from the bubbles could be discovered in about one year of operation, for a neutrino spectrum with a cutoff at 100 TeV and a detector with about 6 km(3) of instrumented volume. The effect of a possible lower cutoff is also considered. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Fermi Bubbles; KM3NeT

Determining the neutrino mass ordering and oscillation parameters with KM3NeT/ORCA - Aiello, S.; Domi, Alba; Albert, A.; Alves Garre, S.; Aly, Z.; Ambrosone, A.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, G.; et al. (European Physical Journal C: Particles and Fields, 2022)
The next generation of water Cherenkov neutrino telescopes in the Mediterranean Sea are under construction offshore France (KM3NeT/ORCA) and Sicily (KM3NeT/ARCA). The KM3NeT/ORCA detector features an energy detection threshold which allows to collect atmospheric neutrinos to study flavour oscillation. This paper reports the KM3NeT/ORCA sensitivity to this phenomenon. The event reconstruction, selection and classification are described. The sensitivity to determine the neutrino mass ordering was evaluated and found to be 4.4σ if the true ordering is normal and 2.3σ if inverted, after 3 years of data taking. The precision to measure Δm322 and θ23 were also estimated and found to be 85.10-6eV2 and (-3.1+1.9)∘ for normal neutrino mass ordering and, 75.10-6eV2 and (-7.0+2.0)∘ for inverted ordering. Finally, a unitarity test of the leptonic mixing matrix by measuring the rate of tau neutrinos is described. Three years of data taking were found to be sufficient to exclude [InlineEquation not available: see fulltext.] event rate variations larger than 20% at 3 σ level.
CRIS-Team Scopus Importer:2022-01-21

Developing new analysis tools for near surface radio-based neutrino detectors - Anker, A.; Baldi, P.; Barwick, S.; Beise, J.; Besson, D.; Chen, P.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hanson, J.; Klein, S.; Kleinfelder, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2023)
The ARIANNA experiment is an Askaryan radio detector designed to measure high-energy neutrino induced cascades within the Antarctic ice. Ultra-high-energy neutrinos above 1016 eV have an extremely low flux, so experimental data captured at trigger level need to be classified correctly to retain as much neutrino signal as possible. We first describe two new physics-based neutrino selection methods, or “cuts”, (the updown and dipole cut) that extend the previously published analysis to a specialized ARIANNA station with 8 antenna channels, which is double the number used in the prior analysis. For a standard trigger with a threshold signal to noise ratio at 4.4, the new cuts produce a neutrino efficiency of > 95% per station-year of operation, while rejecting 99.93% of the background (corresponding to 53 remaining experimental background events). When the new cuts are combined with a previously developed cut using neutrino waveform templates, all background is removed at no change of efficiency. In addition, the neutrino efficiency is extrapolated to 1,000 station-years of operation, obtaining 91%. This work then introduces a new selection method (the deep learning cut) to augment the identification of neutrino events by using deep learning methods and compares the efficiency to the physics-based analysis. The deep learning cut gives 99% signal efficiency per station-year of operation while rejecting 99.997% of the background (corresponding to 2 remaining experimental background events), which are subsequently removed by the waveform template cut at no significant change in efficiency. The results of the deep learning cut were verified using measured cosmic rays which shows that the simulations do not introduce artifacts with respect to experimental data. The paper demonstrates that the background rejection and signal efficiency of near surface antennas meets the requirements of a large scale future array, as considered in baseline design of the radio component of IceCube-Gen2.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Machine learning; neutrino astronomy; neutrino detectors; ultra high energy photons and neutrinos

Development of an analysis to probe the neutrino mass ordering with atmospheric neutrinos using three years of IceCube DeepCore data: IceCube Collaboration - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (European Physical Journal C: Particles and Fields, 2020)
The Neutrino Mass Ordering (NMO) remains one of the outstanding questions in the field of neutrino physics. One strategy to measure the NMO is to observe matter effects in the oscillation pattern of atmospheric neutrinos above ∼1GeV, as proposed for several next-generation neutrino experiments. Moreover, the existing IceCube DeepCore detector can already explore this type of measurement. We present the development and application of two independent analyses to search for the signature of the NMO with three years of DeepCore data. These analyses include a full treatment of systematic uncertainties and a statistically-rigorous method to determine the significance for the NMO from a fit to the data. Both analyses show that the dataset is fully compatible with both mass orderings. For the more sensitive analysis, we observe a preference for normal ordering with a p-value of pIO= 15.3 % and CL s= 53.3 % for the inverted ordering hypothesis, while the experimental results from both analyses are consistent within their uncertainties. Since the result is independent of the value of δCP and obtained from energies Eν≳5GeV, it is complementary to recent results from long-baseline experiments. These analyses set the groundwork for the future of this measurement with more capable detectors, such as the IceCube Upgrade and the proposed PINGU detector.
CRIS-Team Scopus Importer:2020-01-14

Diffuse Galactic gamma-ray emission with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2014)
Diffuse γ-ray emission is the most prominent observable signature of celestial cosmic-ray interactions at high energies. While already being investigated at GeV energies over several decades, assessments of diffuse γ-ray emission at TeV energies remain sparse. After completion of the systematic survey of the inner Galaxy, the H.E.S.S. experiment is in a prime position to observe large-scale diffuse emission at TeV energies. Data of the H.E.S.S. Galactic Plane Survey are investigated in regions off known γ-ray sources. Corresponding γ-ray flux measurements were made over an extensive grid of celestial locations. Longitudinal and latitudinal profiles of the observed γ-ray fluxes show characteristic excess emission not attributable to known γ-ray sources. For the first time large-scale γ-ray emission along the Galactic plane using imaging atmospheric Cherenkov telescopes has been observed. While the background subtraction technique limits the ability to recover modest variation on the scale of the H.E.S.S. field of view or larger, which is characteristic of the inverse Compton scatter-induced Galactic diffuse emission, contributions of neutral pion decay as well as emission from unresolved γ-ray sources can be recovered in the observed signal to a large fraction. Calculations show that the minimum γ-ray emission from π0 decay represents a significant contribution to the total signal. This detection is interpreted as a mix of diffuse Galactic γ-ray emission and unresolved sources.

Discovery and follow-up studies of the extended, off-plane, VHE gamma-ray source HESS J1507-622 - Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; et al. (Astronomy & Astrophysics, 2010)
Context. The detection of gamma-rays in the very-high-energy (VHE) range (100 GeV-100 TeV) offers the possibility of studying the parent population of ultrarelativistic particles found in astrophysical sources, so it is useful for understanding the underlying astrophysical processes in nonthermal sources. Aims. The discovery of the VHE gamma-ray source HESS J1507-622 is reported and possibilities regarding its nature are investigated. Methods. The H.E.S.S. array of imaging atmospheric Cherenkov telescopes (IACTs) has a high sensitivity compared with previous instruments (∼1% of the Crab flux in 25 h observation time for a 5σ point-source detection) and has a large field of view (∼5° in diameter). HESS J1507-622 was discovered within the ongoing H.E.S.S. survey of the inner Galaxy, and the source was also studied by means of dedicated multiwavelength observations. Results. A Galactic gamma-ray source, HESS J1507-622, located ∼3.5° from the Galactic plane was detected with a statistical significance >9σ. Its energy spectrum is well fitted by a power law with spectral index Γ = 2.24 ± 0.16 ± 0.20 and a flux above 1 TeV of (1.5 ± 0.4 ± 0.3) × 10 cm s. Possible interpretations (considering both hadronic and leptonic models) of the VHE gamma-ray emission are discussed in the absence of an obvious counterpart. © ESO 2010.
Keywords: gamma rays: general; X-rays: general

Discovery of a point-like very-high-energy γ-ray source in Monoceros - Funk, Stefan; van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2007)
Aims. The complex Monoceros Loop SNR/Rosette Nebula region contains several potential sources of very-high-energy (VHE) y-ray emission and two as yet unidentified high-energy EGRET sources. Sensitive VHE observations are required to probe acceleration processes in this region. Methods. The HESS telescope array has been used to search for very high-energy y-ray sources in this region. CO data from the NANTEN telescope were used to map the molecular clouds in the region, which could act as target material for γ-ray production via hadronic interactions. Results. We announce the discovery of a new y-ray source, HESS J0632+057, located close to the rim of the Monoceros SNR. This source is unresolved by HESS and has no clear counterpart at other wavelengths but is possibly associated with the weak X-ray source 1RXS J063258.3+054857, the Be-star MWC 148 and/or the lower energy γ-ray source 3EGJ0634+0521. No evidence for an associated molecular cloud was found in the CO data. © ESO 2007.
Keywords: Gamma rays: observations

Discovery of a VHE gamma-ray source coincident with the supernova remnant CTB 37A - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Borrel, V.; Braun, Isabel; et al. (Astronomy & Astrophysics, 2008)
Aims. The supernova remnant (SNR) complex CTB 37 is an interesting candidate for observations with very high energy (VHE) γ-ray telescopes such as HESS. In this region, three SNRs are seen. One of them is potentially associated with several molecular clouds, a circumstance that can be used to probe the acceleration of hadronic cosmic rays. Methods. This region was observed with the HESS Cherenkov telescopes and the data were analyzed with standard HESS procedures. Recent X-ray observations with Chandra and XMM-Newton were used to search for X-ray counterparts. Results. The discovery of a new VHE γ-ray source HESS J1714-385 coincident with the remnant CTB 37A is reported. The energy spectrum is well described by a power-law with a photon index of Γ = 2.30 ± 0.13 and a differential flux at 1 TeV of Φ = (8.7 ± 1.0 ± 1.8) × 10 cm s TeV. The integrated flux above 1 TeV is equivalent to 3% of the flux of the Crab nebula above the same energy. This VHE γ-ray source is a counterpart candidate for the unidentified EGRET source 3EG J1714-3857. The observed VHE emission is consistent with the molecular gas distribution around CTB 37A; a close match is expected in a hadronic scenario for γ-ray production. The X-ray observations reveal the presence of thermal X-rays from the NE part of the SNR. In the NW part of the remnant, an extended non-thermal X-ray source, CXOU J171419.8-383023, is discovered as well. Possible connections of the X-ray emission to the newly found VHE source are discussed. © ESO 2008.
Keywords: Gamma rays: observations; ISM: supernova remnants; X-rays: individuals: G348.5+0.1

Discovery of gamma-ray emission from the extragalactic pulsar wind nebula N 157B with H.E.S.S. - Abramowski, A.; Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
We present the significant detection of the first extragalactic pulsar wind nebula (PWN) detected in gamma rays, N- 157B, located in the large Magellanic Cloud (LMC). Pulsars with high spin-down luminosity are found to power energised nebulae that emit gamma rays up to energies of several tens of TeV. N- 157B is associated with PSR- J0537-6910, which is the pulsar with the highest known spin-down luminosity. The High Energy Stereoscopic System telescope array observed this nebula on a yearly basis from 2004 to 2009 with a dead-time corrected exposure of 46- h. The gamma-ray spectrum between 600- GeV and 12- TeV is well-described by a pure power-law with a photon index of 2.8 ± 0.2 ± 0.3 and a normalisation at 1- TeV of (8.2 ± 0.8 ± 2.5 ) × 10 cm - s - TeV . A leptonic multi-wavelength model shows that an energy of about 4 × 10 erg is stored in electrons and positrons. The apparent efficiency, which is the ratio of the TeV gamma-ray luminosity to the pulsar's spin-down luminosity, 0.08% ± 0.01%, is comparable to those of PWNe found in the Milky Way. The detection of a PWN at such a large distance is possible due to the pulsar's favourable spin-down luminosity and a bright infrared photon-field serving as an inverse-Compton-scattering target for accelerated leptons. By applying a calorimetric technique to these observations, the pulsar's birth period is estimated to be shorter than 10 ms. © ESO, 201
Keywords: Gamma rays: general; ISM: supernova remnants; Magellanic Clouds; Pulsars: individual: PSR J0537-6910

Discovery of gamma-ray emission from the shell-type supernova remnant RCW 86 with Hess - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astrophysical Journal, 2009)
The shell-type supernova remnant (SNR) RCW 86, possibly associated with the historical supernova SN 185, with its relatively large size (about 40′ in diameter) and the presence of nonthermal X-rays is a promising target for γ-ray observations. The high sensitivity, good angular resolution of a few arcminutes and the large field of view of the High Energy Stereoscopic System (HESS) make it ideally suited for the study of γ-ray morphology of such extended sources. HESS observations have indeed led to the discovery of the SNR RCW 86 in very high energy (VHE; E > 100 GeV) γ-rays. With 31 hr of observation time, the source is detected with a statistical significance of 8.5σ and is significantly more extended than the HESS point-spread function. Morphological studies have been performed and show that the γ-ray flux does not correlate perfectly with the X-ray emission. The flux from the remnant is ∼10% of the flux from the Crab nebula, with a similar photon index of about 2.5. Possible origins of the VHE γ-ray emission, via either Inverse Compton scattering by electrons or the decay of neutral pions produced by proton interactions, are discussed on the basis of spectral features obtained both in the X-ray and γ-ray regimes. © 2009. The American Astronomical Society. All rights reserved.
Keywords: gamma rays: observations; ISM: individual (RCW 86; G315.4-2.3); supernova remnants

Discovery of high and very high-energy emission from the BL Lacertae object SHBL J001355.9-185406 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy and Astrophysics, 2013)
Keywords: BL Lacertae objects: individual: SHBL J001355.9-185406; gamma rays: general

Discovery of TeV γ-ray emission from PKS 0447-439 and derivation of an upper limit on its redshift - Abramowski, A.; Acero, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Behera, B.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Very high-energy γ-ray emission from PKS 0447-439 was detected with the H.E.S.S. Cherenkov telescope array in December 2009. This blazar is one of the brightest extragalactic objects in the Fermi bright source list and has a hard spectrum in the MeV to GeV range. In the TeV range, a photon index of 3.89 ± 0.37 (stat) ±0.22 (sys) and a flux normalisation at 1 TeV, Φ = (3.5 ± 1.1(stat) ± 0.9(sys)) × 10 cm s TeV were found. The detection with H.E.S.S. triggered observations in the X-ray band with the Swift and RXTE telescopes. Simultaneous UV and optical data from Swift UVOT and data from the optical telescopes ATOM and ROTSE are also available. The spectrum and light curve measured with H.E.S.S. are presented and compared to the multi-wavelength data at lower energies. A rapid flare is seen in the Swift XRT and RXTE data, together with a flux variation in the UV band, at a time scale of the order of one day. A firm upper limit of z < 0.59 on the redshift of PKS 0447-439 is derived from the combined Fermi-LAT and H.E.S.S. data, given the assumptions that there is no upturn in the intrinsic spectrum above the Fermi-LAT energy range and that absorption on the extragalactic background light (EBL) is not weaker than the lower limit provided by current models. The spectral energy distribution is well described by a simple one-zone synchrotron self-Compton scenario, if the redshift of the source is less than z â‰ 0.4. © 2013 ESO.
Keywords: BL Lacertae objects: individual: PKS 0447-439; Galaxies: active; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Discovery of the Hard Spectrum VHE γ-Ray Source HESS J1641-463 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Uner, E. O. Ang; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astrophysical Journal Letters, 2014)
Keywords: cosmic rays; gamma rays: general; ISM: individual objects (SNR G338.30.0; SNR G338.5+0.1)

Discovery of the source HESS J1356-645 associated with the young and energetic PSR J1357-6429 - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astronomy & Astrophysics, 2011)
Context. Several newly discovered very-high-energy (VHE; E > 100 GeV) γ-ray sources in the Galaxy are thought to be associated with energetic pulsars. Among them, middle-aged (10 yr) systems exhibit large centre-filled VHE nebulae, offset from the pulsar position, which result from the complex relationship between the pulsar wind and the surrounding medium, and reflect the past evolution of the pulsar. Aims. Imaging Atmospheric Cherenkov Telescopes (IACTs) have been successful in revealing extended emission from these sources in the VHE regime. Together with radio and X-ray observations, this observational window allows one to probe the energetics and magnetic field inside these large-scale nebulae. Methods. H.E.S.S., with its large field of view, angular resolution of 0.1° and unprecedented sensitivity, has been used to discover a large population of such VHE sources. In this paper, the H.E.S.S. data from the continuation of the Galactic Plane Survey (-80° < < 60°, |b| < 3°), together with the existing multi-wavelength observations, are used. Results. A new VHE γ-ray source was discovered at RA (J2000) = 135600, Dec (J2000) =-64°30′00′′ with a 2′ statistical error in each coordinate, namely HESS J1356-645. The source is extended, with an intrinsic Gaussian width of (0.20 ± 0.02)°. Its integrated energy flux between 1 and 10 TeV of 8 × 10 erg cm s represents ∼11% of the Crab Nebula flux in the same energy band. The energy spectrum between 1 and 20 TeV is well described by a power law dN/dE E with photon index Γ = 2.2 ± 0.2 ± 0.2. The inspection of archival radio images at three frequencies and the analysis of X-ray data from ROSAT/PSPC and XMM-Newton/MOS reveal the presence of faint non-thermal diffuse emission coincident with HESS J1356-645. Conclusions. HESS J1356-645 is most likely associated with the young and energetic pulsar PSR J1357-6429 (d = 2.4 kpc, τ = 7.3 kyr and Å-= 3.1 × 10 erg s), located at a projected distance of ∼5 pc from the centroid of the VHE emission. HESS J1356-645 and its radio and X-ray counterparts would thus represent the nebula resulting from the past history of the PSR J1357-6429 wind. In a simple one-zone model, © 2011 ESO.
Keywords: gamma rays: general; ISM: individual objects: HESS J1356-645; ISM: individual objects: PSR J1357-6429; surveys

Discovery of the two "wings" of the Kookaburra complex in VHE γ-rays with HESS - Funk, Stefan; van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2006)
Aims. Search for Very High Energy γ-ray emission in the Kookaburra complex through observations with the HESS array. Methods. Stereoscopic imaging of Cherenkov light emission of the γ-ray showers in the atmosphere is used for the reconstruction and selection of the events to search for γ-ray signals. Their spectrum is derived by a forward-folding maximum likelihood fit. Results. Two extended γ-ray sources with an angular (68%) radius of 3.3-3.4′ are discovered at high (>13σ) statistical significance: HESS J1420-607 and HESS J1418-609. They exhibit a flux above 1 TeV of (2.97 ±0.188 ±0.60) × 10 and (2.17 ±0.17 ±0.43) × 10 cm s, respectively, and similar hard photon indices ∼2.2. Multi-wavelength comparisons show spatial coincidence with the wings of the Kookaburra. Two pulsar wind nebulae candidates, K3/PSR J1420-6048 and the Rabbit, lie on the edge of the HESS sources. Conclusions. The two new sources confirm the non-thermal nature of at least parts of the two radio wings which overlap with the γ-ray emission and establish their connection with the two X-ray pulsar wind nebulae candidates. Given the large point spread function of EGRET, the unidentified source(s) 3EG J1420-6038/GeV J1417-6100 could possibly be related to either or both HESS sources. The most likely explanation for the Very High Energy γ-rays discovered by HESS is inverse Compton emission of accelerated electrons on the Cosmic Microwave Background near the two candidate pulsar wind nebulæ, K3/PSR J1420-6048 and the Rabbit. Two scenarios which could lead to the observed large (∼10 pc) offset-nebula type morphologies are briefly discussed. © ESO 2006.
Keywords: Gamma rays: observations; ISM: general; Radiation mechanisms: non-thermal

Discovery of the VHE gamma-ray source HESS J1832-093 in the vicinity of SNR G22.7-0.2 - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
Keywords: astroparticle physics; ISM: individual objects: HESS J1832-093; ISM: individual objects: SNR G22.7-0.2; gamma-rays: general

Discovery of variable VHE gamma-ray emission from the binary system 1FGL J1018.6-5856 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balzer, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; Bernhard, S.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2015)
Re-observations with the HESS telescope array of the very high-energy (VHE) source HESS J1018-589A that is coincident with the Fermi-LAT gamma-ray binary 1FGL J1018.6-5856 have resulted in a source detection significance of more than 9 sigma and the detection of variability (chi(2)/nu of 238.3/155) in the emitted gamma-ray flux. This variability confirms the association of HESS J1018-589A with the high-energy gamma-ray binary detected Fermi-LAT and also confirms the point-like source as a new VHE binary system. The spectrum of HESS J1018-589A is best fit with a power-law function with photon index Gamma = 2.20 +/- 0.14(stat) +/- 0.2(sys). Emission is detected up to similar to 20 TeV. The mean differential flux level is (2.9 +/- 0.4) x 10(-13) TeV-1 cm(-2) s(-1) at 1 TeV, equivalent to similar to 1% of the flux from the Crab Nebula at the same energy. Variability is clearly detected the night-by-night light curve. When folded on the orbital period of 16.58 days, the rebinned light curve peaks in phase with the observed X-ray high-energy phaseograms. The fit of the HESS phaseogram to a constant flux provides evidence of periodicity at the level of N-sigma > 3 sigma. The of the VHE phaseogram and measured spectrum suggest a low-inclination, low-eccentricity system with a modest impact from VHE gamma-ray due to pair production (tau less than or similar to 1 at 300 GeV).
Keywords: Acceleration of particles; Gamma rays: stars; Radiation mechanisms: non-thermal; Stars: individual: 1FGL J1018.6-5856; X-rays: binaries

Discovery of very high energy gamma-ray emission coincident with molecular clouds in the W 28 (G6.4-0.1) field - Aharonian, F.; Akhperjanian, A. G.; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, Wystan; Berge, David; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
Aims. Observations of shell-type supernova remnants (SNRs) in the GeV to multi-TeV -ray band, coupled with those at millimetre radio wavelengths, are motivated by the search for cosmic-ray accelerators in our Galaxy. The old-age mixed-morphology SNR W 28 (distance ∼2 kpc) is a prime target due to its interaction with molecular clouds along its northeastern boundary and other clouds situated nearby.Methods. We observed the W 28 field (for ∼40 h) at very high energy (VHE) -ray energies ( 0.1]]> TeV) with the HESS. Cherenkov telescopes. A reanalysis of EGRET 100]]> MeV data was also undertaken. Results from the NANTEN 4 m telescope Galactic plane survey and other CO observations were used to study molecular clouds. Results. We have discovered VHE -ray emission (HESS J1801-233) coincident with the northeastern boundary of W 28 and a complex of sources (HESS J1800-240A, B and C) ∼0.5° south of W 28 in the Galactic disc. The EGRET source (GRO J1801-2320) is centred on HESS J1801-233 but may also be related to HESS J1800-240 given the large EGRET point spread function. The VHE differential photon spectra are well fit by pure power laws with indices ∼2.3 to 2.7. The spectral indices of HESS J1800-240A, B, and C are consistent within statistical errors. All VHE sources are ∼10 in intrinsic radius except for HESS J1800-240C, which appears pointlike. The NANTEN CO() data reveal molecular clouds positionally associating with the VHE emission, spanning a ∼15 km s range in local standard of rest velocity. Conclusions. The VHE/molecular cloud association could indicate a hadronic origin for HESS J1801-233 and HESS J1800-240, and several cloud components in projection may contribute to the VHE emission. The clouds have components covering a broad velocity range encompassing the distance estimates for W 28 (∼2 kpc) and extending up to ∼4 kpc. Assuming hadronic origin and distances of 2 and 4 kpc for cloud components, the required cosmic-ray density enhancement factors (with respect to the solar value) are in the range ∼10 to ∼30. If situated at 2 kpc distance, such cosmic-ray densities may be supplied by SNRs like W 28. Additionally and/or alternatively, particle acceleration may come from several catalogued SNRs and SNR candidates, the energetic ultra compact HII region W 28A2, and the HII regions M 8 and M 20, along with their associated open clusters. Further sub-mm observations would be recommended to probe in detail the dynamics of the molecular clouds at velocites ]]> 10 km s and their possible connection to W 28. © 2008 ESO.
Keywords: Gamma rays: observations

Discovery of very high energy γ-ray emission from centaurus a with H.E.S.S. - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astrophysical Journal, 2009)
We report the discovery of faint very high energy (VHE; E > 100GeV) γ-ray emission from the radio galaxy Centaurus A in observations performed with the High Energy Stereoscopic System (H.E.S.S.) experiment, an imaging atmospheric Cherenkov telescope array consisting of four telescopes located in Namibia. Centaurus A has been observed for more than 120hr. A signal with a statistical significance of 5.0σ is detected from the region including the radio core and the inner kpc jets. The integral flux above an energy threshold of 250 GeV is measured to be 0.8% of the flux of the Crab Nebula (apparent luminosity: L(>250GeV) 2.6 × 10ergs, adopting a distance of 3.8Mpc). The spectrum can be described by a power law with a photon index of 2.7 0.5 0.2. No significant flux variability is detected in the data set. However, the low flux only allows detection of variability on the timescale of days to flux increments above a factor of 15-20 (3σ and 4σ, respectively). The discovery of VHE γ-ray emission from Centaurus A reveals particle acceleration in the source to >TeV energies and, together with M87, establishes radio galaxies as a class of VHE emitters. © 2009. The American Astronomical Society. All rights reserved..
Keywords: Galaxies: active; Galaxies: individual (Cen A); Gamma rays: observations

(untitled) - van Eldik, Christopher; et al.
The extreme synchrotron BL Lac object H 2356-309, located at a redshift of z = 0.165, was observed from June to December 2004 with a total exposure of ≈40 h live-time with the HESS (High Energy Stereoscopic System) array of atmospheric-Cherenkov telescopes (ACTs). Analysis of this data set yields, for the first time, a strong excess of 453 γ-rays (10 standard deviations above background) from H 2356-309, corresponding to an observed integral flux above 200 GeV of I(>200 GeV) = (4.1 ±0.5) × 10 cm s (statistical error only). The differential energy spectrum of the source between 200 GeV and 1.3TeV is well-described by a power law with a normalisation (at 1 TeV) of N = (3.00 ±0.80 ± 0.31 )× 10 cm s TeV and a photon index of γ = 3.09 ± 0.24 ± 0.10 . H 2356-309 is one of the most distant BL Lac objects detected at very-high-energy γ-rays so far. Results from simultaneous observations from ROTSE-III (optical), RXTE (X-rays) and NRT (radio) are also included and used together with the HESS data to constrain a single-zone homogeneous synchrotron self-Compton (SSC) model. This model provides an adequate fit to the HESS data when using a reasonable set of model parameters. © ESO 200

Discovery of very high energy γ-ray emission from the BL Lacertae object PKS 0301-243 with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2013)
The active galactic nucleus PKS 0301-243 (z = 0.266) is a high-synchrotron-peaked BL Lac object that is detected at high energies (HE, 100 MeV <e 0301-243="" 100="" at="" by="" discovery="" e="" energies="" fermi="" high="" lat.="" of="" on="" paper="" pks="" reports="" the="" this="" very=""> 100 GeV) by the High Energy Stereoscopic System (H.E.S.S.) from observations between September 2009 and December 2011 for a total live time of 34.9 h. Gamma rays above 200 GeV are detected at a significance of 9.4σ. A hint of variability at the 2.5σ level is found. An integral flux I(E > 200 GeV) = (3.3 ± 1.1 ± 0.7) × 10 ph cm s and a photon index Γ = 4.6 ± 0.7 ± 0.2 are measured. Multi-wavelength light curves in HE, X-ray and optical bands show strong variability, and a minimal variability timescale of eight days is estimated from the optical light curve. A single-zone leptonic synchrotron self-Compton scenario satisfactorily reproduces the multi-wavelength data. In this model, the emitting region is out of equipartition and the jet is particle dominated. Because of its high redshift compared to other sources observed at TeV energies, the very high energy emission from PKS 0301-243 is attenuated by the extragalactic background light (EBL) and the measured spectrum is used to derive an upper limit on the opacity of the EBL. © 2013 ESO.</e>
Keywords: BL Lacertae objects: general; BL Lacertae objects: individual: PKS 0301-243; Galaxies: active; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Discovery of very-high-energy γ-rays from the Galactic Centre ridge - van Eldik, Christopher; et al. (Nature, 2006)
The source of Galactic cosmic rays (with energies up to 10 eV) remains unclear, although it is widely believed that they originate in the shock waves of expanding supernova remnants. At present the best way to investigate their acceleration and propagation is by observing the γ-rays produced when cosmic rays interact with interstellar gas . Here we report observations of an extended region of very-high-energy (>10 eV) γ-ray emission correlated spatially with a complex of giant molecular clouds in the central 200 parsecs of the Milky Way. The hardness of the γ-ray spectrum and the conditions in those molecular clouds indicate that the cosmic rays giving rise to the γ-rays are likely to be protons and nuclei rather than electrons. The energy associated with the cosmic rays could have come from a single supernova explosion around 10 years ago. © 2006 Nature Publishing Group.

Discovery of VHE γ-ray emission and multi-wavelength observations of the BL Lacertae object 1RXS J101015.9-311909 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astronomy & Astrophysics, 2012)
Keywords: gamma rays: galaxies; galaxies: active; BL Lacertae objects: individual: 1RXS J101015.9-311909

Discovery of VHE γ-rays from the high-frequency-peaked BL Lacertae object RGB J0152+017 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Borrel, V.; Braun, Isabel V; Brion, E.; et al. (Astronomy & Astrophysics, 2008)
Keywords: galaxies: BL Lacertae objects: individual: RGB J0152+017; gamma rays: observations; galaxies: BL Lacertae objects: general; galaxies: active

Discovery of VHE emission towards the Carina arm region with the H.E.S.S. telescope array: HESS? J1018-589 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astronomy & Astrophysics, 2012)
The Carina arm region, containing the supernova remnant SNR? G284.3-1.8, the high-energy (HE; E > 100 MeV) binary 1FGL? J1018.6-5856 and the energetic pulsar PSR? J1016-5857 and its nebula, has been observed with the H.E.S.S. telescope array. The observational coverage of the region in very-high-energy (VHE; E > 0.1? TeV) γ-rays benefits from deep exposure (40? h) of the neighboring open cluster Westerlund 2. The observations have revealed a new extended region of VHE γ-ray emission. The new VHE source HESS? J1018-589 shows a bright, point-like emission region positionally coincident with SNR? G284.3-1.8 and 1FGL? J1018.6-5856 and a diffuse extension towards the direction of PSR? J1016-5857. A soft (Γ = 2.7 ± 0.5) photon? index, with a differential flux at 1? TeV of N = (4.2 ± 1.1) × 10? TeV? cm? s is found for the point-like source, whereas the total emission region including the diffuse emission region is well fit by a power-law function with spectral index Γ = 2.9 ± 0.4 and differential flux at 1? TeV of N = (6.8 ± 1.6) × 10? TeV? cm? s. This H.E.S.S. detection motivated follow-up X-ray observations with the XMM-Newton satellite to investigate the origin of the VHE emission. The analysis of the XMM-Newton data resulted in the discovery of a bright, non-thermal point-like source (XMMU J101855.4-58564) with a photon index of Γ = 1.65 ± 0.08 in the center of SNR? G284.3-1.8, and a thermal, extended emission region coincident with its bright northern filament. The characteristics of this thermal emission are used to estimate the plasma density in the region as n 0.5 cm (2.9? kpc/d). The position of XMMU? J101855.4-58564 is compatible with the position reported by the Fermi-LAT collaboration for the binary system 1FGL? J1018.6-5856 and the variable Swift XRT source identified with it. The new X-ray data are used alongside archival multi-wavelength data to investigate the relationship between the VHE γ-ray emission from HESS? J1018-589 and the various potential counterparts in the Carina arm region. © ESO, 2012.
Keywords: Gamma rays: stars; ISM: individual objects: 1FGL J1018.6-5856; ISM: individual objects: PSRJ1016-5857; ISM: individual objects: SNRG284.3-1.8

Discovery of VHE γ -rays from the BL Lacertae object PKS 0548-322 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2010)
Aims. PKS 0548-322 (z = 0.069) is a "high-frequency-peaked" BL Lac object and a candidate very high energy (VHE, E > 100 GeV) γ-ray emitter, due to its high X-ray and radio flux. Observations at the VHE band provide insights into the origin of very energetic particles present in this source and the radiation processes at work. Methods. We report observations made between October 2004 and January 2008 with the HESS array, a four imaging atmospheric-Cherenkov telescopes. Contemporaneous UV and X-ray observations with the Swift satellite in November 2006 are also reported. Results. PKS 0548-322 is detected for the first time in the VHE band with HESS We measure an excess of 216 γ-rays corresponding to a significance of 5.6 standard deviations. The photon spectrum of the source is described by a power-law, with a photon index of Γ = 2.86 ± 0.34 ± 0.10 . The integral flux above 200 GeV is ∼1.3% of the flux of the Crab Nebula, and is consistent with being constant in time. Contemporaneous Swift/XRT observations reveal an X-ray flux between 2 and 10 keV of F = (2.3±0.2)×10 erg cm s, an intermediate intensity state with respect to previous observations. The spectral energy distribution can be reproduced using a simple one-zone synchrotron self Compton model, with parameters similar those observed for other sources of this type. © 2010 ESO.
Keywords: BL Lacertae objects: individual: PKS 0548-322; galaxies: active; gamma rays: observations

Dual-frequency VLBI study of Centaurus A on sub-parsec scales The highest-resolution view of an extragalactic jet - Müller, Cornelia; Kadler, Matthias; Roopesh, Ojha; Wilms, Jörn; Böck, Moritz; Edwards, P. G.; Fromm, C. M.; Hase, H.; Horiuchi, S.; Katz, Uli; Lovell, J. E. J.; Ploetz, C.; et al. (Astronomy & Astrophysics, 2011)
Context. Centaurus A is the closest active galactic nucleus. High resolution imaging using Very Long Baseline Interferometry (VLBI) enables us to study the spectral and kinematic behavior of the radio jet-counterjet system on sub-parsec scales, providing essential information for jet emission and formation models.Aims. Our aim is to study the structure and spectral shape of the emission from the central-parsec region of Cen A.Methods. As a target of the Southern Hemisphere VLBI monitoring program TANAMI (Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry), VLBI observations of Cen A are made regularly at 8.4 and 22.3 GHz with the Australian Long Baseline Array (LBA) and associated telescopes in Antarctica, Chile, and South Africa.Results. The first dual-frequency images of this source are presented along with the resulting spectral index map. An angular resolution of 0.4 mas x 0.7 mas is achieved at 8.4 GHz, corresponding to a linear scale of less than 0.013 pc. Hence, we obtain the highest resolution VLBI image of CenA, comparable to previous space-VLBI observations. By combining with the 22.3 GHz image, which has been taken without contributing transoceanic baselines at somewhat lower resolution, we present the corresponding dual-frequency spectral index distribution along the sub-parsec scale jet revealing the putative emission regions for recently detected gamma-rays from the core region by Fermi/LAT.Conclusions. We resolve the innermost structure of the milliarcsecond scale jet and counterjet system of CenA into discrete components. The simultaneous observations at two frequencies provide the highest resolved spectral index map of an AGN jet allowing us to identify multiple possible sites as the origin of the high energy emission.
Keywords: techniques: high angular resolution; galaxies: individual: Centaurus A; black hole physics; galaxies: active; galaxies: individual: NGC 5128; galaxies: jets

Dynamics of Development of Laser-Induced Structures on the Surface of a Titanium Alloy - Fomicheva, Iana; Druzhinin, Petr; Amler, Hans; Schuesslbauer, Wolfgang; Christiansen, Silke; Leuchs, Gerd (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
We investigated the dynamics of LSFL (Low Spatial Frequency LIPSS) evolution on the titanium alloy surface. To create them, 12 W picosecond 1.064 μm laser with a pulse repetition rate from 50 kHz to 500 kHz was used. For different laser repetition rate (500, 150, 100 and 50 kHz), the ranges of LSFL periods and peak Fluence of pulse (Fp) for which the maximum period is reached were determined. We also determined the laser parameters at which the resulting LSFL have good quality and uniformity, regardless of the initial surface roughness.
CRIS-Team Scopus Importer:2023-06-02
Keywords: HSFL; LIPSS; LSFL; surface patterning; Ti6Al4V; titanium alloy

Dynamikerweiterung durch Weißabgleich im Bildsensor - Schöberl, Michael; Schnurrer, Wolfgang; Foessel, S.; Kaup, André (16. Farbworkshop der German Color Group, Ilmenau, 2010)
Heutige Kameras besitzen eine feste spektrale Empfindlichkeit und können bei Beleuchtung ungünstiger Farbtemperatur nur einen reduzierten Dynamikbereich aufnehmen. Diese Einschränkung kann über ein neues Verfahren deutlich reduziert werden: Über ein digitales Neutraldichtefilte(ND-Filter) wird eine selektive Reduktion der Sensorempfindlichkeit für manche Farbkanäle erreicht. Dies führt zu einer Angleichung der Farbkanäle und damit einer Erweiterung des nutzbaren Dynamikumfangs. Die Anpassungen können digital schaltbar realisiert werden bei gleichzeitigem Erhalt der Blende, Bewegungsunschärfe und Sensorempfindlichkei

Effective LQC model for k=+1 isotropic cosmologies from spatial discretizations - Liegener, Klaus; Weigl, Stefan (Physical Review D, 2020)
The closed, spatially isotropic Friedmann-Lemaître-Robertson-Walker universe (k=+1) is endowed with modifications due to a discrete underlying space-structure. Motivated from loop quantum gravity techniques, a full Thiemann regularization is performed. The impact of these modifications of the single-graph-sector appearing in the scalar constraint are interpreted as physical quantum gravity effects. We investigate the form of the modified scalar constraint and its analytical approximations for k=+1 spacetimes and assume this effective constraint as the generator of dynamics on the reduced isotropic phase space. It transpires that the system still features a classical recollapse with only marginal discreteness corrections. Moreover, the initial and final singularities are resolved and we present an effective model mirroring the qualitative features of system.
CRIS-Team Scopus Importer:2020-12-11

Efficient propagation of systematic uncertainties from calibration to analysis with the SnowStorm method in IceCube - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Alispach, C.; Atoum, B. Al; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2019)
Efficient treatment of systematic uncertainties that depend on a large number of nuisance parameters is a persistent difficulty in particle physics and astrophysics experiments. Where low-level effects are not amenable to simple parameterization or re-weighting, analyses often rely on discrete simulation sets to quantify the effects of nuisance parameters on key analysis observables. Such methods may become computationally untenable for analyses requiring high statistics Monte Carlo with a large number of nuisance degrees of freedom, especially in cases where these degrees of freedom parameterize the shape of a continuous distribution. In this paper we present a method for treating systematic uncertainties in a computationally efficient and comprehensive manner using a single simulation set with multiple and continuously varied nuisance parameters. This method is demonstrated for the case of the depth-dependent effective dust distribution within the IceCube Neutrino Telescope.
CRIS-Team Scopus Importer:2019-12-13
Keywords: neutrino detectors; neutrino experiments; ultra high energy photons and neutrinos

Electromagnetic pulse protective shielding for digital x-ray detectors - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Fröjdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
Laser-driven x-ray backlighting can be used to image fast dynamic processes like the propagation of laser-driven shock waves in matter. We demonstrate and evaluate the feasibility of operating the JUNGFRAU detector designed by PSI, a direct detecting x-ray detector, in environments with extreme electromagnetic pulses. The electromagnetic pulse-protective housing is specifically designed for this detector and optimized for pump-probe experiments at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) facility at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. The beryllium x-ray entrance window of the protective housing has a high x-ray transmission of 94% at 8 keV. Measurements have shown that the housing simultaneously provides a relative damping of the electromagnetic field on average higher than 1000 in the frequency range of 100 MHz to 5 GHz. The results demonstrate the feasibility of operating digital detectors in experiments where strong electromagnetic pulses are present.
CRIS-Team Scopus Importer:2023-08-11

Energy dependent γ-ray morphology in the pulsar wind nebula HESS J1825-137 - Funk, Stefan; van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2006)
Aims. We present results from deep γ-ray observations of the Galactic pulsar wind nebula HESS J1825-137 performed with the HESS array. Methods. Detailed morphological and spatially resolved spectral studies reveal the very high-energy (VHE) γ-ray aspects of this object with unprecedented precision. Results. We confirm previous results obtained in a survey of the Galactic Plane in 2004. The γ-ray emission extends asymmetrically to the south and south-west of the energetic pulsar PSR J1826-1334, that is thought to power the pulsar wind nebula. The differential γ-ray spectrum of the whole emission region is measured over more than two orders of magnitude, from 270 GeV to 35 TeV, and shows indications for a deviation from a pure power law. Spectra have also been determined for spatially separated regions of HESS J1825-137. The photon indices from a power-law fit in the different regions show a softening of the spectrum with increasing distance from the pulsar and therefore an energy dependent morphology. Conclusions. This is the first time that an energy dependent morphology has been detected in the VHE γ-ray regime. The VHE γ-ray emission of HESS J1825-137 is phenomenologically discussed in the scenario where the γ-rays are produced by VHE electrons via Inverse Compton scattering. The high γ-ray luminosity of the source cannot be explained on the basis of constant spin-down power of the pulsar and requires higher injection power in past. © ESO 2006.
Keywords: Gamma rays: observations; ISM: individual objects: G 18.0-0.7; ISM: individual objects: HESS J1825; ISM: individual objects: PSR B1823-13; ISM: supernova remnants; Pulsars: general

Energy spectrum of cosmic-ray electrons at TeV energies - Aharonian, F.; Akhperjanian, A. G.; Barres De Almeida, Ulisses; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Physical Review Letters, 2008)
The very large collection area of ground-based γ-ray telescopes gives them a substantial advantage over balloon or satellite based instruments in the detection of very-high-energy (>600GeV) cosmic-ray electrons. Here we present the electron spectrum derived from data taken with the High Energy Stereoscopic System (H.E.S.S.) of imaging atmospheric Cherenkov telescopes. In this measurement, the first of this type, we are able to extend the measurement of the electron spectrum beyond the range accessible to direct measurements. We find evidence for a substantial steepening in the energy spectrum above 600 GeV compared to lower energies. © 2008 The American Physical Society.

Erratum: H.E.S.S. detection of TeV emission from the interaction region between the supernova remnant G349.7+0.2 and a molecular cloud (Astronomy and Astrophysics (2015)) - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
Keywords: Errata; addenda; Gamma rays: general; ISM: clouds; ISM: supernova remnants

Erratum: Primary particle acceleration above 100 TeV in the shell-type supernova remnant RX J1713.7-3946 with deep H.E.S.S. observations (Astronomy and Astrophysics (2007) 464 (235-243)) - Aharonian, F.; Akhperjanian, A. G.; Bazer-Bachi, A. R.; Beilicke, M.; Benbow, W.; Berge, David; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; Brion, E.; et al. (Astronomy & Astrophysics, 2011)
Keywords: acceleration of particles; cosmic rays; errata addenda; gamma rays: observations; ISM: supernova remnants

Erratum: Publisher's Note: HESS observations of the galactic center region and their possible dark matter interpretation (Physical Review Letters (2006) 97 (221102)) - van Eldik, Christopher; et al. (Physical Review Letters, 2006)

Erratum: "Search for Dark Matter Annihilation Signals from the Fornax Galaxy Cluster with H.E.S.S.'' (2012, ApJ, 750, 123) - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Barres De Almeida, U.; Becherini, Y.; Becker, J.; Behera, B.; Bernlöhr, K.; et al. (Astrophysical Journal, 2014)

Erratum to HESS J1640-465 - an exceptionally luminous TeV γ -ray supernova remnant - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
Keywords: Addenda; Errata; ISM: individual objects: G338.3-0.0; ISM: supernova remnants; Radiation mechanisms: non-thermal

Erratum to “Results from the search for dark matter in the Milky Way with 9 years of data of the ANTARES neutrino telescope” [Phys. Lett. B 769 (2017)249–254](S037026931730254X)(10.1016/j.physletb.2017.03.063) - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Physics Letters B, 2019)
Limits on the neutrino flux for a given mass [Formula presented] and annihilation channel are calculated as in Eq. (7)(page 252), with the integrated acceptances defined in Eq. (8)(page 252)as the effective area averaged over the neutrino energy. A numerical approximation of WIMP annihilation spectra, adapted from [1]with a too coarse binning, led to an overestimation of the integrated acceptances for dark-matter induced neutrino events. The spectra were replaced with a fine-binned version both in the likelihood and in the acceptances. The main change is a weaker limit for WIMP masses larger than 1 TeV/ [Formula presented]. Updated versions of Figs. 3–6 are provided.
CRIS-Team Scopus Importer:2019-06-04

Erratum to: Search for annihilating dark matter in the Sun with 3 years of IceCube data: IceCube Collaboration (The European Physical Journal C, (2017), 77, 3, (146), 10.1140/epjc/s10052-017-4689-9) - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Archinger, M.; et al. (European Physical Journal C: Particles and Fields, 2019)
In the analysis published in 1, constraints on the number of signal events can be interpreted as constraints on the volumetric neutrino to muon conversion rate.
CRIS-Team Scopus Importer:2019-05-02

Erratum to: Search for non-relativistic magnetic monopoles with IceCube (The European Physical Journal C, (2014), 74, 7, (2938), 10.1140/epjc/s10052-014-2938-8) - Aartsen, M. G.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Altmann, D.; Arguelles, C.; Arlen, T. C.; Auffenberg, J.; Bai, X.; Baker, M.; et al. (European Physical Journal C: Particles and Fields, 2019)
In the analyses, published in Ref. [1], the exclusion limits are calculated in dependence of the mean free path of the magnetic monopole - nucleon catalysis interaction.
CRIS-Team Scopus Importer:2019-05-02

Erratum: V0 production in p+A collisions at √ s=41.6 GeV (European Physical Journal C (2009) 61 (207-221) DOI: 10.1140/epjc/s10052-009-1005-3) - Abt, I.; Adams, M.; Agari, M.; Albrecht, H.; Aleksandrov, A.; Amaral, Vasco; Amorim, Antonio; Aplin, S. J.; Aushev, Volodymyr; Bagaturia, Y.; Balagura, V.; Bargiotti, M.; et al. (European Physical Journal C, 2009)

Evaluation of the Weighted Mean X-ray Energy for an Imaging System Via Propagation-Based Phase-Contrast Imaging - Seifert, Maria; Weule, Mareike; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Michel, Thilo; Neumayer, Paul; Schuster, Max; Wolf, Andreas; Anton, Gisela; Funk, Stefan; et al. (Journal of Imaging, 2020)
For imaging events of extremely short duration, like shock waves or explosions, it is necessary to be able to image the object with a single-shot exposure. A suitable setup is given by a laser-induced X-ray source such as the one that can be found at GSI (Helmholtzzentrum fur Schwerionenforschung GmbH) in Darmstadt (Society for Heavy Ion Research), Germany. There, it is possible to direct a pulse from the high-energy laser Petawatt High Energy Laser for Heavy Ion eXperiments (PHELIX) on a tungsten wire to generate a picosecond polychromatic X-ray pulse, called backlighter. For grating-based single-shot phase-contrast imaging of shock waves or exploding wires, it is important to know the weighted mean energy of the X-ray spectrum for choosing a suitable setup. In propagation-based phase-contrast imaging the knowledge of the weighted mean energy is necessary to be able to reconstruct quantitative phase images of unknown objects. Hence, we developed a method to evaluate the weighted mean energy of the X-ray backlighter spectrum using propagation-based phase-contrast images. In a first step wave-field simulations are performed to verify the results. Furthermore, our evaluation is cross-checked with monochromatic synchrotron measurements with known energy at Diamond Light Source (DLS, Didcot, UK) for proof of concepts.
CRIS-Team WoS Importer:2020-08-28

Event reconstruction for KM3NeT/ORCA using convolutional neural networks - Aiello, S.; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; Ardid, M.; Aublin, J.; et al. (Journal of Instrumentation, 2020)
The KM3NeT research infrastructure is currently under construction at two locations in the Mediterranean Sea. The KM3NeT/ORCA water-Cherenkov neutrino detector off the French coast will instrument several megatons of seawater with photosensors. Its main objective is the determination of the neutrino mass ordering. This work aims at demonstrating the general applicability of deep convolutional neural networks to neutrino telescopes, using simulated datasets for the KM3NeT/ORCA detector as an example. To this end, the networks are employed to achieve reconstruction and classification tasks that constitute an alternative to the analysis pipeline presented for KM3NeT/ORCA in the KM3NeT Letter of Intent. They are used to infer event reconstruction estimates for the energy, the direction, and the interaction point of incident neutrinos. The spatial distribution of Cherenkov light generated by charged particles induced in neutrino interactions is classified as shower- or track-like, and the main background processes associated with the detection of atmospheric neutrinos are recognized. Performance comparisons to machine-learning classification and maximum-likelihood reconstruction algorithms previously developed for KM3NeT/ORCA are provided. It is shown that this application of deep convolutional neural networks to simulated datasets for a large-volume neutrino telescope yields competitive reconstruction results and performance improvements with respect to classical approaches.
CRIS-Team WoS Importer:2020-10-30

Evidence for neutrino emission from the nearby active galaxy NGC 1068 - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Science, 2022)
A supermassive black hole, obscured by cosmic dust, powers the nearby active galaxy NGC 1068. Neutrinos, which rarely interact with matter, could provide information on the galaxy's active core. We searched for neutrino emission from astrophysical objects using data recorded with the IceCube neutrino detector between 2011 and 2020. The positions of 110 known gamma-ray sources were individually searched for neutrino detections above atmospheric and cosmic backgrounds. We found that NGC 1068 has an excess of 79(-20)(+22) neutrinos at tera-electron volt energies, with a global significance of 4.2 sigma, which we interpret as associated with the active galaxy. The flux of high-energy neutrinos that we measured from NGC 1068 is more than an order of magnitude higher than the upper limit on emissions of tera-electron volt gamma rays from this source.
CRIS-Team WoS Importer:2023-01-27

Evidence for VHE γ-ray emission from the distant BL Lac PG 1553+113 - van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2006)
The high-frequency peaked BL Lac PG 1553+113 was observed in 2005 with the HESS stereoscopic array of imaging atmospheric-Cherenkov telescopes in Namibia. Using the HESS standard analysis, an excess was measured at the 4.0σ level in these observations (7.6 hours live time). Three alternative, lower-threshold analyses yield >5σ excesses. The observed integral flux above 200 GeV is (4.8 ± 1.3 ± 1.0) × 10 cm s, and shows no evidence for variability. The measured energy spectrum is characterized by a very soft power law (photon index of Γ = 4.0 ± 0.6). Although the redshift of PG 1553+113 is unknown, there are strong indications that it is greater than z = 0.25 and possibly larger than z = 0.78. The observed spectrum is interpreted in the context of VHE γ-ray absorption by the Extragalactic Background Light, and is used to place an upper limit on the redshift of z < 0.74. © ESO 2006.
Keywords: BL Lacertae objects: individual: PG 1553+113; Galaxies: active; Gamma rays: observations

Evidence for γ-ray emission from the remnant of Kepleras supernova based on deep H.E.S.S. observations - Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Böttcher, M.; Boisson, C.; et al. (Astronomy & Astrophysics, 2022)
Observations with imaging atmospheric Cherenkov telescopes (IACTs) have enhanced our knowledge of nearby supernova (SN) remnants with ages younger than 500 yr by establishing Cassiopeia A and the remnant of Tychoas SN as very-high-energy (VHE) ?-ray sources. The remnant of Kepleras SN, which is the product of the most recent naked-eye SN in our Galaxy, is comparable in age to the other two, but is significantly more distant. If the ?-ray luminosities of the remnants of Tychoas and Kepleras SNe are similar, then the latter is expected to be one of the faintest ?-ray sources within reach of the current generation IACT arrays. Here we report evidence at a statistical level of 4.6? for a VHE signal from the remnant of Kepleras SN based on deep observations by the High Energy Stereoscopic System (H.E.S.S.) with an exposure of 152 h. The measured integral flux above an energy of 226 GeV is ?0.3% of the flux of the Crab Nebula. The spectral energy distribution (SED) reveals a ?-ray emitting component connecting the VHE emission observed with H.E.S.S.To the emission observed at GeV energies with Fermi-LAT. The overall SED is similar to that of the remnant of Tychoas SN, possibly indicating the same nonthermal emission processes acting in both these young remnants of thermonuclear SNe.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Gamma rays: General; Ism: Supernova remnants; Radiation mechanisms: Non-Thermal; Supernovae: Individual: Kepler

Expansion cone for the 3-inch PMTs of the KM3NeT optical modules - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Journal of Instrumentation, 2013)
Detection of high-energy neutrinos from distant astrophysical sources will open a new window on the Universe. The detection principle exploits the measurement of Cherenkov light emitted by charged particles resulting from neutrino interactions in the matter containing the telescope. A novel multi-PMT digital optical module (DOM) was developed to contain 31 3-inch photomultiplier tubes (PMTs). In order to maximize the detector sensitivity, each PMT will be surrounded by an expansion cone which collects photons that would otherwise miss the photocathode. Results for various angles of incidence with respect to the PMT surface indicate an increase in collection efficiency by 30% on average for angles up to 45 degrees with respect to the perpendicular. Ray-tracing calculations could reproduce the measurements, allowing to estimate an increase in the overall photocathode sensitivity, integrated over all angles of incidence, by 27% (for a single PMT). Prototype DOMs, being built by the KM3NeT consortium, will be equipped with these expansion cones.
Keywords: Optical detector readout concepts; Instrument optimisation; Cherenkov detectors; Large detector systems for particle and astroparticle physics

Exploring a SNR/molecular cloud association within HESS J1745-303 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, Wystan; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
Aims. HESS J1745-303 is an extended, unidentified VHE (very high energy) gamma-ray source discovered using HESS in the Galactic Plane Survey. Since no obvious counterpart has previously been found in longer-wavelength data, the processes that power the VHE emission are not well understood.Methods. Combining the latest VHE data with recent XMM-Newton observations and a variety of source catalogs and lower-energy survey data, we attempt to match (from an energetic and positional standpoint) the various parts of the emission of HESS J1745-303 with possible candidates.Results. Though no single counterpart is found to fully explain the VHE emission, we postulate that at least a fraction of the VHE source may be explained by a supernova-remnant/molecular-cloud association and/or a high-spin-down-flux pulsar. © 2008 ESO.
Keywords: Galaxy: general; Gamma rays: observations; ISM: clouds; ISM: cosmic rays; X-rays: general

Extended VHE gamma-ray emission towards SGR1806-20, LBV 1806-20, and stellar cluster Cl*1806-20 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Using the High Energy Spectroscopic System (H.E.S.S.) telescopes we have discovered a steady and extended very high-energy (VHE) gamma-ray source towards the luminous blue variable candidate LBV 1806-20, massive stellar cluster Cl* 1806-20, and magnetar SGR 1806-20. The new VHE source, HESS J1808-204, was detected at a statistical significance of >6 sigma (post-trial) with a photon flux normalisation (2.9 +/- 0.4(stat) +/- 0.5(sys)) x 10(-13) ph cm(-2) s(-1) TeV-1 at 1 TeV and a power-law photon index of 2.3 +/- 0.2(stat) +/- 0.3(sys). The luminosity of this source (0.2 to 10 TeV; scaled to distance d = 8 : 7 kpc) is L-VHE similar to 1.6 x 10(34)(d = 8.7 kpc)(2) erg s(-1). The VHE gamma-ray emission is extended and is well fit by a single Gaussian with statistical standard deviation of 0.095 degrees +/- 0.015 degrees. This extension is similar to that of the synchrotron radio nebula G10.0-0.3, which is thought to be powered by LBV 1806-20. The VHE gamma-ray luminosity could be provided by the stellar wind luminosity of LBV 1806-20 by itself and/or the massive star members of Cl* 1806-20. Alternatively, magnetic dissipation (e.g. via reconnection) from SGR 1806-20 can potentially account for the VHE luminosity. The origin and hadronic and/or leptonic nature of the accelerated particles responsible for HESS J1808-204 is not yet clear. If associated with SGR 1806 20, the potentially young age of the magnetar (650 yr) can be used to infer the transport limits of these particles to match the VHE source size. This discovery provides new interest in the potential for high-energy particle acceleration from magnetars, massive stars, and/or stellar clusters.
Keywords: gamma rays: general; stars: magnetars; stars: massive

First all-flavor neutrino pointlike source search with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
A search for cosmic neutrino sources using the data collected with the ANTARES neutrino telescope between early 2007 and the end of 2015 is performed. For the first time, all neutrino interactions-charged and neutral-current interactions of all flavors-are considered in a search for point-like sources with the ANTARES detector. In previous analyses, only muon neutrino charged-current interactions were used. This is achieved by using a novel reconstruction algorithm for shower-like events in addition to the standard muon track reconstruction. The shower channel contributes about 23% of all signal events for an E-2 energy spectrum. No significant excess over background is found. The most signal-like cluster of events is located at (alpha, delta) = (343.8 degrees, 23.5 degrees) with a significance of 1.9 sigma. The neutrino flux sensitivity of the search is about E(2)d Phi/dE = 6 x 10(-9) GeV cm(-2) s(-1) for declinations from -90 degrees up to -42 degrees, and below 10(-8) GeV cm(-2) s(-1) for declinations up to 5 degrees. The directions of 106 source candidates and 13 muon track events from the IceCube high-energy sample events are investigated for a possible neutrino signal and upper limits on the signal flux are determined.

First all-flavor search for transient neutrino emission using 3-years of IceCube DeepCore data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Ansseau, I.; et al. (Journal of Cosmology and Astroparticle Physics, 2022)
Since the discovery of a flux of high-energy astrophysical neutrinos, searches for their origins have focused primarily at TeV-PeV energies. Compared to sub-TeV searches, high-energy searches benefit from an increase in the neutrino cross section, improved angular resolution on the neutrino direction, and a reduced background from atmospheric neutrinos and muons. However, the focus on high energy does not preclude the existence of sub-TeV neutrino emission where IceCube retains sensitivity. Here we present the first all-flavor search from IceCube for transient emission of low-energy neutrinos, focusing on the energy region of 5.6-100 GeV using three years of data obtained with the IceCube-DeepCore detector. We find no evidence of transient neutrino emission in the data, thus leading to a constraint on the volumetric rate of astrophysical transient sources in the range of ∼ 705-2301 Gpc-3 yr-1 for sources following a subphotospheric energy spectrum with a mean energy of 100 GeV and a bolometric energy of 1052 erg.
CRIS-Team Scopus Importer:2022-02-11
Keywords: gamma ray burst experiments; neutrino astronomy; neutrino experiments

First detection of a VHE gamma-ray spectral maximum from a cosmic source: HESS discovery of the Vela X nebula - van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2006)
The Vela supernova remnant (SNR) is a complex region containing a number of sources of non-thermal radiation. The inner section of this SNR, within 2 degrees of the pulsar PSR B0833-45, has been observed by the HESS γ-ray atmospheric Cherenkov detector in 2004 and 2005. A strong signal is seen from an extended region to the south of the pulsar, within an integration region of radius 0.8° around the position (α = 0835 00, δ = -45°36′ J2000.0). The excess coincides with a region of hard X-ray emission seen by the ROSAT and ASCA satellites. The observed energy spectrum of the source between 550 GeV and 65 TeV is well fit by a power law function with photon index Γ = 1.45 ± 0.09 ± 0.2 and an exponential cutoff at an energy of 13.8 ± 2.3 ± 4.1 TeV. The integral flux above 1 TeV is (1.28 ± 0.17 ± 0.38) × 10 cm s. This result is the first clear measurement of a peak in the spectral energy distribution from a VHE γ-ray source, likely related to inverse Compton emission. A fit of an Inverse Compton model to the HESS spectral energy distribution gives a total energy in non-thermal electrons of ∼2 × 10 erg between 5 TeV and 100 TeV, assuming a distance of 290 parsec to the pulsar. The best fit electron power law index is 2.0, with a spectral break at 67 TeV. © ESO 2006.
Keywords: Gamma rays: observations; Ism: plerions

First detection of VHE γ-rays from SN 1006 by HESS - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Beilicke, M.; Bernloehr, K.; Bochow, A.; Boisson, C.; et al. (Astronomy & Astrophysics, 2010)
Aims. Recent theoretical predictions of the lowest very high energy (VHE) luminosity of SN 1006 are only a factor 5 below the previously published HESS upper limit, thus motivating further in-depth observations of this source. Methods. Deep observations at VHE energies (above 100 GeV) were carried out with the high energy stereoscopic system (HESS) of Cherenkov Telescopes from 2003 to 2008. More than 100 h of data have been collected and subjected to an improved analysis procedure. Results. Observations resulted in the detection of VHE γ-rays from SN 1006. The measured γ-ray spectrum is compatible with a power-law, the flux is of the order of 1% of that detected from the Crab Nebula, and is thus consistent with the previously established HESS upper limit. The source exhibits a bipolar morphology, which is strongly correlated with non-thermal X-rays. Conclusions. Because the thickness of the VHE-shell is compatible with emission from a thin rim, particle acceleration in shock waves is likely to be the origin of the γ-ray signal. The measured flux level can be accounted for by inverse Compton emission, but a mixed scenario that includes leptonic and hadronic components and takes into account the ambient matter density inferred from observations also leads to a satisfactory description of the multi-wavelength spectrum. © 2010 ESO.
Keywords: Gamma rays: stars; Supernovae: individual: SN 1006 (G327.6+14.6)

First ground-based measurement of atmospheric Cherenkov light from cosmic rays - van Eldik, Christopher; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2007)
A recently proposed novel technique for the detection of cosmic rays with arrays of Imaging Atmospheric Cherenkov Telescopes is applied to data from the High Energy Stereoscopic System (H.E.S.S.). The method relies on the ground-based detection of Cherenkov light emitted from the primary particle prior to its first interaction in the atmosphere. The charge of the primary particle (Z) can be estimated from the intensity of this light, since it is proportional to Z2. Using H.E.S.S. data, an energy spectrum for cosmic-ray iron nuclei in the energy range 13-200 TeV is derived. The reconstructed spectrum is consistent with previous direct measurements and is one of the most precise so far in this energy range. © 2007 The American Physical Society.

First ground-based measurement of sub-20 GeV to 100 GeV gamma-Rays from the Vela pulsar with HESS II - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Aims. We report on the measurement and investigation of pulsed high-energy y-ray emission from the Vela pulsar, PSR B0833-45, based on observations with the largest telescope of H.E.S.S., CT5, in monoscopic mode, and on data obtained with the Fermi-LAT.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-Thermal

First intensity interferometry measurements with the H.E.S.S. telescopes - Zmija, Andreas; Vogel, Naomi; Wohlleben, Frederik; Anton, Gisela; Zink, Adrian; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2024)
Intensity interferometry for astrophysical observations has gained increasing interest in the last decade. The method of correlating photon fluxes at different telescopes for high resolution astronomy without access to the phase of the incoming light is insensitive to atmospheric turbulence and does not require high-precision optical path control. The necessary large collection areas can be provided by Imaging Atmospheric Cherenkov Telescopes. Implementation of intensity interferometers to existing telescope systems such as VERITAS and MAGIC has proven to be successful for high-resolution imaging of stars. In 2022 April we equipped two telescopes of the H.E.S.S. array in Namibia with an intensity interferometry setup to measure southern sky stars and star systems during the bright moon period. We mounted an external optical system to the lid of the telescope cameras, which splits the incoming light and feeds it into two photomultipliers in order to measure the zero-baseline correlation within one telescope in addition to the cross-correlation between the telescopes. The optical elements are motorized, which enables live correction of tracking inaccuracies of the telescopes. During the campaign we measured the spatial correlation curves and thereby the angular diameters of λ Sco (Shaula) and σ Sgr (Nunki), while we also performed systematic studies of our interferometer using the multiple star system of α Cru (Acrux).
CRIS-Team Scopus Importer:2024-01-26
Keywords: instrumentation: high angular resolution; instrumentation: interferometers; methods: observational; stars: imaging; techniques: interferometric; telescopes

First limits on the very-high energy gamma-ray afterglow emission of a fast radio burst: H.E.S.S. Observations of FRB 150418 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; et al. (Astronomy & Astrophysics, 2017)
Aims. Following the detection of the fast radio burst FRB150418 by the SUPERB project at the Parkes radio telescope, we aim to search for very-high energy gamma-ray afterglow emission.Methods. Follow-up observations in the very-high energy gamma-ray domain were obtained with the H.E.S.S. imaging atmospheric Cherenkov telescope system within 14.5 h of the radio burst.Results. The obtained 1.4 h of gamma-ray observations are presented and discussed. At the 99% C.L. we obtained an integral upper limit on the gamma-ray flux of Phi(gamma)(E > 350 GeV) < 1.33 x 10(-8) m(-2) s(-1). Differential flux upper limits as function of the photon energy were derived and used to constrain the intrinsic high-energy afterglow emission of FRB 150418.Conclusions. No hints for high-energy afterglow emission of FRB 150418 were found. Taking absorption on the extragalactic background light into account and assuming a distance of z = 0 : 492 based on radio and optical counterpart studies and consistent with the FRB dispersion, we constrain the gamma-ray luminosity at 1 TeV to L < 5 : 1 x 10(47) erg/s at 99% C.L.
Keywords: Astroparticle physics; Gamma rays: general

First results on dark matter annihilation in the Sun using the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anton, L.; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for high-energy neutrinos coming from the direction of the Sun has been performed using the data recorded by the ANTARES neutrino telescope during 2007 and 2008. The neutrino selection criteria have been chosen to maximize the selection of possible signals produced by the self-annihilation of weakly interacting massive particles accumulated in the centre of the Sun with respect to the atmospheric background. After data unblinding, the number of neutrinos observed towards the Sun was found to be compatible with background expectations. The 90% CL upper limits in terms of spin-dependent and spin-independent WIMP-proton cross-sections are derived and compared to predictions of two supersymmetric models, CMSSM and MSSM-7. The ANTARES limits are comparable with those obtained by other neutrino observatories and are more stringent than those obtained by direct search experiments for the spin-dependent WIMP-proton cross-section in the case of hard self-annihilation channels (W+W-, tau(+)tau(-)).
Keywords: neutrino experiments; dark matter detectors; supersymmetry and cosmology; particle physics - cosmology connection

First search for neutrinos in correlation with gamma-ray bursts with the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for neutrino-induced muons in correlation with a selection of 40 gamma-ray bursts that occurred in 2007 has been performed with the ANTARES neutrino telescope. During that period, the detector consisted of 5 detection lines. The ANTARES neutrino telescope is sensitive to TeV-PeV neutrinos that are predicted from gamma-ray bursts. No events were found in correlation with the prompt photon emission of the gamma-ray bursts and upper limits have been placed on the flux and fluence of neutrinos for different models.
Keywords: neutrino experiments; neutrino astronomy; gamma ray bursts theory

FIRST SEARCH FOR POINT SOURCES OF HIGH-ENERGY COSMIC NEUTRINOS WITH THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astrophysical Journal Letters, 2011)
Results are presented of a search for cosmic sources of high-energy neutrinos with the ANTARES neutrino telescope. The data were collected during 2007 and 2008 using detector configurations containing between 5 and 12 detection lines. The integrated live time of the analyzed data is 304 days. Muon tracks are reconstructed using a likelihood-based algorithm. Studies of the detector timing indicate a median angular resolution of 0.5 +/- 0.1 deg. The neutrino flux sensitivity is 7.5 x 10(-8)(E(v)/GeV)(-2) GeV(-1) s(-1) cm(-2) for the part of the sky that is always visible (delta < -48 deg), which is better than limits obtained by previous experiments. No cosmic neutrino sources have been observed.
Keywords: astroparticle physics; cosmic rays; neutrinos

FlashCam: A fully digital camera for the Cherenkov telescope array medium-sized telescopes - Pühlhofer, G.; Barcelo, M.; Bauer, C.; Bi, B.; Catalano, Jacqueline; Diebold, S.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
FlashCam is an innovative camera designed for the focal plane instrumentation of Cherenkov telescopes. The concept of the FlashCam trigger and readout system is based on the continuous digitization and digital processing of the photo detector signals on FPGAs, and on a high performance, Ethernet-based front-end readout. Because of the modular design, the electronics that have been developed can serve either photomultiplier tubes or silicon-based photon detectors. In the framework of the CTA (Cherenkov telescope array) project, the FlashCam team has developed a PMT-based camera that is suitable for the medium-sized telescopes. With over 100 Cherenkov telescopes, the CTA observatory will run the most sensitive ground-based telescope systems for TeV gamma-ray astronomy when the two arrays in the Northern and Southern Hemisphere (with three different telescope sizes) will go into operation in the upcoming years.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Cherenkov Telescope Array; electronics; gamma-rays; Imaging Atmospheric Cherenkov Telescopes

Flux upper limits for 47 AGN observed with H.E.S.S. in 2004 - 2011 - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Context. About 40% of the observation time of the High Energy Stereoscopic System (H.E.S.S.) is dedicated to studying active galactic nuclei (AGN), with the aim of increasing the sample of known extragalactic very-high-energy (VHE, E > 100 GeV) sources and constraining the physical processes at play in potential emitters. Aims. H.E.S.S. observations of AGN, spanning a period from April 2004 to December 2011, are investigated to constrain their γ-ray fluxes. Only the 47 sources without significant excess detected at the position of the targets are presented. Methods. Upper limits on VHE fluxes of the targets were computed and a search for variability was performed on the nightly time scale. Results. For 41 objects, the flux upper limits we derived are the most constraining reported to date. These constraints at VHE are compared with the flux level expected from extrapolations of Fermi-LAT measurements in the two-year catalog of AGN. The H.E.S.S. upper limits are at least a factor of two lower than the extrapolated Fermi-LAT fluxes for 11 objects. Taking into account the attenuation by the extragalactic background light reduces the tension for all but two of them, suggesting intrinsic curvature in the high-energy spectra of these two AGN. Conclusions. Compilation efforts led by current VHE instruments are of critical importance for target-selection strategies before the advent of the Cherenkov Telescope Array (CTA). © ESO, 2014.
Keywords: Galaxies: active; Gamma rays: galaxies

Follow-up of Astrophysical Transients in Real Time with the IceCube Neutrino Observatory - Aartsen, M. G.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Amin, N. M.; Andeen, K.; Anderson, T.; Ansseau, I.; et al. (Astrophysical Journal, 2021)
In multi-messenger astronomy, rapid investigation of interesting transients is imperative. As an observatory with a 4 pi steradian field of view, and similar to 99% uptime, the IceCube Neutrino Observatory is a unique facility to follow up transients, as well as to provide valuable insights for other observatories and inform their observational decisions. Since 2016, IceCube has been using low-latency data to rapidly respond to interesting astrophysical events reported by the multi-messenger observational community. Here, we describe the pipeline used to perform these followup analyses, and provide a summary of the 58 analyses performed as of July 2020. We find no significant signal in the first 58 analyses performed. The pipeline has helped inform various electromagnetic observation strategies, and has constrained neutrino emission from potential hadronic cosmic accelerators.
CRIS-Team WoS Importer:2021-04-02

Framework and tools for the simulation and analysis of the radio emission from air showers at IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Journal of Instrumentation, 2022)
The Surface Enhancement of the IceTop air-shower array will include the addition of radio antennas and scintillator panels, co-located with the existing ice-Cherenkov tanks and covering an area of about 1 km2. Together, these will increase the sensitivity of the IceCube Neutrino Observatory to the electromagnetic and muonic components of cosmic-ray-induced air showers at the South Pole. The inclusion of the radio technique necessitates an expanded set of simulation and analysis tools to explore the radio-frequency emission from air showers in the 70 MHz to 350 MHz band. In this paper we describe the software modules that have been developed to work with time- and frequency-domain information within IceCube's existing software framework, IceTray, which is used by the entire IceCube collaboration. The software includes a method by which air-shower simulation, generated using CoREAS, can be reused via waveform interpolation, thus overcoming a significant computational hurdle in the field.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Antennas; Data analysis; Simulation methods and programs; Software architectures (event data models; frameworks and databases)

Früh zur Datenkompetenz - Krieger, Michael; Weber, Heiko B.; van Eldik, Christopher (Physik Journal, 2022)

FV 0 production in p+A collisions at √s=41.6 GeV - Abt, I.; Adams, M.; Agari, M.; Albrecht, H.; Aleksandrov, A.; Amaral, Vasco; Amorim, Antonio; Aplin, S. J.; Aushev, V.; Bagaturia, Y.; Balagura, V.; Bargiotti, M.; et al. (European Physical Journal C, 2009)
Inclusive doubly differential cross sections d σ /dx ∈ dp as a function of Feynman-x (x ) and transverse momentum (p ) for the production of K , Λ and Λ in proton-nucleus interactions at 920 GeV are presented. The measurements were performed by HERA-B in the negative x range (-0.12
Keywords: 13.85.Hd; 14.20.Jn; 14.40.Aq; Inelastic scattering: many-particle final states; Hyperons; pi K and eta mesons

Gammapy: A Python package for gamma-ray astronomy - Donath, Axel; Terrier, Régis; Remy, Quentin; Sinha, Atreyee; Nigro, Cosimo; Pintore, Fabio; Khélifi, Bruno; Olivera-Nieto, Laura; Ruiz, Jose Enrique; Brügge, Kai; Linhoff, Maximilian; Contreras, Jose Luis; et al. (Astronomy & Astrophysics, 2023)
Context. Traditionally, TeV-γ-ray astronomy has been conducted by experiments employing proprietary data and analysis software. However, the next generation of γ-ray instruments, such as the Cherenkov Telescope Array Observatory (CTAO), will be operated as open observatories. Alongside the data, they will also make the associated software tools available to a wider community. This necessity prompted the development of open, high-level, astronomical software customized for high-energy astrophysics. Aims. In this article, we present Gammapy, an open-source Python package for the analysis of astronomical γ-ray data, and illustrate the functionalities of its first long-term-support release, version 1.0. Built on the modern Python scientific ecosystem, Gammapy provides a uniform platform for reducing and modeling data from different γ-ray instruments for many analysis scenarios. Gammapy complies with several well-established data conventions in high-energy astrophysics, providing serialized data products that are interoperable with other software packages. Methods. Starting from event lists and instrument response functions, Gammapy provides functionalities to reduce these data by binning them in energy and sky coordinates. Several techniques for background estimation are implemented in the package to handle the residual hadronic background affecting γ-ray instruments. After the data are binned, the flux and morphology of one or more γ-ray sources can be estimated using Poisson maximum likelihood fitting and assuming a variety of spectral, temporal, and spatial models. Estimation of flux points, likelihood profiles, and light curves is also supported. Results. After describing the structure of the package, we show, using publicly available gamma-ray data, the capabilities of Gammapy in multiple traditional and novel γ-ray analysis scenarios, such as spectral and spectro-morphological modeling and estimations of a spectral energy distribution and a light curve. Its flexibility and its power are displayed in a final multi-instrument example, where datasets from different instruments, at different stages of data reduction, are simultaneously fitted with an astrophysical flux model.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Astroparticle physics; Gamma rays: general; Methods: data analysis; Methods: statistical

Gamma-ray blazar spectra with H.E.S.S. II mono analysis: The case of PKS 2155-304 and PG 1553+113 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Astronomy & Astrophysics, 2017)
Context. The addition of a 28 m Cherenkov telescope (CT5) to the H.E.S.S. array extended the experiment's sensitivity to lower energies. The lowest energy threshold is obtained using monoscopic analysis of data taken with CT5, providing access to gamma-ray energies below 100 GeV for small zenith angle observations. Such an extension of the instrument's energy range is particularly beneficial for studies of active galactic nuclei with soft spectra, as expected for those at a redshift ≥0.5. The high-frequency peaked BL Lac objects PKS 2155-304 (z = 0:116) and PG 1553+113 (0:43 < z < 0:58) are among the brightest objects in the gamma-ray sky, both showing clear signatures of gamma-ray absorption at E > 100 GeV interpreted as being due to interactions with the extragalactic background light (EBL). Aims. The aims of this work are twofold: to demonstrate the monoscopic analysis of CT5 data with a low energy threshold, and to obtain accurate measurements of the spectral energy distributions (SED) of PKS 2155-304 and PG 1553+113 near their SED peaks at energies 100 GeV. Methods. Multiple observational campaigns of PKS 2155-304 and PG 1553+113 were conducted during 2013 and 2014 using the full H.E.S.S. II instrument (CT1'5). A monoscopic analysis of the data taken with the new CT5 telescope was developed along with an investigation into the systematic uncertainties on the spectral parameters which are derived from this analysis. Results. Using the data from CT5, the energy spectra of PKS 2155-304 and PG 1553+113 were reconstructed down to conservative threshold energies of 80 GeV for PKS 2155-304, which transits near zenith, and 110 GeV for the more northern PG 1553+113. The measured spectra, well fitted in both cases by a log-parabola spectral model (with a 5.0φ statistical preference for non-zero curvature for PKS 2155-304 and 4.5φ for PG 1553+113), were found consistent with spectra derived from contemporaneous Fermi-LAT data, indicating a sharp break in the observed spectra of both sources at E 100 GeV. When corrected for EBL absorption, the intrinsic H.E.S.S. II mono and Fermi-LAT spectrum of PKS 2155-304 was found to show significant curvature. For PG 1553+113, however, no significant detection of curvature in the intrinsic spectrum could be found within statistical and systematic uncertainties.
Keywords: BL Lacertae objects: individual: PG 1553+113; BL Lacertae objects: individual: PKS 2155-304; Galaxies: active; Gamma rays: galaxies

Gamma rays from the Galactic Centre region: A review - van Eldik, Christopher (Astroparticle Physics, 2015)
Abstract During the last decades, increasingly precise astronomical observations of the Galactic Centre (GC) region at radio, infrared, and X-ray wavelengths laid the foundations to a detailed understanding of the high energy astroparticle physics of this most remarkable location in the Galaxy. Recently, observations of this region in high energy (HE, 10 MeV-100 GeV) and very high energy (VHE, > 100 GeV) γ-rays added important insights to the emerging picture of the Galactic nucleus as a most violent and active region where acceleration of particles to very high energies - possibly up to a PeV - and their transport can be studied in great detail. Moreover, the inner Galaxy is believed to host large concentrations of dark matter (DM), and is therefore one of the prime targets for the indirect search for γ-rays from annihilating or decaying dark matter particles. In this article, the current understanding of the γ-ray emission emanating from the GC is summarised and the results of recent DM searches in HE and VHE γ-rays are reviewed.
Keywords: Dark matter: annihilation; Dark matter: indirect detection; Galaxy: centre; Galaxy: star formation; Gamma rays: observations

Gamma rays from the Galactic Centre region - Su, Meng; van Eldik, Christopher (Comptes Rendus Physique, 2015)
During the last decades, increasingly precise astronomical observations of the Galactic Centre region at radio, infrared, and X-ray wavelengths laid the foundations for a detailed understanding of the high-energy astroparticle physics of this most remarkable location in the Galaxy. Recently, observations of this region in high energy (HE, 10 MeV-100 GeV) and very high energy (VHE, >100 GeV) γ-rays added important insights into the emerging picture of the Galactic nucleus as a most violent and active region where acceleration of particles to highest energies and their transport can be studied in great detail. We review the current understanding of the γ-ray emission emanating from the Galactic Centre.
Keywords: Fermi bubbles; Galactic Centre; Gamma rays; Observations

Gateless patterning of epitaxial graphene by local intercalation - Sorger, Christian; Hertel, Stefan; Jobst, Johannes; Steiner, Christian; Meil, Katharina; Ullmann, Konrad; Albert, A.; Wang, Yabin; Krieger, Michael; Ristein, Jürgen; Maier, Sabine; Weber, Heiko B. (Nanotechnology, 2015)
We present a technique to pattern the charge density of a large-area epitaxial graphene sheet locally without using metallic gates. Instead, local intercalation of the graphene-substrate interface can selectively be established in the vicinity of graphene edges or prede fined voids. It provides changes of the work function of several hundred meV, corresponding to a conversion from n-type to p-type charge carriers. This assignment is supported by photoelectron spectroscopy, scanning tunneling microscopy, scanning electron microscopy and Hall effect measurements. The technique introduces materials contrast to a graphene sheet in a variety of geometries and thus allows for novel experiments and novel functionalities.
UnivIS-Import:2015-04-14:Pub.2015.nat.dphy.IAP.LAP.gatele
Keywords: Graphene; Intercalation; Patterning

Geometrische Eigenschaften der Verschränkungsentropie in der Loop-Quantengravitation - Stritzelberger, Nadine; Sahlmann, Hanno (2014)

GiBUU based neutrino interaction simulations in KM3NeT - Schumann, Johannes; Jung, B. (Journal of Instrumentation, 2021)
The simulation of the neutrino interaction is a crucial step in the simulation chain of a neutrino experiment. The different processes taking part in the neutrino scattering on a nucleus require several approximations in order to make the simulation possible and to realize reasonable computation times. This can be realised in different ways, e.g. by parametrised models for the different scattering processes and energy regimes as it is implemented in GENIE. The GiBUU neutrino generator utilises the Boltzmann-Uehling-Uhlenbeck equation to simulate the particle flow after the neutrino interactions, the so-called final state interactions. The detector-specific results in form of the visible energy in the detector after the light propagation simulation and the KM3NeT event reconstruction are presented. In addition to that, the comparison to the GENIE based simulation environment in KM3NeT (gSeaGen) is drawn.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Neutrino detectors; Simulation methods and programs

Graph Neural Networks for low-energy event classification & reconstruction in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves Jr, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Journal of Instrumentation, 2022)
IceCube, a cubic-kilometer array of optical sensors built to detect atmospheric and astrophysical neutrinos between 1 GeV and 1 PeV, is deployed 1.45 km to 2.45 km below the surface of the ice sheet at the South Pole. The classification and reconstruction of events from the in-ice detectors play a central role in the analysis of data from IceCube. Reconstructing and classifying events is a challenge due to the irregular detector geometry, inhomogeneous scattering and absorption of light in the ice and, below 100 GeV, the relatively low number of signal photons produced per event. To address this challenge, it is possible to represent IceCube events as point cloud graphs and use a Graph Neural Network (GNN) as the classification and reconstruction method. The GNN is capable of distinguishing neutrino events from cosmic-ray backgrounds, classifying different neutrino event types, and reconstructing the deposited energy, direction and interaction vertex. Based on simulation, we provide a comparison in the 1 GeV-100 GeV energy range to the current state-of-the-art maximum likelihood techniques used in current IceCube analyses, including the effects of known systematic uncertainties. For neutrino event classification, the GNN increases the signal efficiency by 18% at a fixed background rate, compared to current IceCube methods. Alternatively, the GNN offers a reduction of the background (i.e. false positive) rate by over a factor 8 (to below half a percent) at a fixed signal efficiency. For the reconstruction of energy, direction, and interaction vertex, the resolution improves by an average of 13%-20% compared to current maximum likelihood techniques in the energy range of 1 GeV-30 GeV. The GNN, when run on a GPU, is capable of processing IceCube events at a rate nearly double of the median IceCube trigger rate of 2.7 kHz, which opens the possibility of using low energy neutrinos in online searches for transient events.
CRIS-Team WoS Importer:2023-02-17

Graph neural networks for reconstruction and classification in KM3NeT - Reck, Stefan; Guderian, D.; Vermarien, G.; Domi, A. (Journal of Instrumentation, 2021)
KM3NeT, a neutrino telescope currently under construction in the Mediterranean Sea, consists of a network of large-volume Cherenkov detectors. Its two different sites, ORCA and ARCA, are optimised for few GeV and TeV-PeV neutrino energies, respectively. This allows for studying a wide range of physics topics spanning from the determination of the neutrino mass hierarchy to the detection of neutrinos from astrophysical sources. Deep learning techniques provide promising methods to analyse the signatures induced by charged particles traversing the detector. This document will cover a deep learning based approach using graph convolutional networks to classify and reconstruct events in both the ORCA and ARCA detector. Performance studies on simulations as well as applications to real data will be presented, together with comparisons to classical approaches.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Cherenkov detectors; Data analysis; Neutrino detectors; Pattern recognition; cluster finding; calibration and fitting methods

Growth of two-dimensional dodecagonal colloidal quasicrystals: Particles with isotropic pair interactions with two length scales vs. patchy colloids with preferred binding angles - Gemeinhardt, Anja; Martinsons, Miriam; Schmiedeberg, Michael (European Physical Journal E, 2018)

gSeaGen: The KM3NeT GENIE-based code for neutrino telescopes - Aiello, S.; Kalekin, Oleg; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, G.; et al. (Computer Physics Communications, 2020)
The gSeaGen code is a GENIE-based application developed to efficiently generate high statistics samples of events, induced by neutrino interactions, detectable in a neutrino telescope. The gSeaGen code is able to generate events induced by all neutrino flavours, considering topological differences between track-type and shower-like events. Neutrino interactions are simulated taking into account the density and the composition of the media surrounding the detector. The main features of gSeaGen are presented together with some examples of its application within the KM3NeT project. Program summary: Program Title: gSeaGen CPC Library link to program files: http://dx.doi.org/10.17632/ymgxvy2br4.1 Licensing provisions: GPLv3 Programming language: C++ External routines/libraries: GENIE [1] and its external dependencies. Linkable to MUSIC [2] and PROPOSAL [3]. Nature of problem: Development of a code to generate detectable events in neutrino telescopes, using modern and maintained neutrino interaction simulation libraries which include the state-of-the-art physics models. The default application is the simulation of neutrino interactions within KM3NeT [4]. Solution method: Neutrino interactions are simulated using GENIE, a modern framework for Monte Carlo event generators. The GENIE framework, used by nearly all modern neutrino experiments, is considered as a reference code within the neutrino community. Additional comments including restrictions and unusual features: The code was tested with GENIE version 2.12.10 and it is linkable with release series 3. Presently valid up to 5 TeV. This limitation is not intrinsic to the code but due to the present GENIE valid energy range. References: [1] C. Andreopoulos at al., Nucl. Instrum. Meth. A614 (2010) 87. [2] P. Antonioli et al., Astropart. Phys. 7 (1997) 357. [3] J. H. Koehne et al., Comput. Phys. Commun. 184 (2013) 2070. [4] S. Adrián-Martínez et al., J. Phys. G: Nucl. Part. Phys. 43 (2016) 084001.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Astroparticle physics; GENIE; High energy neutrinos; KM3NeT; Monte Carlo event generator; Neutrino oscillations; Neutrino telescopes

HESS and Fermi-LAT discovery of γ-rays from the blazar 1ES 1312-423 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2013)
A deep observation campaign carried out by the High Energy Stereoscopic System (HESS) on Centaurus A enabled the discovery of γ-rays from the blazar 1ES 1312-423, 2° away from the radio galaxy. With a differential flux at 1 TeV of f(1 TeV) = (1.9 ± 0.6 ± 0.4) × 10 cm s TeV corresponding to 0.5 per cent of the Crab nebula differential flux and a spectral index γ = 2.9 ± 0.5 ± 0.2, 1ES 1312-423 is one of the faintest sources ever detected in the very high energy (E <100 GeV) extragalactic sky. A careful analysis using three and a half years of Fermi Large Area Telescope (Fermi-LAT) data allows the discovery at high energies (100 < E MeV) of a hard spectrum (γ =1.4±0.4stat ±0.2sys) source coincident with 1ES 1312-423. Radio, optical, UV and X-ray observations complete the spectral energy distribution of this blazar, now covering 16 decades in energy. The emission is successfully fitted with a synchrotron self-Compton model for the non-thermal component, combined with a blackbody spectrum for the optical emission from the host galaxy. © 2013 The Authors. Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Bl Lacertae objects: individual: 1ES 1312-423; Galaxies: active; Galaxies: jets; Gamma-rays: galaxies.; Radiation mechanisms: non-thermal

HESS and Fermi-LAT observations of PSR B1259-63/LS 2883 during its 2014 and 2017 periastron passages - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. PSR B1259-63/LS 2883 is a gamma-ray binary system consisting of a pulsar in an eccentric orbit around a bright Oe stellar-type companion star that features a dense circumstellar disc. The bright broad-band emission observed at phases close to periastron offers a unique opportunity to study particle acceleration and radiation processes in binary systems. Observations at gamma-ray energies constrain these processes through variability and spectral characterisation studies.
CRIS-Team WoS Importer:2020-01-31
Keywords: Pulsars: general; Radiation mechanisms: non-thermal; Shock waves; γ-rays: general; Binaries: general; Astroparticle physics

HESS and Suzaku observations of the Vela X pulsar wind nebula - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Berge, D.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2019)
Context. Pulsar wind nebulae (PWNe) represent the most prominent population of Galactic very-high-energy gamma-ray sources and are thought to be an efficient source of leptonic cosmic rays. Vela X is a nearby middle-aged PWN, which shows bright X-ray and TeV gamma-ray emission towards an elongated structure called the cocoon.
CRIS-Team WoS Importer:2019-07-23
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-thermal; Stars: winds; outflows; Acceleration of particles

H.E.S.S. constraints on dark matter annihilations towards the sculptor and carina dwarf galaxies - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; Barres De Almeida, U.; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernlöhr, K.; et al. (Astroparticle Physics, 2011)
The Sculptor and Carina dwarf spheroidal galaxies were observed with the H.E.S.S. Cherenkov telescope array between January 2008 and December 2009. The data sets consist of a total of 11.8 h and 14.8 h of high quality data, respectively. No gamma-ray signal was detected at the nominal positions of these galaxies above 220 GeV and 320 GeV, respectively. Upper limits on the gamma-ray fluxes at 95% CL assuming two forms for the spectral energy distribution (a power law shape and one derived from dark matter annihilation) are obtained at the level of 10-10 cm s in the TeV range. Constraints on the velocity weighted dark matter particle annihilation cross section for both Sculptor and Carina dwarf galaxies range from 〈σv〉 ∼ 10 cm s down to 〈σv〉 ∼ 10 cm s depending on the dark matter halo model used. Possible enhancements of the gamma-ray flux are studied: the Sommerfeld effect, which is found to exclude some dark matter particle masses, the internal Bremsstrahlung and clumps in the dark-matter halo distributions. © 2011 Published by Elsevier B.V.
Keywords: Carina; Dark matter; Gamma-rays: observations - Dwarf spheroidal galaxy; Internal Bremsstrahlung; Sculptor; Sommerfeld enhancement

H.E.S.S. detection of TeV emission from the interaction region between the supernova remnant G349.7+0.2 and a molecular cloud - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E. O.; Backes, Michael; Balenderans, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
G349.7+0.2 is a young Galactic supernova remnant (SNR) located at the distance of 11.5 kpc and observed across the entire electromagnetic spectrum from radio to high energy (HE; 0.1 GeV < E < 100 GeV) γ-rays. Radio and infrared observations indicate that the remnant is interacting with a molecular cloud. In this paper, the detection of very high energy (VHE, E > 100 GeV) γ-ray emission coincident with this SNR with the High Energy Stereoscopic System (H.E.S.S.) is reported. This makes it one of the farthest Galactic SNR ever detected in this domain. An integral flux F (E > 400 GeV) = (6.5 ± 1.1 ± 1.3) × 10 ph cm s corresponding to ∼0.7% of that of the Crab Nebula and to a luminosity of ∼10 erg s above the same energy threshold, and a steep photon index Γ = 2.8 ± 0.27stat ± 0.20 are measured. The analysis of more than 5 yr of Fermi-LAT data towards this source shows a power-law like spectrum with a best-fit photon index Γ = 2.2 ± 0.04 . The combined γ-ray spectrum of G349.7+0.2 can be described by either a broken power-law (BPL) or a power-law with exponential (or sub-exponential) cutoff(PLC). In the former case, the photon break energy is found at E = 55 GeV, slightly higher than what is usually observed in the HE/VHE γ-ray emitting middle-aged SNRs known to be interacting with molecular clouds. In the latter case, the exponential (respectively sub-exponential) cutoff energy is measured at E = 1.4 (respectively 0.35 ) TeV. A pion-decay process resulting from the interaction of the accelerated protons and nuclei with the dense surrounding medium is clearly the preferred scenario to explain the γ-ray emission. The BPL with a spectral steepening of 0.5-1 and the PLC provide equally good fits to the data. The product of the average gas density and the total energy content of accelerated protons and nuclei amounts to n W ∼ 5 × 10 erg cm.
Keywords: Gamma rays: General; ISM: clouds; ISM: supernova remnants

HESS detection of very high-energy gamma-ray emission from the quasar PKS 0736+017 - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. Flat-spectrum radio-quasars (FSRQs) are rarely detected at very high energies (E& x2004;>=& x2004;100 GeV) due to their low-frequency-peaked spectral energy distributions. At present, only six FSRQs are known to emit very high-energy (VHE) photons, representing only 7% of the VHE extragalactic catalog, which is largely dominated by high-frequency-peaked BL Lacertae objects. Aims. Following the detection of MeV-GeV gamma-ray flaring activity from the FSRQ PKS 0736+017 (z& x2004;=& x2004;0.189) with Fermi-LAT, the H.E.S.S. array of Cherenkov telescopes triggered target-of-opportunity (ToO) observations on February 18, 2015, with the goal of studying the gamma-ray emission in the VHE band. Methods. H.E.S.S. ToO observations were carried out during the nights of February 18, 19, 21, and 24, 2015. Together with Fermi-LAT, the multi-wavelength coverage of the flare includes Swift observations in soft X-ray and optical-UV bands, and optical monitoring (photometry and spectro-polarimetry) by the Steward Observatory, and the ATOM, the KAIT, and the ASAS-SN telescopes. Results. VHE emission from PKS 0736+017 was detected with H.E.S.S. only during the night of February 19, 2015. Fermi-LAT data indicate the presence of a gamma-ray flare, peaking at the time of the H.E.S.S. detection, with a flux doubling timescale of around six hours. The gamma-ray flare was accompanied by at least a 1 mag brightening of the non-thermal optical continuum. No simultaneous observations at longer wavelengths are available for the night of the H.E.S.S. detection. The gamma-ray observations with H.E.S.S. and Fermi-LAT are used to put constraints on the location of the gamma-ray emitting region during the flare: it is constrained to be just outside the radius of the broad-line region r(BLR) with a bulk Lorentz factor Gamma& x2004;similar or equal to& x2004;20, or at the level of the radius of the dusty torus r(torus) with Gamma& x2004;similar or equal to& x2004;60. Conclusions. PKS 0736+017 is the seventh FSRQ known to emit VHE photons, and at z& x2004;=& x2004;0.189 is the nearest so far. The location of the gamma-ray emitting region during the flare can be tightly constrained thanks to opacity, variability, and collimation arguments.
CRIS-Team WoS Importer:2020-02-18
Keywords: Astroparticle physics; Gamma rays: general; Quasars: individual: PKS 0736+017; Relativistic processes

HESS discovery of very high energy gamma-ray emission from PKS 0625-354 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguner, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
PKS 0625-354 (z = 0.055) was observed with the four High Energy Stereoscopic System (H.E.S.S.) telescopes in 2012 during 5.5 h. The source was detected above an energy threshold of 200 GeV at a significance level of 6.1 sigma. No significant variability is found in these observations. The source is well described with a power-law spectrum with photon index Gamma = 2.84 +/- 0.50(stat) +/- 0.10(syst) and normalization (at E-0 = 1.0 TeV) N-0(E-0)=(0.58 +/- 0.22(stat) +/- 0.12(syst)) x 10(-12) TeV-1 cm(-2) s(-1). Multiwavelength data collected with Fermi-LAT, Swift-XRT, Swift-UVOT, ATOM and WISE are also analysed. Significant variability is observed only in the Fermi-LAT gamma-ray and Swift-XRT X-ray energy bands. Having a good multiwavelength coverage from radio to very high energy, we performed a broad-band modelling from two types of emission scenarios. The results from a one zone lepto-hadronic and a multizone leptonic models are compared and discussed. On the grounds of energetics, our analysis favours a leptonic multizone model. Models associated to the X-ray variability constraint support previous results, suggesting a BL Lac nature of PKS 0625-354 with, however, a large-scale jet structure typical of a radio galaxy.
Keywords: radiation mechanisms: non-thermal; galaxies: active; galaxies: individual: PKS 0625-354; galaxies: jets; gamma-rays: galaxies

H.E.S.S. discovery of VHE γ-rays from the quasar PKS 1510-089 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2013)
The quasar PKS 1510-089 (z = 0.361) was observed with the H.E.S.S. array of imaging atmospheric Cherenkov telescopes during high states in the optical and GeV bands, to search for very high energy (VHE, defined as E ≥ 0.1 TeV) emission. VHE γ-rays were detected with a statistical significance of 9.2 standard deviations in 15.8 h of H.E.S.S. data taken during March and April 2009. A VHE integral flux of I(0.15 TeV < E < 1.0TeV) = (1.0 ±0.2 ±0.2) ×10 cm s is measured. The best-fit power law to the VHE data has a photon index of γ = 5.4 ± 0.7 ± 0.3. The GeV and optical light curves show pronounced variability during the period of H.E.S.S. observations. However, there is insufficient evidence to claim statistically significant variability in the VHE data. Because of its relatively high redshift, the VHE flux from PKS 1510-089 should suffer considerable attenuation in the intergalactic space due to the extragalactic background light (EBL). Hence, the measured γ-ray spectrum is used to derive upper limits on the opacity due to EBL, which are found to be comparable with the previously derived limits from relatively-nearby BL Lac objects. Unlike typical VHE-detected blazars where the broadband spectrum is dominated by nonthermal radiation at all wavelengths, the quasar PKS 1510-089 has a bright thermal component in the optical to UV frequency band. Among all VHE detected blazars, PKS 1510-089 has the most luminous broad line region. The detection of VHE emission from this quasar indicates a low level of γ - γ absorption on the internal optical to UV photon field. © 2013 ESO.
Keywords: Gamma rays: galaxies; Infrared: diffuse background; Quasars: individual: PKS 1510; 089

HESS Follow-up Observations of Binary Black Hole Coalescence Events during the Second and Third Gravitational-wave Observing Runs of Advanced LIGO and Advanced Virgo - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Ashkar, H.; Backes, M.; Baghmanyan,; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlohr, K.; et al. (Astrophysical Journal, 2021)
We report on the observations of four well-localized binary black hole (BBH) mergers by the High Energy Stereoscopic System (H.E.S.S.) during the second and third observing runs of Advanced LIGO and Advanced Virgo, O2 and O3. H.E.S.S. can observe 20 deg(2) of the sky at a time and follows up gravitational-wave (GW) events by "tiling" localization regions to maximize the covered localization probability. During O2 and O3, H.E.S.S. observed large portions of the localization regions, between 35% and 75%, for four BBH mergers (GW170814, GW190512_180714, GW190728_064510, and S200224ca). For these four GW events, we find no significant signal from a pointlike source in any of the observations, and we set upper limits on the very high energy (>100 GeV) gamma-ray emission. The 1-10 TeV isotropic luminosity of these GW events is below 10(45) erg s(-1) at the times of the H.E.S.S. observations, around the level of the low-luminosity GRB 190829A. Assuming no changes are made to how follow-up observations are conducted, H.E.S.S. can expect to observe over 60 GW events per year in the fourth GW observing run, O4, of which eight would be observable with minimal latency.
CRIS-Team WoS Importer:2021-12-24

H.E.S.S. II - Telescope structure, reflector and drive system - Deil, C.; van Eldik, Christopher; Förster, A.; Hermann, G.; Hofmann, W.; Panter, M. (4th International Meeting on High Energy Gamma-Ray Astronomy, 2009)
The currently operating phase I of the imaging atmospheric Cherenkov telescope array H.E.S.S. consists of four telescopes, each with a 107 m reflector, which are arranged on the corners of a square of 120 m side length. At the moment, the collaboration is building a much larger 600 m telescope in the center of the array. This will not only increase the sensitivity in the currently accessible energy regime, but will in addition lower the energy threshold of the system. The H.E.S.S. II telescope will have a parabolic reflector of 36 m focal length consisting of 850 individual mirrors, which can be automatically aligned, similar to the H.E.S.S. I telescopes. The drive system will have a repositioning speed of 100 deg/min in elevation and 200 deg/min in azimuth and achieve an online tracking accuracy of - 1 arcmin and an offline absolute pointing accuracy of - 10 arcsec. This proceeding contribution presents details on the technical implementation of the telescope mechanics, optics and drive system. © 2009 American Institute of Physics.
Keywords: Cherenkov telescope; H.E.S.S.

H.E.S.S. II-Telescope Structure, Reflector and Drive System - Deil, C.; van Eldik, Christopher; Förster, A.; Hermann, G.; Hofmann, W.; Panter, M. (American Institute of Physics Conference Series, 2008)
Keywords: Astronomical and space-research instrumentation; Particle acceleration; gamma-ray

HESS J1640-465-an exceptionally luminous TeV γ-ray supernova remnant - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
The results of follow-up observations of the TeV γ-ray source HESS J1640-465 from 2004 to 2011 with the High Energy Stereoscopic System (HESS) are reported in this work. The spectrum is well described by an exponential cut-offpower law with photon index γ = 2.11 ± 0.09 ± 0.10, and a cut-offenergy of E = 6.0 TeV. The TeV emission is significantly extended and overlaps with the northwestern part of the shell of the SNR G338.3-0.0. The new HESS results, a re-analysis of archival XMM-Newton data and multiwavelength observations suggest that a significant part of the γ-ray emission from HESS J1640-465 originates in the supernova remnant shell. In a hadronic scenario, as suggested by the smooth connection of the GeV and TeV spectra, the product of total proton energy and mean target density could be as high as W 4 × 10(d/10kpc) erg cm. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: G338.3-0.0-ISM; Individual objects; Non-thermal-ISM; Radiation mechanisms; Supernova remnants

HESS J1741-302: a hidden accelerator in the Galactic plane - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
The H.E.S.S. Collaboration has discovered a new very high energy (VHE, E > 0.1 TeV) gamma-ray source, HESS J1741-302, located in the Galactic plane. Despite several attempts to constrain its nature, no plausible counterpart has been found so far at X-ray and MeV/GeV gamma-ray energies, and the source remains unidentified. An analysis of 145-h of observations of HESS J1741-302 at VHEs has revealed a steady and relatively weak TeV source (similar to 1% of the Crab Nebula flux), with a spectral index of Gamma = 2.3 +/- 0.2(stat) +/- 0.2(sys), extending to energies up to 10 TeV without any clear signature of a cut-off. In a hadronic scenario, such a spectrum implies an object with particle acceleration up to energies of several hundred TeV. Contrary to most H.E.S.S. unidentified sources, the angular size of HESS J1741-302 is compatible with the H.E.S.S. point spread function at VHEs, with an extension constrained to be below 0.068 degrees at a 99% confidence level. The gamma-ray emission detected by H.E.S.S. can be explained both within a hadronic scenario, due to collisions of protons with energies of hundreds of TeV with dense molecular clouds, and in a leptonic scenario, as a relic pulsar wind nebula, possibly powered by the middle-aged (20 kyr) pulsar PSR B1737-30. A binary scenario, related to the compact radio source 1LC 358.266+0.038 found to be spatially coincident with the best fit position of HESS J1741-302, is also envisaged.
Keywords: gamma rays: ISM; gamma rays: general; cosmic rays; ISM: clouds

HESS J1809-193: A halo of escaped electrons around a pulsar wind nebula? - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Boettcher, M.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2023)
Context. HESS J1809-193 is an unassociated very-high-energy gamma-ray source located on the Galactic plane. While it has been connected to the nebula of the energetic pulsar PSR J1809-1917, supernova remnants and molecular clouds present in the vicinity also constitute possible associations. Recently, the detection of gamma-ray emission up to energies of similar to 100 TeV with the HAWC observatory has led to renewed interest in HESS J1809-193.Aims. We aim to understand the origin of the gamma-ray emission of HESS J1809-193.Methods. We analysed 93.2 h of data taken on HESS J1809-193 above 0.27 TeV with the High Energy Stereoscopic System (H.E.S.S.), using a multi-component, three-dimensional likelihood analysis. In addition, we provide a new analysis of 12.5 yr of Fermi-LAT data above 1 GeV within the region of HESS J1809-193. The obtained results are interpreted in a time-dependent modelling framework.Results. For the first time, we were able to resolve the emission detected with H.E.S.S. into two components: an extended component (modelled as an elongated Gaussian with a 1-sigma semi-major and semi-minor axis of similar to 0.62 degrees and similar to 0.35 degrees, respectively) that exhibits a spectral cutoff at similar to 13 TeV, and a compact component (modelled as a symmetric Gaussian with a 1-sigma radius of similar to 0.1 degrees) that is located close to PSR J1809-1917 and shows no clear spectral cutoff. The Fermi-LAT analysis also revealed extended gamma-ray emission, on scales similar to that of the extended H.E.S.S. component.Conclusions. Our modelling indicates that based on its spectrum and spatial extent, the extended H.E.S.S. component is likely caused by inverse Compton emission from old electrons that form a halo around the pulsar wind nebula. The compact component could be connected to either the pulsar wind nebula or the supernova remnant and molecular clouds. Due to its comparatively steep spectrum, modelling the Fermi-LAT emission together with the H.E.S.S. components is not straightforward.
CRIS-Team WoS Importer:2023-05-05

HESS J1818-154, a new composite supernova remnant discovered in TeV gamma rays and X-rays - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Composite supernova remnants (SNRs) constitute a small subclass of the remnants of massive stellar explosions where non-thermal radiation is observed from both the expanding shell-like shock front and from a pulsar wind nebula (PWN) located inside of the SNR. These systems represent a unique evolutionary phase of SNRs where observations in the radio, X-ray, and γ-ray regimes allow the study of the co-evolution of both these energetic phenomena. In this article, we report results from observations of the shell-type SNR G 15.4+0.1 performed with the High Energy Stereoscopic System (H.E.S.S.) and XMM-Newton. A compact TeV γ-ray source, HESS J1818-154, located in the center and contained within the shell of G 15.4+0.1 is detected by H.E.S.S. and featurs a spectrum best represented by a power-law model with a spectral index of-2.3 ± 0.3 ± 0.2 and an integral flux of F(> 0.42 TeV) = (0.9 ± 0.3 ± 0.2) × 10 cm s. Furthermore, a recent observation with XMM-Newton reveals extended X-ray emission strongly peaked in the center of G 15.4+0.1. The X-ray source shows indications of an energy-dependent morphology featuring a compact core at energies above 4 keV and more extended emission that fills the entire region within the SNR at lower energies. Together, the X-ray and VHE γ-ray emission provide strong evidence of a PWN located inside the shell of G 15.4+0.1 and this SNR can therefore be classified as a composite based on these observations. The radio, X-ray, and γ-ray emission from the PWN is compatible with a one-zone leptonic model that requires a low average magnetic field inside the emission region. An unambiguous counterpart to the putative pulsar, which is thought to power the PWN, has been detected neither in radio nor in X-ray observations of G 15.4+0.1. © 2014 ESO.
Keywords: Gamma rays: general; Methods: observational; Supernovae: individual: HESS J1818-154; X-rays: general; X-rays: individuals: G15.4+0.1

HESS J1943+213: A candidate extreme BL Lacertae object - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; et al. (Astronomy & Astrophysics, 2011)
Context. The H.E.S.S. Cherenkov telescope array has been surveying the Galactic plane for new VHE (>100 GeV) gamma-ray sources. Aims. We report on a newly detected point-like source, HESS J1943+213. This source coincides with an unidentified hard X-ray source IGR J19443+2117, which was proposed to have radio and infrared counterparts. Methods. We combine new H.E.S.S., Fermi/LAT and Nançay Radio Telescope observations with pre-existing non-simultaneous multi-wavelength observations of IGR J19443+2117 and discuss the likely source associations as well as the interpretation as an active galactic nucleus, a gamma-ray binary or a pulsar wind nebula. Results. HESS J1943+213 is detected at the significance level of 7.9σ (post-trials) at RA(J2000)= 19 4355 ± 1 ± 1 , Dec(J2000)= +21° 18'8" ± 17" ± 20". The source has a soft spectrum with photon index Γ = 3.1 ± 0.3 ± 0.2 and a flux above 470 GeV of (1.3 ± 0.2 ± 0.3) × 10 cm s . There is no Fermi/LAT counterpart down to a flux limit of 6 × 10 cm s in the 0.1-100 GeV energy range (95% confidence upper limit calculated for an assumed power-law model with a photon index Γ = 2.0). The data from radio to VHE gamma-rays do not show any significant variability. Conclusions. The lack of a massive stellar counterpart disfavors the binary hypothesis, while the soft VHE spectrum would be very unusual in case of a pulsar wind nebula. In addition, the distance estimates for Galactic counterparts places them outside of the Milky Way. All available observations favor an interpretation as an extreme, high-frequency peaked BL Lac object with a redshift z > 0.14. This would be the first time a blazar is detected serendipitously from ground-based VHE observations, and the first VHE AGN detected in the Galactic Plane. © 2011 ESO.
Keywords: BL Lacertae objects: individual: IGR J19443+2117; galaxies: active; gamma rays: general

H.E.S.S. Limits on Linelike Dark Matter Signatures in the 100 GeV to 2 TeV Energy Range Close to the Galactic Center - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Physical Review Letters, 2016)
A search for dark matter linelike signals iss performed in the vicinity of the Galactic Center by the H.E.S.S. experiment on observational data taken in 2014. An unbinned likelihood analysis iss developed to improve the sensitivity to linelike signals. The upgraded analysis along with newer data extend the energy coverage of the previous measurement down to 100 GeV. The 18 h of data collected with the H.E.S.S. array allow one to rule out at 95% C.L. the presence of a 130 GeV line (at l=-1.5°, b=0° and for a dark matter profile centered at this location) previously reported in Fermi-LAT data. This new analysis overlaps significantly in energy with previous Fermi-LAT and H.E.S.S. results. No significant excess associated with dark matter annihilations was found in the energy range of 100 GeV to 2 TeV and upper limits on the gamma-ray flux and the velocity weighted annihilation cross section are derived adopting an Einasto dark matter halo profile. Expected limits for present and future large statistics H.E.S.S. observations are also given.

Hess observarions of the prompt and afterglow phases of GRB 060602B - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Borrel, V.; Braun, Isabel V; Brion, E.; et al. (Astrophysical Journal, 2009)
We report on the first completely simultaneous observation of a gamma-ray burst (GRB) using an array of Imaging Atmospheric Cherenkov Telescopes, which is sensitive to photons in the very high energy (VHE) γ-ray range (≳ 100 GeV). On 2006 June 2, the Swift Burst Alert Telescope (BAT) registered an unusually soft γ-ray burst (GRB 060602B). The burst position was under observation using the High Energy Stereoscopic System (HESS) at the time the burst occurred. Data were taken before, during, and after the burst. A total of 5 hr of observations were obtained during the night of 2006 June 2-3, and five additional hours were obtained over the next three nights. No VHE γ-ray signal was found during the period covered by the HESS observations. The 99% confidence level flux upper limit (> 1 TeV) for the prompt phase (9 s) of GRB 060602B is 2.9 × 10 erg cm s. Due to the very soft BAT spectrum of the burst compared with other Swift GRBs and its proximity to the Galactic center, the burst is likely associated with a Galactic X-ray burster, although the possibility of it being a cosmological GRB cannot be ruled out. We discuss the implications of our flux limits in the context of these two bursting scenarios. © 2009. The American Astronomical Society. All rights reserved.
Keywords: Bursts-gamma rays; Gamma rays; Observations

HESS observations and VLT spectroscopy of PG 1553+113 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
Keywords: galaxies: active; galaxies: BL Lacertae objects: individual: PG 1553+113; gamma rays: observations

HESS observations of RX J1713.7-3946 with improved angular and spectral resolution: Evidence for gamma-ray emission extending beyond the X-ray emitting shell - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; et al. (Astronomy & Astrophysics, 2018)
Supernova remnants exhibit shock fronts (shells) that can accelerate charged particles up to very high energies. In the past decade, measurements of a handful of shell-type supernova remnants in very high-energy gamma rays have provided unique insights into the acceleration process. Among those objects, RX J1713.7-3946 (also known as G347.3-0.5) has the largest surface brightness, allowing us in the past to perform the most comprehensive study of morphology and spatially resolved spectra of any such very high-energy gamma-ray source. Here we present extensive new H.E.S.S. measurements of RX J1713.7-3946, almost doubling the observation time compared to our previous publication. Combined with new improved analysis tools, the previous sensitivity is more than doubled. The H.E.S.S. angular resolution of 0.048 degrees (0.036 degrees above 2 TeV) is unprecedented in gamma-ray astronomy and probes physical scales of 0.8 (0.6) parsec at the remnant's location. The new H. E. S. S. image of RX J1713.7-3946 allows us to reveal clear morphological di ff erences between X-rays and gamma rays. In particular, for the outer edge of the brightest shell region, we find the first ever indication for particles in the process of leaving the acceleration shock region. By studying the broadband energy spectrum, we furthermore extract properties of the parent particle populations, providing new input to the discussion of the leptonic or hadronic nature of the gamma-ray emission mechanism.
CRIS-Team WoS Importer:2020-01-15
Keywords: ISM: Supernova remnants; cosmic rays; gamma rays: General; Acceleration of particles; astroparticle physic

H.E.S.S. observations of the binary system PSR B1259-63/LS 2883 around the 2010/2011 periastron passage - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Aims. We present very high energy (VHE; E > 100 GeV) data from the γ-ray binary system PSR B1259-63/LS 2883 taken around its periastron passage on 15th of December 2010 with the High Energy Stereoscopic System (H.E.S.S.) of Cherenkov Telescopes. We aim to search for a possible TeV counterpart of the GeV flare detected by the Fermi LAT. In addition, we aim to study the current periastron passage in the context of previous observations taken at similar orbital phases, testing the repetitive behaviour of the source. Methods. Observations at VHEs were conducted with H.E.S.S. from 9th to 16th of January 2011. The total dataset amounts to 6 h of observing time. The data taken around the 2004 periastron passage were also re-analysed with the current analysis techniques in order to extend the energy spectrum above 3 TeV to fully compare observation results from 2004 and 2011. Results. The source is detected in the 2011 data at a significance level of 11.5σ revealing an averaged integral flux above 1 TeV of (1.01 ± 0.18 ± 0.20) × 10 cm s. The differential energy spectrum follows a power-law shape with a spectral index Γ = 2.92 ± 0.30 ± 0.20 and a flux normalisation at 1 TeV of N = (1.95 ± 0.32 ± 0.39) × 10 TeV cm s. The measured light curve does not show any evidence for variability of the source on the daily scale. The re-analysis of the 2004 data yields results compatible with the published ones. The differential energy spectrum measured up to 10 TeV is consistent with a power law with a spectral index Γ = 2.81 ± 0.10 ± 0.20 and a flux normalisation at 1 TeV of N = (1.29 ± 0.08 ± 0.26) × 10 TeV cm s. Conclusions. The measured integral flux and the spectral shape of the 2011 data are compatible with the results obtained around previous periastron passages. The absence of variability in the H.E.S.S. data indicates that the GeV flare observed by Fermi LAT in the time period covered also by H.E.S.S. observations originates in a different physical scenario than the TeV emission. Moreover, the comparison of the new results to the results from the 2004 observations made at a similar orbital phase provides a stronger evidence of the repetitive behaviour of the source. © ESO, 2013.
Keywords: Gamma rays: general; Pulsars: individual: PSR B1259-63; Stars: individual: LS 2883; X-rays: binaries

HESS observations of the Carina nebula and its enigmatic colliding wind binary Eta Carinae - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
The massive binary system Eta Carinae and the surrounding Hii complex, the Carina nebula, are potential particle acceleration sites from which very high energy (VHE; E≥ 100GeV) γ-ray emission could be expected. This paper presents data collected during VHE γ-ray observations with the HESS telescope array from 2004 to 2010, which cover a full orbit of Eta Carinae. In the 33.1-h data set no hint of significant γ-ray emission from Eta Carinae has been found and an upper limit on the γ-ray flux of (99per cent confidence level) is derived above the energy threshold of 470GeV. Together with the detection of high energy (HE; 0.1 ≤E≤ 100GeV) γ-ray emission by the Fermi Large Area Telescope up to 100GeV, and assuming a continuation of the average HE spectral index into the VHE domain, these results imply a cut-off in the γ-ray spectrum between the HE and VHE γ-ray range. This could be caused either by a cut-off in the accelerated particle distribution or by severe γ-γ absorption losses in the wind collision region. Furthermore, the search for extended γ-ray emission from the Carina nebula resulted in an upper limit on the γ-ray flux of (99per cent confidence level). The derived upper limit of ∼23 on the cosmic ray enhancement factor is compared with results found for the old-age mixed-morphology supernova remnant W28. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.
Keywords: Acceleration of particles; ISM: individual objects: Carina nebula; ISM: individual objects: Eta Carina; Open clusters and associations: general; Radiation mechanisms: non-thermal; X-rays: binaries

H.E.S.S. observations of the Crab during its March 2013 GeV gamma-ray flare - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
Context. On March 4, 2013 the Fermi-LAT and AGILE reported a flare from the direction of the Crab nebula in which the high-energy (HE; E > 100 MeV) flux was six times above its quiescent level. Simultaneous observations in other energy bands give us hints about the emission processes during the flare episode and the physics of pulsar wind nebulae in general. Aims. We search for variability in the emission of the Crab nebula at very-high energies (VHE; E > 100 GeV), using contemporaneous data taken with the H.E.S.S. array of Cherenkov telescopes. Methods. Observational data taken with the H.E.S.S. instrument on five consecutive days during the flare were analysed for the flux and spectral shape of the emission from the Crab nebula. Night-wise light curves are presented with energy thresholds of 1 TeV and 5 TeV. Results. The observations conducted with H.E.S.S. on March 6 to March 10, 2013 show no significant changes in the flux. They limit the variation in the integral flux above 1 TeV to less than 63% and the integral flux above 5 TeV to less than 78% at a 95% confidence level. © 2014 ESO.
Keywords: Gamma rays: ISM; ISM: individual objects: Crab nebula; Radiation mechanisms: non-thermal; Relativistic processes

HESS observations of the flaring gravitationally lensed galaxy PKS 1830-211 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
PKS 1830-211 is a known macrolensed quasar located at a redshift of z = 2.5. Its highenergy gamma-ray emission has been detected with the Fermi-Large Area Telescope (LAT) instrument and evidence for lensing was obtained by several authors from its high-energy data. Observations of PKS 1830-211 were taken with the High Energy Stereoscopic System (H.E.S.S.) array of Imaging Atmospheric Cherenkov Telescopes in 2014 August, following a flare alert by the Fermi-LAT Collaboration. The H.E.S.S observations were aimed at detecting a gamma-ray flare delayed by 20-27 d from the alert flare, as expected from observations at other wavelengths. More than 12 h of good-quality data were taken with an analysis threshold of similar to 67 GeV. The significance of a potential signal is computed as a function of the date and the average significance over the whole period. Data are compared to simultaneous observations by Fermi-LAT. No photon excess or significant signal is detected. An upper limit on PKS 1830-211 flux above 67 GeV is computed and compared to the extrapolation of the Fermi-LAT flare spectrum.
CRIS-Team WoS Importer:2019-07-26
Keywords: gamma-rays: galaxies; gravitational lensing: strong; diffuse radiation

HESS observations of the galactic center region and their possible dark matter interpretation - van Eldik, Christopher; et al. (Physical Review Letters, 2006)
The detection of γ rays from the source HESS J1745-290 in the Galactic Center (GC) region with the High Energy Spectroscopic System (HESS) array of Cherenkov telescopes in 2004 is presented. After subtraction of the diffuse γ-ray emission from the GC ridge, the source is compatible with a point source with spatial extent less than 1.2′(stat) (95% C.L.). The measured energy spectrum above 160 GeV is compatible with a power law with photon index of 2.25±0.04(stat)±0.10(syst) and no significant flux variation is detected. It is finally found that the bulk of the very high energy emission must have non-dark-matter origin. © 2006 The American Physical Society.

H.E.S.S. observations of the globular clusters NGC 6388 and M15 and search for a dark matter signal - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; et al. (Astrophysical Journal, 2011)
Observations of the globular clusters (GCs) NGC 6388 and M15 were carried out by the High Energy Stereoscopic System array of Cherenkov telescopes for a live time of 27.2 and 15.2 hr, respectively. No gamma-ray signal is found at the nominal target position of NGC 6388 and M15. In the primordial formation scenario, GCs are formed in a dark matter (DM) halo and DM could still be present in the baryon-dominated environment of GCs. This opens the possibility of observing a DM self-annihilation signal. The DM content of the GCs NGC 6388 and M15 is modeled taking into account the astrophysical processes that can be expected to influence the DM distribution during the evolution of the GC: the adiabatic contraction of DM by baryons, the adiabatic growth of a black hole in the DM halo, and the kinetic heating of DM by stars. Ninety-five percent confidence level exclusion limits on the DM particle velocity-weighted annihilation cross section are derived for these DM halos. In the TeV range, the limits on the velocity-weighted annihilation cross section are derived at the 10 cm s level and a few 10 cm s for NGC 6388 and M15, respectively. © 2011. The American Astronomical Society. All rights reserved..
Keywords: black hole physics; dark matter; gamma rays: general; globular clusters: individual (NGC 6388; M15)

(untitled) - van Eldik, Christopher; et al.

H.E.S.S. reveals a lack of TeV emission from the supernova remnant Puppis A - Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Angüner, E. O.; Backes, M.; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Becker Tjus, J.; Berge, D.; et al. (Astronomy & Astrophysics, 2015)
Results. The analysis of the H.E.S.S. data does not reveal any significant emission towards Puppis A. The derived upper limits on the differential photon flux imply that its broadband γ-ray spectrum must exhibit a spectral break or cutoff. By combining Fermi-LAT and H.E.S.S. measurements, the 99% confidence-level upper limits on such a cutoff are found to be 450 and 280 GeV, assuming a power law with a simple exponential and a sub-exponential cutoff, respectively. It is concluded that none of the standard limitations (age, size, radiative losses) on the particle acceleration mechanism, assumed to be continuing at present, can explain the lack of VHE signal. The scenario in which particle acceleration has ceased some time ago is considered as an alternative explanation. The HE/VHE spectrum of Puppis A could then exhibit a break of non-radiative origin (as observed in several other interacting SNRs, albeit at somewhat higher energies), owing to the interaction with dense and neutral material, in particular towards the NE region.
Keywords: Acceleration of particles; Cosmic rays; Gamma rays: ISM; ISM: individual objects: Puppis A; Radiation mechanisms: non-thermal

HESS upper limit on the very high energy γ-ray emission from the globular cluster 47 Tucanae - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2009)
Observations of the globular cluster 47 Tucanae (NGC 104), which contains at least 23 ms pulsars, were performed with the HESS telescope system. The observations lead to an upper limit of F(E < 800 GeV) < 6.7 × 10-13 cm-2 s-1 on the integral γ-ray photon flux from 47 Tucanae. Considering millisecond pulsars as the unique potential source of γ-rays in the globular cluster, constraints based on emission models are derived: on the magnetic field in the average pulsar nebula and on the conversion efficiency of spin-down power to γ-ray photons or to relativistic leptons. © 2009 ESO.
Keywords: Galaxy: globular clusters: individual: 47 Tucanae; Gamma rays: observations; Stars: pulsars: general

HESS upper limits for Kepler's supernova remnant - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Berge, David; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; et al. (Astronomy & Astrophysics, 2008)
Keywords: gamma rays: observations; ISM: supernova remnants; ISM: individual objects: Kepler's SNR; SN1604; G4.5+6.8

Hess upper limits on very high energy gamma-ray emission from the microquasar grs 1915+105 - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; et al. (Astronomy & Astrophysics, 2009)
Context: High energy particles reside in the relativistic jets of microquasars, making them possible sources of very high energy radiation (VHE, < 100 GeV). Detecting this emission would provide a new handle on jet physics. Aims: Observations of the microquasar GRS 1915+105 with the HESS telescope array were undertaken in 2004-2008 to search for VHE emission. Methods: Stereoscopic imaging of Cherenkov radiation from extensive air showers is used to reconstruct the energy and direction of the incident gamma rays. Results: There is no evidence for a VHE gamma-ray signal either from the direction of the microquasar or its vicinity. An upper limit of 6.1 × 10ph cms (99.9% confidence level) is set on the photon flux above 410 GeV, equivalent to a VHE luminosity of ̃ 10erg s at 11 kpc. Conclusions. The VHE to X-ray luminosity ratio in GRS 1915+105 is at least four orders of magnitude lower than the ratio observed in gamma-ray binaries. The VHE radiative efficiency of the compact jet is less than 0.01% based on its estimated total power of 10 erg s. Particle acceleration in GRS 1915+105 is not efficient at high energies and/or the magnetic field is too strong. It is also possible that VHE gamma-rays are produced by GRS 1915+105, but the emission is highly time-dependent. © 2009 ESO.
Keywords: Gamma rays: observations; X-rays: binaries; X-rays: individuals: GRS 1915+105

HESS very-high-energy gamma-ray sources without identified counterparts - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
Context. The detection of gamma rays in the very-high-energy (VHE) energy range (100 GeV-100 TeV) provides a direct view of the parent population of ultra-relativistic particles found in astrophysical sources. For this reason, VHE gamma rays are useful for understanding the underlying astrophysical processes in non-thermal sources. Aims. We investigate unidentified VHE gamma-ray sources that have been discovered with HESS in the most sensitive blind survey of the Galactic plane at VHE energies conducted so far. Methods. The HESS array of imaging atmospheric Cherenkov telescopes (IACTs) has a high sensitivity compared with previous instruments (∼0.01 Crab in 25 h observation time for a 5σ point-source detection), and with its large field of view, is well suited for scan-based observations. The on-going HESS survey of the inner Galaxy has revealed a large number of new VHE sources, and for each we attempt to associate the VHE emission with multi-wavelength data in the radio through X-ray wavebands. Results. For each of the eight unidentified VHE sources considered here, we present the energy spectra and. sky maps of the sources and their environment. The VHE morphology is compared with available multi-wavelength data (mainly radio and X-rays). No plausible counterparts are found. © ESO 2007.
Keywords: Cosmic rays; Galaxy: general; Gamma rays: observations; Surveys

High-energy neutrino follow-up search of gravitational wave event GW150914 with ANTARES and IceCube - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2016)
We present the high-energy-neutrino follow-up observations of the first gravitational wave transient GW150914 observed by the Advanced LIGO detectors on September 14, 2015. We search for coincident neutrino candidates within the data recorded by the IceCube and Antares neutrino detectors. A possible joint detection could be used in targeted electromagnetic follow-up observations, given the significantly better angular resolution of neutrino events compared to gravitational waves. We find no neutrino candidates in both temporal and spatial coincidence with the gravitational wave event. Within ±500 s of the gravitational wave event, the number of neutrino candidates detected by IceCube and Antares were three and zero, respectively. This is consistent with the expected atmospheric background, and none of the neutrino candidates were directionally coincident with GW150914. We use this nondetection to constrain neutrino emission from the gravitational-wave event.

High-Precision Determination of Oxygen Kα Transition Energy Excludes Incongruent Motion of Interstellar Oxygen - Leutenegger, M. A.; Kühn, S.; Micke, P.; Steinbrügge, R.; Stierhof, Jakob; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (Physical Review Letters, 2020)
We demonstrate a widely applicable technique to absolutely calibrate the energy scale of x-ray spectra with experimentally well-known and accurately calculable transitions of highly charged ions, allowing us to measure the K-shell Rydberg spectrum of molecular O2 with 8 meV uncertainty. We reveal a systematic ∼450 meV shift from previous literature values, and settle an extraordinary discrepancy between astrophysical and laboratory measurements of neutral atomic oxygen, the latter being calibrated against the aforementioned O2 literature values. Because of the widespread use of such, now deprecated, references, our method impacts on many branches of x-ray absorption spectroscopy. Moreover, it potentially reduces absolute uncertainties there to below the meV level.
CRIS-Team Scopus Importer:2020-12-25

High-resolution X-ray spectroscopy of the stellar wind in Vela X-1 during a flare - Lomaeva, M.; Grinberg, V.; Guainazzi, M.; Hell, N.; Bianchi, S.; Bissinger, Matthias; Fürst, F.; Kretschmar, P.; Martínez-Chicharro, M.; Martínez-Núñez, S.; Torrejón, J. M. (Astronomy & Astrophysics, 2020)
Context. We present a 130 ks observation of the prototypical wind-accreting, high-mass X-ray binary Vela X-1 collected with XMM-Newton at orbital phases between 0.12 and 0.28. A strong flare took place during the observation that allows us to investigate the reaction of the clumpy stellar wind to the increased X-ray irradiation. Aims. To examine the wind's reaction to the flare, we performed both time-averaged and time-resolved analyses of the RGS spectrum and examined potential spectral changes. Methods. We focused on the high-resolution XMM-Newton RGS spectra and divided the observation into pre-flare, flare, and post-flare phases. We modeled the time-averaged and time-resolved spectra with phenomenological components and with the self-consistent photoionization models calculated via CLOUDY and XSTAR in the pre-flare phase, where strong emission lines due to resonant transitions of highly ionized ions are seen. Results. In the spectra, we find emission lines corresponding to K-shell transitions in highly charged ions of oxygen, neon, magnesium, and silicon as well as radiative recombination continua (RRC) of oxygen. Additionally, we observe potential absorption lines of magnesium at a lower ionization stage and features identified as iron L lines. The CLOUDY and XSTAR photoionization models provide contradictory results, either pointing towards uncertainties in theory or possibly a more complex multi-phase plasma, or both. Conclusions. We are able to demonstrate the existence of a plethora of variable narrow features, including the firm detection of oxygen lines and RRC that RGS enables to observe in this source for the first time. We show that Vela X-1 is an ideal source for future high-resolution missions, such as XRISM and Athena.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Stars: massive; Stars: winds; outflows; X-rays: binaries

History of acoustic neutrino detection - Lahmann, Robert (8TH INTERNATIONAL CONFERENCE ON ACOUSTIC AND RADIO EEV NEUTRINO DETECTION ACTIVITIES (ARENA 2018), 2019)
CRIS-Team WoS Importer:2020-10-30

Hydrophone characterization for the KM3NeT experiment - Muller, Rasa; Von Benda-Beckmann, Sander; Doppenberg, Ed; Lahmann, Robert; Buis, Ernst-Jan (8TH INTERNATIONAL CONFERENCE ON ACOUSTIC AND RADIO EEV NEUTRINO DETECTION ACTIVITIES (ARENA 2018), 2019)
CRIS-Team WoS Importer:2020-10-30

IceCube-Gen2: The window to the extreme Universe - Aartsen, M. G.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Journal of Physics G: Nuclear and Particle Physics, 2021)
The observation of electromagnetic radiation from radio to γ-ray wavelengths has provided a wealth of information about the Universe. However, at PeV (1015 eV) energies and above, most of the Universe is impenetrable to photons. New messengers, namely cosmic neutrinos, are needed to explore the most extreme environments of the Universe where black holes, neutron stars, and stellar explosions transform gravitational energy into non-thermal cosmic rays. These energetic particles havemillions of times higher energies than those produced in the most powerful particle accelerators on Earth. As neutrinos can escape from regions otherwise opaque to radiation, they allow an unique view deep into exploding stars and the vicinity of the event horizons of black holes. The discovery of cosmic neutrinos with IceCube has opened this new window on the Universe. IceCube has been successful in finding first evidence for cosmic particle acceleration in the jet of an active galactic nucleus. Yet, ultimately, its sensitivity is too limited to detect even the brightest neutrino sources with high significance, or to detect populations of less luminous sources. In thiswhite paper, we present an overview of a next-generation instrument, IceCube-Gen2, which will sharpen our understanding of the processes and environments that govern the Universe at the highest energies. IceCube-Gen2 is designed to: (a) Resolve the high-energy neutrino sky from TeV to EeV energies (b) Investigate cosmic particle acceleration through multi-messenger observations (c) Reveal the sources and propagation of the highest energy particles in the Universe (d) Probe fundamental physics with high-energy neutrinos IceCube-Gen2 will enhance the existing IceCube detector at the South Pole. It will increase the annual rate of observed cosmic neutrinos by a factor of ten compared to IceCube, and will be able to detect sources five times fainter than its predecessor. Furthermore, through the addition of a radio array, IceCube- Gen2 will extend the energy range by several orders of magnitude compared to IceCube. Construction will take 8 years and cost about 350M. The goal is to have IceCube-Gen2 fully operational by 2033. IceCube-Gen2 will play an essential role in shaping the new era of multimessenger astronomy, fundamentally advancing our knowledge of the highenergy Universe. This challenging mission can be fully addressed only through the combination of the information from the neutrino, electromagnetic, and gravitational wave emission of high-energy sources, in concert with the new survey instruments across the electromagnetic spectrum and gravitational wave detectors which will be available in the coming years.
CRIS-Team Scopus Importer:2021-05-21
Keywords: High-energy astrophysics; Neutrino astronomy; Neutrino telescopes

IceCube high-energy starting event sample: Description and flux characterization with 7.5 years of data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Ansseau,; et al. (Physical Review D, 2021)
The IceCube Neutrino Observatory has established the existence of a high-energy all-sky neutrino flux of astrophysical origin. This discovery was made using events interacting within a fiducial region of the detector surrounded by an active veto and with reconstructed energy above 60 TeV, commonly known as the high-energy starting event sample (HESE). We revisit the analysis of the HESE sample with an additional 4.5 years of data, newer glacial ice models, and improved systematics treatment. This paper describes the sample in detail, reports on the latest astrophysical neutrino flux measurements, and presents a source search for astrophysical neutrinos. We give the compatibility of these observations with specific isotropic flux models proposed in the literature as well as generic power-law-like scenarios. Assuming v(e): v(mu): v(tau) = 1:1:1, and an equal flux of neutrinos and antineutrinos, we find that the astrophysical neutrino spectrum is compatible with an unbroken power law, with a preferred spectral index of 2.87(-0.19)(+0.20) for the 68% confidence interval.
CRIS-Team WoS Importer:2021-07-23

IceCube Search for High-energy Neutrino Emission from TeV Pulsar Wind Nebulae - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Astrophysical Journal, 2020)
Pulsar wind nebulae (PWNe) are the main gamma-ray emitters in the Galactic plane. They are diffuse nebulae that emit nonthermal radiation. Pulsar winds, relativistic magnetized outflows from the central star, shocked in the ambient medium produce a multiwavelength emission from the radio through gamma-rays. Although the leptonic scenario is able to explain most PWNe emission, a hadronic contribution cannot be excluded. A possible hadronic contribution to the high-energy gamma-ray emission inevitably leads to the production of neutrinos. Using 9.5 yr of all-sky IceCube data, we report results from a stacking analysis to search for neutrino emission from 35 PWNe that are high-energy gamma-ray emitters. In the absence of any significant correlation, we set upper limits on the total neutrino emission from those PWNe and constraints on hadronic spectral components.
CRIS-Team WoS Importer:2020-10-02

IceCube Search for Neutrinos Coincident with Compact Binary Mergers from LIGO-Virgo's First Gravitational-wave Transient Catalog - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Astrophysical Journal Letters, 2020)
Using the IceCube Neutrino Observatory, we search for high-energy neutrino emission coincident with compact binary mergers observed by the LIGO and Virgo gravitational-wave (GW) detectors during their first and second observing runs. We present results from two searches targeting emission coincident with the sky localization of each GW event within a 1000 s time window centered around the reported merger time. One search uses a model-independent unbinned maximum-likelihood analysis, which uses neutrino data from IceCube to search for pointlike neutrino sources consistent with the sky localization of GW events. The other uses the Low-Latency Algorithm for Multi-messenger Astrophysics, which incorporates astrophysical priors through a Bayesian framework and includes LIGO-Virgo detector characteristics to determine the association between the GW source and the neutrinos. No significant neutrino coincidence is seen by either search during the first two observing runs of the LIGO-Virgo detectors. We set upper limits on the time-integrated neutrino emission within the 1000 s window for each of the 11 GW events. These limits range from 0.02 to 0.7 GeV cm-2. We also set limits on the total isotropic equivalent energy, E iso, emitted in high-energy neutrinos by each GW event. These limits range from 1.7 × 1051 to 1.8 × 1055 erg. We conclude with an outlook for LIGO-Virgo observing run O3, during which both analyses are running in real time.
CRIS-Team Scopus Importer:2020-08-14

Identification of HESS J1303-631 as a pulsar wind nebula through γ -ray, X-ray, and radio observations - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
Aims. The previously unidentified very high-energy (VHE; E > 100 GeV) γ-ray source HESS J1303-631, discovered in 2004, is re-examined including new data from the H.E.S.S. Cherenkov telescope array in order to identify this object. Archival data from the XMM-Newton X-ray satellite and from the PMN radio survey are also examined. Methods. Detailed morphological and spectral studies of VHE γ-ray emission as well as of the XMM-Newton X-ray data are performed. Radio data from the PMN survey are used as well to construct a leptonic model of the source. The γ-ray and X-ray spectra and radio upper limit are used to construct a one zone leptonic model of the spectral energy distribution (SED). Results. Significant energy-dependent morphology of the γ-ray source is detected with high-energy emission (E > 10 TeV) positionally coincident with the pulsar PSR J1301-6305 and lower energy emission (E < 2 TeV) extending ∼0.4° to the southeast of the pulsar. The spectrum of the VHE source can be described with a power-law with an exponential cut-off N = (5.6 ± 0.5) × 10 ± TeV ± cm ± s, Γ = 1.5 ± 0.2) and E = (7.7 ± ± ± 2.2) TeV. The pulsar wind nebula (PWN) is also detected in X-rays, extending ∼2-3′ from the pulsar position towards the center of the γ-ray emission region. A potential radio counterpart from the PMN survey is also discussed, showing a hint for a counterpart at the edge of the X-ray PWN trail and is taken as an upper limit in the SED. The extended X-ray PWN has an unabsorbed flux of F ∼ 1.6 × 10 erg cm and is detected at a significance of 6.5σ. The SED is well described by a one zone leptonic scenario which, with its associated caveats, predicts a very low average magnetic field for this source. Conclusions. Significant energy-dependent morphology of this source, as well as the identification of an associated X-ray PWN from XMM-Newton observations enable identification of the VHE source as an evolved PWN associated to the pulsar PSR J1301-6305. This identification is supported by the one zone leptonic model, which suggests that the energetics of the γ-ray and X-ray radiation are such that they may have a similar origin in the pulsar nebula. However, the large discrepancy in emission region sizes and the low level of synchrotron radiation suggest a multi-population leptonic nature. The low implied magnetic field suggests that the PWN has undergone significant expansion. This would explain the low level of synchrotron radiation and the difficulty in detecting counterparts at lower energies, the reason this source was originally classified as a "dark" VHE γ-ray source. © ESO, 2012.
Keywords: Gamma rays: general; ISM: individual objects: HESS J1303-631; Pulsars: individual: PSR J1301-6305

Improved Characterization of the Astrophysical Muon-neutrino Flux with 9.5 Years of IceCube Data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Astrophysical Journal, 2022)
We present a measurement of the high-energy astrophysical muon-neutrino flux with the IceCube Neutrino Observatory. The measurement uses a high-purity selection of 650k neutrino-induced muon tracks from the northern celestial hemisphere, corresponding to 9.5 yr of experimental data. With respect to previous publications, the measurement is improved by the increased size of the event sample and the extended model testing beyond simple power-law hypotheses. An updated treatment of systematic uncertainties and atmospheric background fluxes has been implemented based on recent models. The best-fit single power-law parameterization for the astrophysical energy spectrum results in a normalization of φ@100TeVνμ+ν¯μ=1.44-0.26+0.25×10-18GeV-1cm-2s-1sr-1 and a spectral index γSPL=2.37-0.09+0.09, constrained in the energy range from 15 TeV to 5 PeV. The model tests include a single power law with a spectral cutoff at high energies, a log-parabola model, several source-class-specific flux predictions from the literature, and a model-independent spectral unfolding. The data are consistent with a single power-law hypothesis, however, spectra with softening above one PeV are statistically more favorable at a two-sigma level.
CRIS-Team Scopus Importer:2022-04-22

Improved measurement of the bb̄ production cross section in 920 GeV fixed-target proton-nucleus collisions - van Eldik, Christopher; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2006)
A new measurement of the bb̄ production cross section in 920 GeV proton-nucleus collisions is presented by the HERA-B Collaboration. The bb̄ production is tagged via inclusive bottom quark decays into J/ψ mesons by exploiting the longitudinal separation of J/ψ→l+l- decay vertices from the primary proton-nucleus interaction point. Both e+e- and μ+μ- channels are reconstructed for a total of 83±12 inclusive b→J/ψX events found. The combined analysis yields a bb̄ to prompt J/ψ cross section ratio of Δσ(bb̄)ΔσJ/ψ=0.032±0. 005stat±0.004sys measured in the xF acceptance (-0.35
Keywords: Inclusive production with identified hadrons; Decays of bottom mesons; Inclusive production with identified leptons photons or other nonhadronic particles; Quarks gluons and QCD in nuclei and nuclear processes

Improving sensitivity of the ARIANNA detector by rejecting thermal noise with deep learning - Anker, A.; Baldi, P.; Barwick, S. W.; Beise, J.; Besson, D. Z.; Bouma, Sjoerd; Cataldo, Maddalena; Chen, P.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hallmann, S.; et al. (Journal of Instrumentation, 2022)
The ARIANNA experiment is an Askaryan detector designed to record radio signals induced by neutrino interactions in the Antarctic ice. Because of the low neutrino flux at high energies (Eν > 1016 eV), the physics output is limited by statistics. Hence, an increase in sensitivity significantly improves the interpretation of data and offers the ability to probe new parameter spaces. The amplitudes of the trigger threshold are limited by the rate of triggering on unavoidable thermal noise fluctuations. We present a real-time thermal noise rejection algorithm that enables the trigger thresholds to be lowered, which increases the sensitivity to neutrinos by up to a factor of two (depending on energy) compared to the current ARIANNA capabilities. A deep learning discriminator, based on a Convolutional Neural Network (CNN), is implemented to identify and remove thermal events in real time. We describe a CNN trained on MC data that runs on the current ARIANNA microcomputer and retains 95% of the neutrino signal at a thermal noise rejection factor of 105, compared to a template matching procedure which reaches only 102 for the same signal efficiency. Then the results are verified in a lab measurement by feeding in generated neutrino-like signal pulses and thermal noise directly into the ARIANNA data acquisition system. Lastly, the same CNN is used to classify cosmic-rays events to make sure they are not rejected. The network classified 102 out of 104 cosmic-ray events as signal.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Cherenkov detectors; Neutrino detectors; Real-time monitoring

Improving the muon track reconstruction of IceCube and IceCube-Gen2 - Bradascio, Federica; Glüsenkamp, Thorsten (VERY LARGE VOLUME NEUTRINO TELESCOPES (VLVNT-2018), 2019)
CRIS-Team WoS Importer:2020-02-04

Inclusive V0 production cross sections from 920 GeV fixed target proton-nucleus collisions: The HERA-B Collaboration - van Eldik, Christopher; et al. (European Physical Journal C, 2003)
Inclusive differential cross sections dσ/dx and dσ/dp for the production of K , Λ, and Λ̄ particles are measured at HERA in proton-induced reactions on C, Al, Ti, and W targets. The incident beam energy is 920 GeV, corresponding to √s = 41.6 GeV in the proton-nucleon system. The ratios of differential cross sections dσ(K )/dσ(Λ) and dσ(Λ̄)/dσ(Λ) are measured to be 6.2 ± 0.5 and 0.66 ± 0.07, respectively, for x ≈ -0.06. No significant dependence upon the target material is observed. Within errors, the slopes of the transverse momentum distributions dσ/dp also show no significant dependence upon the target material. The dependence of the extrapolated total cross sections σ on the atomic mass A of the target material is discussed, and the deduced cross sections per nucleon σ are compared with results obtained at other energies.

Indirect search for dark matter in the Galactic Centre with IceCube - Iovine, Nadège; Aguilar, Juan A.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; et al. (Proceedings of Science, 2022)
Even though there are strong astrophysical and cosmological indications to support the existence of dark matter, its exact nature remains unknown. We expect dark matter to produce standard model particles when annihilating or decaying, assuming that it is composed of Weakly Interacting Massive Particles (WIMPs). These standard model particles could in turn yield neutrinos that can be detected by the IceCube neutrino telescope. The Milky Way is expected to be permeated by a dark matter halo with an increased density towards its centre. This halo is expected to yield the strongest dark matter annihilation signal at Earth coming from any celestial object, making it an ideal target for indirect searches. In this contribution, we present the sensitivities of an indirect search for dark matter in the Galactic Centre using IceCube data. This low energy dark matter search allows us to cover dark matter masses ranging from 5 GeV to 1 TeV. The sensitivities obtained for this analysis show considerable improvements over previous IceCube results in the considered energy range.
CRIS-Team Scopus Importer:2022-12-23

In situ, broadband measurement of the radio frequency attenuation length at Summit Station, Greenland - Aguilar, J. A.; Allison, P.; Beatty, J. J.; Besson, D.; Bishop, A.; Botner, O.; Bouma, Sjoerd; Buitink, S.; Cataldo, Maddalena; Clark, B. A.; Curtis-Ginsberg, Z.; Connolly, A.; et al. (Journal of Glaciology, 2022)
Over the last 25 years, radiowave detection of neutrino-generated signals, using cold polar ice as the neutrino target, has emerged as perhaps the most promising technique for detection of extragalactic ultra-high energy neutrinos (corresponding to neutrino energies in excess of 0.01 Joules, or 10(17) electron volts). During the summer of 2021 and in tandem with the initial deployment of the Radio Neutrino Observatory in Greenland (RNO-G), we conducted radioglaciological measurements at Summit Station, Greenland to refine our understanding of the ice target. We report the result of one such measurement, the radio-frequency electric field attenuation length L-alpha. We find an approximately linear dependence of L-alpha on frequency with the best fit of the average field attenuation for the upper 1500 m of ice: < L-alpha > = ((1154 +/- 121) - (0.81 +/- 0.14) (v/MHz)) m for frequencies v is an element of [145 - 3501 MHz.
CRIS-Team WoS Importer:2022-06-10

In-situ calibration of the single-photoelectron charge response of the IceCube photomultiplier tubes - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Journal of Instrumentation, 2020)
We describe an improved in-situ calibration of the single-photoelectron charge distributions for each of the in-ice Hamamatsu Photonics R7081-02[MOD] photomultiplier tubes in the IceCube Neutrino Observatory. The characterization of the individual PMT charge distributions is important for PMT calibration, data and Monte Carlo simulation agreement, and understanding the effect of hardware differences within the detector. We discuss the single photoelectron identification procedure and how we extract the single-photoelectron charge distribution using a deconvolution of the multiple-photoelectron charge distribution.
CRIS-Team WoS Importer:2020-07-24

Intrinsic limits on resolutions in muon- and electron-neutrino charged-current events in the KM3NeT/ORCA detector - Adrian-Martinez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of High Energy Physics, 2017)
Studying atmospheric neutrino oscillations in the few-GeV range with a multimegaton detector promises to determine the neutrino mass hierarchy. This is the main science goal pursued by the future KM3NeT/ORCA water Cherenkov detector in the Mediterranean Sea. In this paper, the processes that limit the obtainable resolution in both energy and direction in charged-current neutrino events in the ORCA detector are investigated. These processes include the composition of the hadronic fragmentation products, the subsequent particle propagation and the photon-sampling fraction of the detector. GEANT simulations of neutrino interactions in seawater produced by GENIE are used to study the effects in the 1-20 GeV range. It is found that fluctuations in the hadronic cascade in conjunction with the variation of the inelasticity y are most detrimental to the resolutions. The effect of limited photon sampling in the detector is of significantly less importance. These results will therefore also be applicable to similar detectors/media, such as those in ic
Keywords: Neutrino Detectors and Telescopes (experiments)

Introducing the CTA concept - Acharya, B. S.; Actis, M.; Aghajani, T.; Agnetta, G.; Aguilar, J.; Aharonian, F.; Ajello, M.; Akhperjanian, A.; Alcubierre, M.; Aleksic, J.; Alfaro, R.; Aliu, E.; et al. (Astroparticle Physics, 2013)
The Cherenkov Telescope Array (CTA) is a new observatory for very high-energy (VHE) gamma rays. CTA has ambitions science goals, for which it is necessary to achieve full-sky coverage, to improve the sensitivity by about an order of magnitude, to span about four decades of energy, from a few tens of GeV to above 100 TeV with enhanced angular and energy resolutions over existing VHE gamma-ray observatories. An international collaboration has formed with more than 1000 members from 27 countries in Europe, Asia, Africa and North and South America. In 2010 the CTA Consortium completed a Design Study and started a three-year Preparatory Phase which leads to production readiness of CTA in 2014. In this paper we introduce the science goals and the concept of CTA, and provide an overview of the project. © 2013 Elsevier B.V. All rights reserved.
Keywords: Air showers; Cherenkov Telescopes; TeV gamma-ray astronomy

Investigation of Gravitaxis and Phototaxis in Euglena gracilis - Häder, Donat-Peter; Faddoul, Jaoudat; Lebert, Michael; Richter, Peter; Schuster, Martin; Richter, Roland; Strauch, Sebastian; Daiker, Viktor (Advances in Life Sciences, 2010)
This article provides an overview of the research of phototaxis and gravitaxis in the unicellular flagellate Euglena gracilis. The cells show positive phototaxis at low light intensities (swimming towards the light source, below 10 W/m2, sunlight) and a negative one upon high irradiances (>10 W/m2). Phototaxis is based on a blue light-activated adenylyl cyclase, which produces cAMP upon irradiation. The further steps following the transient rise of the cAMP concentration are still unknown. Gravitaxis is a movement parallel to an acceleration vector. In the absence of external stimuli the cells swim upward in the water column (negative gravitaxis), upon stress gravitaxis inverts into a positive one. The results of sounding rocket campaigns and of a large number of ground experiments led to the following model of signal perception and transduction in gravitaxis of Euglena gracilis: The body of the cell is heavier than the surrounding medium, sediments and thereby exerts a force onto the lower membrane. Upon deviation from a vertical swimming path mechano-sensitive elements are activated. This leads to an increase in the intracellular calcium concentration and a change of the membrane potential. The increased calcium concentration regulates the action of calmodulin, which in turn modulates an adenylyl cyclase, which converts ATP to cAMP. cAMP probably controls the flagellar beat and/or probably the shape of the cell. Phototaxis as well as gravitaxis are probably controlled by certain protein kinases. The blockage of different protein kinases (PK) by means of RNAi gave rise to the assumption that both signal pathways activate certain PKs. The blockage of one PK resulted in a loss of gravitaxis, the blockage of another one in loss of phototactic behaviour.
Keywords: Euglena gracilis; phototaxis; gravitaxis; RNA interference; signal transduction

Investigation of Two Fermi-LAT Gamma-Ray Blazars Coincident with High-energy Neutrinos Detected by IceCube - Garrappa, S.; Buson, S.; Franckowiak, A.; Shappee, B. J.; Beacom, J. F.; Dong, S.; Holoien, T. W-S; Kochanek, C. S.; Prieto, J. L.; Stanek, K. Z.; Thompson, T. A.; Aartsen, M. G.; et al. (Astrophysical Journal, 2019)
After the identification of the gamma-ray blazar TXS 0506+056 as the first compelling IceCube neutrino source candidate, we perform a systematic analysis of all high-energy neutrino events satisfying the IceCube realtime trigger criteria. We find one additional known gamma-ray source, the blazar GB6 J1040+0617, in spatial coincidence with a neutrino in this sample. The chance probability of this coincidence is 30% after trial correction. For the first time, we present a systematic study of the gamma-ray flux, spectral and optical variability, and multiwavelength behavior of GB6 J1040+0617 and compare it to TXS 0506+056. We find that TXS 0506+056 shows strong flux variability in the Fermi-Large Area Telescope gamma-ray band, being in an active state around the arrival of IceCube-170922A, but in a low state during the archival IceCube neutrino flare in 2014/15. In both cases the spectral shape is statistically compatible (<= 2 sigma) with the average spectrum showing no indication of a significant relative increase of a high-energy component. While the association of GB6 J1040+0617 with the neutrino is consistent with background expectations, the source appears to be a plausible neutrino source candidate based on its energetics and multiwavelength features, namely a bright optical flare and modestly increased gamma-ray activity. Finding one or two neutrinos originating from gamma-ray blazars in the given sample of high-energy neutrinos is consistent with previously derived limits of neutrino emission from gamma-ray blazars, indicating the sources of the majority of cosmic high-energy neutrinos remain unknown.
CRIS-Team WoS Importer:2019-08-16

Investigations of ice and emitter properties from radio signals recorded with ARIANNA - Lahmann, Robert (Proceedings of Science, 2019)
ARIANNA is an in-ice radio detector for neutrinos in the energy range from 1016 eV to 1020 eV which is currently in its pilot-phase in Antarctica. It exploits the so-called Askaryan effect by which radio signals are emitted from neutrino-induced particle showers in ice. Geometric optics is an efficient tool to study the propagation of electromagnetic signals through a medium such as ice, using ray tracing to predict the response induced in an antenna for a given arrangement of emitter and receiver within the medium. Analyzing and understanding the antenna response to calibration signals under well-defined conditions is important to develop reconstruction algorithms of neutrino properties, most notably the interaction vertex and energy, and to understand and characterize the properties of the ice. Recent results obtained with the data collected during the 2018-2019 Antarctic season will be presented.
CRIS-Team Scopus Importer:2021-04-20

Joint Constraints on Galactic Diffuse Neutrino Emission from the ANTARES and IceCube Neutrino Telescopes - Albert, A.; Grasso, D.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The existence of diffuse Galactic neutrino production is expected from cosmic-ray interactions with Galactic gas and radiation fields. Thus, neutrinos are a unique messenger offering the opportunity to test the products of Galactic cosmic-ray interactions up to energies of hundreds of TeV. Here we present a search for this production using ten years of Astronomy with a Neutrino Telescope and Abyss environmental RESearch (ANTARES) track and shower data, as well as seven years of IceCube track data. The data are combined into a joint likelihood test for neutrino emission according to the KRA(gamma) model assuming a 5 PeV per nucleon Galactic cosmic-ray cutoff. No significant excess is found. As a consequence, the limits presented in this Letter start constraining the model parameter space for Galactic cosmic-ray production and transport.
Keywords: cosmic rays; diffusion; Galaxy: disk; gamma rays: diffuse background; neutrinos

J/ψ production via χc decays in 920 GeV pA interactions - van Eldik, Christopher; et al. (Physics Letters B, 2003)
Using data collected by the HERA-B experiment, we have measured the fraction of J/ψ's produced via radiative χ decays in interactions of 920 GeV protons with carbon and titanium targets. We obtained R, = 0.32 ± 0.06 ± 0.04 for the fraction of J/ψ from χ decays averaged over proton-carbon and proton-titanium collisions. This result is in agreement with previous measurements and is compared with theoretical predictions. © 2003 Published by Elsevier Science B.V.

K*0 and φ meson production in proton-nucleus interactions at √s=41.6 GeV - van Eldik, Christopher; et al. (European Physical Journal C, 2007)
The inclusive production cross sections of the strange vector mesons K*, K, and φ have been measured in interactions of 920 GeV protons with C, Ti, and W targets with the HERA-B detector at the HERA storage ring. Differential cross sections as a function of rapidity and transverse momentum have been measured in the central rapidity region and for transverse momenta up to p = 3.5 GeV/c. The atomic number dependence is parametrised as σ=σ *A, where σ is the proton-nucleon cross section. Within the phase space accessible, α(K )=0.86±0.03, α(K*)=0. 87±0.03, and α(φ)=0.96±0.02. The total proton-nucleon cross sections, determined by extrapolating the differential measurements to full phase space, are σ=(5.06±0.54) ∈mb, σ=(4.02±0.45)∈mb, and σ=(1.17±0.11)∈mb. For all resonances the Cronin effect is observed; compared to the measurements of Cronin et al. for K mesons, the measured values of α for φ mesons coincide with those of K mesons for all transverse momenta, while the enhancement for K/K mesons is smaller. © Springer-Verlag Berlin Heidelberg 2007.

Kinematic distributions and nuclear effects of J/ψ production in 920 GeV fixed-target proton-nucleus collisions - Abt, I.; Adams, M.; Agari, M.; Albrecht, H.; Aleksandrov, A.; Amaral, Vasco; Amorim, Antonio; Aplin, S. J.; Aushev, V.; Bagaturia, Y.; Balagura, V.; Bargiotti, M.; et al. (European Physical Journal C, 2009)
Measurements of the kinematic distributions of J/ψ mesons produced in p-C, p-Ti and p-W collisions at sqrts=41.6∼GeV in the Feynman-x region -0.34

KM3NeT front-end and readout electronics system: hardware, firmware, and software - Aiello, Sebastiano; Amllei, Fabrizio; Andre, Michel; Androulakis, Giorgos; Anghinolfi, Marco; Anton, Gisela; Ardid, Miquel; Aublin, Julien; Bagatelas, Christos; Barbarino, Giancarlo; Baret, Bruny; Du Pree, Suzan Basegmez; et al. (Journal of Astronomical Telescopes, Instruments, and Systems, 2019)
The KM3NeT research infrastructure being built at the bottom of the Mediterranean Sea will host water-Cherenkov telescopes for the detection of cosmic neutrinos. The neutrino telescopes will consist of large volume three-dimensional grids of optical modules to detect the Cherenkov light from charged particles produced by neutrino-induced interactions. Each optical module houses 31 3-in. photomultiplier tubes, instrumentation for calibration of the photomultiplier signal and positioning of the optical module, and all associated electronics boards. By design, the total electrical power consumption of an optical module has been capped at seven Watts. We present an overview of the front-end and readout electronics system inside the optical module, which has been designed for a 1-ns synchronization between the clocks of all optical modules in the grid during a life time of at least 20 years. (C) 2019 Society of Photo-Optical Instrumentation Engineers (SPIE)
CRIS-Team WoS Importer:2020-02-28

LeptonInjector and LeptonWeighter: A neutrino event generator and weighter for neutrino observatories - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Computer Physics Communications, 2021)
We present a high-energy neutrino event generator, called LeptonInjector, alongside an event weighter, called LeptonWeighter. Both are designed for large-volume Cherenkov neutrino telescopes such as IceCube. The neutrino event generator allows for quick and flexible simulation of neutrino events within and around the detector volume, and implements the leading Standard Model neutrino interaction processes relevant for neutrino observatories: neutrino-nucleon deep-inelastic scattering and neutrino-electron annihilation. In this paper, we discuss the event generation algorithm, the weighting algorithm, and the main functions of the publicly available code, with examples. Program summary: Program Titles: LeptonInjector and LeptonWeighter CPC Library link to program files: https://doi.org/10.17632/662gkpjfd9.1 Developer's repository links: https://github.com/icecube/LeptonInjector and https://github.com/icecube/LeptonWeighter Licensing provisions: GNU Lesser General Public License, version 3. Programming Language: C++11 External Routines: • Boost • HDF5 • nuflux (https://github.com/icecube/nuflux) • nuSQuIDS (https://github.com/arguelles/nuSQuIDS) • Photospline (https://github.com/icecube/photospline) • SuiteSparse (https://github.com/DrTimothyAldenDavis/SuiteSparse) Nature of problem: LeptonInjector: Generate neutrino interaction events of all possible topologies and energies throughout and around a detector volume. LeptonWeighter: Reweight Monte Carlo events, generated by a set of LeptonInjector Generators, to any desired physical neutrino flux or cross section. Solution method: LeptonInjector: Projected ranges of generated leptons and the extent of the detector, in terms of column depth, are used to inject events in and around the detector volume. Event kinematics follow distributions provided in cross section files. LeptonWeighter: Event generation probabilities are calculated for each Generator, which are then combined into a generation weight and used to calculate an overall event weight.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Event generator; Neutrino generator; Neutrino interaction; Neutrino simulation; Weighting

Letter of intent for KM3NeT 2.0 - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; et al. (Journal of Physics G: Nuclear and Particle Physics, 2016)
The main objectives of the KM3NeT Collaboration are (i) the discovery and subsequent observation of high-energy neutrino sources in the Universe and (ii) the determination of the mass hierarchy of neutrinos. These objectives are strongly motivated by two recent important discoveries, namely: (1) the high-energy astrophysical neutrino signal reported by IceCube and (2) the sizable contribution of electron neutrinos to the third neutrino mass eigenstate as reported by Daya Bay, Reno and others. To meet these objectives, the KM3NeT Collaboration plans to build a new Research Infrastructure consisting of a network of deep-sea neutrino telescopes in the Mediterranean Sea. A phased and distributed implementation is pursued which maximises the access to regional funds, the availability of human resources and the synergistic opportunities for the Earth and sea sciences community. Three suitable deep-sea sites are selected, namely off-shore Toulon (France), Capo Passero (Sicily, Italy) and Pylos (Peloponnese, Greece). The infrastructure will consist of three so-called building blocks. A building block comprises 115 strings, each string comprises 18 optical modules and each optical module comprises 31 photo-multiplier tubes. Each building block thus constitutes a three-dimensional array of photo sensors that can be used to detect the Cherenkov light produced by relativistic particles emerging from neutrino interactions. Two building blocks will be sparsely configured to fully explore the IceCube signal with similar instrumented volume, different methodology, improved resolution and complementary field of view, including the galactic plane. One building block will be densely configured to precisely measure atmospheric neutrino oscillations.
Keywords: deep sea neutrino telescope; neutrino astronomy; neutrino mass hierarchy; neutrino physics

Letter of interest for a neutrino beam from Protvino to KM3NeT/ORCA - Akindinov, V.; Anassontzis, E. G.; Anton, Gisela; Ardid, M.; Aublin, J.; Baret, B.; Bertin,; Bourret, S.; Bozza, C.; Bruchner, M.; Bruijn, R.; Brunner, J.; et al. (European Physical Journal C: Particles and Fields, 2019)
The Protvino accelerator facility located in the Moscow region, Russia, is in a good position to offer a rich experimental research program in the field of neutrino physics. Of particular interest is the possibility to direct a neutrino beam from Protvino towards the KM3NeT/ORCA detector, which is currently under construction in the Mediterranean Sea 40 km offshore Toulon, France. This proposal is known as P2O. Thanks to its baseline of 2595 km, this experiment would yield an unparalleled sensitivity to matter effects in the Earth, allowing for the determination of the neutrino mass ordering with a high level of certainty after only a few years of running at a modest beam intensity of sensitivity to the leptonic CP-violating Dirac phase can be achieved. A second stage of the experiment, comprising a further intensity upgrade of the accelerator complex and a densified version of the ORCA detector (Super-ORCA), would allow for up to a 6 sigma[12pt] resolution on the CP phase after 10 years of running with a 450 kW beam, competitive with other planned experiments. The initial composition and energy spectrum of the neutrino beam would need to be monitored by a near detector, to be constructed several hundred meters downstream from the proton beam target. The same neutrino beam and near detector set-up would also allow for neutrino-nucleus cross section measurements to be performed. A short-baseline sterile neutrino search experiment would also be possible.
CRIS-Team WoS Importer:2019-10-04

Light dark bosons in the JUNO-TAO neutrino detector - Smirnov, Mikhail; Yang, Guang; Liao, Jiajun; Hu, Zhuojun; Ling, Jiajie (Physical Review D, 2021)
This work presents a sensitivity study of a reactor liquid scintillator detector to three kinds of dark bosons with masses below 1 MeV, such as dark photons, axion-like particles, and light scalar bosons. The JUNO-TAO detector with Taishan nuclear reactor is taken as a reference. With a proposed 180 days of data taking, the best sensitivity result at the level of similar to 10(-5) 95% C.L. is achieved for dark photons with an optimized signal to background ratio for the electron coupling constant gX through inverse Compton-like scattering. Similar calculations are completed for axion-like particles and scalar bosons. The background systematic uncertainty presents as the main limiting factor for the further sensitivity improvement. Several remarks are made to the controversial analysis for the NEOS experiment. Additionally the differential and the inverse differential cross sections have been derived for all three boson types and their interactions with electrons in liquid scintillator.
CRIS-Team WoS Importer:2022-02-04

Limits for the central production of Θ+ and Ξ- - pentaquarks in 920-GeV pA collisions - van Eldik, Christopher; et al. (Physical Review Letters, 2004)
The limits for the central production of θ and ξ pentaquark candidates in proton-induced reactions on C, Ti and W in 920-GeV pA collisions was investigated. It was found that there was no evidence for narrow signals in the θ → pK and ξ → ξπ channels. It was observed that the upper limits (UL) for the inclusive production cross section times branching fraction Bdσ/dyι were (4-16) μb/N. It was also observed that the calculated UL for θ/λ(1520) < 2.7% was lower than statistical hadronization predictions.
Keywords: Hyperons; Limits on production of particles

Limits on an energy dependence of the speed of light from a flare of the active galaxy PKS 2155-304 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Physical Review Letters, 2008)
In the past few decades, several models have predicted an energy dependence of the speed of light in the context of quantum gravity. For cosmological sources such as active galaxies, this minuscule effect can add up to measurable photon-energy dependent time lags. In this Letter a search for such time lags during the High Energy Stereoscopic System observations of the exceptional very high energy flare of the active galaxy PKS 2155-304 on 28 July 2006 is presented. Since no significant time lag is found, lower limits on the energy scale of speed of light modifications are derived. © 2008 The American Physical Society.

Limits on dark matter annihilation in the sun using the ANTARES neutrino telescope - Adrian-Martineza, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2016)
A search for muon neutrinos originating from dark matter annihilations in the Sun is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. In order to obtain the best possible sensitivities to dark matter signals, an optimisation of the event selection criteria is performed taking into account the background of atmospheric muons, atmospheric neutrinos and the energy spectra of the expected neutrino signals. No significant excess over the background is observed and 90% C.L. upper limits on the neutrino flux, the spin-dependent and spin-independent WIMP-nucleon cross-sections are derived for WIMP masses ranging from 50 GeV to 5 TeV for the annihilation channels WIMP+WIMP→bb-,WW and ττ.
Keywords: Dark matter; Indirect detection; Neutralino; Neutrino telescope; Sun; WIMP

Limits on the nuclearite flux using the ANTARES neutrino telescope - Albert, A.; Alves, S.; André, M.; Ardid, M.; Ardid, S.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; Benfenati, F.; et al. (Journal of Cosmology and Astroparticle Physics, 2023)
In this work, a search for nuclearites of strange quark matter by using nine years of ANTARES data taken in the period 2009-2017 is presented. The passage through matter of these particles is simulated taking into account a detailed description of the detector response to nuclearites and of the data acquisition conditions. A down-going flux of cosmic nuclearites with Galactic velocities (β = 10-3) was considered for this study. The mass threshold for detecting these particles at the detector level is 4 × 1013 GeV/c 2. Upper limits on the nuclearite flux for masses up to 1017 GeV/c 2 at the level of ∼ 5 × 10-17 cm-2 s-1 sr-1 are obtained. These are the first upper limits on nuclearites established with a neutrino telescope and the most stringent ever set for Galactic velocities.
CRIS-Team Scopus Importer:2023-01-27
Keywords: dark matter detectors; neutrino detectors

Localising the H.E.S.S. Galactic Center point source - van Eldik, Christopher; Bolz, Oliver; Braun, Isabel; Hermann, German; Hinton, James; Hofmann, Werner (30th International Cosmic Ray Conference, ICRC 2007, 2007)
Observations by the H.E.S.S. system of imaging atmospheric Cherenkov telescopes provide the most sensitive measurements of the Galactic Centre region in the energy range 150 GeV - 30 TeV. The vicinity of the kinetic centre of our galaxy harbours numerous objects which could potentially accelerate particles to very high energies (VHE, > 100 GeV) and thus produce the gamma;-ray flux observed. Within statistical and systematic errors, the centroid of the point-like emission measured by H.E.S.S. was found [1] to be in good agreement with the position of the supermassive black hole Sgr A* and the recently discovered PWN candidate G359.95-0.04 [2]. Given a systematic pointing error of about 30", a possible association with the SNR Sgr A East could not be ruled out with the 2004 H.E.S.S. data. In this contribution an update is given on the position of the H.E.S.S. Galactic Centre source using 2005/2006 data. The systematic pointing error is reduced to 6" per axis using guiding telescopes for pointing corrections, making it possible to exclude with high significance Sgr A East as the source of the VHE gamma;-rays.

Localising the HESS galactic centre point source - van Eldik, Christopher; Braun, Isabel; Bolz, Oliver; Hermann, German; Hinton, James; Hofmann, Werner (Journal of Physics Conference Series, 2008)

Localizing the VHE γ-ray source at the galactic centre - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Monthly Notices of the Royal Astronomical Society, 2010)
The inner 10 pc of our Galaxy contains many counterpart candidates of the very high energy (VHE; >100 GeV) γ-ray point source HESS J1745-290. Within the point spread function of the H.E.S.S. measurement, at least three objects are capable of accelerating particles to VHE and beyond and of providing the observed γ-ray flux. Previous attempts to address this source confusion were hampered by the fact that the projected distances between these objects were of the order of the error circle radius of the emission centroid (34 arcsec, dominated by the pointing uncertainty of the H.E.S.S. instrument). Here we present H.E.S.S. data of the Galactic Centre region, recorded with an improved control of the instrument pointing compared to H.E.S.S. standard pointing procedures. Stars observed during γ-ray observations by optical guiding cameras mounted on each H.E.S.S. telescope are used for off-line pointing calibration, thereby decreasing the systematic pointing uncertainties from 20 to 6 arcsec per axis. The position of HESS J1745-290 is obtained by fitting a multi-Gaussian profile to the background-subtracted γ-ray count map. A spatial comparison of the best-fitting position of HESS J1745-290 with the position and morphology of candidate counterparts is performed. The position is, within a total error circle radius of 13 arcsec, coincident with the position of the supermassive black hole Sgr A* and the recently discovered pulsar wind nebula candidate G359.95-0.04. It is significantly displaced from the centroid of the supernova remnant Sgr A East, excluding this object with high probability as the dominant source of the VHE γ-ray emission. © 2009 The Authors. Journal compilation © 2009 RAS.
Keywords: Galaxy: centre; Gamma-rays: observations; ISM: individual: G 359.95-0.04; ISM: individual: Sgr A East; ISM: individual: Sgr A*

Long-term monitoring of PKS 2155-304 with ATOM and H.E.S.S.: Investigation of optical/γ-ray correlations in different spectral states - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguner, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astronomy & Astrophysics, 2014)
In this paper we report on the analysis of all the available optical and very high-energy γ-ray (>200 GeV) data for the BL Lac object PKS 2155-304, collected simultaneously with the ATOM and H.E.S.S. telescopes from 2007 until 2009. This study also includes X-ray (RXTE, Swift) and high-energy γ-ray (Fermi-LAT) data. During the period analysed, the source was transitioning from its flaring to quiescent optical states, and was characterized by only moderate flux changes at different wavelengths on the timescales of days and months. A flattening of the optical continuum with an increasing optical flux can be noted in the collected dataset, but only occasionally and only at higher flux levels. We did not find any universal relation between the very high-energy γ-ray and optical flux changes on the timescales from days and weeks up to several years. On the other hand, we noted that at higher flux levels the source can follow two distinct tracks in the optical flux-colour diagrams, which seem to be related to distinct γ-ray states of the blazar. The obtained results therefore indicate a complex scaling between the optical and γ-ray emission of PKS 2155-304, with different correlation patterns holding at different epochs, and a γ-ray flux depending on the combination of an optical flux and colour rather than a flux alone.
Keywords: BL Lacertae objects: individual: PKS 2155-304; Black hole physics; Galaxies: active; Galaxies: jets; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Long-term monitoring of the ANTARES optical module efficiencies using 40K decays in sea water: The ANTARES Collaboration - Domi, Alba; et al. (European Physical Journal C: Particles and Fields, 2018)

Long-term monitoring of the ANTARES optical module efficiencies using K-40 decays in sea water - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
Cherenkov light induced by radioactive decay products is one of the major sources of background light for deep-sea neutrino telescopes such as ANTARES. These decays are at the same time a powerful calibration source. Using data collected by the ANTARES neutrino telescope from mid 2008 to 2017, the time evolution of the photon detection efficiency of optical modules is studied. A modest loss of only 20% in 9 years is observed. The relative time calibration between adjacent modules is derived as well.

Long-term TeV and X-ray observations of the gamma-ray binary hess j0632+057 - Aliu, E.; Archambault, S.; Aune, T.; Behera, B.; Beilicke, M.; Benbow, W.; Berger, K.; Bird, Ralph; Bouvier, A.; Buckley, J. H.; Bugaev, V.; Byrum, K.; et al. (Astrophysical Journal, 2014)
HESS J0632+057 is the only gamma-ray binary known so far whose position in the sky allows observations with ground-based observatories in both the northern and southern hemispheres. Here we report on long-term observations of HESS J0632+057 conducted with the Very Energetic Radiation Imaging Telescope Array System and High Energy Stereoscopic System Cherenkov telescopes and the X-ray satellite Swift, spanning a time range from 2004 to 2012 and covering most of the system's orbit. The very-high-energy (VHE) emission is found to be variable and is correlated with that at X-ray energies. An orbital period of days is derived from the X-ray data set, which is compatible with previous results, P = (321 ± 5) days. The VHE light curve shows a distinct maximum at orbital phases close to 0.3, or about 100 days after periastron passage, which coincides with the periodic enhancement of the X-ray emission. Furthermore, the analysis of the TeV data shows for the first time a statistically significant (>6.5σ) detection at orbital phases 0.6-0.9. The obtained gamma-ray and X-ray light curves and the correlation of the source emission at these two energy bands are discussed in the context of the recent ephemeris obtained for the system. Our results are compared to those reported for other gamma-ray binaries. © 2014. The American Astronomical Society. All rights reserved..
Keywords: acceleration of particles; binaries:general

Luminosity determination at HERA-B - van Eldik, Christopher; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2007)
A detailed description of an original method used to measure the luminosity accumulated by the HERA-B experiment for a data sample taken during the 2002-2003 HERA running period is reported. We show that, with this method, a total luminosity measurement can be achieved with a typical precision, including overall systematic uncertainties, at a level of 5% or better. We also report evidence for the detection of δ-rays generated in the target and comment on the possible use of such delta rays to measure luminosity. © 2007 Elsevier B.V. All rights reserved.
Keywords: Delta rays; Fixed target experiments; Luminosity determination; Proton nucleon collisions

Machine learning for kM3Net/Orca - Hallmann, Steffen; Moser, Michael; Reck, Stefan; Eberl, Thomas (Proceedings of Science, 2019)
The KM3NeT research infrastructure is currently under construction in two locations in the Mediterranean Sea. The KM3NeT/ORCA water-Cherenkov neutrino detector off the French coast will instrument several megatons of seawater with photosensors. Its main objective is the determination of the neutrino mass ordering. For the first time, deep convolutional neural networks are employed to achieve three specific reconstruction and classification tasks that constitute a complete alternative analysis pipeline for KM3NeT/ORCA detector data. The values and uncertainties of the energy, direction, and the interaction vertex of the incident neutrinos are reconstructed. The neutrino interaction type is recognized as shower- or track-like, and the main backgrounds to the detection of atmospheric neutrinos are classified and suppressed. Performance comparisons to other machine-learning methods used and maximum-likelihood reconstruction algorithms previously developed for KM3NeT/ORCA are provided. It is shown that this image recognition technique yields competitive results and performance improvements for large-volume neutrino telescopes.
CRIS-Team Scopus Importer:2021-04-20

Measurement of atmospheric neutrino mixing with improved IceCube DeepCore calibration and data processing - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Physical Review D, 2023)
We describe a new data sample of IceCube DeepCore and report on the latest measurement of atmospheric neutrino oscillations obtained with data recorded between 2011-2019. The sample includes significant improvements in data calibration, detector simulation, and data processing, and the analysis benefits from a sophisticated treatment of systematic uncertainties, with significantly greater level of detail since our last study. By measuring the relative fluxes of neutrino flavors as a function of their reconstructed energies and arrival directions we constrain the atmospheric neutrino mixing parameters to be sin2θ23=0.51±0.05 and Δm322=2.41±0.07×10-3 eV2, assuming a normal mass ordering. The errors include both statistical and systematic uncertainties. The resulting 40% reduction in the error of both parameters with respect to our previous result makes this the most precise measurement of oscillation parameters using atmospheric neutrinos. Our results are also compatible and complementary to those obtained using neutrino beams from accelerators, which are obtained at lower neutrino energies and are subject to different sources of uncertainties.
CRIS-Team Scopus Importer:2023-08-25

Measurement of atmospheric neutrino oscillations with the ANTARES neutrino telescope ANTARES Collaboration - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Basa, S.; et al. (Physics Letters B, 2012)
The data taken with the ANTARES neutrino telescope from 2007 to 2010, a total live time of 863 days, are used to measure the oscillation parameters of atmospheric neutrinos. Muon tracks are reconstructed with energies as low as 20 GeV. Neutrino oscillations will cause a suppression of vertical upgoing muon neutrinos of such energies crossing the Earth. The parameters determining the oscillation of atmospheric neutrinos are extracted by fitting the event rate as a function of the ratio of the estimated neutrino energy and reconstructed flight path through the Earth. Measurement contours of the oscillation parameters in a two-flavour approximation are derived. Assuming maximal mixing, a mass difference of Delta m(32)(2) = (3.1 +/- 0.9) . 10(-3) eV(2) is obtained, in good agreement with the world average value. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino oscillations; Neutrino telescope; ANTARES

Measurement of atmospheric tau neutrino appearance with IceCube DeepCore - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Physical Review D, 2019)
We present a measurement of atmospheric tau neutrino appearance from oscillations with three years of data from the DeepCore subarray of the IceCube Neutrino Observatory. This analysis uses atmospheric neutrinos from the full sky with reconstructed energies between 5.6 and 56 GeV to search for a statistical excess of cascadelike neutrino events which are the signature of nu(tau) interactions. For CC thorn NC (CC-only) interactions, we measure the tau neutrino normalization to be 0.73(-0.24)(+0.30) (0.57(-0.30)(+0.36)) and exclude the absence of tau neutrino oscillations at a significance of 3.2 sigma (2.0 sigma) These results are consistent with, and of similar precision to, a confirmatory IceCube analysis also presented, as well as measurements performed by other experiments.
CRIS-Team WoS Importer:2019-02-27

Measurement of cosmic ray electrons with H.E.S.S. - van Eldik, Christopher; et al. (30th International Cosmic Ray Conference, ICRC 2007, 2007)
Due to energy losses in the interstellar medium, cosmic ray electrons at TeV energies carry information on local (within a few hundred parsecs) accelerators. However, measurements of the spectrum of the cosmic ray electrons beyond 1 TeV are extremely difficult due to the rapidly declining flux and the much more numerous background of nucleonic cosmic rays. The very large collection area of Cherenkov telescope arrays makes them promising instruments with which to measure these high energy electrons. While Cherenkov telescopes solve the problem of low fluxes of cosmic ray electrons in the TeV range, they still have to deal with the problem of distinguishing electrons from the nucleonic background. Here we report on first results towards a measurement of the cosmic ray electron spectrum with the High Energy Stereoscopic System (H.E.S.S.). The improved background supression that is needed for such a measurement is achieved by an event classification with the "Random Forest" algorithm based on decision trees.

Measurement of D0, D+, Ds + and D*+ production in fixed target 920∈GeV proton-nucleus collisions - van Eldik, Christopher; et al. (European Physical Journal C, 2007)
The inclusive production cross sections of the charmed mesons D ,D,D and D* have been measured in interactions of 920 GeV protons on C, Ti, and W targets with the HERA-B detector at the HERA storage ring. Differential cross sections as a function of transverse momentum and Feynman's x variable are given for the central rapidity region and for transverse momenta up to p=3.5 GeV/c. The atomic mass number dependence and the leading to non-leading particle production asymmetries are presented as well. © 2007 Springer-Verlag / Società Italiana di Fisica.

Measurement of the atmospheric nu (mu) energy spectrum from 100 GeV to 200 TeV with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (European Physical Journal C, 2013)
Atmospheric neutrinos are produced during cascades initiated by the interaction of primary cosmic rays with air nuclei. In this paper, a measurement of the atmospheric energy spectrum in the energy range 0.1-200 TeV is presented, using data collected by the ANTARES underwater neutrino telescope from 2008 to 2011. Overall, the measured flux is similar to 25 % higher than predicted by the conventional neutrino flux, and compatible with the measurements reported in ice. The flux is compatible with a single power-law dependence with spectral index gamma (meas)=3.58 +/- 0.12. With the present statistics the contribution of prompt neutrinos cannot be established.

Measurement of the atmospheric νe and νμ energy spectra with the ANTARES neutrino telescope - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Physics Letters B, 2021)
This letter presents a combined measurement of the energy spectra of atmospheric νe and νμ in the energy range between ∼100 GeV and ∼50 TeV with the ANTARES neutrino telescope. The analysis uses 3012 days of detector livetime in the period 2007–2017, and selects 1016 neutrinos interacting in (or close to) the instrumented volume of the detector, yielding shower-like events (mainly from νe+ν‾e charged current plus all neutrino neutral current interactions) and starting track events (mainly from νμ+ν‾μ charged current interactions). The contamination by atmospheric muons in the final sample is suppressed at the level of a few per mill by different steps in the selection analysis, including a Boosted Decision Tree classifier. The distribution of reconstructed events is unfolded in terms of electron and muon neutrino fluxes. The derived energy spectra are compared with previous measurements that, above 100 GeV, are limited to experiments in polar ice and, for νμ, to Super-Kamiokande.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ANTARES; Atmospheric neutrinos; Neutrino telescope

Measurement of the bb̄ production cross section in 920 GeV fixed-target proton-nucleus collisions: The HERA - B collaboration - van Eldik, Christopher; et al. (European Physical Journal C, 2003)
Using the HERA - B detector, the bb̄ production cross section has been measured in 920 GeV proton collisions on carbon and titanium targets. The bb̄ production was tagged via inclusive bottom quark decays into J/ψ by exploiting the longitudinal separation of J/ψ → ll decay vertices from the primary proton-nucleus interaction. Both ee and μμ channels have been reconstructed and the combined analysis yields the cross section σ(bb̄) = 32 (stat)(sys) nb/nucleon.

Measurement of the EBL spectral energy distribution using the VHE gamma-ray spectra of HESS blazars - Abdalla, H.; Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Andersson, T.; Angüner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; et al. (Astronomy & Astrophysics, 2017)
Very high-energy gamma rays (VHE, E greater than or similar to 100 GeV) propagating over cosmological distances can interact with the low-energy photons of the extragalactic background light (EBL) and produce electron-positron pairs. The transparency of the Universe to VHE gamma rays is then directly related to the spectral energy distribution (SED) of the EBL. The observation of features in the VHE energy spectra of extragalactic sources allows the EBL to be measured, which otherwise is very difficult. An EBL model-independent measurement of the EBL SED with the H.E.S.S. array of Cherenkov telescopes is presented. It was obtained by extracting the EBL absorption signal from the reanalysis of high-quality spectra of blazars. From H.E.S.S. data alone the EBL signature is detected at a significance of 9.5 sigma, and the intensity of the EBL obtained in different spectral bands is presented together with the associated gamma-ray horizon.
CRIS-Team WoS Importer:2020-01-15
Keywords: Infrared: diffuse background; Cosmic background radiation; Gamma rays: galaxies; BL Lacertae objects: general

Measurement of the extragalactic background light imprint on the spectra of the brightest blazars observed with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
The extragalactic background light (EBL) is the diffuse radiation with the second highest energy density in the Universe after the cosmic microwave background. The aim of this study is the measurement of the imprint of the EBL opacity to γ-rays on the spectra of the brightest extragalactic sources detected with the High Energy Stereoscopic System (H.E.S.S.). The originality of the method lies in the joint fit of the EBL optical depth and of the intrinsic spectra of the sources, assuming intrinsic smoothness. Analysis of a total of ∼10γ-ray events enables the detection of an EBL signature at the 8.8σ level and constitutes the first measurement of the EBL optical depth using very-high energy (E > 100 GeV) γ-rays. The EBL flux density is constrained over almost two decades of wavelengths [0.30 μm, 17 μm] and the peak value at 1.4 μm is derived as λF = 15 ± 2 ± 3 nW m sr. © 2013 ESO.
Keywords: BL Lacertae objects: general; Cosmic background radiation; Gamma rays: galaxies

Measurement of the group velocity of light in sea water at the ANTARES site - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Astroparticle Physics, 2012)
The group velocity of light has been measured at eight different wavelengths between 385 nm and 532 nm in the Mediterranean Sea at a depth of about 2.2 km with the ANTARES optical beacon systems. A parametrisation of the dependence of the refractive index on wavelength based on the salinity, pressure and temperature of the sea water at the ANTARES site is in good agreement with these measurements. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino telescope; Optical beacon system; Velocity of light; Refractive index

Measurement of the high-energy all-flavor neutrino-nucleon cross section with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Ansseau,; et al. (Physical Review D, 2021)
The flux of high-energy neutrinos passing through the Earth is attenuated due to their interactions with matter. The interaction rate is determined by the neutrino interaction cross section and affects the flux arriving at the IceCube Neutrino Observatory, a cubic-kilometer neutrino detector embedded in the Antarctic ice sheet. We present a measurement of the neutrino cross section between 60 TeV and 10 PeV using the high-energy starting event (HESE) sample from IceCube with 7.5 years of data. The result is binned in neutrino energy and obtained using both Bayesian and frequentist statistics. We find it compatible with predictions from the Standard Model. While the cross section is expected to be flavor independent above 1 TeV, additional constraints on the measurement are included through updated experimental particle identification (PID) classifiers, proxies for the three neutrino flavors. This is the first such measurement to use a ternary PID observable and the first to account for neutrinos from tau decay.
CRIS-Team WoS Importer:2021-07-23

Measurement of the J / ψ production cross section in 920 GeV / c fixed-target proton-nucleus interactions - van Eldik, Christopher; et al. (Physics Letters B, 2006)
The mid-rapidity (d σ / d y at y = 0) and total (σ ) production cross sections of Jψ mesons are measured in proton-nucleus interactions. Data collected by the HERA-B experiment in interactions of 920 GeV / c protons with carbon, titanium and tungsten targets are used for this analysis. The Jψ mesons are reconstructed by their decay into lepton pairs. The total production cross section obtained is σ = 663 ± 74 ± 46 nb / nucleon. In addition, our result is compared with previous measurements. © 2006 Elsevier B.V. All rights reserved.
Keywords: Decays of J/psi Upsilon and other quarkonia; Inclusive production with identified hadrons; Quarks gluons and QCD in nuclei and nuclear processes

Measurement of the Υhooked production cross section in 920 GeV fixed-target proton-nucleus collisions - van Eldik, Christopher; et al. (Physics Letters B, 2006)
The cross section ratio R = Br (Υhooked → l l ) ṡ d σ (Υhooked) / d y | / σ (J / ψ) has been measured with the HERA-B spectrometer in fixed-target proton-nucleus collisions at 920 GeV proton beam energy corresponding to a proton-nucleon c.m.s. energy of sqrt(s) = 41.6 GeV. The combined results for the decay channels Υhooked → e e and Υhooked → μ μ yield a ratio R = (9.0 ± 2.1) × 10 . The corresponding Υhooked production cross section per nucleon at mid-rapidity (y = 0) has been determined to be Br (Υhooked → l l ) ṡ d σ (Υhooked) / d y | = 4.5 ± 1.1 pb / nucleon. © 2006 Elsevier B.V. All rights reserved.
Keywords: Υhooked mesons; Cross section; Proton-nucleus collisions; sqrt(s) = 41.6 GeV

Measurements using the inelasticity distribution of multi-TeV neutrino interactions in IceCube - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Ahrens, M.; Al Samarai, I.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; et al. (Physical Review D, 2019)
Inelasticity, the fraction of a neutrino's energy transferred to hadrons, is a quantity of interest in the study of astrophysical and atmospheric neutrino interactions at multi-TeV energies with IceCube. In this work, a sample of contained neutrino interactions in IceCube is obtained from five years of data and classified as 2650 tracks and 965 cascades. Tracks arise predominantly from charged-current nu(mu) interactions, and we demonstrate that we can reconstruct their energy and inelasticity. The inelasticity distribution is found to be consistent with the calculation of Cooper-Sarkar et al. across the energy range from similar to 1 to similar to 100 TeV. Along with cascades from neutrinos of all flavors, we also perform a fit over the energy, zenith angle, and inelasticity distribution to characterize the flux of astrophysical and atmospheric neutrinos. The energy spectrum of diffuse astrophysical neutrinos is described well by a power law in both track and cascade samples, and a best-fit index gamma = 2.62 +/- 0.07 is found in the energy range from 3.5 TeV to 2.6 PeV. Limits are set on the astrophysical flavor composition and are compatible with a ratio of (1/3 : 1/3 : 1/3)(circle plus). Exploiting the distinct inelasticity distribution of nu(mu) and (nu) over bar (mu) interactions, the atmospheric nu(mu) to (nu) over bar (mu) flux ratio in the energy range from 770 GeV to 21 TeV is found to be 0.77(-0.25)(+0.44) times the calculation by Honda et al. Lastly, the inelasticity distribution is also sensitive to neutrino charged-current charm production. The data are consistent with a leading-order calculation, with zero charm production excluded at 91% confidence level. Future analyses of inelasticity distributions may probe new physics that affects neutrino interactions both in and beyond the Standard Model.
CRIS-Team WoS Importer:2019-02-27

Measuring the atmospheric neutrino oscillation parameters and constraining the 3+1 neutrino model with ten years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Physics, 2019)
The ANTARES neutrino telescope has an energy threshold of a few tens of GeV. This allows to study the phenomenon of atmospheric muon neutrino disappearance due to neutrino oscillations. In a similar way, constraints on the 3+1 neutrino model, which foresees the existence of one sterile neutrino, can be inferred. Using data collected by the ANTARES neutrino telescope from 2007 to 2016, a new measurement of Δm322 and θ23 has been performed — which is consistent with world best-fit values — and constraints on the 3+1 neutrino model have been derived.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-07-02
Keywords: Neutrino Detectors and Telescopes (experiments); Oscillation

Measuring the neutrino mass hierarchy with KM3NeT/ORCA - Hofestädt, Jannik (Journal of Physics: Conference Series, 2020)
ORCA is the low-energy branch of KM3NeT, the next-generation research infrastructure hosting underwater Cherenkov detectors in the Mediterranean Sea. ORCA's primary goal is the determination of the neutrino mass hierarchy by measuring the matter-induced modifications on the oscillation probabilities of few-GeV atmospheric neutrinos. The technical design of the ORCA detector foresees a dense configuration of optical modules, optimised for the study of interactions of neutrinos in the energy range of 3-30 GeV. The first ORCA detection string was successfully deployed on 22nd September 2017 and is providing high-quality data since then. With an instrumented mass of 8 Mton for the full-size ORCA detector, it will be possible to probe with a high-statistics neutrino sample a wide range of energies and baselines through the Earth. This allows to detmerine the neutrino mass hierarchy with 3 σ after 3-4 years of operation, to probe the unitarity assumption of 3-neutrino mixing with a high-statistics measurement of tau-neutrino appearance in the atmospheric neutrino flux, and to improve the measurement precision on other oscillation parameters.
CRIS-Team Scopus Importer:2020-02-18

Measuring the polarization reconstruction resolution of the ARIANNA neutrino detector with cosmic rays - Anker, A.; Baldi, P.; Barwick, S. W.; Beise, J.; Besson, D. Z.; Bouma, Sjoerd; Cataldo, Maddalena; Chen, P.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hallmann, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2022)
The ARIANNA detector is designed to detect neutrinos with energies above 1017 eV. Due to the similarities in generated radio signals, cosmic rays are often used as test beams for neutrino detectors. Some ARIANNA detector stations are equipped with antennas capable of detecting air showers. Since the radio emission properties of air showers are well understood, and the polarization of the radio signal can be predicted from the arrival direction, cosmic rays can be used as a proxy to assess the reconstruction capabilities of the ARIANNA neutrino detector. We report on dedicated efforts of reconstructing the polarization of cosmic-ray radio pulses. After correcting for difference in hardware, the two stations used in this study showed similar performance in terms of event rate and agreed with simulation. Subselecting high quality cosmic rays, the polarizations of these cosmic rays were reconstructed with a resolution of 2.5° (68% containment), which agrees with the expected value obtained from simulation. A large fraction of this resolution originates from uncertainties in the predicted polarization because of the contribution of the subdominant Askaryan effect in addition to the dominant geomagnetic emission. Subselecting events with a zenith angle greater than 70° removes most influence of the Askaryan emission, and, with limited statistics, we found the polarization uncertainty is reduced to 1.3° (68% containment).
CRIS-Team Scopus Importer:2022-05-13
Keywords: cosmological neutrinos; neutrino astronomy; neutrino detectors; ultra high energy photons and neutrinos

Meeting the challenge of Open Science in KM3NeT - Schnabel, Jutta; Kalaczyński, P.; Bozza, C.; Gál, Tamás (Journal of Instrumentation, 2021)
In the upcoming decades, the KM3NeT detectors will produce valuable data that can be used in various scientific contexts, from astro- and particle physics to environmental and Earth and Sea science. Based on the Open Science policy established by the KM3NeT Collaboration, several efforts to offer science-ready data, foster common analysis approaches and publish open source software are currently pursued. In this contribution, ongoing projects focusing on the exchange of high-level data and simulation derivatives and establishment of an integrated computing environment supporting an open-science focused workflow will be discussed.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Data analysis; Neutrino detectors; Software architectures (event data models; frameworks and databases)

Microplastics in the abyss: a first investigation into sediments at 2443-m depth (Toulon, France) - Domi, Alba; et al. (Environmental Science and Pollution Research, 2022)
Keywords: KM3NeT project; Microplastics; Deep sea; µRaman; Sea currents; Toulon (France)

Model-independent search for neutrino sources with the ANTARES neutrino telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Astroparticle Physics, 2020)
A novel method to analyse the spatial distribution of neutrino candidates recorded with the ANTARES neutrino telescope is introduced, searching for an excess of neutrinos in a region of arbitrary size and shape from any direction in the sky. Techniques originating from the domains of machine learning, pattern recognition and image processing are used to purify the sample of neutrino candidates and for the analysis of the obtained skymap. In contrast to a dedicated search for a specific neutrino emission model, this approach is sensitive to a wide range of possible morphologies of potential sources of high-energy neutrino emission. The application of these methods to ANTARES data yields a large-scale excess with a post-trial significance of 2.5σ. Applied to public data from IceCube in its IC40 configuration, an excess consistent with the results from ANTARES is observed with a post-trial significance of 2.1σ.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Anisotropy; Astroparticle physics; Neutrino astronomy; Pattern recognition

Monte Carlo simulations for the ANTARES underwater neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
Monte Carlo simulations are a unique tool to check the response of a detector and to monitor its performance. For a deep-sea neutrino telescope, the variability of the environmental conditions that can affect the behaviour of the data acquisition system must be considered, in addition to a reliable description of the active parts of the detector and of the features of physics events, in order to produce a realistic set of simulated events. In this paper, the software tools used to produce neutrino and cosmic ray signatures in the telescope and the strategy developed to represent the time evolution of the natural environment and of the detector efficiency are described.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Cosmic ray experiments; Neutrino astronomy; Neutrino detectors; Neutrino experiments

Monte Carlo studies for the optimisation of the Cherenkov Telescope Array layout - Acharyya, A.; Agudo, I.; Angüner, E. O.; Alfaro, R.; Alfaro, J.; Alispach, C.; Aloisio, R.; Alves Batista, R.; Amans, J. P.; Amati, L.; Amato, E.; Ambrosi, G.; et al. (Astroparticle Physics, 2019)
The Cherenkov Telescope Array (CTA) is the major next-generation observatory for ground-based very-high-energy gamma-ray astronomy. It will improve the sensitivity of current ground-based instruments by a factor of five to twenty, depending on the energy, greatly improving both their angular and energy resolutions over four decades in energy (from 20 GeV to 300 TeV). This achievement will be possible by using tens of imaging Cherenkov telescopes of three successive sizes. They will be arranged into two arrays, one per hemisphere, located on the La Palma island (Spain) and in Paranal (Chile). We present here the optimised and final telescope arrays for both CTA sites, as well as their foreseen performance, resulting from the analysis of three different large-scale Monte Carlo productions.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cherenkov telescopes; Cosmic rays; Gamma rays; IACT technique; Monte Carlo simulations

Multimessenger gamma-ray and neutrino coincidence alerts using hawc and icecube subthreshold data - Solares, H. A.Ayala; Coutu, S.; DeLaunay, J. J.; Fox, D. B.; Grégoire, T.; Keivani, A.; Krauß, F.; Mostafá, M.; Murase, K.; Turley, C. F.; Albert, A.; Alfaro, R.; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cerenkov (HAWC) and IceCube observatories, through the Astrophysical Multimessenger Observatory Network (AMON) framework, have developed a multimessenger joint search for extragalactic astrophysical sources. This analysis looks for sources that emit both cosmic neutrinos and gamma rays that are produced in photohadronic or hadronic interactions. The AMON system is running continuously, receiving subthreshold data (i.e., data that are not suited on their own to do astrophysical searches) from HAWC and IceCube, and combining them in real time. Here we present the analysis algorithm, as well as results from archival data collected between 2015 June and 2018 August, with a total live time of 3.0 yr. During this period we found two coincident events that have a false-alarm rate (FAR) of <1 coincidence yr-1, consistent with the background expectations. The real-time implementation of the analysis in the AMON system began on 2019 November 20 and issues alerts to the community through the Gamma-ray Coordinates Network with an FAR threshold of <4 coincidences yr-1.
CRIS-Team Scopus Importer:2021-01-22

Multi-messenger Observations of a Binary Neutron Star Merger - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, Paolo; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; Afrough, M.; et al. (Astrophysical Journal Letters, 2017)
On 2017 August 17 a binary neutron star coalescence candidate (later designated GW170817) with merger time 12:41:04 UTC was observed through gravitational waves by the Advanced LIGO and Advanced Virgo detectors. The Fermi Gamma-ray Burst Monitor independently detected a gamma-ray burst (GRB 170817A) with a time delay of similar to 1.7 s with respect to the merger time. From the gravitational-wave signal, the source was initially localized to a sky region of 31 deg(2) at a luminosity distance of 40(-8)(+8) Mpc and with component masses consistent with neutron stars. The component masses were later measured to be in the range 0.86 to 2.26 M-circle dot. An extensive observing campaign was launched across the electromagnetic spectrum leading to the discovery of a bright optical transient (SSS17a, now with the IAU identification of AT 2017gfo) in NGC 4993 (at similar to 40 Mpc) less than 11 hours after the merger by the One-Meter, Two Hemisphere (1M2H) team using the 1 m Swope Telescope. The optical transient was independently detected by multiple teams within an hour. Subsequent observations targeted the object and its environment. Early ultraviolet observations revealed a blue transient that faded within 48 hours. Optical and infrared observations showed a redward evolution over similar to 10 days. Following early non-detections, X-ray and radio emission were discovered at the transient's position similar to 9 and similar to 16 days, respectively, after the merger. Both the X-ray and radio emission likely arise from a physical process that is distinct from the one that generates the UV/optical/near-infrared emission. No ultra-high-energy gamma-rays and no neutrino candidates consistent with the source were found in follow-up searches. These observations support the hypothesis that GW170817 was produced by the merger of two neutron stars in NGC4993 followed by a short gamma-ray burst (GRB 170817A) and a kilonova/macronova powered by the radioactive decay of r-process nuclei synthesized in the ejecta.
Keywords: gravitational waves; stars: neutron

Multi-wavelength observations of H 2356-309 - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2010)
Aims. The properties of the broad-band emission from the high-frequency peaked BL Lac H 2356-309 (z = 0.165) are investigated. Methods. Very high energy (VHE; E > 100 GeV) observations of H 2356-309 were performed with the High Energy Stereoscopic System (HESS) from 2004 through 2007. Simultaneous optical/UV and X-ray observations were made with the XMM-Newton satellite on June 12/13 and June 14/15, 2005. NRT radio observations were also contemporaneously performed in 2005. ATOM optical monitoring observations were also made in 2007. Results. A strong VHE signal, ∼13σ total, was detected by HESS after the four years HESS observations (116.8 h live time). The integral flux above 240 GeV is I(>240 GeV) = (3.06 ± 0.26 ± 0.61) × 10 cm s, corresponding to ∼1.6% of the flux observed from the Crab Nebula. A time-averaged energy spectrum is measured from 200 GeV to 2 TeV and is characterized by a power law (photon index of Γ = 3.06 ± 0.15 ± 0.10). Significant small-amplitude variations in the VHE flux from H 2356-309 are seen on time scales of months and years, but not on shorter time scales. No evidence for any variations in the VHE spectral slope are found within these data. The XMM-Newton X-ray measurements show a historically low X-ray state, characterized by a hard, broken-power-law spectrum on both nights. Conclusions. The broad-band spectral energy distribution (SED) of the blazar can be adequately fit using a simple one-zone synchrotron self-Compton (SSC) model. In the SSC scenario, higher VHE fluxes could be expected in the future since the observed X-ray flux is at a historically low level. © 2010 ESO.
Keywords: BL Lacertae objects: individual: H 2356-309; Galaxies: active; Gamma rays: galaxies

Muon Energy Reconstruction for the Neutrino Telescope ANTARES using Neural Networks - Schnabel, Jutta (2010)

Muon energy reconstruction in the ANTARES detector - Schnabel, Jutta (2013)

MURCHISON WIDEFIELD ARRAY LIMITS on RADIO EMISSION from ANTARES NEUTRINO EVENTS - Croft, Steve; Kaplan, D. L.; Tingay, S. J.; Murphy, Tara; Bell, M. E.; Rowlinson, Antonia; Adrian-Martinez, S.; Ageron, M.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; et al. (Astrophysical Journal Letters, 2016)
We present a search, using the Murchison Widefield Array (MWA), for electromagnetic (EM) counterparts to two candidate high-energy neutrino events detected by the ANTARES neutrino telescope in 2013 November and 2014 March. These events were selected by ANTARES because they are consistent, within 0°.4, with the locations of galaxies within 20 Mpc of Earth. Using MWA archival data at frequencies between 118 and 182 MHz, taken ∼20 days prior to, at the same time as, and up to a year after the neutrino triggers, we look for transient or strongly variable radio sources that are consistent with the neutrino positions. No such counterparts are detected, and we set a 5σ upper limit for low-frequency radio emission of ∼10 erg s for progenitors at 20 Mpc. If the neutrino sources are instead not in nearby galaxies, but originate in binary neutron star coalescences, our limits place the progenitors at z 0.2. While it is possible, due to the high background from atmospheric neutrinos, that neither event is astrophysical, the MWA observations are nevertheless among the first to follow up neutrino candidates in the radio, and illustrate the promise of wide-field instruments like MWA for detecting EM counterparts to such events.
Keywords: neutrinos; radio continuum: general

Nanobeacon: A time calibration device for the KM3NeT neutrino telescope - Aiello, S.; Domi, Alba; Albert, A.; Alshamsi, M.; Garre, S. Alves; Aly, Z.; Ambrosone, A.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2022)
The KM3NeT Collaboration is currently constructing a multi-site high-energy neutrino telescope in the Mediterranean Sea consisting of matrices of pressure-resistant glass spheres, each holding a set of 31 small-area photomultipliers. The main goals of the telescope are the observation of neutrino sources in the Universe and the measurement of the neutrino oscillation parameters with atmospheric neutrinos. A relative time synchronisation between photomultipliers of the nanosecond order needed to guarantee the required angular resolution of the detector. Due to the large detector volumes to be instrumented by KM3NeT, a cost reduction of the different systems is a priority. To this end, the inexpensive Nanobeacon has been designed and developed by the KM3NeT Collaboration to be used for detector time-calibration studies. At present, more than 600 Nanobeacons have been already produced. The characterisation of the optical pulse and the wavelength emission profile of the devices is critical for the time calibration. The optical pulse rise time has been quantified as less than 3 ns, while the Full Width Half Maximum is less than 6 ns. The wavelength drift, due to a variation of the supply voltage, has also been qualified as lower than 10 nm for the full range of the Nanobeacon. In this paper, more details about the main features of the Nanobeacon design, production and operation, together with the main properties of the light pulse generated are described.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Instrumentation; Neutrino telescopes; Time calibration

Neutrino astrophysics with the ANTARES Cherenkov detector - Schnabel, Jutta (2013)

Neutrinos below 100 TeV from the southern sky employing refined veto techniques to IceCube data - Aartsen, M. G.; Ackermann, M.; Adams, J.; A. Aguilar, J.; Ahlers, M.; Ahrens, M.; Alispach, C.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; et al. (Astroparticle Physics, 2020)
Many Galactic sources of gamma rays, such as supernova remnants, are expected to produce neutrinos with a typical energy cutoff well below 100 TeV. For the IceCube Neutrino Observatory located at the South Pole, the southern sky, containing the inner part of the Galactic plane and the Galactic Center, is a particularly challenging region at these energies, because of the large background of atmospheric muons. In this paper, we present recent advancements in data selection strategies for track-like muon neutrino events with energies below 100 TeV from the southern sky. The strategies utilize the outer detector regions as veto and features of the signal pattern to reduce the background of atmospheric muons to a level which, for the first time, allows IceCube searching for point-like sources of neutrinos in the southern sky at energies between 100 GeV and several TeV in the muon neutrino charged current channel. No significant clustering of neutrinos above background expectation was observed in four years of data recorded with the completed IceCube detector. Upper limits on the neutrino flux for a number of spectral hypotheses are reported for a list of astrophysical objects in the southern hemisphere.
CRIS-Team Scopus Importer:2019-11-22
Keywords: Neutrinos; Point sources; Veto techniques

Neutrino vertex reconstruction with in-ice radio detectors using surface reflections and implications for the neutrino energy resolution - Anker, A.; Barwick, S. W.; Bernhoff, H.; Besson, D. Z.; Bingefors, N.; Garcia-Fernandez, D.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hanson, J. C.; Klein, S. R.; Kleinfelder, S. A.; et al. (Journal of Cosmology and Astroparticle Physics, 2019)

New constraints on all flavor Galactic diffuse neutrino emission with the ANTARES telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The flux of very high-energy neutrinos produced in our Galaxy by the interaction of accelerated cosmic rays with the interstellar medium is not yet determined. The characterization of this flux will shed light on Galactic accelerator features, gas distribution morphology and Galactic cosmic ray transport. The central Galactic plane can be the site of an enhanced neutrino production, thus leading to anisotropies in the extraterrestrial neutrino signal as measured by the IceCube Collaboration. The ANTARES neutrino telescope, located in the Mediterranean Sea, offers a favorable view of this part of the sky, thereby allowing for a contribution to the determination of this flux. The expected diffuse Galactic neutrino emission can be obtained, linking a model of generation and propagation of cosmic rays with the morphology of the gas distribution in the Milky Way. In this paper, the so-called "gamma model" introduced recently to explain the high-energy gamma-ray diffuse Galactic emission is assumed as reference. The neutrino flux predicted by the "gamma model" depends on the assumed primary cosmic ray spectrum cutoff. Considering a radially dependent diffusion coefficient, this proposed scenario is able to account for the local cosmic ray measurements, as well as for the Galactic gamma-ray observations. Nine years of ANTARES data are used in this work to search for a possible Galactic contribution according to this scenario. All flavor neutrino interactions are considered. No excess of events is observed, and an upper limit is set on the neutrino flux of 1.1 (1.2) times the prediction of the "gamma model," assuming the primary cosmic ray spectrum cutoff at 5 (50) PeV. This limit excludes the diffuse Galactic neutrino emission as the major cause of the "spectral anomaly" between the two hemispheres measured by IceCube.

New constraints on the mid-IR EBL from the HESS discovery of VHE γ-rays from 1ES 0229+200 - van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2007)
Aims. To investigate the very high energy (VHE: > 100 GeV) y-ray emission from the high-frequency peaked BL Lac IES 0229+200. Methods. Observations of IES 0229+200 at energies above 580 GeV were performed with the High Energy Stereoscopic System (HESS) in 2005 and 2006. Results. IES 0229+200 is discovered by HESS to be an emitter of VHE photons. A signal is detected at the 6.6σ level in the HESS observations (41.8 h live time). The integral flux above 580 GeV is (9.4 ± 1.5 ± 1.9 ) × 10 cm s corresponding to ∼1.8% of the flux observed from the Crab Nebula. The data show no evidence for significant variability on any time scale. The observed spectrum is characterized by a hard power law (T = 2.50 ± 0.19 ± 0.10 ) from 500 GeV to ∼15 TeV. Conclusions. The high-energy range and hardness of the observed spectrum, coupled with the object's relatively large redshift (z = 0.1396), enable the strongest constraints so far on the density of the Extragalactic Background Light (EBL) in the mid-infrared band. Assuming that the emitted spectrum is not harder than T ≈ 1.5, the HESS data support an EBL spectrum σλ and density close to the lower limit from source counts measured by Spitzer, confirming the previous indications from the HEGRA data of IES 1426+428 (z = 0.129). Irrespective of the EBL models used, the intrinsic spectrum of IES 0229+200 is hard, thus locating the high-energy peak of its spectral energy distribution above a few TeV. © ESO 2007.
Keywords: BL lacertae objects: individual: IES 0229+200; Galaxies; Gamma rays: observations

New Flux Limits in the Low Relativistic Regime for Magnetic Monopoles at IceCube - Lauber, Frederik Hermann; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
Magnetic monopoles are hypothetical particles that carry magnetic charge. Depending on their velocity, different light production mechanisms exist to facilitate detection. In this work, a previously unused light production mechanism, luminescence of ice, is introduced. This light production mechanism is nearly independent of the velocity of the incident magnetic monopole and becomes the only viable light production mechanism in the low relativistic regime (0.1-0.55c). An analysis in the low relativistic regime searching for magnetic monopoles in seven years of IceCube data is presented. While no magnetic monopole detection can be claimed, a new flux limit in the low relativistic regime is presented, superseding the previous best flux limit by 2 orders of magnitude.
CRIS-Team Scopus Importer:2022-12-23

Non-standard neutrino interactions in IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Proceedings of Science, 2022)
Non-standard neutrino interactions (NSI) may arise in various types of new physics. Their existence would change the potential that atmospheric neutrinos encounter when traversing Earth matter and hence alter their oscillation behavior. This imprint on coherent neutrino forward scattering can be probed using high-statistics neutrino experiments such as IceCube and its low-energy extension, DeepCore. Both provide extensive data samples that include all neutrino flavors, with oscillation baselines between tens of kilometers and the diameter of the Earth. DeepCore event energies reach from a few GeV up to the order of 100 GeV - which marks the lower threshold for higher energy IceCube atmospheric samples, ranging up to 10 TeV. In DeepCore data, the large sample size and energy range allow us to consider not only flavor-violating and flavor-nonuniversal NSI in the μ − τ sector, but also those involving electron flavor. The effective parameterization used in our analyses is independent of the underlying model and the new physics mass scale. In this way, competitive limits on several NSI parameters have been set in the past. The 8 years of data available now result in significantly improved sensitivities. This improvement stems not only from the increase in statistics but also from substantial improvement in the treatment of systematic uncertainties, background rejection and event reconstruction.
CRIS-Team Scopus Importer:2022-06-03

NuRadioMC: simulating the radio emission of neutrinos from interaction to detector - Glaser, C.; García-Fernández, D.; Nelles, Anna; Alvarez-Muñiz, J.; Barwick, S. W.; Besson, D. Z.; Clark, B. A.; Connolly, A.; Deaconu, C.; de Vries, K. D.; Hanson, J. C.; Hokanson-Fasig, B.; et al. (European Physical Journal C: Particles and Fields, 2020)
NuRadioMC is a Monte Carlo framework designed to simulate ultra-high energy neutrino detectors that rely on the radio detection method. This method exploits the radio emission generated in the electromagnetic component of a particle shower following a neutrino interaction. NuRadioMC simulates everything from the neutrino interaction in a medium, the subsequent Askaryan radio emission, the propagation of the radio signal to the detector and finally the detector response. NuRadioMC is designed as a modern, modular Python-based framework, combining flexibility in detector design with user-friendliness. It includes a state-of-the-art event generator, an improved modelling of the radio emission, a revisited approach to signal propagation and increased flexibility and precision in the detector simulation. This paper focuses on the implemented physics processes and their implications for detector design. A variety of models and parameterizations for the radio emission of neutrino-induced showers are compared and reviewed. Comprehensive examples are used to discuss the capabilities of the code and different aspects of instrumental design decisions.
CRIS-Team Scopus Importer:2020-02-11

NuRadioMC - Simulation Code for the Next Generation of Radio Neutrino Detectors - García-Fernández, D.; Glaser, C.; Nelles, Anna; Alvarez-Muñiz, J.; Barwick, S.; Besson, D. Z.; Buitink, S.; Clark, B. A.; Connolly, A.; Deaconu, C.; de Vries, K.; Hanson, J.; et al. (Proceedings of Science, 2021)
The detection of astrophysical neutrinos by IceCube has opened a new window for the observation of our universe. The use of antennas for detecting astroparticles has been proven useful and accurate after many years of radio cosmic-ray detections, and will be a valuable asset for increasing the statistics for the detection of neutrinos < 10 PeV and reaching out to the highest energies. The radio technique requires realistic and precise simulations of the electric field created after the neutrino interacts with the detector volume, how it propagates through media, and what measurable signal it produces in the detector. With the goal of providing accurate, fast simulations of neutrino-induced electric fields, we have created the NuRadioMC code. It builds on the experience of software used for current radio neutrino and cosmic ray experiments.
CRIS-Team Scopus Importer:2023-08-15

NuRadioReco: a reconstruction framework for radio neutrino detectors - Glaser, Christian; Nelles, Anna; Plaisier, Ilse; Welling, Christoph; Barwick, Steven W.; Garcia-Fernandez, Daniel; Gaswint, Geoffrey; Lahmann, Robert; Persichilli, Christopher (European Physical Journal C: Particles and Fields, 2019)
While the radio detection of cosmic rays has advanced to a standard method in astroparticle physics, the radio detection of neutrinos is just about to start its full bloom. The successes of pilot-arrays have to be accompanied by the development of modern and flexible software tools to ensure rapid progress in reconstruction algorithms and data processing. We present NuRadioReco as such a modern Python-based data analysis tool. It includes a suitable data-structure, a database-implementation of a time-dependent detector, modern browser-based data visualization tools, and fully separated analysis modules. We describe the framework and examples, as well as new reconstruction algorithms to obtain the full three-dimensional electric field from distributed antennas which is needed for high-precision energy reconstruction of particle showers.
CRIS-Team Scopus Importer:2019-06-18

Observation of classically 'forbidden' electromagnetic wave propagation and implications for neutrino detection. - Barwick, S. W.; Berg, E. C.; Besson, D. Z.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hanson, J. C.; Klein, S. R.; Kleinfelder, S.; Köpke, L.; Kravchenko, I.; Lahmann, Robert; et al. (Journal of Cosmology and Astroparticle Physics, 2018)
Ongoing experimental efforts in Antarctica seek to detect ultra-high energy neutrinos by measurement of radio-frequency (RF) Askaryan radiation generated by the collision of a neutrino with an ice molecule. An array of RF antennas, deployed either in-ice or in-air, is used to infer the properties of the neutrino. To evaluate their experimental sensitivity, such experiments require a refractive index model for ray tracing radio-wave trajectories from a putative in-ice neutrino interaction point to the receiving antennas; this gives the degree of signal absorption or ray bending from source to receiver. The gradient in the density profile over the upper 200 meters of Antarctic ice, coupled with Fermat's least-time principle, implies ray "bending" and the existence of "forbidden" zones for predominantly horizontal signal propagation at shallow depths. After re-deriving the formulas describing such shadowing, we report on experimental results that, somewhat unexpectedly, demonstrate the existence of electromagnetic wave transport modes from nominally shadowed regions. The fact that this shadow-signal propagation is observed both at South Pole and the Ross Ice Shelf in Antarctica suggests that the effect may be a generic property of polar ice, with potentially important implications for experiments seeking to detect neutrinos.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Cosmic ray experiments; ultra high energy photons and neutrinos

Observation of high-energy neutrinos from the Galactic plane - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Science, 2023)
The origin of high-energy cosmic rays, atomic nuclei that continuously impact Earth's atmosphere, is unknown. Because of deflection by interstellar magnetic fields, cosmic rays produced within the Milky Way arrive at Earth from random directions. However, cosmic rays interact with matter near their sources and during propagation, which produces high-energy neutrinos. We searched for neutrino emission using machine learning techniques applied to 10 years of data from the IceCube Neutrino Observatory. By comparing diffuse emission models to a background-only hypothesis, we identified neutrino emission from the Galactic plane at the 4.5σ level of significance. The signal is consistent with diffuse emission of neutrinos from the Milky Way but could also arise from a population of unresolved point sources.
CRIS-Team Scopus Importer:2023-07-21

Observation of seasonal variations of the flux of high-energy atmospheric neutrinos with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; et al. (European Physical Journal C: Particles and Fields, 2023)
Atmospheric muon neutrinos are produced by meson decays in cosmic-ray-induced air showers. The flux depends on meteorological quantities such as the air temperature, which affects the density of air. Competition between decay and re-interaction of those mesons in the first particle production generations gives rise to a higher neutrino flux when the air density in the stratosphere is lower, corresponding to a higher temperature. A measurement of a temperature dependence of the atmospheric νμ flux provides a novel method for constraining hadronic interaction models of air showers. It is particularly sensitive to the production of kaons. Studying this temperature dependence for the first time requires a large sample of high-energy neutrinos as well as a detailed understanding of atmospheric properties. We report the significant (>10σ) observation of a correlation between the rate of more than 260,000 neutrinos, detected by IceCube between 2012 and 2018, and atmospheric temperatures of the stratosphere, measured by the Atmospheric Infrared Sounder (AIRS) instrument aboard NASA’s AQUA satellite. For the observed 10 % seasonal change of effective atmospheric temperature we measure a 3.5(3) % change in the muon neutrino flux. This observed correlation deviates by about 2-3 standard deviations from the expected correlation of 4.3 % as obtained from theoretical predictions under the assumption of various hadronic interaction models.
CRIS-Team Scopus Importer:2023-09-15

Observation of the cosmic ray shadow of the Sun with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, S.; et al. (Physical Review D, 2020)
The ANTARES detector is an undersea neutrino telescope in the Mediterranean Sea. The search for pointlike neutrino sources is one of the main goals of the ANTARES telescope, requiring a reliable method to evaluate the detector angular resolution and pointing accuracy. This work describes the study of the Sun "shadow" effect with the ANTARES detector. The shadow is the deficit in the atmospheric muon flux in the direction of the Sun caused by the absorption of the primary cosmic rays. This analysis is based on the data collected between 2008 and 2017 by the ANTARES telescope. The observed statistical significance of the Sun shadow detection is 3.7 sigma, with an estimated angular resolution of 0.59 degrees +/- 0.10 degrees for downward-going muons. The pointing accuracy is found to be consistent with the expectations and no evidence of systematic pointing shifts is observed.
CRIS-Team WoS Importer:2021-01-15

Observations of the Crab nebula with H.E.S.S. - van Eldik, Christopher; et al. (29th International Cosmic Ray Conference, ICRC 2005, 2005)
The H.E.S.S. stereoscopic Cherenkov telescope system observed the Crab nebula in January-February and October-November 2004 with the complete four telescope array. The data, taken at large zenith angles, show a clear signal with a significance in excess of 100 standard deviations and serve to verify the performance and calibration of the instrument. The energy spectrum of γ -ray emission from the Crab nebula is measured and is found to follow a straight power law, given by dN/dE =2.86±0.06(stat)±0.57(say.) X 10 E±0.03(stat)±0.1(say.)cm sTeV between 440 GeV and 10 TeV. The position of the source is fitted and compared with X-ray observations.

Observations of the Crab nebula with HESS - van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2006)
Context. The Crab nebula was observed with the HESS stereoscopic Cherenkov-telescope array between October 2003 and January 2005 for a total of 22.9 h (after data quality selection). This period of time partly overlapped with the commissioning phase of the experiment; observations were made with three operational telescopes in late 2003 and with the complete 4 telescope array in January-February 2004 and October 2004-January 2005. Aims. Observations of the Crab nebula are discussed and used as an example to detail the flux and spectral analysis procedures of HESS. The results are used to evaluate the systematic uncertainties in HESS flux measurements. Methods. The Crab nebula data are analysed using standard HESS analysis procedures, which are described in detail. The flux and spectrum of γ-rays from the source are calculated on run-by-run and monthly time-scales, and a correction is applied for long-term variations in the detector sensitivity. Comparisons of the measured flux and spectrum over the observation period, along with the results from a number of different analysis procedures are used to estimate systematic uncertainties in the measurements. Results. The data, taken at a range of zenith angles between 45° and 65°, show a clear signal with over 7500 excess events. The energy spectrum is found to follow a power law with an exponential cutoff, with photon index Γ = 2.39 ± 0.03 and cutoff energy E = (14.3 ± 2.1 ) TeV between 440 GeV and 40 TeV. The observed integral flux above 1 TeV is (2.26 ± 0.08 ) × 10 cm s . The estimated systematic error on the flux measurement is estimated to be 20%, while the estimated systematic error on the spectral slope is 0.1. © ESO 2006.
Keywords: Gamma rays: observations; ISM: individual objects: Crab nebula; ISM: supernova remnants

Observations of the Crab Nebula with H.E.S.S. Phase II - Holler, M.; Berge, D.; van Eldik, Christopher; Lenain, J. P.; Marandon, V.; Murach, T.; De Naurois, M.; Parsons, R. D.; Prokoph, H.; Zaborov, D. (34th International Cosmic Ray Conference (ICRC2015), 2015)
The High Energy Stereoscopic System (H.E.S.S.) phase I instrument was an array of four 100m2 mirror area Imaging Atmospheric Cherenkov Telescopes (IACTs) that has very successfully mapped the sky at photon energies above 100GeV. Recently, a 600m2 telescope was added to the centre of the existing array, which can be operated either in standalone mode or jointly with the four smaller telescopes. The large telescope lowers the energy threshold for gamma-ray observations to several tens of GeV, making the array sensitive at energies where the Fermi-LAT instrument runs out of statistics. At the same time, the new telescope makes the H.E.S.S. phase II instrument. This is the first hybrid IACT array, as it operates telescopes of different size (and hence different trigger rates) and different field of view. In this contribution we present results of H.E.S.S. phase II observations of the Crab Nebula, compare them to earlier observations, and evaluate the performance of the new instrument with Monte Carlo simulations.

Observations of the Sagittarius dwarf galaxy by the HESS experiment and search for a dark matter signal - Aharonian, F.; Akhperjanian, A. G.; Bazer-Bachi, A. R.; Beilicke, M.; Benbow, W.; Berge, David; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; Brion, E.; et al. (Astroparticle Physics, 2008)
Observations of the Sagittarius dwarf spheroidal (Sgr dSph) galaxy were carried out with the HESS array of four imaging air Cherenkov telescopes in June 2006. A total of 11 h of high quality data are available after data selection. There is no evidence for a very high energy γ-ray signal above the energy threshold at the target position. A 95% CL flux limit of 3.6 × 10 cm s above 250 GeV has been derived. Constraints on the velocity-weighted cross-section 〈 σ v 〉 are calculated in the framework of dark matter particle annihilation using realistic models for the dark matter halo profile of Sagittarius dwarf galaxy. Two different models have been investigated encompassing a large class of halo types. A 95% CL exclusion limit on 〈 σ v 〉 of the order of 2 × 10 cm s is obtained for a core profile in the 100 GeV-1 TeV neutralino mass range. © 2007 Elsevier B.V. All rights reserved.
Keywords: Dark matter; Dwarf spheroidal galaxy; Gamma-rays: observations

Open Science in KM3NeT - Schnabel, Jutta (2024)

Optical and X-ray early follow-up of ANTARES neutrino alerts - Adrian-Martinez, S.; Ageron, M.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
High-energy neutrinos could be produced in the interaction of charged cosmic rays with matter or radiation surrounding astrophysical sources. Even with the recent detection of extraterrestrial high-energy neutrinos by the IceCube experiment, no astrophysical neutrino source has yet been discovered. Transient sources, such as gamma-ray bursts, core-collapse supernovae, or active galactic nuclei are promising candidates. Multi-messenger programs offer a unique opportunity to detect these transient sources. By combining the information provided by the ANTARES neutrino telescope with information coming from other observatories, the probability of detecting a source is enhanced, allowing the possibility of identifying a neutrino progenitor from a single detected event. A method based on optical and X-ray follow-ups of high-energy neutrino alerts has been developed within the ANTARES collaboration. This method does not require any assumptions on the relation between neutrino and photon spectra other than time-correlation. This program, denoted as TAToO, triggers a network of robotic optical telescopes (TAROT and ROTSE) and the Swift-XRT with a delay of only a few seconds after a neutrino detection, and is therefore well-suited to search for fast transient sources. To identify an optical or X-ray counterpart to a neutrino signal, the images provided by the follow-up observations are analysed with dedicated pipelines. A total of 42 alerts with optical and 7 alerts with X-ray images taken with a maximum delay of 24 hours after the neutrino trigger have been analysed. No optical or X-ray counterparts associated to the neutrino triggers have been found, and upper limits on transient source magnitudes have been derived. The probability to reject the gamma-ray burst origin hypothesis has been computed for each alert.

Optimization of the optical array geometry for IceCube-Gen2 - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
IceCube-Gen2 is a planned extension of the IceCube Neutrino Observatory at the South Pole designed to study the high-energy neutrino sky from TeV to EeV energies with a five times better point source sensitivity than the current IceCube detector. This is achieved by deploying 120 new strings with attached optical sensors in a pattern around IceCube that features considerably larger distances between individual strings than the ∼125 m for the existing detector. Here, we present the results of an optimization study searching for the best point source sensitivity while varying the IceCube-Gen2 string spacing between 150 m and 350 m.
CRIS-Team Scopus Importer:2023-08-15

Particle transport within the pulsar wind nebula HESS J1825-137 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2019)
Context. We present a detailed view of the pulsar wind nebula (PWN) HESS J1825-137. We aim to constrain the mechanisms dominating the particle transport within the nebula, accounting for its anomalously large size and spectral characteristics. Aims. The nebula was studied using a deep exposure from over 12 years of H.E.S.S. I operation, together with data from H.E.S.S. II that improve the low-energy sensitivity. Enhanced energy-dependent morphological and spatially resolved spectral analyses probe the very high energy (VHE, E > 0.1 TeV) γ-ray properties of the nebula. Methods. The nebula emission is revealed to extend out to 1.5° from the pulsar, ∼1.5 times farther than previously seen, making HESS J1825-137, with an intrinsic diameter of ∼100 pc, potentially the largest γ-ray PWN currently known. Characterising the strongly energy-dependent morphology of the nebula enables us to constrain the particle transport mechanisms. A dependence of the nebula extent with energy of RE α with α = -0.29 ± 0.04 stat ± 0.05 sys disfavours a pure diffusion scenario for particle transport within the nebula. The total γ-ray flux of the nebula above 1 TeV is found to be (1.12 ± 0.03 stat ± 0.25 sys ) × 10 -11 cm -2 s -1 , corresponding to ∼64% of the flux of the Crab nebula. Results. HESS J1825-137 is a PWN with clearly energy-dependent morphology at VHE γ-ray energies. This source is used as a laboratory to investigate particle transport within intermediate-age PWNe. Based on deep observations of this highly spatially extended PWN, we produce a spectral map of the region that provides insights into the spectral variation within the nebula.
CRIS-Team Scopus Importer:2019-05-02
Keywords: gamma rays: general; acceleration of particles; convection; diffusion; pulsars: general

Performance studies for a next-generation optical sensor for IceCube-Gen2 - Shimizu, Nobuhiro; Ishihara, Aya; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; et al. (Proceedings of Science, 2022)
For the in-ice component of the next generation neutrino observatory at the South Pole, IceCubeGen2, a new sensor module is being developed, which is an evolution of the D-Egg and mDOM sensors developed for the IceCube Upgrade. The sensor design features up to 18 4-inch PMTs distributed homogeneously in a borosilicate glass pressure vessel. Challenges arise for the mechanical design from the tight constraints on the bore hole diameter (which will be 2 inches smaller than for IceCube Upgrade) and from the close packing of the PMTs. The electronics design must meet the space constraints posed by the mechanical design as well as the power consumption and cost considerations from over 10,000 optical modules being deployed. This contribution presents forward-looking solutions to these design considerations. Prototype modules will be installed and integrated in the IceCube Upgrade.
CRIS-Team Scopus Importer:2023-08-15

Performance verification of the FlashCam prototype camera for the Cherenkov Telescope Array - Werner, F.; Bauer, C.; Bernhard, S.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (ELSEVIER SCIENCE BV, 2017)
The Cherenkov Telescope Array (CTA) is a future gamma-ray observatory that is planned to significantly improve upon the sensitivity and precision of the current generation of Cherenkov telescopes. The observatory will consist of several dozens of telescopes with different sizes and equipped with different types of cameras. Of these, the FlashCam camera system is the first to implement a fully digital signal processing chain which allows for a traceable, configurable trigger scheme and flexible signal reconstruction. As of autumn 2016, a prototype FlashCam camera for the medium-sized telescopes of CTA nears completion. First results of the ongoing system tests demonstrate that the signal chain and the readout system surpass CTA requirements. The stability of the system is shown using long-term temperature cycling.
Keywords: Gamma-ray astronomy; Cherenkov camera; Performance verification; Temperature stability; CTA; MST; FlashCam

Performance verification of the FlashCam prototype camera for the Cherenkov Telescope Array - Werner, F.; Bauer, C.; Bernhard, S.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (ELSEVIER SCIENCE BV, 2017)
The Cherenkov Telescope Array (CTA) is a future gamma-ray observatory that is planned to significantly improve upon the sensitivity and precision of the current generation of Cherenkov telescopes. The observatory will consist of several dozens of telescopes with different sizes and equipped with different types of cameras. Of these, the FlashCam camera system is the first to implement a fully digital signal processing chain which allows for a traceable, configurable trigger scheme and flexible signal reconstruction. As of autumn 2016, a prototype FlashCam camera for the medium-sized telescopes of CTA nears completion. First results of the ongoing system tests demonstrate that the signal chain and the readout system surpass CTA requirements. The stability of the system is shown using long-term temperature cycling.
Keywords: Gamma-ray astronomy; Cherenkov camera; Performance verification; Temperature stability; CTA; MST; FlashCam

Photodynamic Treatment of Chaoborus crystallinus Larvae with Chlorophyllin Induces Necrosis and Apoptosis - Wohllebe, Stephanie; Ulbrich, Claudia; Grimm, Daniela; Pietsch, Jessica; Erzinger, Gilmar; Richter, Roland; Lebert, Michael; Richter, Peter; Haeder, Donat-Peter (Photochemistry and Photobiology, 2011)
Chlorophyllin kills mosquito larvae (Culex, Aedes) in the aquatic habitat at low concentrations via photodynamic reactions under irradiation. The effects of chlorophyllin were investigated at the cellular level using the transparent larvae of Chaoborus crystallinus as a model system. Their transparency enabled in situ fluorescence investigation, showing that chlorophyllin accumulates in the intestine of the larvae. Uptake of chlorophyllin at room temperature took about 2 h. The fluorescence signal peaked after 5 h of incubation. Chlorophyllin accumulates up to about 15 ng per larvae. The intestine of treated larvae was dissected and stained with several dyes (acridine orange, Hoechst 33342 and propidium iodide). Apoptosis and necrosis increased with higher concentrations of chlorophyllin (to a smaller extent in dark controls) and were elevated in irradiated samples. Single cells from treated larvae were isolated and subjected to Annexin V flow cytometry. The fraction of apoptotic and necrotic cells increased significantly at a high chlorophyllin concentration (21.4 mg L(-1)) and under intensive irradiation. The activity of caspases-3, -8 and -9 as well as Bcl-2 and cytochrome c was investigated by means of western blot analysis. The data suggest a possible chlorophyllin concentration-dependent shift of the apoptotic pathway.

Photoluminescent properties of the carbon-dimer defect in hexagonal boron-nitride: A many-body finite-size cluster approach - Winter, Michael; Bousquet, Manon H. E.; Jacquemin, Denis; Duchemin, Ivan; Blase, Xavier (Physical Review Materials, 2021)
We study the carbon-dimer defect in a hexagonal boron-nitride monolayer using the and Bethe-Salpeter many-body perturbation theories within a finite-size cluster approach. While quasiparticle energies converge very slowly with system size due to missing long-range polarization effects, optical excitations converge much faster, with a scaling law with respect to cluster average radius. We obtain a luminescence zero-phonon energy of 4.36 eV, including significant 0.13 eV zero-point vibrational energy and 0.15 eV reorganization energy contributions. Interlayer screening decreases further the emission energy by about 0.3 eV. These results bring support to the recent identification of the substitutional carbon dimer as the likely source of the zero-phonon 4.1 eV luminescence line. Finally, the quasiparticle energies are extrapolated to the infinite -BN monolayer limit, leading to a predicted defect highest occupied molecular orbital to lowest unoccupied molecular orbital photoemission gap of 7.6 eV. Comparison with the optical gap yields a very large excitonic binding energy of 3 eV for the associated localized Frenkel exciton.
CRIS-Team Scopus Importer:2021-10-22

PKS2005-489 at VHE: Four years of monitoring with HESS and simultaneous multi-wavelength observations - Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Bochow, A.; Boisson, C.; et al. (Astronomy & Astrophysics, 2010)
Aims: Our aim is to study the very high energy (VHE; E > 100 GeV) Γ-ray emission from BL Lac objects and the evolution in time of their broad-band spectral energy distribution (SED). Methods: VHE observations of the high-frequency peaked BL Lac object PKS 2005-489 were made with the High Energy Stereoscopic System (HESS) from 2004 through 2007. Three simultaneous multi-wavelength campaigns at lower energies were performed during the HESS data taking, consisting of several individual pointings with the XMM-Newton and RXTE satellites. Results: A strong VHE signal, ∼17ρ total, from PKS 2005-489 was detected during the four years of HESS observations (90.3 h live time). The integral flux above the average analysis threshold of 400 GeV is ∼3% of the flux observed from the Crab Nebula and varies weakly on time scales from days to years. The average VHE spectrum measured from ∼300 GeV to ∼5 TeV is characterized by a power law with a photon index, Γ = 3.20 ± 0.16 ± 0.10 At X-ray energies the flux is observed to vary by more than an order of magnitude between 2004 and 2005. Strong changes in the X-ray spectrum (ΔΓ ≈ 0.7) are also observed, which appear to be mirrored in the VHE band. Conclusions: The SED of PKS 2005-4 constructed for the first time with contemporaneous data on both humps, shows significant evolution. The large flux variations in the X-ray band, coupled with weak or no variations in the VHE band and a similar spectral behavior, suggest the emergence of a new, separate, harder emission component in September 2005. © 2010 ESO.
Keywords: BL Lacertae objects: individual: PKS 2005-489; Galaxies: active; Gamma rays: galaxies; X-rays: individuals: PKS 2005-489

PMT characterisation for the KM3NeT project - Herold, Björn; Kalekin, Oleg (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2011)
Keywords: High energy neutrino detection; Cherenkov light; Photomultiplier; KM3NeT

PMT characterisation for the KM3NeT project - Herold, Björn; Kalekin, Oleg; Reubelt, Jonas (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2011)
Keywords: Cherenkov light; KM3NeT; High energy neutrino detection; Photomultiplier

Polarization of Λ and over(Λ, ̄) in 920 GeV fixed-target proton-nucleus collisions - van Eldik, Christopher; et al. (Physics Letters B, 2006)
A measurement of the polarization of Λ and over(Λ, ̄) baryons produced in pC and pW collisions at sqrt(s) = 41.6 GeV has been performed with the HERA-B spectrometer. The measurements cover the kinematic range of 0.6 GeV / c < p < 1.2 GeV / c in transverse momentum and - 0.15 < x < 0.01 in Feynman-x. The polarization results from the two different targets agree within the statistical error. In the combined data set, the largest deviation from zero, + 0.054 ± 0.029, is measured for x ≲ - 0.07. Zero polarization is expected at x = 0 in the absence of nuclear effects. The polarization results for the Λ agree with a parametrization of previous measurements which were performed at positive x values, where the Λ polarization is negative. Results of over(Λ, ̄) polarization measurements are consistent with zero. © 2006 Elsevier B.V. All rights reserved.

Population study of Galactic supernova remnants at very high gamma-ray energies with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Shell-type supernova remnants (SNRs) are considered prime candidates for the acceleration of Galactic cosmic rays (CRs) up to the knee of the CR spectrum at E approximate to 3 x 10(15) eV. Our MilkyWay galaxy hosts more than 350 SNRs discovered at radio wavelengths and at high energies, of which 220 fall into the H.E.S.S. Galactic Plane Survey (HGPS) region. Of those, only 50 SNRs are coincident with a H.E.S.S source and in 8 cases the very high-energy (VHE) emission is firmly identified as an SNR. The H.E.S.S. GPS provides us with a legacy for SNR population study in VHE gamma-rays and we use this rich data set to extract VHE flux upper limits from all undetected SNRs. Overall, the derived flux upper limits are not in contradiction with the canonical CR paradigm. Assuming this paradigm holds true, we can constrain typical ambient density values around shell-type SNRs to n <= 7 cm(-3) and electron-to-proton energy fractions above 10 TeV to epsilon(ep) <= 5 x 10(-3). Furthermore, comparisons of VHE with radio luminosities in non-interacting SNRs reveal a behaviour that is in agreement with the theory of magnetic field amplification at shell-type SNRs.
Keywords: gamma rays: general; ISM: supernova remnants

Potential of the Julia Programming Language for High Energy Physics Computing - Eschle, Jonas; Gál, Tamás; Giordano, Mosè; Gras, Philippe; Hegner, Benedikt; Heinrich, Lukas; Hernandez Acosta, Uwe; Kluth, Stefan; Ling, Jerry; Mato, Pere; Mikhasenko, Mikhail; Moreno Briceño, Alexander; et al. (Computing and Software for Big Science, 2023)
Research in high energy physics (HEP) requires huge amounts of computing and storage, putting strong constraints on the code speed and resource usage. To meet these requirements, a compiled high-performance language is typically used; while for physicists, who focus on the application when developing the code, better research productivity pleads for a high-level programming language. A popular approach consists of combining Python, used for the high-level interface, and C++, used for the computing intensive part of the code. A more convenient and efficient approach would be to use a language that provides both high-level programming and high-performance. The Julia programming language, developed at MIT especially to allow the use of a single language in research activities, has followed this path. In this paper the applicability of using the Julia language for HEP research is explored, covering the different aspects that are important for HEP code development: runtime performance, handling of large projects, interface with legacy code, distributed computing, training, and ease of programming. The study shows that the HEP community would benefit from a large scale adoption of this programming language. The HEP-specific foundation libraries that would need to be consolidated are identified.
CRIS-Team Scopus Importer:2023-10-20
Keywords: HEP; High energy and nuclear physics; HPC; Julia; Programming language; Python

Primary particle acceleration above 100 TeV in the shell-type supernova remnant RX J1713.7-3946 with deep HESS observations - van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2007)
Aims. We present deep HESS observations of the supernova remnant (SNR) RX J1713.7-3946. Combining data of three years - from 2003 to 2005 - we obtain significantly increased statistics and energy coverage as compared to earlier 2003 and 2004 results. Methods. The data are analysed separately for the different years. Results. Very good agreement of the gamma-ray morphology and the differential spectra is found when comparing the three years. The combined gamma-ray image of the 2004 and 2005 data reveals the morphology of RX J1713.7-3946 with unprecedented precision. An angular resolution of 0.06° is achieved, revealing the detailed structure of the remnant. The combined spectrum of all three years extends over three orders of magnitude, with significant gamma-ray emission approaching 100 TeV. The cumulative significance above 30 TeV is 4.8σ, while for energies between 113 and 294 TeV an upper limit on the gamma-ray flux of 1.6 × 10 cm s is obtained. Conclusions. The energy coverage of the HESS data is presumably at the limit of present generation Cherenkov telescopes. The measurement of significant gamma-ray emission beyond 30 TeV formally implies the existence of primary particles of at least that energy. However, for realistic scenarios of very-high-energy gamma-ray production, the Inverse Compton scattering of very-high-energy electrons and π decay following inelastic proton-proton interactions, the measured gamma-ray energies imply that efficient acceleration of primary particles to energies exceeding 100 TeV is taking place in the shell of the SNR RX J1713.7-3946. © ESO 2007.
Keywords: Acceleration of particles; Gamma rays: observations; ISM: cosmic rays; ISM: supernova remnants

Probing the angular and polarization reconstruction of the ARIANNA detector at the South Pole - Anker, A.; Barwick, S. W.; Bernhoff, H.; Besson, D. Z.; Bingefors, N.; García-Fernández, D.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hanson, J. C.; Klein, S. R.; Kleinfelder, S. A.; et al. (Journal of Instrumentation, 2020)
The sources of ultra-high energy (UHE) cosmic rays, which can have energies up to 1020 eV, remain a mystery. UHE neutrinos may provide important clues to understanding the nature of cosmic-ray sources. ARIANNA aims to detect UHE neutrinos via radio (Askaryan) emission from particle showers when a neutrino interacts with ice, which is an efficient method for neutrinos with energies between 1016 eV and 1020 eV. The ARIANNA radio detectors are located in Antarctic ice just beneath the surface. Neutrino observation requires that radio pulses propagate to the antennas at the surface with minimum distortion by the ice and firn medium. Using the residual hole from the South Pole Ice Core Project, radio pulses were emitted from a transmitter located up to 1.7 km below the snow surface. By measuring these signals with an ARIANNA surface station, the angular and polarization reconstruction abilities are quantified, which are required to measure the direction of the neutrino. After deconvolving the raw signals for the detector response and attenuation from propagation through the ice, the signal pulses show no significant distortion and agree with a reference measurement of the emitter made in an anechoic chamber. Furthermore, the signal pulses reveal no significant birefringence for our tested geometry of mostly vertical ice propagation. The origin of the transmitted radio pulse was measured with an angular resolution of 0.37◦ indicating that the neutrino direction can be determined with good precision if the polarization of the radio-pulse can be well determined. In the present study we obtained a resolution of the polarization vector of 2.7◦. Neither measurement show a significant offset relative to expectation.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Data analysis; Neutrino detectors; Performance of High Energy Physics Detectors; Systematic effects

Probing the ATIC peak in the cosmic-ray electron spectrum with H.E.S.S. - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, Julien; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
The measurement of an excess in the cosmic-ray electron spectrum between 300 and 800 GeV by the ATIC experiment has - together with the PAMELA detection of a rise in the positron fraction up to ≈100 GeV - motivated many interpretations in terms of dark matter scenarios; alternative explanations assume a nearby electron source like a pulsar or supernova remnant. Here we present a measurement of the cosmic-ray electron spectrum with H.E.S.S. starting at 340 GeV. While the overall electron flux measured by H.E.S.S. is consistent with the ATIC data within statistical and systematic errors, the H.E.S.S. data exclude a pronounced peak in the electron spectrum as suggested for interpretation by ATIC. The H.E.S.S. data follow a power-law spectrum with spectral index of 3.0 ±0.1(stat.) ±0.3(syst.), which steepens at about 1 TeV. © ESO 2009.
Keywords: Cosmic rays; Methods: data analysis

Probing the gamma-ray emission from HESS J1834-087 using H.E.S.S. and Fermi LAT observations - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2015)
Aims. Previous observations with the High Energy Stereoscopic System (H.E.S.S.) have revealed an extended very-high-energy (VHE; E > 100 GeV) γ-ray source, HESS J1834-087, coincident with the supernova remnant (SNR)W41. The origin of the γ-ray emission was investigated in more detail with the H.E.S.S. array and the Large Area Telescope (LAT) onboard the Fermi Gamma-ray Space Telescope. Methods. The γ-ray data provided by 61 h of observations with H.E.S.S., and four years with the Fermi LAT were analyzed, covering over five decades in energy from 1.8 GeV up to 30 TeV. The morphology and spectrum of the TeV and GeV sources were studied and multiwavelength data were used to investigate the origin of the γ-ray emission toward W41. Results. The TeV source can be modeled with a sum of two components: one point-like and one significantly extended (σ = 0.17° ± 0. 01°), both centered on SNR W41 and exhibiting spectra described by a power law with index Γ ≃ 2.6. The GeV source detected with Fermi LAT is extended (σ = 0.15° ± 0.03°) and morphologically matches the VHE emission. Its spectrum can be described by a power-law model with an index Γ = 2.15 ± 0.12 and smoothly joins the spectrum of the whole TeV source. A break appears in the γ-ray spectra around 100 GeV. No pulsations were found in the GeV range. Conclusions. Two main scenarios are proposed to explain the observed emission: a pulsar wind nebula (PWN) or the interaction of SNRW41 with an associated molecular cloud. X-ray observations suggest the presence of a point-like source (a pulsar candidate) near the center of the remnant and nonthermal X-ray di ffuse emission that could arise from the possibly associated PWN. The PWN scenario is supported by the compatible positions of the TeV and GeV sources with the putative pulsar. However, the spectral energy distribution from radio to γ-rays is reproduced by a one-zone leptonic model only if an excess of low-energy electrons is injected following a Maxwellian distribution by a pulsar with a high spin-down power (>10 ergs). This additional low-energy component is not needed if we consider that the point-like TeV source is unrelated to the extended GeV and TeV sources. The interacting SNR scenario is supported by the spatial coincidence between the γ-ray sources, the detection of OH (1720 MHz) maser lines, and the hadronic modeling.
Keywords: Acceleration of particles; Cosmic rays; Ism: Clouds; Ism: Supernova remnants

Production of the charmonium states χc1 and χc2 in proton nucleus interactions at s=41.6GeV - Abt, I.; Adams, M.; Agari, M.; Albrecht, H.; Aleksandrov, A.; Amaral, Vasco; Amorim, Antonio; Aplin, S. J.; Aushev, V.; Bagaturia, Y.; Balagura, V.; Bargiotti, M.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2009)
A measurement of the ratio Rχc=(χc→J/ψ+γ)/J/ψ in pC, pTi, and pW interactions at 920GeV/c (s=41.6GeV) in the Feynman-x range -0.35
Keywords: Decays of J/psi Upsilon and other quarkonia; Hadron-induced high- and super-high-energy interactions; Quarks gluons and QCD in nuclei and nuclear processes; Polarization in interactions and scattering

Prospects for Cherenkov Telescope Array Observations of the Young Supernova Remnant RX J1713.73946 - Acero, F.; Aloisio, R.; Amans, J.; Amato, E.; Antonelli, L. A.; Aramo, C.; Armstrong, T.; Arqueros, F.; Asano, K.; Ashley, M.; Backes, M.; Balazs, C.; et al. (Astrophysical Journal, 2017)
Keywords: cosmic rays; gamma rays: ISM; ISM: individual objects: RX J1713.7 dash3946; G347.3 dash0.5

Publishing Multi-Purpose Data Sets from KM3NeT - Schnabel, Jutta (CEUR Workshop Proceedings, 2020)
The KM3NeT neutrino detector, a water Cherenkov experiment to detect relativistic charged particles, is currently under construction at two deep-sea locations in the Mediterranean Sea. As crossdomain experiment between neutrino, astro-particle and astrophysics, data processing and data publication from KM3NeT draws on computing paradigms and standardization from all fields. In this contribution, key considerations for the provision of multi-purpose open data sets, interface options and interoperability requirements are presented.
CRIS-Team Scopus Importer:2021-04-19
Keywords: KM3NeT; neutrino astronomy; neutrino physics; open data

Quantum gravity phenomenology at the dawn of the multi-messenger era—A review - Addazi, A.; Alvarez-Muniz, J.; Alves Batista, R.; Amelino-Camelia, G.; Antonelli, V.; Arzano, M.; Asorey, M.; Atteia, J. L.; Bahamonde, S.; Bajardi, F.; Ballesteros, A.; Baret, B.; et al. (Progress in Particle and Nuclear Physics, 2022)
The exploration of the universe has recently entered a new era thanks to the multi-messenger paradigm, characterized by a continuous increase in the quantity and quality of experimental data that is obtained by the detection of the various cosmic messengers (photons, neutrinos, cosmic rays and gravitational waves) from numerous origins. They give us information about their sources in the universe and the properties of the intergalactic medium. Moreover, multi-messenger astronomy opens up the possibility to search for phenomenological signatures of quantum gravity. On the one hand, the most energetic events allow us to test our physical theories at energy regimes which are not directly accessible in accelerators; on the other hand, tiny effects in the propagation of very high energy particles could be amplified by cosmological distances. After decades of merely theoretical investigations, the possibility of obtaining phenomenological indications of Planck-scale effects is a revolutionary step in the quest for a quantum theory of gravity, but it requires cooperation between different communities of physicists (both theoretical and experimental). This review, prepared within the COST Action CA18108 “Quantum gravity phenomenology in the multi-messenger approach”, is aimed at promoting this cooperation by giving a state-of-the art account of the interdisciplinary expertise that is needed in the effective search of quantum gravity footprints in the production, propagation and detection of cosmic messengers.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Cosmic neutrinos; Gamma-ray astronomy; Gravitational waves; Lorentz invariance violation and deformation; Ultra-high-energy cosmic rays

Radiofrequency ice dielectric measurements at Summit Station, Greenland - Aguilar, Juan Antonio; Allison, Patrick; Besson, Dave; Bishop, Abby; Botner, Olga; Bouma, Sjoerd; Buitink, Stijn; Cataldo, Maddalena; Clark, Brian A.; Couberly, Kenny; Curtis-Ginsberg, Zach; Dasgupta, Paramita; et al. (Journal of Glaciology, 2023)
We recently reported on the radio-frequency attenuation length of cold polar ice at Summit Station, Greenland, based on bi-static radar measurements of radio-frequency bedrock echo strengths taken during the summer of 2021. Those data also allow studies of (a) the relative contributions of coherent (such as discrete internal conducting layers with sub-centimeter transverse scale) vs incoherent (e.g. bulk volumetric) scattering, (b) the magnitude of internal layer reflection coefficients, (c) limits on signal propagation velocity asymmetries ('birefringence') and (d) limits on signal dispersion in-ice over a bandwidth of ∼100 MHz. We find that (1) attenuation lengths approach 1 km in our band, (2) after averaging 10 000 echo triggers, reflected signals observable over the thermal floor (to depths of ∼1500 m) are consistent with being entirely coherent, (3) internal layer reflectivities are ≈-60-70 dB, (4) birefringent effects for vertically propagating signals are smaller by an order of magnitude relative to South Pole and (5) within our experimental limits, glacial ice is non-dispersive over the frequency band relevant for neutrino detection experiments.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Arctic glaciology; ice physics; radio-echo sounding

Radio imaging of the very-high-energy γ-ray emission region in the central engine of a radio galaxy - van Eldik, Christopher; Acciari, V. A.; Aliu, E.; Arlen, T.; Bautista, M.; Beilicke, M.; Benbow, W.; Bradbury, S. M.; Buckley, J. H.; Bugaev, V.; Butt, Y.; Byrum, K.; et al. (Science, 2009)
The accretion of matter onto a massive black hole is believed to feed the relativistic plasma jets found in many active galactic nuclei (AGN). Although some AGN accelerate particles to energies exceeding 10 electron volts and are bright sources of very-high-energy (VHE) y-ray emission, it is not yet known where the VHE emission originates. Here we report on radio and VHE observations of the radio galaxy Messier 87, revealing a period of extremely strong VHE y-ray flares accompanied by a strong increase of the radio flux from its nucleus. These results imply that charged particles are accelerated to very high energies in the immediate vicinity of the black hole.

Readout electronics testing during mass production of FlashCam cameras for the Cherenkov Telescope Array - Diebold, S.; Barcelo, M.; Bauer, C.; Bernhard, S.; Biegger, M.; Capasso, M.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; et al. (OPTICS FOR EUV, X-RAY, AND GAMMA-RAY ASTRONOMY VIII, 2017)
CRIS-Team WoS Importer:2020-01-15

Reconstructing the neutrino energy for in-ice radio detectors: A study for the Radio Neutrino Observatory Greenland (RNO-G) - Aguilar, J. A.; Allison, P.; Beatty, J. J.; Bernhoff, H.; Besson, D.; Bingefors, N.; Botner, O.; Bouma, Sjoerd; Buitink, S.; Carter, K.; Cataldo, Maddalena; Clark, B. A.; et al. (European Physical Journal C: Particles and Fields, 2022)
Since summer 2021, the Radio Neutrino Observatory in Greenland (RNO-G) is searching for astrophysical neutrinos at energies > 10 PeV by detecting the radio emission from particle showers in the ice around Summit Station, Greenland. We present an extensive simulation study that shows how RNO-G will be able to measure the energy of such particle cascades, which will in turn be used to estimate the energy of the incoming neutrino that caused them. The location of the neutrino interaction is determined using the differences in arrival times between channels and the electric field of the radio signal is reconstructed using a novel approach based on Information Field Theory. Based on these properties, the shower energy can be estimated. We show that this method can achieve an uncertainty of 13% on the logarithm of the shower energy after modest quality cuts and estimate how this can constrain the energy of the neutrino. The method presented in this paper is applicable to all similar radio neutrino detectors, such as the proposed radio array of IceCube-Gen2.
CRIS-Team Scopus Importer:2022-03-04

Resolving the Crab pulsar wind nebula at teraelectronvolt energies - Abdalla, H.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Becker Tjus, J.; Berge, D.; et al. (Nature Astronomy, 2019)
The Crab nebula is one of the most-studied cosmic particle accelerators, shining brightly across the entire electromagnetic spectrum up to very-high-energy gamma rays1,2. It is known from observations in the radio to gamma-ray part of the spectrum that the nebula is powered by a pulsar, which converts most of its rotational energy losses into a highly relativistic outflow. This outflow powers a pulsar wind nebula, a region of up to ten light-years across, filled with relativistic electrons and positrons. These particles emit synchrotron photons in the ambient magnetic field and produce very-high-energy gamma rays by Compton up-scattering of ambient low-energy photons. Although the synchrotron morphology of the nebula is well established, it has not been known from which region the very-high-energy gamma rays are emitted3–8. Here we report that the Crab nebula has an angular extension at gamma-ray energies of 52 arcseconds (assuming a Gaussian source width), much larger than at X-ray energies. This result closes a gap in the multi-wavelength coverage of the nebula, revealing the emission region of the highest-energy gamma rays. These gamma rays enable us to probe a previously inaccessible electron and positron energy range. We find that simulations of the electromagnetic emission reproduce our measurement, providing a non-trivial test of our understanding of particle acceleration in the Crab nebula.
CRIS-Team Scopus Importer:2019-11-15

Results from the search for dark matter in the Milky Way with 9 years of data of the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2017)
Using data recorded with the ANTARES telescope from 2007 to 2015, a new search for dark matter annihilation in the Milky Way has been performed. Three halo models and five annihilation channels, WIMP + WIMP -> b (b) over bar, W+W-, tau(+)tau(-), mu(+)mu(-) and v (v) over bar, with WIMP masses ranging from 50 2 GeV/C-2 to 100 Tev/C-2, were considered. No excess over the expected background was found, and limits on the thermally averaged annihilation cross-section were set. (C) 2017 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license.
Keywords: Dark matter; WIMP; Indirect detection; Neutrino telescope; Galactic Centre; ANTARES

Revealing x-ray and gamma ray temporal and spectral similarities in the GRB 190829A afterglow - Taylor, Andrew M.; Aharonian, Felix; Romoli, Carlo; Khangulyan, Dmitry; Ruiz-Velasco, Edna; Schüssler, Fabian; Zhu, Sylvia J.; Büchele, Matthias; Eichhorn, Florian; Funk, Stefan; Glawion, Dorit; Jankowsky, David; et al. (Science, 2021)
Gamma-ray bursts (GRBs), which are bright flashes of gamma rays from extragalactic sources followed by fading afterglow emission, are associated with stellar core collapse events. We report the detection of very-high-energy (VHE) gamma rays from the afterglow of GRB 190829A, between 4 and 56 hours after the trigger, using the High Energy Stereoscopic System (H.E.S.S.). The low luminosity and redshift of GRB 190829A reduce both internal and external absorption, allowing determination of its intrinsic energy spectrum. Between energies of 0.18 and 3.3 tera-electron volts, this spectrum is described by a power law with photon index of 2.07 ± 0.09, similar to the x-ray spectrum. The x-ray and VHE gamma-ray light curves also show similar decay profiles. These similar characteristics in the x-ray and gamma-ray bands challenge GRB afterglow emission scenarios.
CRIS-Team Scopus Importer:2021-06-18

REVIEW OF PARTICLE PHYSICS Particle Data Group - Tanabashi, M.; Hagiwara, K.; Hikasa, K.; Nakamura, K.; Sumino, Y.; Takahashi, F.; Tanaka, J.; Agashe, K.; Aielli, G.; Amsler, C.; Antonelli, M.; Asner, D. M.; et al. (Physical Review D, 2018)
The Review summarizes much of particle physics and cosmology. Using data from previous editions, plus 2,873 new measurements from 758 papers, we list, evaluate, and average measured properties of gauge bosons and the recently discovered Higgs boson, leptons, quarks, mesons, and baryons. We summarize searches for hypothetical particles such as supersymmetric particles, heavy bosons, axions, dark photons, etc. Particle properties and search limits are listed in Summary Tables. We give numerous tables, figures, formulae, and reviews of topics such as Higgs Boson Physics, Supersymmetry, Grand Unified Theories, Neutrino Mixing, Dark Energy, Dark Matter, Cosmology, Particle Detectors, Colliders, Probability and Statistics. Among the 118 reviews are many that are new or heavily revised, including a new review on Neutrinos in Cosmology.
CRIS-Team WoS Importer:2019-03-01

Revisiting the Westerlund 2 field with the HESS telescope array - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2011)
Aims. Previous observations with the HESS telescope array revealed the existence of extended very-high-energy (VHE; E > 100 GeV) γ-ray emission, HESS J1023-575, coincident with the young stellar cluster Westerlund 2. At the time of discovery, the origin of the observed emission was not unambiguously identified, and follow-up observations have been performed to further investigate the nature of this γ-ray source. Methods. The Carina region towards the open cluster Westerlund 2 has been re-observed, increasing the total exposure to 45.9 h. The combined dataset includes 33 h of new data and now permits a search for energy-dependent morphology and detailed spectroscopy. Results. A new, hard spectrum VHE γ-ray source, HESS J1026-582, was discovered with a statistical significance of 7σ. It is positionally coincident with the Fermi LAT pulsar PSR J1028-5819. The positional coincidence and radio/γ-ray characteristics of the LAT pulsar favors a scenario where the TeV emission originates from a pulsar wind nebula. The nature of HESS J1023-575 is discussed in light of the deep HESS observations and recent multi-wavelength discoveries, including the Fermi LAT pulsar PSR J1022-5746 and giant molecular clouds in the region. Despite the improved VHE dataset, a clear identification of the object responsible for the VHE emission from HESS J1023-575 is not yet possible, and contribution from the nearby high-energy pulsar and/or the open cluster remains a possibility. © 2010 ESO.
Keywords: gamma rays: stars; HII regions

Searches for a dark matter annihilation signal from the milky way halo with the H.E.S.S. array of imaging atmospheric cherenkov telescopes - Spengler, G.; Birsin, E.; van Eldik, Christopher; Nekrassov, D.; Schwanke, U. (32nd International Cosmic Ray Conference, ICRC 2011, 2011)
The central region of the DM halo of the Milky Way is a promising target for a search for a particle dark matter (DM) self annihilation signal. Recent N-body simulations agree in the description of the radial DM density profile of a DM halo at projected distances from the halo center bigger than 45 pc within a factor of two. A search for a DM annihilation photon flux with the High Energy Stereoscopic System (H.E.S.S.) in the energy range between 300 GeV and 100 TeV originating from distances to the halo center bigger than 45 pc (0.3?) is presented. Assuming that the radial dependence of the DM density of the Milky Way can be described with the results of recent N-body simulations, upper limits for the velocity weighted self annihilation cross section of weakly interacting massive particles (WIMPs) in the order of 10 cm3s at WIMP masses of 1 TeV can be calculated. Prospects on an improvement of the sensitivity are discussed.
Keywords: Cherenkov Telescopes; Dark Matter; Milky Way Halo

Searches for clustering in the time integrated skymap of the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper reports a search for spatial clustering of the arrival directions of high energy muon neutrinos detected by the ANTARES neutrino telescope. An improved two-point correlation method is used to study the autocorrelation of 3058 neutrino candidate events as well as cross-correlations with other classes of astrophysical objects: sources of high energy gamma rays, massive black holes and nearby galaxies. No significant deviations from the isotropic distribution of arrival directions expected from atmospheric backgrounds are observed.
Keywords: neutrino astronomy; neutrino detectors

Searches for connections between dark matter and high-energy neutrinos with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Journal of Cosmology and Astroparticle Physics, 2023)
In this work, we present the results of searches for signatures of dark matter decay or annihilation into Standard Model particles, and secret neutrino interactions with dark matter. Neutrinos could be produced in the decay or annihilation of galactic or extragalactic dark matter. Additionally, if an interaction between dark matter and neutrinos exists then dark matter will interact with extragalactic neutrinos. In particular galactic dark matter will induce an anisotropy in the neutrino sky if this interaction is present. We use seven and a half years of the High-Energy Starting Event (HESE) sample data, which measures neutrinos in the energy range of approximately 60 TeV to 10 PeV, to study these phenomena. This all-sky event selection is dominated by extragalactic neutrinos. For dark matter of ∼ 1 PeV in mass, we constrain the velocity-averaged annihilation cross section to be smaller than 10−23 cm3/s for the exclusive µ+µ− channel and 10−22 cm3/s for the bb̄ channel. For the same mass, we constrain the lifetime of dark matter to be larger than 1028 s for all channels studied, except for decaying exclusively to bb̄ where it is bounded to be larger than 1027 s. Finally, we also search for evidence of astrophysical neutrinos scattering on galactic dark matter in two scenarios. For fermionic dark matter with a vector mediator, we constrain the dimensionless coupling associated with this interaction to be less than 0.1 for dark matter mass of 0.1 GeV and a mediator mass of 10−4 GeV. In the case of scalar dark matter with a fermionic mediator, we constrain the coupling to be less than 0.1 for dark matter and mediator masses below 1 MeV.
CRIS-Team Scopus Importer:2023-12-15
Keywords: dark matter experiments; neutrino astronomy; neutrino experiments; neutrinos; ultra high energy photons

Searches for gamma-ray lines and 'pure WIMP' spectra from Dark Matter annihilations in dwarf galaxies with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Journal of Cosmology and Astroparticle Physics, 2018)
Dwarf spheroidal galaxies are among the most promising targets for detecting signals of Dark Matter (DM) annihilations. The H.E.S.S. experiment has observed five of these systems for a total of about 130 hours. The data are re-analyzed here, and, in the absence of any detected signals, are interpreted in terms of limits on the DM annihilation cross section. Two scenarios are considered: i) DM annihilation into mono-energetic gamma-rays and ii) DM in the form of pure WIMP multiplets that, annihilating into all electroweak bosons, produce a distinctive gamma-ray spectral shape with a high-energy peak at the DM mass and a lower-energy continuum. For case i), upper limits at 95% confidence level of about less than or similar to 3 x 10(-25) cm(3) s(-1) are obtained in the mass range of 400 GeV to 1TeV. For case ii), the full spectral shape of the models is used and several excluded regions are identified, but the thermal masses of the candidates are not robustly ruled out.
CRIS-Team WoS Importer:2020-01-15

Searches for neutrinos from cosmic-ray interactions in the Sun using seven years of IceCube data - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau,; Anton, Gisela; Arguelles, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
Cosmic-ray interactions with the solar atmosphere are expected to produce particle showers which in turn produce neutrinos from weak decays of mesons. These solar atmospheric neutrinos (SAνs) have never been observed experimentally. A detection would be an important step in understanding cosmic-ray propagation in the inner solar system and the dynamics of solar magnetic fields. SAνs also represent an irreducible background to solar dark matter searches and a detection would allow precise characterization of this background. Here, we present the first experimental search based on seven years of data collected from May 2010 to May 2017 in the austral winter with the IceCube Neutrino Observatory. An unbinned likelihood analysis is performed for events reconstructed within 5 degrees of the center of the Sun. No evidence for a SAν flux is observed. After inclusion of systematic uncertainties, we set a 90% upper limit of 1.02+0.20-0.18·10-13 GeV-1cm-2s-1 at 1 TeV.
CRIS-Team Scopus Importer:2021-03-26
Keywords: neutrino astronomy; neutrino detectors; neutrino experiments; solar and atmospheric neutrinos

Searches for Neutrinos from Gamma-Ray Bursts Using the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Astrophysical Journal, 2022)
Gamma-ray bursts (GRBs) are considered as promising sources of ultra-high-energy cosmic rays (UHECRs) due to their large power output. Observing a neutrino flux from GRBs would offer evidence that GRBs are hadronic accelerators of UHECRs. Previous IceCube analyses, which primarily focused on neutrinos arriving in temporal coincidence with the prompt gamma-rays, found no significant neutrino excess. The four analyses presented in this paper extend the region of interest to 14 days before and after the prompt phase, including generic extended time windows and targeted precursor searches. GRBs were selected between 2011 May and 2018 October to align with the data set of candidate muon-neutrino events observed by IceCube. No evidence of correlation between neutrino events and GRBs was found in these analyses. Limits are set to constrain the contribution of the cosmic GRB population to the diffuse astrophysical neutrino flux observed by IceCube. Prompt neutrino emission from GRBs is limited to less than or similar to 1% of the observed diffuse neutrino flux, and emission on timescales up to 10(4) s is constrained to 24% of the total diffuse flux.
CRIS-Team WoS Importer:2023-01-20

Searches for Neutrinos from Large High Altitude Air Shower Observatory Ultra-high-energy γ-Ray Sources Using the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Astrophysical Journal Letters, 2023)
Galactic PeV cosmic-ray accelerators (PeVatrons) are Galactic sources theorized to accelerate cosmic rays up to PeV in energy. The accelerated cosmic rays are expected to interact hadronically with nearby ambient gas or the interstellar medium, resulting in γ-rays and neutrinos. Recently, the Large High Altitude Air Shower Observatory (LHAASO) identified 12 γ-ray sources with emissions above 100 TeV, making them candidates for PeVatrons. While at these high energies the Klein-Nishina effect exponentially suppresses leptonic emission from Galactic sources, evidence for neutrino emission would unequivocally confirm hadronic acceleration. Here, we present the results of a search for neutrinos from these γ-ray sources and stacking searches testing for excess neutrino emission from all 12 sources as well as their subcatalogs of supernova remnants and pulsar wind nebulae with 11 yr of track events from the IceCube Neutrino Observatory. No significant emissions were found. Based on the resulting limits, we place constraints on the fraction of γ-ray flux originating from the hadronic processes in the Crab Nebula and LHAASO J2226+6057.
CRIS-Team Scopus Importer:2023-03-24

SEARCHES FOR POINT-LIKE AND EXTENDED NEUTRINO SOURCES CLOSE TO THE GALACTIC CENTER USING THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J-J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal Letters, 2014)
A search for cosmic neutrino sources using six years of data collected by the ANTARES neutrino telescope has been performed. Clusters of muon neutrinos over the expected atmospheric background have been looked for. No clear signal has been found. The most signal-like accumulation of events is located at equatorial coordinates R.A. = -46 degrees.8 and decl. = -64 degrees.9 and corresponds to a 2.2 sigma background fluctuation. In addition, upper limits on the flux normalization of an E-2 muon neutrino energy spectrum have been set for 50 pre-selected astrophysical objects. Finally, motivated by an accumulation of seven events relatively close to the Galactic Center in the recently reported neutrino sample of the IceCube telescope, a search for point sources in a broad region around this accumulation has been carried out. No indication of a neutrino signal has been found in the ANTARES data and upper limits on the flux normalization of an E-2 energy spectrum of neutrinos from point sources in that region have been set. The 90% confidence level upper limits on the muon neutrino flux normalization vary between 3.5 and 5.1 x 10(-8) GeV cm(-2) s(-1), depending on the exact location of the source.
Keywords: astroparticle physics; Galaxy: center; neutrinos

SEARCH FOR A CORRELATION BETWEEN ANTARES NEUTRINOS AND PIERRE AUGER OBSERVATORY UHECRs ARRIVAL DIRECTIONS - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2013)
A multimessenger analysis optimized for a correlation of arrival directions of ultra-high energy cosmic rays (UHECRs) and neutrinos is presented and applied to 2190 neutrino candidate events detected in 2007-2008 by the ANTARES telescope and 69 UHECRs observed by the Pierre Auger Observatory between 2004 January 1 and 2009 December 31. No significant correlation is observed. Assuming an equal neutrino flux (E-2 energy spectrum) from all UHECR directions, a 90% CL upper limit on the neutrino flux of 5.0 x 10(-8) GeV cm(-2) s(-1) per source is derived.
Keywords: astroparticle physics; cosmic rays; neutrinos

Search for a cosmic neutrino flux from all neutrino flavours with ANTARES - Schnabel, Jutta (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2019)

Search for a dark matter annihilation signal from the galactic center halo with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Barnacka, A.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Physical Review Letters, 2011)
A search for a very-high-energy (VHE; 100GeV) γ-ray signal from self-annihilating particle dark matter (DM) is performed towards a region of projected distance r∼45-150pc from the Galactic center. The background-subtracted γ-ray spectrum measured with the High Energy Stereoscopic System (H.E.S.S.) γ-ray instrument in the energy range between 300-GeV and 30-TeV shows no hint of a residual γ-ray flux. Assuming conventional Navarro-Frenk-White and Einasto density profiles, limits are derived on the velocity-weighted annihilation cross section σv as a function of the DM particle mass. These are among the best reported so far for this energy range and in particular differ only little between the chosen density profile parametrizations. In particular, for the DM particle mass of ∼1TeV, values for σ above 3×1025cm3s1 are excluded for the Einasto density profile. © 2011 American Physical Society.

Search for a diffuse cosmic neutrino flux with ANTARES using track and cascade events - Schnabel, Jutta; et al. (2016)

Search for correlations between the arrival directions of IceCube neutrino events and ultrahigh-energy cosmic rays detected by the Pierre Auger Observatory and the Telescope Array - Aartsen, M. G.; Abraham, K.; Ackermann, Markus; Adams, J.; Aguilar, J. A.; Ahlers, Markus; Ahrens, M.; Altmann, D.; Anderson, T.; Ansseau, I.; Archinger, M.; Arguelles, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
This paper presents the results of different searches for correlations between very high-energy neutrino candidates detected by IceCube and the highest-energy cosmic rays measured by the Pierre Auger Observatory and the Telescope Array. We first consider samples of cascade neutrino events and of high-energy neutrino-induced muon tracks, which provided evidence for a neutrino flux of astrophysical origin, and study their cross-correlation with the ultrahigh-energy cosmic ray (UHECR) samples as a function of angular separation. We also study their possible directional correlations using a likelihood method stacking the neutrino arrival directions and adopting different assumptions on the size of the UHECR magnetic deflections. Finally, we perform another likelihood analysis stacking the UHECR directions and using a sample of through-going muon tracks optimized for neutrino point-source searches with sub-degree angular resolution. No indications of correlations at discovery level are obtained for any of the searches performed. The smallest of the p-values comes from the search for correlation between UHECRs with IceCube high-energy cascades, a result that should continue to be monitored.
Keywords: neutrino experiments; ultra high energy cosmic rays; cosmic ray experiments; neutrino astronomy

Search for Correlations of High-energy Neutrinos Detected in IceCube with Radio-bright AGN and Gamma-Ray Emission from Blazars - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Astrophysical Journal, 2023)
The IceCube Neutrino Observatory sends realtime neutrino alerts with a high probability of being astrophysical in origin. We present a new method to correlate these events and possible candidate sources using 2089 blazars from the Fermi-LAT 4LAC-DR2 catalog and with 3413 active galactic nuclei (AGNs) from the Radio Fundamental Catalog. No statistically significant neutrino emission was found in any of the catalog searches. The result suggests that a small fraction, <1%, of the studied AGNs emit neutrinos that pass the alert criteria, and is compatible with prior evidence for neutrino emission presented by IceCube and other authors from sources such as TXS 0506 + 056 and PKS 1502 + 106. We also present cross-checks to other analyses that claim a significant correlation using similar data samples.
CRIS-Team Scopus Importer:2023-10-20

SEARCH FOR COSMIC NEUTRINO POINT SOURCES WITH FOUR YEARS OF DATA FROM THE ANTARES TELESCOPE - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2012)
In this paper, a time-integrated search for point sources of cosmic neutrinos is presented using the data collected from 2007 to 2010 by the ANTARES neutrino telescope. No statistically significant signal has been found and upper limits on the neutrino flux have been obtained. Assuming an E-nu(-2). spectrum, these flux limits are at 1-10x10(-8) GeV cm(-2) s(-1) for declinations ranging from -90 degrees to 40 degrees. Limits for specific models of RX J1713.7-3946 and Vela X, which include information on the source morphology and spectrum, are also given.
Keywords: astroparticle physics; cosmic rays; neutrinos

Search for dark matter annihilation in the earth using the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics of the Dark Universe, 2017)
A search for a neutrino signal from WIMP pair annihilations in the centre of the Earth has been performed with the data collected with the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria have been developed and tuned to maximise the sensitivity of the experiment to such a neutrino signal. No significant excess of neutrinos over the expected background has been observed. Upper limits at 90% C.L. on the WIMP annihilation rate in the Earth and the spin independent scattering cross-section of WIMPs to nucleons sigma(SI)(p) were calculated for WIMP pair annihilations into either iota(+) iota(-), W+W-, b (b) over bar or the non-SUSY v mu(v) over bar as a function of the WIMP mass (between 25 GeV/c(2) and 1000 GeV/c(2)) and as a function of the thermally averaged annihilation cross section times velocity (Earth) of the WIMPs in the centre of the Earth. For masses of the WIMP close to the mass of iron nuclei (50 GeV/c(2)), the obtained limits on sigma(SI)(p) are more stringent than those obtained by other indirect searches. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Dark matter; Neutrino telescope; ANTARES; Indirect detection; WIMP

Search for dark matter annihilation signals from the Fornax galaxy cluster with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; De Almeida, U. Barres; Becherini, Y.; Becker, J.; Behera, B.; Bernloehr, K.; et al. (Astrophysical Journal, 2012)
The Fornax galaxy cluster was observed with the High Energy Stereoscopic System for a total live time of 14.5hr, searching for very high energy (VHE; E > 100GeV) γ-rays from dark matter (DM) annihilation. No significant signal was found in searches for point-like and extended emissions. Using several models of the DM density distribution, upper limits on the DM velocity-weighted annihilation cross-section 〈σv〉 as a function of the DM particle mass are derived. Constraints are derived for different DM particle models, such as those arising from Kaluza-Klein and supersymmetric models. Various annihilation final states are considered. Possible enhancements of the DM annihilation γ-ray flux, due to DM substructures of the DM host halo, or from the Sommerfeld effect, are studied. Additional γ-ray contributions from internal bremsstrahlung and inverse Compton radiation are also discussed. For a DM particle mass of 1TeV, the exclusion limits at 95% of confidence level reach values of 〈σv〉 10 cm s, depending on the DM particle model and halo properties. Additional contribution from DM substructures can improve the upper limits on 〈σv〉 by more than two orders of magnitude. At masses around 4.5TeV, the enhancement by substructures and the Sommerfeld resonance effect results in a velocity-weighted annihilation cross-section upper limit at the level of 〈σv〉 10 cm s. © 2012. The American Astronomical Society. All rights reserved.

Search for Dark Matter Annihilation Signals from Unidentified Fermi-LAT Objects with HESS - Abdalla, H.; Spencer, Samuel; Aharonian, Felix; Ait Benkhali, F.; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Barbosa-Martins, V.; et al. (Astrophysical Journal, 2021)
Cosmological N-body simulations show that Milky Way-sized galaxies harbor a population of unmerged dark matter (DM) subhalos. These subhalos could shine in gamma-rays and eventually be detected in gamma-ray surveys as unidentified sources. We performed a thorough selection among unidentified Fermi-Large Area Telescope Objects (UFOs) to identify them as possible tera-electron-volt-scale DM subhalo candidates. We search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emissions using H.E.S.S. observations toward four selected UFOs. Since no significant very-high-energy gamma-ray emission is detected in any data set of the four observed UFOs or in the combined UFO data set, strong constraints are derived on the product of the velocity-weighted annihilation cross section sigma v by the J factor for the DM models. The 95% confidence level observed upper limits derived from combined H.E.S.S. observations reach sigma vJ values of 3.7 x 10(-5) and 8.1 x 10(-6) GeV(2 )cm(-2 )s(-1) in the W (+) W (-) and tau (+) tau (-) channels, respectively, for a 1 TeV DM mass. Focusing on thermal weakly interacting massive particles, the H.E.S.S. constraints restrict the J factors to lie in the range 6.1 x 10(19)-2.0 x 10(21) GeV(2 )cm(-5) and the masses to lie between 0.2 and 6 TeV in the W (+) W (-) channel. For the tau (+) tau (-) channel, the J factors lie in the range 7.0 x 10(19)-7.1 x 10(20) GeV(2 )cm(-5) and the masses lie between 0.2 and 0.5 TeV. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the DM models with masses >0.3 TeV for the UFO emissions can be ruled out at high confidence level.
CRIS-Team WoS Importer:2021-09-10

Search for Dark Matter Annihilation Signals in the H.E.S.S. Inner Galaxy Survey - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Armand, C.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; et al. (Physical Review Letters, 2022)
The central region of the Milky Way is one of the foremost locations to look for dark matter (DM) signatures. We report the first results on a search for DM particle annihilation signals using new observations from an unprecedented γ-ray survey of the Galactic Center (GC) region, i.e., the Inner Galaxy Survey, at very high energies (?100 GeV) performed with the H.E.S.S. array of five ground-based Cherenkov telescopes. No significant γ-ray excess is found in the search region of the 2014-2020 dataset and a profile likelihood ratio analysis is carried out to set exclusion limits on the annihilation cross section ?σv?
CRIS-Team Scopus Importer:2022-09-30

Search for dark matter annihilation signatures in H.E.S.S. observations of dwarf spheroidal galaxies - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2014)
Dwarf spheroidal galaxies of the Local Group are close satellites of the Milky Way characterized by a large mass-to-light ratio and are not expected to be the site of nonthermal high-energy gamma-ray emission or intense star formation. Therefore they are among the most promising candidates for indirect dark matter searches. During the last years the High Energy Stereoscopic System (H.E.S.S.) of imaging atmospheric Cherenkov telescopes observed five of these dwarf galaxies for more than 140 hours in total, searching for TeV gamma-ray emission from annihilation of dark matter particles. The new results of the deep exposure of the Sagittarius dwarf spheroidal galaxy, the first observations of the Coma Berenices and Fornax dwarves and the reanalysis of two more dwarf spheroidal galaxies already published by the H.E.S.S. Collaboration, Carina and Sculptor, are presented. In the absence of a significant signal new constraints on the annihilation cross section applicable to weakly interacting massive particles (WIMPs) are derived by combining the observations of the five dwarf galaxies. The combined exclusion limit depends on the WIMP mass and the best constraint is reached at 1-2 TeV masses with a cross-section upper bound of ∼3.9×10-24cm3s-1 at a 95% confidence level.

Search for Dark Matter Annihilations towards the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2016)
The inner region of the Milky Way halo harbors a large amount of dark matter (DM). Given its proximity, it is one of the most promising targets to look for DM. We report on a search for the annihilations of DM particles using gamma-ray observations towards the inner 300 pc of the Milky Way, with the H.E.S.S. array of ground-based Cherenkov telescopes. The analysis is based on a 2D maximum likelihood method using Galactic Center (GC) data accumulated by H.E.S.S. over the last 10 years (2004-2014), and does not show any significant gamma-ray signal above background. Assuming Einasto and Navarro-Frenk-White DM density profiles at the GC, we derive upper limits on the annihilation cross section <sigma nu="">. These constraints are the strongest obtained so far in the TeV DM mass range and improve upon previous limits by a factor 5. For the Einasto profile, the constraints reach <sigma nu=""> values of 6 x 10(-26) cm(3) s(-1) in the W+W- channel for a DM particle mass of 1.5 TeV, and 2 x 10(-26) cm(3) s(-1) in the tau(+)tau(-) channel for a 1 TeV mass. For the first time, ground-based gamma-ray observations have reached sufficient sensitivity to probe <sigma nu=""> values expected from the thermal relic density for TeV DM particles.</sigma></sigma></sigma>

Search for dark matter from the center of the Earth with 8 years of IceCube data - Renzi, Giovanni; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The nature of Dark Matter (DM) remains one of the most important unresolved questions of fundamental physics. Many models, including Weakly Interacting Massive Particles (WIMPs), assume DM to be a particle and predict a weak coupling with Standard Model matter. If DM particles can scatter off nuclei in the vicinity of a massive object such as a star or a planet, they may lose kinetic energy and become gravitationally trapped in the center of such objects, including Earth. As DM accumulates in the center of the Earth, self-annihilation of WIMPs into Standard Model particles can result in an excess of neutrinos which are detectable at the IceCube Neutrino Observatory, situated at the geographic South Pole. A search for excess neutrinos from these annihilations has been performed using 8 years of IceCube data, and results have been interpreted in the context of a number of WIMP annihilation channels (XX → τ+τ−/W+W−/bb¯) and masses ranging from 10 GeV to 10 TeV. We present the latest results from this analysis and compare the outcome with previous analyses by IceCube and other experiments, showing competitive results, which are even world-leading in some parts of the parameter space.
CRIS-Team Scopus Importer:2022-12-23

Search for dark matter towards the Galactic Centre with 11 years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Physics Letters B, 2020)
Neutrino detectors participate in the indirect search for the fundamental constituents of dark matter (DM) in form of weakly interacting massive particles (WIMPs). In WIMP scenarios, candidate DM particles can pair-annihilate into Standard Model products, yielding considerable fluxes of high-energy neutrinos. A detector like ANTARES, located in the Northern Hemisphere, is able to perform a complementary search looking towards the Galactic Centre, where a high density of dark matter is thought to accumulate. Both this directional information and the spectral features of annihilating DM pairs are entered into an unbinned likelihood method to scan the data set in search for DM-like signals in ANTARES data. Results obtained upon unblinding 3170 days of data reconstructed with updated methods are presented, which provides a larger, and more accurate, data set than a previously published result using 2101 days. A non-observation of dark matter is converted into limits on the velocity-averaged cross section for WIMP pair annihilation.
CRIS-Team Scopus Importer:2020-05-12
Keywords: ANTARES; Dark matter indirect detection; Galactic Centre; Neutrino telescope

Search for extended γ-ray emission around AGN with H.E.S.S. and Fermi -LAT - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2014)
Context. Very-high-energy (VHE; E > 100 GeV) γ-ray emission from blazars inevitably gives rise to electron-positron pair production through the interaction of these γ-rays with the extragalactic background light (EBL). Depending on the magnetic fields in the proximity of the source, the cascade initiated from pair production can result in either an isotropic halo around an initially beamed source or a magnetically broadened cascade flux. Aims. Both extended pair-halo (PH) and magnetically broadened cascade (MBC) emission from regions surrounding the blazars 1ES 1101-232, 1ES 0229+200, and PKS 2155-304 were searched for using VHE γ-ray data taken with the High Energy Stereoscopic System (H.E.S.S.) and high-energy (HE; 100 MeV < E < 100 GeV) γ-ray data with the Fermi Large Area Telescope (LAT). Methods. By comparing the angular distributions of the reconstructed γ-ray events to the angular profiles calculated from detailed theoretical models, the presence of PH and MBC was investigated. Results. Upper limits on the extended emission around 1ES 1101-232, 1ES 0229+200, and PKS 2155-304 are found to be at a level of a few per cent of the Crab nebula flux above 1 TeV, depending on the assumed photon index of the cascade emission. Assuming strong extra-Galactic magnetic field (EGMF) values, >10 G, this limits the production of pair haloes developing from electromagnetic cascades. For weaker magnetic fields, in which electromagnetic cascades would result in MBCs, EGMF strengths in the range (0.3-3) × 10 G were excluded for PKS 2155-304 at the 99% confidence level, under the assumption of a 1 Mpc coherence length. © ESO, 2014.
Keywords: BL Lacertae objects: individual: 1ES 0229+200; BL Lacertae objects: individual: 1ES 1101-232; BL Lacertae objects: individual: PKS 2155-304; Galaxies: magnetic fields; Gamma rays: galaxies; Intergalactic medium

Search for Galactic Core-collapse Supernovae in a Decade of Data Taken with the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Astrophysical Journal, 2024)
The IceCube Neutrino Observatory has been continuously taking data to search for O(0.5–10) s long neutrino bursts since 2007. Even if a Galactic core-collapse supernova is optically obscured or collapses to a black hole instead of exploding, it will be detectable via the O(10) MeV neutrino burst emitted during the collapse. We discuss a search for such events covering the time between 2008 April 17 and 2019 December 31. Considering the average data taking and analysis uptime of 91.7% after all selection cuts, this is equivalent to 10.735 yr of continuous data taking. In order to test the most conservative neutrino production scenario, the selection cuts were optimized for a model based on an 8.8 solar mass progenitor collapsing to an O–Ne–Mg core. Conservative assumptions on the effects of neutrino oscillations in the exploding star were made. The final selection cut was set to ensure that the probability to detect such a supernova within the Milky Way exceeds 99%. No such neutrino burst was found in the data after performing a blind analysis. Hence, a 90% C.L. upper limit on the rate of core-collapse supernovae out to distances of ≈25 kpc was determined to be 0.23 yr−1. For the more distant Magellanic Clouds, only high neutrino luminosity supernovae will be detectable by IceCube, unless external information on the burst time is available. We determined a model-independent limit by parameterizing the dependence on the neutrino luminosity and the energy spectrum.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Core-collapse supernovae (304); Neutrino telescopes (1105); Supernova neutrinos (1666)

Search for Gamma-Ray and Neutrino Coincidences Using HAWC and ANTARES Data - Solares, H. A.Ayala; Coutu, S.; Domi, Alba; Cowen, D.; Fox, D. B.; Grégoire, T.; McBride, F.; Mostafá, M.; Murase, K.; Wissel, S.; Zegarelli, A.; Albert, A.; et al. (Astrophysical Journal, 2023)
In the quest for high-energy neutrino sources, the Astrophysical Multimessenger Observatory Network has implemented a new search by combining data from the High Altitude Water Cherenkov (HAWC) Observatory and the Astronomy with a Neutrino Telescope and Abyss environmental RESearch (ANTARES) neutrino telescope. Using the same analysis strategy as in a previous detector combination of HAWC and IceCube data, we perform a search for coincidences in HAWC and ANTARES events that are below the threshold for sending public alerts in each individual detector. Data were collected between 2015 July and 2020 February with a live time of 4.39 yr. Over this time period, three coincident events with an estimated false-alarm rate of <1 coincidence per year were found. This number is consistent with background expectations.
CRIS-Team Scopus Importer:2023-03-10

Search for gamma-Ray Line Signals from Dark Matter Annihilations in the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2018)
Spectral lines are among the most powerful signatures for dark matter (DM) annihilation searches in very-high-energy gamma rays. The central region of the Milky Way halo is one of the most promising targets given its large amount of DM and proximity to Earth. We report on a search for a monoenergetic spectral line from self-annihilations of DM particles in the energy range from 300 GeV to 70 TeV using a two-dimensional maximum likelihood method taking advantage of both the spectral and spatial features of the signal versus background. The analysis makes use of Galactic center observations accumulated over ten years (2004-2014) with the H.E.S.S. array of ground-based Cherenkov telescopes. No significant gamma-ray excess above the background is found. We derive upper limits on the annihilation cross section (sigma v) for monoenergetic DM lines at the level of 4 x 10(-28) cm(3) s(-1) at 1 TeV, assuming an Einasto DM profile for the Milky Way halo. For a DM mass of 1 TeV, they improve over the previous ones by a factor of 6. The present constraints are the strongest obtained so far for DM particles in the mass range 300 GeV-70 TeV. Ground-based gamma-ray observations have reached sufficient sensitivity to explore relevant velocity-averaged cross sections for DM annihilation into two gamma-ray photons at the level expected from the thermal relic density for TeV DM particles.

Search for gamma-ray line signatures with H.E.S.S. - Kieffer, M.; Mora, K. D.; Conrad, J.; Farnier, C.; Jacholkowska, A.; Veh, Johannes; Viana, A. (Proceedings of Science, 2015)
Many results from astrophysical observations point to a 27% contribution of non-baryonic dark matter to the mass-energy budget of the universe. Although still elusive, strongly motivated candidates in form of weakly interactive massive particles could explain the nature of dark matter, and their annihilation or decay would give rise to detectable signatures in gamma-rays. In 2012, the H.E.S.S. collaboration started taking data with the largest imaging atmospheric Cherenkov telescope in the world which significantly lowered the energy threshold of the already operational four-telescope system. In particular, due to its location and improved performance at low energies, the H.E.S.S. experiment is now in a position to extend the search for dark matter line signals down to the 100 GeV mass range. The sensitivity to line searches with a new full likelihood approach will be discussed and preliminary results from observations with the second phase of H.E.S.S. will be presented.
CRIS-Team Scopus Importer:2024-02-15

Search for gamma rays from dark matter annihilations around intermediate mass black holes with the HESS experiment - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Bertone, G.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2008)
The HESS array of Cherenkov telescopes has performed, from 2004 to 2007, a survey of the inner galactic plane at photon energies above 100 GeV. About 400 hours of data have been accumulated in the region between -30 and +60degrees in galactic longitude, and between -3 and +3degrees in galactic latitude. Assuming that dark matter is composed of weakly interacting massive particles, we calculate here the HESS sensitivity map for dark matter annihilations, and derive the first experimental constraints on the ("minispikes") scenario, in which a gamma-ray signal arises from dark matter annihilation around intermediate mass black holes. The data exclude the proposed scenario at a 90% confidence level for dark matter particles with velocity-weighted annihilation cross section σv above 10-28cm3s-1 and mass between 800 GeV and 10 TeV. © 2008 The American Physical Society.

Search for GeV neutrino emission during intense gamma-ray solar flares with the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Physical Review D, 2021)
Solar flares convert magnetic energy into thermal and nonthermal plasma energy, the latter implying particle acceleration of charged particles such as protons. Protons are injected out of the coronal acceleration region and can interact with dense plasma in the lower solar atmosphere, producing mesons that subsequently decay into gamma rays and neutrinos at O(MeV-GeV) energies. We present the results of the first search for GeV neutrinos emitted during solar flares carried out with the IceCube Neutrino Observatory. While the experiment was originally designed to detect neutrinos with energies between 10 GeV and a few PeV, a new approach allowing for a O(GeV) energy threshold will be presented. The resulting limits allow us to constrain some of the theoretical estimates of the expected neutrino flux.
CRIS-Team Scopus Importer:2021-05-28

Search for GeV-scale dark matter annihilation in the Sun with IceCube DeepCore - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Physical Review D, 2022)
The Sun provides an excellent target for studying spin-dependent dark matter-proton scattering due to its high matter density and abundant hydrogen content. Dark matter particles from the Galactic halo can elastically interact with Solar nuclei, resulting in their capture and thermalization in the Sun. The captured dark matter can annihilate into Standard Model particles including an observable flux of neutrinos. We present the results of a search for low-energy (<500 GeV) neutrinos correlated with the direction of the Sun using 7 years of IceCube data. This work utilizes, for the first time, new optimized cuts to extend IceCube's sensitivity to dark matter mass down to 5 GeV. We find no significant detection of neutrinos from the Sun. Our observations exclude capture by spin-dependent dark matter-proton scattering with cross section down to a few times 10-41 cm2, assuming there is equilibrium with annihilation into neutrinos/antineutrinos for dark matter masses between 5 GeV and 100 GeV. These are the strongest constraints at GeV energies for dark matter annihilation directly to neutrinos.
CRIS-Team Scopus Importer:2022-04-22

Search for High-energy Neutrinos from Binary Neutron Star Merger GW170817 with ANTARES, IceCube, and the Pierre Auger Observatory - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal Letters, 2017)
The Advanced LIGO and Advanced Virgo observatories recently discovered gravitational waves from a binary neutron star inspiral. A short gamma-ray burst (GRB) that followed the merger of this binary was also recorded by the Fermi Gamma-ray Burst Monitor (Fermi-GBM), and the Anti-Coincidence Shield for the Spectrometer for the International Gamma-Ray Astrophysics Laboratory (INTEGRAL), indicating particle acceleration by the source. The precise location of the event was determined by optical detections of emission following the merger. We searched for high-energy neutrinos from the merger in the GeV-EeV energy range using the ANTARES, IceCube, and Pierre Auger Observatories. No neutrinos directionally coincident with the source were detected within +/- 500 s around the merger time. Additionally, no MeV neutrino burst signal was detected coincident with the merger. We further carried out an extended search in the direction of the source for high-energy neutrinos within the 14 day period following the merger, but found no evidence of emission. We used these results to probe dissipation mechanisms in relativistic outflows driven by the binary neutron star merger. The non-detection is consistent with model predictions of short GRBs observed at a large off-axis angle.
Keywords: gamma-ray burst: general; gravitational waves; neutrinos

Search for High-energy Neutrinos from Binary Neutron Star Merger GW170817 with ANTARES, IceCube, and the Pierre Auger Observatory - Domi, Alba; et al. (Astrophysical Journal Letters, 2017)
Keywords: gamma-ray burst: general; gravitational waves; neutrinos

Search for high-energy neutrinos from bright GRBs with ANTARES - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
Gamma-ray bursts are thought to be sites of hadronic acceleration, thus neutrinos are expected from the decay of charged particles, produced in p gamma interactions. The methods and results of a search for muon neutrinos in the data of the ANTARES neutrino telescope from four bright GRBs (GRB 080916C, GRB 110918A, GRB 130427A and GRB 130505A) observed between 2008 and 2013 are presented. Two scenarios of the fireball model have been investigated: the internal shock scenario, leading to the production of neutrinos with energies mainly above 100 TeV, and the photospheric scenario, characterized by a low-energy component in neutrino spectra due to the assumption of neutrino production closer to the central engine. Since no neutrino events have been detected in temporal and spatial coincidence with these bursts, upper limits at 90 per cent confidence level on the expected neutrino fluxes are derived. The non-detection allows for directly constraining the bulk Lorentz factor of the jet Gamma and the baryon loading f(p).
Keywords: acceleration of particles; neutrinos; gamma-ray burst: individual: GRB 080916C; gamma-ray burst: individual: GRB 110918A; gamma-ray burst: individual: GRB 130427A; gamma-ray burst: individual: GRB 130505A

Search for high-energy neutrinos from gravitational wave event GW151226 and candidate LVT151012 with ANTARES and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The Advanced LIGO observatories detected gravitational waves from two binary black hole mergers during their first observation run (O1). We present a high-energy neutrino follow-up search for the second gravitational wave event, GW151226, as well as for gravitational wave candidate LVT151012. We find two and four neutrino candidates detected by IceCube, and one and zero detected by ANTARES, within +/- 500 s around the respective gravitational wave signals, consistent with the expected background rate. None of these neutrino candidates are found to be directionally coincident with GW151226 or LVT151012. We use nondetection to constrain isotropic-equivalent high-energy neutrino emission from GW151226, adopting the GW event's 3D localization, to less than 2 x 10(51)-2 x 10(54) erg.

Search for High-energy Neutrinos from Ultraluminous Infrared Galaxies with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Astrophysical Journal, 2022)
Ultraluminous infrared galaxies (ULIRGs) have infrared luminosities L-IR >= 10(12) L-circle dot, making them the most luminous objects in the infrared sky. These dusty objects are generally powered by starbursts with star formation rates that exceed 100M(circle dot) yr(-1), possibly combined with a contribution from an active galactic nucleus. Such environments make ULIRGs plausible sources of astrophysical high-energy neutrinos, which can be observed by the IceCube Neutrino Observatory at the South Pole. We present a stacking search for high-energy neutrinos from a representative sample of 75 ULIRGs with redshift z <= 0.13 using 7.5 yr of IceCube data. The results are consistent with a background-only observation, yielding upper limits on the neutrino flux from these 75 ULIRGs. For an unbroken E-2.5 power-law spectrum, we report an upper limit on the stacked flux Phi(90%)(nu mu+(nu) over bar mu) = 3.24 x 10(-14) TeV-1 cm(-2) S-1 (E/10 TeV)(-2.5) at 90% confidence level. In addition, we constrain the contribution of the ULIRG source population to the observed diffuse astrophysical neutrino flux as well as model predictions.
CRIS-Team WoS Importer:2022-03-04

Search for magnetic monopoles with ten years of the ANTARES neutrino telescope - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Ardid, S.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Astrophysics, 2022)
This work presents a new search for magnetic monopoles using data taken with the ANTARES neutrino telescope over a period of 10 years (January 2008 to December 2017). Compared to previous ANTARES searches, this analysis uses a run-by-run simulation strategy, with a larger exposure as well as a new simulation of magnetic monopoles taking into account the Kasama, Yang and Goldhaber model for their interaction cross-section with matter. No signal compatible with the passage of relativistic magnetic monopoles is observed, and upper limits on the flux of magnetic monopoles with β=v/c≥0.55, are presented. For ultra-relativistic magnetic monopoles the flux limit is ∼7×10−18 cm−2s−1sr−1.
CRIS-Team Scopus Importer:2022-03-25
Keywords: ANTARES telescope; Magnetic monopoles; Neutrino

Search for Multi-flare Neutrino Emissions in 10 yr of IceCube Data from a Catalog of Sources - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Astrophysical Journal Letters, 2021)
A recent time-integrated analysis of a catalog of 110 candidate neutrino sources revealed a cumulative neutrino excess in the data collected by IceCube between 2008 April 6 and 2018 July 10. This excess, inconsistent with the background hypothesis in the Northern Hemisphere at the 3.3 sigma level, is associated with four sources: NGC 1068, TXS 0506+056, PKS 1424+240, and GB6 J1542+6129. This Letter presents two time-dependent neutrino emission searches on the same data sample and catalog: a point-source search that looks for the most significant time-dependent source of the catalog by combining space, energy, and time information of the events, and a population test based on binomial statistics that looks for a cumulative time-dependent neutrino excess from a subset of sources. Compared to previous time-dependent searches, these analyses enable a feature to possibly find multiple flares from a single direction with an unbinned maximum-likelihood method. M87 is found to be the most significant time-dependent source of this catalog at the level of 1.7 sigma post-trial, and TXS 0506+056 is the only source for which two flares are reconstructed. The binomial test reports a cumulative time-dependent neutrino excess in the Northern Hemisphere at the level of 3.0 sigma associated with four sources: M87, TXS 0506+056, GB6 J1542+6129, and NGC 1068.
CRIS-Team WoS Importer:2021-11-05

Search for Multimessenger Sources of Gravitational Waves and High-energy Neutrinos with Advanced LIGO during Its First Observing Run, ANTARES, and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin,; et al. (Astrophysical Journal, 2019)
Astrophysical sources of gravitational waves, such as binary neutron star and black hole mergers or core-collapse supernovae, can drive relativistic outflows, giving rise to non-thermal high-energy emission. High-energy neutrinos are signatures of such outflows. The detection of gravitational waves and high-energy neutrinos from common sources could help establish the connection between the dynamics of the progenitor and the properties of the outflow. We searched for associated emission of gravitational waves and high-energy neutrinos from astrophysical transients with minimal assumptions using data from Advanced LIGO from its first observing run O1, and data from the ANTARES and IceCube neutrino observatories from the same time period. We focused on candidate events whose astrophysical origins could not be determined from a single messenger. We found no significant coincident candidate, which we used to constrain the rate density of astrophysical sources dependent on their gravitational-wave and neutrino emission processes.
Keywords: gravitational waves; neutrinos

Search for muon-neutrino emission from GeV and TeV gamma-ray flaring blazars using five years of data of the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
The ANTARES telescope is well-suited for detecting astrophysical transient neutrino sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. The background due to atmospheric particles can be drastically reduced, and the point-source sensitivity improved, by selecting a narrow time window around possible neutrino production periods. Blazars, being radio-loud active galactic nuclei with their jets pointing almost directly towards the observer, are particularly attractive potential neutrino point sources, since they are among the most likely sources of the very high-energy cosmic rays. Neutrinos and gamma rays may be produced in hadronic interactions with the surrounding medium. Moreover, blazars generally show high time variability in their light curves at different wavelengths and on various time scales. This paper presents a time-dependent analysis applied to a selection of flaring gamma-ray blazars observed by the FERMI/LAT experiment and by TeV Cherenkov telescopes using five years of ANTARES data taken from 2008 to 2012. The results are compatible with fluctuations of the background. Upper limits on the neutrino fluence have been produced and compared to the measured gamma-ray spectral energy distribution.
Keywords: X-ray binaries; neutrino astronomy

Search for muon neutrinos from gamma-ray bursts with the ANTARES neutrino telescope using 2008 to 2011 data - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (Astronomy & Astrophysics, 2013)
Aims. We search for muon neutrinos in coincidence with GRBs with the ANTARES neutrino detector using data from the end of 2007 to 2011.Methods. Expected neutrino fluxes were calculated for each burst individually. The most recent numerical calculations of the spectra using the NeuCosmA code were employed, which include Monte Carlo simulations of the full underlying photohadronic interaction processes. The discovery probability for a selection of 296 GRBs in the given period was optimised using an extended maximum-likelihood strategy.Results. No significant excess over background is found in the data, and 90% confidence level upper limits are placed on the total expected flux according to the model.
Keywords: neutrinos; gamma-ray burst: general; methods: numerical

Search for neutrino counterparts of gravitational-wave events detected by LIGO and Virgo during run O2 with the ANTARES telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (European Physical Journal C: Particles and Fields, 2020)
An offline search for a neutrino counterpart to gravitational-wave (GW) events detected during the second observation run (O2) of Advanced-LIGO and Advanced-Virgo performed with ANTARES data is presented. In addition to the search for long tracks induced by νμ (ν¯ μ) charged current interactions, a search for showering events induced by interactions of neutrinos of any flavour is conducted. The severe spatial and time coincidence provided by the gravitational-wave alert allows regions above the detector horizon to be probed, extending the ANTARES sensitivity over the entire sky. The results of this all-neutrino-flavour and all-sky time dependent analysis are presented. The search for prompt neutrino emission within ±500 s around the time of six GW events yields no neutrino counterparts. Upper limits on the neutrino spectral fluence and constraints on the isotropic energy radiated via high-energy neutrinos (from a few TeV to a few tens of PeV) are set for each GW event analysed.
CRIS-Team Scopus Importer:2020-06-16

Search for neutrino emission from gamma-ray flaring blazars with the ANTARES telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope is well-suited to detect neutrinos produced in astrophysical transient sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. Radio-loud active galactic nuclei with jets pointing almost directly towards the observer, the so-called blazars, are particularly attractive potential neutrino point sources. The all-sky monitor LAT on board the Fermi satellite probes the variability of any given gamma-ray bright blazar in the sky on time scales of hours to months. Assuming hadronic models, a strong correlation between the gamma-ray and the neutrino fluxes is expected. Selecting a narrow time window on the assumed neutrino production period can significantly reduce the background.An unbinned method based on the minimization of a likelihood ratio was applied to a subsample of data collected in 2008 (61 days live time). By searching for neutrinos during the high state periods of the AGN light curve, the sensitivity to these sources was improved by about a factor of two with respect to a standard time-integrated point source search. First results on the search for neutrinos associated with ten bright and variable Fermi sources are presented. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Fermi LAT transient sources; Time-dependent search; Blazars

Search for Neutrinoless Double- β Decay with the Complete EXO-200 Dataset - Anton, Gisela; Badhrees, I.; Barbeau, P. S.; Beck, D.; Belov, V.; Bhatta, T.; Breidenbach, M.; Brunner, T.; Cao, G. F.; Cen, W. R.; Chambers, C.; Cleveland, B.; et al. (Physical Review Letters, 2019)
A search for neutrinoless double-β decay (0νββ) in Xe136 is performed with the full EXO-200 dataset using a deep neural network to discriminate between 0νββ and background events. Relative to previous analyses, the signal detection efficiency has been raised from 80.8% to 96.4±3.0%, and the energy resolution of the detector at the Q value of Xe136 0νββ has been improved from σ/E=1.23% to 1.15±0.02% with the upgraded detector. Accounting for the new data, the median 90% confidence level 0νββ half-life sensitivity for this analysis is 5.0×1025 yr with a total Xe136 exposure of 234.1 kg yr. No statistically significant evidence for 0νββ is observed, leading to a lower limit on the 0νββ half-life of 3.5×1025 yr at the 90% confidence level.
CRIS-Team Scopus Importer:2019-10-29

Search for Neutrinos from the Tidal Disruption Events AT2019dsg and AT2019fdr with the ANTARES Telescope - Albert, A.; Alves, S.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Astrophysical Journal, 2021)
On 2019 October 1, the IceCube Collaboration detected a muon track neutrino with a high probability of being of astrophysical origin, IC191001A. After a few hours, the tidal disruption event (TDE) AT2019dsg, observed by the Zwicky Transient Facility (ZTF), was indicated as the most likely counterpart of the IceCube track. More recently, the follow-up campaign of the IceCube alerts by ZTF suggested a second TDE, AT2019fdr, as a promising counterpart of another IceCube muon track candidate, IC200530A, detected on 2020 May 30. Here, these intriguing associations are followed-up by searching for neutrinos in the ANTARES detector from the directions of AT2019dsg and AT2019fdr using a time-integrated approach. As no significant evidence for space clustering is found in the ANTARES data, upper limits on the one-flavor neutrino flux and fluence are set.
CRIS-Team WoS Importer:2021-10-29

Search for non-standard neutrino interactions with 10 years of ANTARES data - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, G.; Ardid, M.; Ardid, S.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Physics, 2022)
Non-standard interactions of neutrinos arising in many theories beyond the Standard Model can significantly alter matter effects in atmospheric neutrino propagation through the Earth. In this paper, a search for deviations from the prediction of the standard 3-flavour atmospheric neutrino oscillations using the data taken by the ANTARES neutrino telescope is presented. Ten years of atmospheric neutrino data collected from 2007 to 2016, with reconstructed energies in the range from ∼16 GeV to 100 GeV, have been analysed. A log-likelihood ratio test of the dimensionless coefficients εμτ and εττ − εμμ does not provide clear evidence of deviations from standard interactions. For normal neutrino mass ordering, the combined fit of both coefficients yields a value 1.7σ away from the null result. However, the 68% and 95% confidence level intervals for εμτ and εττ − εμμ, respectively, contain the null value. Best fit values, one standard deviation errors and bounds at the 90% confidence level for these coefficients are given for both normal and inverted mass orderings. The constraint on εμτ is among the most stringent to date and it further restrains the strength of possible non-standard interactions in the μ − τ sector. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-07-22
Keywords: Neutrino Detectors and Telescopes (experiments)

Search for nuclearites with the ANTARES detector - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, G.; Ardid, M.; Ardid, S.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; et al. (Proceedings of Science, 2022)
ANTARES is a Cherenkov underwater neutrino telescope operating in the Mediterranean. Its construction was completed in 2008. Even though optimised for the search of cosmic neutrinos, this telescope is also sensitive to nuclearites (massive nuggets of strange quark matter [1]) trough the black body radiation emitted along their path [2]. We discuss here the possible detection of non-relativistic down-going nuclearites with the ANTARES telescope and present the results of an analysis using data collected from 2009 till 2017.
CRIS-Team Scopus Importer:2022-12-23

Search for PeV Gamma-Ray Emission from the Southern Hemisphere with 5 Yr of Data from the IceCube Observatory - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Astrophysical Journal, 2020)
The measurement of diffuse PeV gamma-ray emission from the Galactic plane would provide information about the energy spectrum and propagation of Galactic cosmic rays, and the detection of a pointlike source of PeV gamma-rays would be strong evidence for a Galactic source capable of accelerating cosmic rays up to at least a few PeV. This paper presents several unbinned maximum-likelihood searches for PeV gamma-rays in the Southern Hemisphere using 5 yr of data from the IceTop air shower surface detector and the in-ice array of the IceCube Observatory. The combination of both detectors takes advantage of the low muon content and deep shower maximum of gamma-ray air showers and provides excellent sensitivity to gamma-rays between ∼0.6 and 100 PeV. Our measurements of pointlike and diffuse Galactic emission of PeV gamma-rays are consistent with the background, so we constrain the angle-integrated diffuse gamma-ray flux from the Galactic plane at 2 PeV to 2.61 × 10-19 cm-2 s-1 TeV-1 at 90% confidence, assuming an E -3 spectrum, and we estimate 90% upper limits on pointlike emission at 2 PeV between 10-21 and 10-20 cm-2 s-1 TeV-1 for an E -2 spectrum, depending on decl. Furthermore, we exclude unbroken power-law emission up to 2 PeV for several TeV gamma-ray sources observed by the High Energy Spectroscopic System and calculate upper limits on the energy cutoffs of these sources at 90% confidence. We also find no PeV gamma-rays correlated with neutrinos from IceCube's high-energy starting event sample. These are currently the strongest constraints on PeV gamma-ray emission.
CRIS-Team Scopus Importer:2020-06-09

Search for photon-linelike signatures from dark matter annihilations with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Physical Review Letters, 2013)
Gamma-ray line signatures can be expected in the very-high-energy (E >100 GeV) domain due to self-annihilation or decay of dark matter (DM) particles in space. Such a signal would be readily distinguishable from astrophysical γ-ray sources that in most cases produce continuous spectra that span over several orders of magnitude in energy. Using data collected with the H.E.S.S. γ-ray instrument, upper limits on linelike emission are obtained in the energy range between ∼500 GeV and ∼25 TeV for the central part of the Milky Way halo and for extragalactic observations, complementing recent limits obtained with the Fermi-LAT instrument at lower energies. No statistically significant signal could be found. For monochromatic γ-ray line emission, flux limits of (2×107- 2×105) m2 s1 sr1 and (1×108-2×106) m2 s1 sr1 are obtained for the central part of the Milky Way halo and extragalactic observations, respectively. For a DM particle mass of 1 TeV, limits on the velocity-averaged DM annihilation cross section âŸ̈σvâŸ© reach ∼1027 cm3 s 1, based on the Einasto parametrization of the Galactic DM halo density profile. © 2013 American Physical Society.

Search for photon line-like signatures from Dark Matter annihilations with H.E.S.S. - van Eldik, Christopher; Nekrassov, Daniil (5th International Meeting on High Energy Gamma-Ray Astronomy, 2012)
Gamma-ray line signatures can be expected in the very-high-energy (E > 100GeV) domain due to annihilation or decay of Dark Matter particles in space. Such a signal would be readily distinguishable from astrophysical gamma-ray sources that in most cases produce continuous spectra which span over several orders of magnitude in energy. Using data collected by the H.E.S.S. gamma-ray instrument, upper limits on line emission and signatures produced by internal photon bremsstrahlung are obtained in the energy range between 500 GeV and 25 TeV for the central part of the Milky Way halo and for extragalactic observations, complementing recent limits obtained with the Fermi-LAT instrument at lower energies. For the process χχ → γγ, limits are derived on the velocity-averaged DM annihilation cross section < σν >, based on the Einasto parametrization of the Galactic DM halo. © 2012 American Institute of Physics.
Keywords: Dark matter: annihilation; Gamma rays: observations

Search for pulsed VHE gamma-ray emission from young pulsars with HESS - van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2007)
Aims. We present the results of a search for pulsed very-high-energy (VHE) γ-ray emission from young pulsars using data taken with the HESS imaging atmospheric Cherenkov telescope system. Methods. Data on eleven pulsars, selected according to their spin-down luminosity relative to distance, are searched for y-ray signals with periodicity at the respective pulsar spin period. Special analysis efforts were made to improve the sensitivity in the 100 GeV γ-ray energy domain in an attempt to reduce the gap between satellite and ground-based γ-ray instruments. Results. No significant evidence for pulsed emission is found in any data set. Differential upper limits on pulsed energy flux are determined for all selected pulsars in the approximate γ-ray energy range between 100 GeV and 50 TeV, using different limit determination methods, testing a wide range of possible pulsar light curves and energy spectra. Conclusions. The limits derived here imply that the magnetospheric VHE γ-ray production efficiency in young pulsars is less than 10 of the pulsar spin-down luminosity, requiring spectral turnovers for the high-energy emission of four established γ-ray pulsars, and constrain the inverse Compton radiation component predicted by several outer gap models. © ESO 2007.
Keywords: Gamma rays: observations; Pulsars: individual: Crab pulsar; Pulsars: individual: PSR B1259-63; Pulsars: individual: PSR B1509-58; Pulsars: individual: PSR B1706-44; Pulsars: individual: Vela pulsar

Search for quantum gravity using astrophysical neutrino flavour with IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Nature Physics, 2022)
Along their long propagation from production to detection, neutrinos undergo flavour conversions that convert their types or flavours1,2. High-energy astrophysical neutrinos propagate unperturbed over a billion light years in vacuum3 and are sensitive to small effects caused by new physics. Effects of quantum gravity4 are expected to appear at the Planck energy scale. Such a high-energy universe would have existed only immediately after the Big Bang and is inaccessible by human technologies. On the other hand, quantum gravity effects may exist in our low-energy vacuum5–8, but are suppressed by inverse powers of the Planck energy. Measuring the coupling of particles to such small effects is difficult via kinematic observables, but could be observable through flavour conversions. Here we report a search with the IceCube Neutrino Observatory, using astrophysical neutrino flavours9,10 to search for new space–time structure. We did not find any evidence of anomalous flavour conversion in the IceCube astrophysical neutrino flavour data. We apply the most stringent limits of any known technologies, down to 10−42 GeV−2 with Bayes factor greater than 10 on the dimension-six operators that parameterize the space–time defects. We thus unambiguously reach the parameter space of quantum-gravity-motivated physics.
CRIS-Team Scopus Importer:2022-11-04

Search for Relativistic Magnetic Monopoles with Eight Years of IceCube Data - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; Anderson, T.; et al. (Physical Review Letters, 2022)
We present an all-sky 90% confidence level upper limit on the cosmic flux of relativistic magnetic monopoles using 2886 days of IceCube data. The analysis was optimized for monopole speeds between 0.750c and 0.995c, without any explicit restriction on the monopole mass. We constrain the flux of relativistic cosmic magnetic monopoles to a level below 2.0 x 10(-19) cm(-2) s(-1) sr(-1) over the majority of the targeted speed range. This result constitutes the most strict upper limit to date for magnetic monopoles with beta > 0.8 and up to beta similar to 0.995 and fills the gap between existing limits on the cosmic flux of nonrelativistic and ultrarelativistic magnetic monopoles.
CRIS-Team WoS Importer:2022-02-18

Search for relativistic magnetic monopoles with five years of the ANTARES detector data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Journal of High Energy Physics, 2017)
A search for magnetic monopoles using five years of data recorded with the ANTARES neutrino telescope from January 2008 to December 2012 with a total live time of 1121 days is presented. The analysis is carried out in the range beta > 0.6 of magnetic monopole velocities using a strategy based on run-by-run Monte Carlo simulations. No signal above the background expectation from atmospheric muons and atmospheric neutrinos is observed, and upper limits are set on the magnetic monopole flux ranging from 5.7 x 10(-16) to 1.5 x 10(-18) cm(-2).s(-1).sr(-1).
Keywords: Exotics; Neutrino Detectors and Telescopes (experiments)

Search for relativistic magnetic monopoles with the ANTARES neutrino telescope - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; et al. (Astroparticle Physics, 2012)
Magnetic monopoles are predicted in various unified gauge models and could be produced at intermediate mass scales. Their detection in a neutrino telescope is facilitated by the large amount of light emitted compared to that from muons. This paper reports on a search for upgoing relativistic magnetic monopoles with the ANTARES neutrino telescope using a data set of 116 days of live time taken from December 2007 to December 2008. The one observed event is consistent with the expected atmospheric neutrino and muon background, leading to a 90% C.L. upper limit on the monopole flux between 1.3 x 10-(17) and 8.9 x 10(-17) CM-2 s(-1) sr(-1) for monopoles with velocity beta >= 0.625. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic monopole; Neutrino telescopes; ANTARES

Search for sources of astrophysical neutrinos using seven years of icecube cascade events - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (Astrophysical Journal, 2019)
Low-background searches for astrophysical neutrino sources anywhere in the sky can be performed using cascade events induced by neutrinos of all flavors interacting in IceCube with energies as low as ∼1 TeV. Previously we showed that, even with just two years of data, the resulting sensitivity to sources in the southern sky is competitive with IceCube and ANTARES analyses using muon tracks induced by charge current muon neutrino interactions - especially if the neutrino emission follows a soft energy spectrum or originates from an extended angular region. Here, we extend that work by adding five more years of data, significantly improving the cascade angular resolution, and including tests for point-like or diffuse Galactic emission to which this data set is particularly well suited. For many of the signal candidates considered, this analysis is the most sensitive of any experiment to date. No significant clustering was observed, and thus many of the resulting constraints are the most stringent to date. In this paper we will describe the improvements introduced in this analysis and discuss our results in the context of other recent work in neutrino astronomy.
CRIS-Team Scopus Importer:2020-02-21

Search for Spatial Correlations of Neutrinos with Ultra-high-energy Cosmic Rays - Albert, A.; Domi, Alba; Alves, S.; Andre, M.; Anghinolfi, M.; Ardid, S.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Astrophysical Journal, 2022)
For several decades, the origin of ultra-high-energy cosmic rays (UHECRs) has been an unsolved question of high-energy astrophysics. One approach for solving this puzzle is to correlate UHECRs with high-energy neutrinos, since neutrinos are a direct probe of hadronic interactions of cosmic rays and are not deflected by magnetic fields. In this paper, we present three different approaches for correlating the arrival directions of neutrinos with the arrival directions of UHECRs. The neutrino data are provided by the IceCube Neutrino Observatory and ANTARES, while the UHECR data with energies above similar to 50 EeV are provided by the Pierre Auger Observatory and the Telescope Array. All experiments provide increased statistics and improved reconstructions with respect to our previous results reported in 2015. The first analysis uses a high-statistics neutrino sample optimized for point-source searches to search for excesses of neutrino clustering in the vicinity of UHECR directions. The second analysis searches for an excess of UHECRs in the direction of the highest-energy neutrinos. The third analysis searches for an excess of pairs of UHECRs and highest-energy neutrinos on different angular scales. None of the analyses have found a significant excess, and previously reported overfluctuations are reduced in significance. Based on these results, we further constrain the neutrino flux spatially correlated with UHECRs.
CRIS-Team WoS Importer:2022-08-26

Search for steady point-like sources in the astrophysical muon neutrino flux with 8 years of IceCube data - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Altmann, D.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (European Physical Journal C, 2019)
The IceCube Collaboration has observed a high-energy astrophysical neutrino flux and recently found evidence for neutrino emission from the blazar TXS 0506+056. These results open a new window into the high-energy universe. However, the source or sources of most of the observed flux of astrophysical neutrinos remains uncertain. Here, a search for steady point-like neutrino sources is performed using an unbinned likelihood analysis. The method searches for a spatial accumulation of muon-neutrino events using the very high-statistics sample of about 497,000 neutrinos recorded by IceCube between 2009 and 2017. The median angular resolution is approximate to 1 degrees at 1 TeV and improves to approximate to 0.3 degrees for neutrinos with an energy of 1 PeV. Compared to previous analyses, this search is optimized for point-like neutrino emission with the same flux-characteristics as the observed astrophysical muon-neutrino flux and introduces an improved event-reconstruction and parametrization of the background. The result is an improvement in sensitivity to the muon-neutrino flux compared to the previous analysis of approximate to 35% assuming an E-2 spectrum. The sensitivity on the muon-neutrino flux is at a level of E2dN/dE=310-13s-1. No new evidence for neutrino sources is found in a full sky scan and in an a priori candidate source list that is motivated by gamma-ray observations. Furthermore, no significant excesses above background are found from populations of sub-threshold sources. The implications of the non-observation for potential source classes are discussed.
CRIS-Team WoS Importer:2019-03-29

Search for Sterile Neutrinos with KM3NeT/ORCA and ANTARES - Domi, Alba; et al. (36th International Cosmic Ray Conference, ICRC 2019, 2021)

Search for sub-TeV Neutrino Emission from Novae with IceCube-DeepCore - Abbasi, R.; Ackermann, M.; Adams, J.; Aggarwal, N.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Astrophysical Journal, 2023)
The understanding of novae, the thermonuclear eruptions on the surfaces of white dwarf stars in binaries, has recently undergone a major paradigm shift. Though the bolometric luminosity of novae was long thought to arise directly from photons supplied by the thermonuclear runaway, recent gigaelectronvolt (GeV) gamma-ray observations have supported the notion that a significant portion of the luminosity could come from radiative shocks. More recently, observations of novae have lent evidence that these shocks are acceleration sites for hadrons for at least some types of novae. In this scenario, a flux of neutrinos may accompany the observed gamma rays. As the gamma rays from most novae have only been observed up to a few GeV, novae have previously not been considered as targets for neutrino telescopes, which are most sensitive at and above teraelectronvolt (TeV) energies. Here, we present the first search for neutrinos from novae with energies between a few GeV and 10 TeV using IceCube-DeepCore, a densely instrumented region of the IceCube Neutrino Observatory with a reduced energy threshold. We search both for a correlation between gamma-ray and neutrino emission as well as between optical and neutrino emission from novae. We find no evidence for neutrino emission from the novae considered in this analysis and set upper limits for all gamma-ray detected novae.
CRIS-Team Scopus Importer:2023-12-01

Search for TeV gamma-ray emission from GRB 100621A, an extremely bright GRB in X-rays, with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2014)
The long gamma-ray burst (GRB) 100621A, at the time the brightest X-ray transient ever detected by Swift-XRT in the 0.3-10 keV range, has been observed with the H.E.S.S. imaging air Cherenkov telescope array, sensitive to gamma radiation in the very-high-energy (VHE, >100 GeV) regime. Due to its relatively small redshift of z 0.5, the favourable position in the southern sky and the relatively short follow-up time (<700 s after the satellite trigger) of the H.E.S.S. observations, this GRB could be within the sensitivity reach of the H.E.S.S. instrument. The analysis of the H.E.S.S. data shows no indication of emission and yields an integral flux upper limit above 380 GeV of 4.2 × 10 cm s (95% confidence level), assuming a simple Band function extension model. A comparison to a spectral-temporal model, normalised to the prompt flux at sub-MeV energies, constraints the existence of a temporally extended and strong additional hard power law, as has been observed in the other bright X-ray GRB 130427A. A comparison between the H.E.S.S. upper limit and the contemporaneous energy output in X-rays constrains the ratio between the X-ray and VHE gamma-ray fluxes to be greater than 0.4. This value is an important quantity for modelling the afterglow and can constrain leptonic emission scenarios, where leptons are responsible for the X-ray emission and might produce VHE gamma rays. © 2014 ESO.
Keywords: Gamma rays: general; Gamma rays: stars; Gamma-ray burst: individual: GRB 100621A; X-rays: stars

Search for the flavor-changing neutral current decay D0 → μ+μ- with the HERA-B detector - van Eldik, Christopher; et al. (Physics Letters B, 2004)
We report on a search for the flavor-changing neutral current decay D0→μ+μ- using 50×106 events recorded with a dimuon trigger in interactions of 920 GeV protons with nuclei by the HERA-B experiment. We find no evidence for such decays and set a 90% confidence level upper limit on the branching fraction B(D0→μ+μ-)<2.0×10-6. © 2004 Elsevier B.V.
Keywords: 13.20.Fc; 14.40.Lb; Decays of charmed mesons; FCNC

Search for transient optical counterparts to high-energy IceCube neutrinos with Pan-STARRS1 - Kankare, E.; Huber, M.; Smartt, S. J.; Chambers, K.; Smith, K. W.; Mcbrien, O.; Chen, T-W; Flewelling, H.; Lowe, T.; Magnier, E.; Schultz, A.; Waters, C.; et al. (Astronomy & Astrophysics, 2019)
In order to identify the sources of the observed diffuse high-energy neutrino flux, it is crucial to discover their electromagnetic counterparts. To increase the sensitivity of detecting counterparts of transient or variable sources by telescopes with a limited field of view, IceCube began releasing alerts for single high-energy (Eνâ> â60 TeV) neutrino detections with sky localisation regions of order 1° radius in 2016. We used Pan-STARRS1 to follow-up five of these alerts during 2016-2017 to search for any optical transients that may be related to the neutrinos. Typically 10-20 faint (miP1âââ22.5 mag) extragalactic transients are found within the Pan-STARRS1 footprints and are generally consistent with being unrelated field supernovae (SNe) and AGN. We looked for unusual properties of the detected transients, such as temporal coincidence of explosion epoch with the IceCube timestamp, or other peculiar light curve and physical properties. We found only one transient that had properties worthy of a specific follow-up. In the Pan-STARRS1 imaging for IceCube-160427A (probability to be of astrophysical origin of ∼50%), we found a SN PS16cgx, located at 10.0′ from the nominal IceCube direction. Spectroscopic observations of PS16cgx showed that it was an H-poor SN at redshift zâ=â0.2895â ±â 0.0001. The spectra and light curve resemble some high-energy Type Ic SNe, raising the possibility of a jet driven SN with an explosion epoch temporally coincident with the neutrino detection. However, distinguishing Type Ia and Type Ic SNe at this redshift is notoriously difficult. Based on all available data we conclude that the transient is more likely to be a Type Ia with relatively weak Siâ» II absorption and a fairly normal rest-frame r-band light curve. If, as predicted, there is no high-energy neutrino emission from Type Ia SNe, then PS16cgx must be a random coincidence, and unrelated to the IceCube-160427A. We find no other plausible optical transient for any of the five IceCube events observed down to a 5σ limiting magnitude of miP1â≈â22 mag, between 1 day and 25 days after detection.
CRIS-Team Scopus Importer:2019-07-12
Keywords: Astroparticle physics; Neutrinos; Supernovae: general

Search for Unstable Sterile Neutrinos with the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; Anton, Gisela; et al. (Physical Review Letters, 2022)
We present a search for an unstable sterile neutrino by looking for a resonant signal in eight years of atmospheric νμ data collected from 2011 to 2019 at the IceCube Neutrino Observatory. Both the (stable) three-neutrino and the 3+1 sterile neutrino models are disfavored relative to the unstable sterile neutrino model, though with p values of 2.8% and 0.81%, respectively, we do not observe evidence for 3+1 neutrinos with neutrino decay. The best-fit parameters for the sterile neutrino with decay model from this study are Δm412=6.7-2.5+3.9 eV2, sin22θ24=0.33-0.17+0.20, and g2=2.5π±1.5π, where g is the decay-mediating coupling. The preferred regions of the 3+1+decay model from short-baseline oscillation searches are excluded at 90% C.L.
CRIS-Team Scopus Importer:2022-10-28

Search for very-high-energy γ-ray emission from Galactic globular clusters with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2013)
Context. Globular clusters (GCs) are established emitters of high-energy (HE, 100 MeV < E < 100 GeV) γ-ray radiation which could originate from the cumulative emission of the numerous millisecond pulsars (msPSRs) in the clusters' cores or from inverse Compton (IC) scattering of relativistic leptons accelerated in the GC environment. These stellar clusters could also constitute a new class of sources in the very-high-energy (VHE, E > 100 GeV) γ-ray regime, judging from the recent detection of a signal from the direction of Terzan 5 with the H.E.S.S. telescope array. Aims. To search for VHE γ-ray sources associated with other GCs, and to put constraints on leptonic emission models, we systematically analyzed the observations towards 15 GCs taken with the H.E.S.S. array of imaging atmospheric Cherenkov telescopes. Methods. We searched for point-like and extended VHE γ-ray emission from each GC in our sample and also performed a stacking analysis combining the data from all GCs to investigate the hypothesis of a population of faint emitters. Assuming IC emission as the origin of the VHE γ-ray signal from the direction of Terzan 5, we calculated the expected γ-ray flux from each of the 15 GCs, based on their number of millisecond pulsars, their optical brightness and the energy density of background photon fields. Results. We did not detect significant VHE γ-ray emission from any of the 15 GCs in either of the two analyses. Given the uncertainties related to the parameter determinations, the obtained flux upper limits allow to rule out the simple IC/msPSR scaling model for NGC 6388 and NGC 7078. The upper limits derived from the stacking analyses are factors between 2 and 50 below the flux predicted by the simple leptonic scaling model, depending on the assumed source extent and the dominant target photon fields. Therefore, Terzan 5 still remains exceptional among all GCs, as the VHE γ-ray emission either arises from extra-ordinarily efficient leptonic processes, or from a recent catastrophic event, or is even unrelated to the GC itself. © 2013 ESO.
Keywords: Gamma rays: general; Globular clusters: general; Pulsars: general; Radiation mechanisms: non-thermal

Searching for TeV Gamma-Ray Emission from SGR 1935+2154 during Its 2020 X-Ray and Radio Bursting Phase - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Astrophysical Journal, 2021)
Magnetar hyperflares are the most plausible explanation for fast radio bursts (FRBs)-enigmatic powerful radio pulses with durations of several milliseconds and high brightness temperatures. The first observational evidence for this scenario was obtained in 2020 April when an FRB was detected from the direction of the Galactic magnetar and soft gamma-ray repeater SGR 1935+2154. The FRB was preceded by two gamma-ray outburst alerts by the BAT instrument aboard the Swift satellite, which triggered follow-up observations by the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observed SGR 1935+2154 for 2 hr on 2020 April 28. The observations are coincident with X-ray bursts from the magnetar detected by INTEGRAL and Fermi-GBM, thus providing the first very high energy gamma-ray observations of a magnetar in a flaring state. High-quality data acquired during these follow-up observations allow us to perform a search for short-time transients. No significant signal at energies E > 0.6 TeV is found, and upper limits on the persistent and transient emission are derived. We here present the analysis of these observations and discuss the obtained results and prospects of the H.E.S.S. follow-up program for soft gamma-ray repeaters.
CRIS-Team WoS Importer:2021-10-08

Search of dark matter annihilation in the galactic centre using the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
A search for high-energy neutrinos coming from the direction of the Galactic Centre is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria are chosen to maximise the sensitivity to possible signals produced by the self-annihilation of weakly interacting massive particles accumulated around the centre of the Milky Way with respect to the atmospheric background. After data unblinding, the number of neutrinos observed in the line of sight of the Galactic Centre is found to be compatible with background expectations. The 90% C.L. upper limits in terms of the neutrino+anti-neutrino flux, Phi(nu mu + (nu) over bar mu), and the velocity averaged annihilation cross-section, , are derived for the WIMP self-annihilation channels into b (b) over bar; W+W-; tau(+)tau(-); mu(+)mu(-); nu(nu) over bar. The ANTARES limits for are shown to be the most stringent for a neutrino telescope over the WIMP masses 25 GeV < M-WIMP < 10TeV.
Keywords: neutrino experiments; dark matter experiments; neutrino astronomy

Sensitivity of the Cherenkov Telescope Array to a dark matter signal from the Galactic centre - Acharyya, A.; Adam, R.; van Eldik, Christopher; Spencer, Samuel; Adams, C.; Agudo, I.; Aguirre-Santaella, A.; Alfaro, R.; Alfaro, J.; Alispach, C.; Aloisio, R.; Alves Batista, R.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
We provide an updated assessment of the power of the Cherenkov Telescope Array (CTA) to search for thermally produced dark matter at the TeV scale, via the associated gamma-ray signal from pair-annihilating dark matter particles in the region around the Galactic centre. We find that CTA will open a new window of discovery potential, significantly extending the range of robustly testable models given a standard cuspy profile of the dark matter density distribution. Importantly, even for a cored profile, the projected sensitivity of CTA will be sufficient to probe various well-motivated models of thermally produced dark matter at the TeV scale. This is due to CTA's unprecedented sensitivity, angular and energy resolutions, and the planned observational strategy. The survey of the inner Galaxy will cover a much larger region than corresponding previous observational campaigns with imaging atmospheric Cherenkov telescopes. CTA will map with unprecedented precision the large-scale diffuse emission in high-energy gamma rays, constituting a background for dark matter searches for which we adopt state-of-the-art models based on current data. Throughout our analysis, we use up-to-date event reconstruction Monte Carlo tools developed by the CTA consortium, and pay special attention to quantifying the level of instrumental systematic uncertainties, as well as background template systematic errors, required to probe thermally produced dark matter at these energies.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Dark matter experiments; Dark matter theory; Galaxy morphology; Gamma ray experiments

Sensitivity of the KM3NeT/ARCA neutrino telescope to point-like neutrino sources - Aiello, S.; Akrame, S. E.; Ameli, F.; G. Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Bagatelas, C.; et al. (Astroparticle Physics, 2019)
KM3NeT will be a network of deep-sea neutrino telescopes in the Mediterranean Sea. The KM3NeT/ARCA detector, to be installed at the Capo Passero site (Italy), is optimised for the detection of high-energy neutrinos of cosmic origin. Thanks to its geographical location on the Northern hemisphere, KM3NeT/ARCA can observe upgoing neutrinos from most of the Galactic Plane, including the Galactic Centre. Given its effective area and excellent pointing resolution, KM3NeT/ARCA will measure or significantly constrain the neutrino flux from potential astrophysical neutrino sources. At the same time, it will test flux predictions based on gamma-ray measurements and the assumption that the gamma-ray flux is of hadronic origin. Assuming this scenario, discovery potentials and sensitivities for a selected list of Galactic sources and to generic point sources with an E −2 spectrum are presented. These spectra are assumed to be time independent. The results indicate that an observation with 3σ significance is possible in about six years of operation for the most intense sources, such as Supernovae Remnants RX J1713.7-3946 and Vela Jr. If no signal will be found during this time, the fraction of the gamma-ray flux coming from hadronic processes can be constrained to be below 50% for these two objects.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Astrophysical neutrino sources; Cherenkov underwater neutrino telescope; KM3NeT

Sensitivity studies for the IceCube-Gen2 radio array - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory at the South Pole has measured the diffuse astrophysical neutrino flux up to ∼PeV energies and is starting to identify first point source candidates. The next generation facility, IceCube-Gen2, aims at extending the accessible energy range to EeV in order to measure the continuation of the astrophysical spectrum, to identify neutrino sources, and to search for a cosmogenic neutrino flux. As part of IceCube-Gen2, a radio array is foreseen that is sensitive to detect Askaryan emission of neutrinos beyond ∼30 PeV. Surface and deep antenna stations have different benefits in terms of effective area, resolution, and the capability to reject backgrounds from cosmic-ray air showers and may be combined to reach the best sensitivity. The optimal detector configuration is still to be identified. This contribution presents the full-array simulation efforts for a combination of deep and surface antennas, and compares different design options with respect to their sensitivity to fulfill the science goals of IceCube-Gen2.
CRIS-Team Scopus Importer:2023-08-15

Sensitivity to light sterile neutrino mixing parameters with KM3NeT/ORCA - Aiello, S.; Albert, A.; Alshamsi, M.; Garre, S. Alves; Aly, Z.; Ambrosone, Antonio; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (Journal of High Energy Physics, 2021)
KM3NeT/ORCA is a next-generation neutrino telescope optimised for atmospheric neutrino oscillations studies. In this paper, the sensitivity of ORCA to the presence of a light sterile neutrino in a 3+1 model is presented. After three years of data taking, ORCA will be able to probe the active-sterile mixing angles theta(14), theta(24), theta(34) and the effective angle theta(mu e), over a broad range of mass squared difference Delta m(41)(2) similar to [10(-5), 10] eV(2), allowing to test the eV-mass sterile neutrino hypothesis as the origin of short baseline anomalies, as well as probing the hypothesis of a very light sterile neutrino, not yet constrained by cosmology. ORCA will be able to explore a relevant fraction of the parameter space not yet reached by present measurements.
CRIS-Team WoS Importer:2021-11-12

Simulation and sensitivities for a phased IceCube-Gen2 deployment - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The IceCube Neutrino Observatory opened the window on high-energy neutrino astronomy by confirming the existence of PeV astrophysical neutrinos and identifying the first compelling astrophysical neutrino source in the blazar TXS0506+056. Planning is underway to build an enlarged detector, IceCube-Gen2, which will extend measurements to higher energies, increase the rate of observed cosmic neutrinos and provide improved prospects for detecting fainter sources. IceCube-Gen2 is planned to have an extended in-ice optical array, a radio array at shallower depths for detecting ultra-high-energy (>100 PeV) neutrinos, and a surface component studying cosmic rays. In this contribution, we will discuss the simulation of the in-ice optical component of the baseline design of the IceCube-Gen2 detector, which foresees the deployment of an additional ∼ 120 new detection strings to the existing 86 in IceCube over ∼ 7 Antarctic summer seasons. Motivated by the phased construction plan for IceCube-Gen2, we discuss how the reconstruction capabilities and sensitivities of the instrument are expected to progress throughout its deployment.
CRIS-Team Scopus Importer:2023-08-15

Simulation of diffusive particle propagation and related TeV γ-ray emission at the Galactic Center - van Eldik, Christopher; Ziegler, Alexander (34th International Cosmic Ray Conference (ICRC2015), 2015)

Simulation studies for large scale acoustic neutrino detectors - Kießling, Dominik; Lahmann, Robert (8TH INTERNATIONAL CONFERENCE ON ACOUSTIC AND RADIO EEV NEUTRINO DETECTION ACTIVITIES (ARENA 2018), 2019)
CRIS-Team WoS Importer:2020-10-30

Simulation study for the future IceCube-Gen2 surface array - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; Andeen, K.; et al. (Proceedings of Science, 2022)
The next generation of the IceCube Neutrino Observatory, IceCube-Gen2, will constitute a much larger detector, increasing the rate of high-energy neutrinos. IceCube-Gen2 will address the long-standing questions about astrophysical accelerators. The experiment will also include a surface air-shower detector which will allow for measurements of cosmic rays in the energy region where a transition between Galactic and extragalactic accelerators is expected. As a baseline design for the surface detector, we consider a surface array above the optical in-ice array consisting of the same type of stations used for the IceTop enhancement, i.e., scintillation detectors and radio antennas. In order to better understand the capabilities of such an array, we performed simulations of its response to air showers, including both detector types. We will show the results of this simulation study and discuss the prospects for the surface array of IceCube-Gen2.
CRIS-Team Scopus Importer:2023-08-15

Simultaneous HESS and Chandra observations of Sagitarius A during an X-ray flare - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
The rapidly varying ( 10 min timescale) non-thermal X-ray emission observed from Sgr A implies that particle acceleration is occuring close to the event horizon of the supermassive black hole. The TeV γ-ray source HESSJ1745-290 is coincident with Sgr A* and may be closely related to its X-ray emission. Simultaneous X-ray and TeV observations are required to elucidate the relationship between these objects. We report on joint HESS/Chandra observations performed in July 2005, during which an X-ray flare was detected. Despite a factor of ≈9 increase in the X-ray flux of Sgr A*, no evidence is found for an increase in the TeV γ-ray flux from this region. We find that an increase in the γ-ray flux of a factor of 2 or greater can be excluded at a confidence level of 99%. This finding disfavours scenarios in which the keV and TeV emission are associated with the same population of accelerated particles and in which the bulk of the γ-ray emission is produced within ∼ cm (∼100 Rs) of the supermassive black hole. © 2008 ESO.
Keywords: Gamma rays: observations; X-rays: individuals: Sgr A

Simultaneous multiwavelength observations of the second exceptional γ-ray flare of PKS 2155-304 in July 2006 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Keywords: galaxies: active; galaxies: BL Lacertae objects: individual: PKS 2155-304; gamma rays: observations; X-rays: galaxies

Spectral analysis and interpretation of the γ-ray emission from the starburst galaxy NGC253 - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; Biteau, J.; et al. (Astrophysical Journal, 2012)
Very high energy (VHE; E ≥ 100 GeV) and high-energy (HE; 100 MeV ≤ E ≤ 100 GeV) data from γ-ray observations performed with the H.E.S.S. telescope array and the Fermi-LAT instrument, respectively, are analyzed in order to investigate the non-thermal processes in the starburst galaxy NGC253. The VHE γ-ray data can be described by a power law in energy with differential photon index Γ = 2.14 ± 0.18 ± 0.30 and differential flux normalization at 1TeV of F = (9.6 ± 1.5(+ 5.7, -2.9)) × 10 TeV cm s. A power-law fit to the differential HE γ-ray spectrum reveals a photon index of Γ = 2.24 ± 0.14 ± 0.03 and an integral flux between 200MeV and 200GeV of F(0.2-200 GeV) = (4.9 ± 1.0 ± 0.3) × 10 cm s. No evidence for a spectral break or turnover is found over the dynamic range of both the LAT instrument and the H.E.S.S. experiment: a combined fit of a power law to the HE and VHE γ-ray data results in a differential photon index Γ = 2.34 ± 0.03 with a p-value of 30%. The γ-ray observations indicate that at least about 20% of the energy of the cosmic rays (CRs) capable of producing hadronic interactions is channeled into pion production. The smooth alignment between the spectra in the HE and VHE γ-ray domain suggests that the same transport processes dominate in the entire energy range. Advection is most likely responsible for charged particle removal from the starburst nucleus from GeV to multiple TeV energies. In a hadronic scenario for the γ-ray production, the single overall power-law spectrum observed would therefore correspond to the mean energy spectrum produced by the ensemble of CR sources in the starburst region. © 2012. The American Astronomical Society. All rights reserved.
Keywords: convection; diffusion; galaxies: individual (NGC 253); galaxies: starburst; gamma rays: galaxies; radiation mechanisms: non-thermal

Spectrum and variability of the Galactic center VHE γ-ray source HESS J1745-290 - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Aims. A detailed study of the spectrum and variability of the source HESS J1745-290 in the Galactic Center (GC) region using new data from the H.E.S.S. array of Cherenkov telescopes is presented. Flaring activity and quasi periodic oscillations (QPO) of HESS J1745-290 are investigated. Methods. The image analysis is performed with a combination of a semi-analytical shower model and the statistical moment-based Hillas technique. The spectrum and lightcurves of HESS J1745-290 are derived with a likelihood method based on a spectral shape hypothesis. Rayleigh tests and Fourier analysis of the H.E.S.S. GC signal are used to study the periodicity of the source. Results. With a three-fold increase in statistics compared to previous work, a deviation from a simple power law spectrum is detected for the first time. The measured energy spectrum over the three years 2004, 2005 and 2006 of data taking is compatible with both a power law spectrum with an exponential cut-off and a broken power law spectrum. The curvature of the energy spectrum is likely to be intrinsic to the photon source, as opposed to effects of interstellar absorption. The power law spectrum with an exponential cut-off is characterized by a photon index of 2.10 ± 0.04 ± 0.10 and a cut-off energy at 15.7 ± 3.4±2.5 TeV. The broken power law spectrum exhibits spectral indices of 2.02 ± 0.08 ± 0.10 and 2.63 ± 0.14 ± 0.10 with a break energy at 2.57 ± 0.19stat ± 0.44 TeV. No significant flux variation is found. Increases in the γ-ray flux of HESS J1745-290 by at least a factor of two would be required for a 3cr detection of a flare with time scales of an hour. Investigation of possible QPO activity at periods claimed to be detected in X-rays does not show any periodicities in the H.E.S.S. signal. © ESO 2009.
Keywords: Galaxy: center; gamma rays: observations; methods: data analysis

Sperm whale long-range echolocation sounds revealed by ANTARES, a deep-sea neutrino telescope - Andre, Michel; Caballe, A.; Van Der Schaar, M.; Solsona, A.; Houegnigan, L.; Zaugg, S.; Sanchez, A. M.; Castell, J. V.; Sole, Marta; Vila, F.; Djokic, D.; Adrian-Martinez, S.; et al. (Scientific Reports, 2017)
Despite dedicated research has been carried out to adequately map the distribution of the sperm whale in the Mediterranean Sea, unlike other regions of the world, the species population status is still presently uncertain. The analysis of two years of continuous acoustic data provided by the ANTARES neutrino telescope revealed the year-round presence of sperm whales in the Ligurian Sea, probably associated with the availability of cephalopods in the region. The presence of the Ligurian Sea sperm whales was demonstrated through the real-time analysis of audio data streamed from a cabled-to-shore deep-sea observatory that allowed the hourly tracking of their long-range echolocation behaviour on the Internet. Interestingly, the same acoustic analysis indicated that the occurrence of surface shipping noise would apparently not condition the foraging behaviour of the sperm whale in the area, since shipping noise was almost always present when sperm whales were acoustically detected. The continuous presence of the sperm whale in the region confirms the ecological value of the Ligurian sea and the importance of ANTARES to help monitoring its ecosystems.

Stabilizing quasicrystals composed of patchy colloids by narrowing the patch width - Gemeinhardt, Anja; Martinsons, Miriam; Schmiedeberg, Michael (EPL - Europhysics Letters, 2019)
We explore the behavior of two-dimensional patchy colloidal particles with 8 or 10 symmetrically arranged patches by employing Monte Carlo simulations. The particles interact according to an isotropic pair potential that possesses only one typical length. The patches lead to additional attractions that are anisotropic and depend on the relative orientation of two neighboring particles. We investigate the assembled structures with a special interest in quasicrystals. We found that the patch width is of great importance: Only in the case of narrow patch widths we are able to observe metastable octagonal and decagonal quasicrystals, while dodecagonal quasicrystals can also occur for broad patches. These results are important to understand the role of interactions with preferred binding angles in order to obtain quasicrystals. Our findings suggest that in the case of sharp binding angles, as they occur in metallic alloys, octagonal and decagonal symmetries might be observed more often than in systems with less sharp binding angles as it is the case in soft-matter systems where dodecagonal quasicrystals dominate.

Statistical biases of spectral analysis with the ON-OFF likelihood statistic - Jouvin, L.; Lemière, A.; Terrier, R.; Ohm, S.; Oya, I.; van Eldik, Christopher (34th International Cosmic Ray Conference (ICRC2015), 2015)
Spectral extraction in data from ground-based gamma-ray observations is usually performed using the on-off likelihood statistic which is based on the profile likelihood technique. The latter is known to lead to inconsistent estimators in some situations. We present here a systematic Monte Carlo study of the distribution of fitted spectral parameters for typical observations with VHE (very high energy; >100GeV) observatories and show that in some conditions spectral extraction yields inconsistent estimators. We discuss some techniques to alleviate this effect and the impact on the search for spectral cutoffs in the very low statistic regime.

Status of the photomultiplier-based FlashCam camera for the Cherenkov Telescope Array - Puehlhofer, Gerd; Jung-Richardt, Ira; Kalekin, Oleg; Lahmann, Robert; et al. (Proceedings of SPIE, 2014)

Status of the Real-time Multi-messenger Program of KM3NeT - Lincetto, Massimiliano; Dornic, Damien; Huang, Feifei; Schnabel, Jutta (2022)

Status of the technologies for the production of the Cherenkov telescope array (CTA) mirrors - Pareschi, Giovanni; Armstrong, T.; Baba, H.; Baehr, J.; Bonardi, A.; Bonnoli, Giacomo; Brun, P.; Canestrari, Rodolfo; Chadwick, Paula; Chikawa, M.; Carton, P. -H.; De Souza, V.; et al. (Optics for EUV, X-Ray, and Gamma-Ray Astronomy VI, 2013)
The Cherenkov Telescope Array (CTA) is the next generation very high-energy gamma-ray observatory, with at least 10 times higher sensitivity than current instruments. CTA will comprise several tens of Imaging Atmospheric Cherenkov Telescopes (IACTs) operated in array-mode and divided into three size classes: large, medium and small telescopes. The total reflective surface could be up to 10,000 m requiring unprecedented technological efforts. The properties of the reflector directly influence the telescope performance and thus constitute a fundamental ingredient to improve and maintain the sensitivity. The R&D status of lightweight, reliable and cost-effective mirror facets for the CTA telescope reflectors for the different classes of telescopes is reviewed in this paper. © 2013 SPIE.
Keywords: Cherenkov Telescope Array; Cherenkov Telescopes; mirrors; reflecting coatings

Strong Constraints on Neutrino Nonstandard Interactions from TeV-Scale ν_μ Disappearance at IceCube - Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alameddine, J. M.; Alispach, C.; Alves, A. A.; Amin, N. M.; Andeen, K.; Anderson, T.; et al. (Physical Review Letters, 2022)
We report a search for nonstandard neutrino interactions (NSI) using eight years of TeV-scale atmospheric muon neutrino data from the IceCube Neutrino Observatory. By reconstructing incident energies and zenith angles for atmospheric neutrino events, this analysis presents unified confidence intervals for the NSI parameter ε_μτ. The best-fit value is consistent with no NSI at a p value of 25.2%. With a 90% confidence interval of -0.0041≤ε_μτ≤0.0031 along the real axis and similar strength in the complex plane, this result is the strongest constraint on any NSI parameter from any oscillation channel to date.
CRIS-Team Scopus Importer:2022-08-05

Studies towards an understanding of global array pointing for the cherenkov telescope array - Eschbach, Stefan; Ziegler, Alexander; van Eldik, Christopher; Veh, Johannes; Berge, David; Gaug, Markus (34th International Cosmic Ray Conference (ICRC2015), 2015)
Current arrays of Imaging Atmospheric Cherenkov Telescopes (IACTs) routinely achieve an astrometric point-source location accuracy of 20-30 seconds of arc (given large photon statistics), which is well below the angular resolution obtained for individual photons. The location accuracy is mainly limited by systematic uncertainties due to possible deformations of the telescopes' structures, causing a mis-orientation between the nominal optical axes of the telescopes and their actual pointing directions. Usually, only a subset of telescopes is triggered for a given gammaray event, and their mis-orientations enter the gamma-ray direction reconstruction in a combined manner. Hence, in general, the average location accuracy for a set of gamma-ray observations depends in a complex way on the individual telescope accuracy and the geometry of the array, but also on the observing conditions, the energy spectrum of the source and the chosen event selection cuts. For the proposed Cherenkov Telescope Array (CTA), a post-calibration point-source location accuracy of 3 seconds of arc is aimed for under favorable observing conditions and for gamma-ray energies exceeding 100 GeV. In this contribution, results of first studies on the location accuracy are presented. These studies are based on a toy Monte Carlo simulation of a typical CTA-South array layout, taking into account the expected trigger rates of the different CTA telescope types and the gamma-ray spectrum of the simulated source. With this simulation code it is possible to study the location accuracy as a function of arbitrary telescope mis-orientations and for typical observing patterns on the sky. Results are presented for various scenarios, including one for which all individual telescopes are randomly mis-oriented within their specified limits. The study provides solid lower limits for the expected source location accuracy of CTA, and can be easily extended to include various other important effects like atmospheric refraction or partial cloud coverage.

Super-ORCA: Measuring the leptonic CP-phase with atmospheric neutrinos and beam neutrinos - Hofestädt, Jannik; Bruchner, Marc; Eberl, Thomas (Proceedings of Science, 2019)
Studying the atmospheric neutrino oscillation probabilities below 2 GeV with a multi-megaton Cherenkov detector allows for a measurement of the leptonic CP-phase dCP. The most relevant CP-sensitive energy range is below the neutrino detection threshold of KM3NeT/ORCA, which is an underwater Cherenkov detector optimised to determine the neutrino mass ordering by measuring the oscillation pattern of 3-30 GeV atmospheric neutrinos. With Super-ORCA, a 10 times more-densely instrumented version of ORCA, the detection threshold can be lowered and the event reconstruction capabilities improved. In this paper, the key detector performance indicators for a possible Super-ORCA detector and the sensitivity to dCP with atmospheric neutrinos are presented. Including systematics, a 1s-resolution on dCP of about 38? (23?) is achieved for dCP = 0 (dCP = p/2) after 10 years. In addition, the potential of using a neutrino beam from the Protvino accelerator facility to the Super-ORCA detector is discussed. With this, a 1s-resolution on dCP of about 10? (16?) is achieved for dCP = 0 (dCP = p/2) after 10 years.
CRIS-Team Scopus Importer:2021-04-20

TANAMI blazars in the IceCube PeV-neutrino fields - Krauß, Felicia; Kadler, Matthias; Mannheim, K.; Schulz, Robert; Truestedt, J.; Wilms, Jörn; Ojha, R.; Ros, Eduardo; Anton, Gisela; Baumgartner, W.; Beuchert, Tobias; Blanchard, J.; et al. (Astronomy & Astrophysics, 2014)
The IceCube Collaboration has announced the discovery of a neutrino flux in excess of the atmospheric background. Owing to the steeply falling atmospheric background spectrum, events at PeV energies most likely have an extraterrestrial origin. We present the multiwavelength properties of the six radio-brightest blazars that are positionally coincident with these events using contemporaneous data of the TANAMI blazar sample, including high-resolution images and spectral energy distributions. Assuming the X-ray to gamma-ray emission originates in the photoproduction of pions by accelerated protons, the integrated predicted neutrino luminosity of these sources is high enough to explain the two detected PeV events.
Keywords: neutrinos; galaxies: active; quasars: general

TANAMI: Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry - Mueller, C.; Kadler, M.; Ojha, R.; Schulz, Robert; Truestedt, J.; Edwards, P. G.; Ros, E.; Carpenter, B.; Angioni, R.; Blanchard, J.; Böck, Moritz; Burd, P. R.; et al. (Astronomy & Astrophysics, 2018)
Context. TANAMI is a multiwavelength program monitoring active galactic nuclei (AGN) south of -30 degrees declination including high-resolution very long baseline interferometry (VLBI) imaging, radio, optical/UV, X-ray, and gamma-ray studies. We have previously published first-epoch 8.4 GHz VLBI images of the parsec-scale structure of the initial sample. In this paper, we present images of 39 additional sources. The full sample comprises most of the radio-and gamma-ray brightest AGN in the southern quarter of the sky, overlapping with the region from which high-energy (>100 TeV) neutrino events have been found.Aims. We characterize the parsec-scale radio properties of the jets and compare them with the quasi-simultaneous Fermi/LAT gamma-ray data. Furthermore, we study the jet properties of sources which are in positional coincidence with high-energy neutrino events compared to the full sample. We test the positional agreement of high-energy neutrino events with various AGN samples.Methods. TANAMI VLBI observations at 8.4 GHz are made with southern hemisphere radio telescopes located in Australia, Antarctica, Chile, New Zealand, and South Africa.Results. Our observations yield the first images of many jets below -30 degrees declination at milliarcsecond resolution. We find that gamma-ray loud TANAMI sources tend to be more compact on parsec-scales and have higher core brightness temperatures than gamma-ray faint jets, indicating higher Doppler factors. No significant structural difference is found between sources in positional coincidence with high-energy neutrino events and other TANAMI jets. The 22 gamma-ray brightest AGN in the TANAMI sky show only a weak positional agreement with high-energy neutrinos demonstrating that the >100 TeV IceCube signal is not simply dominated by a small number of the gamma-ray brightest blazars. Instead, a larger number of sources have to contribute to the signal with each individual source having only a small Poisson probability for producing an event in multi-year integrations of current neutrino detectors.
Keywords: galaxies: active; galaxies: jets; galaxies: nuclei; radio continuum: galaxies; techniques: high angular resolution; neutrinos

TANAMI: tracking active galactic nuclei with austral milliarcsecond interferometry I. First-epoch 8.4GHz images - Ojha, R.; Kadler, Matthias; Böck, Moritz; Booth, R.; Dutka, M. S.; Edwards, P. G.; Fey, A. L.; Fuhrmann, L.; Gaume, R. A.; Hase, H.; Horiuchi, S.; Jauncey, D. L.; et al. (Astronomy & Astrophysics, 2010)
Context. A number of theoretical models vie to explain the gamma-ray emission from active galactic nuclei (AGN). This was a key discovery of EGRET. With its broader energy coverage, higher resolution, wider field of view and greater sensitivity, the Large Area Telescope (LAT) of the Fermi Gamma-ray Space Telescope is dramatically increasing our knowledge of AGN gamma-ray emission. However, discriminating between competing theoretical models requires quasi-simultaneous observations across the electromagnetic spectrum. By resolving the powerful parsec-scale relativistic outflows in extragalactic jets and thereby allowing us to measure critical physical properties, Very Long Baseline Interferometry observations are crucial to understanding the physics of extragalactic gamma-ray objects.Aims. We introduce the TANAMI program (Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry) which is monitoring an initial sample of 43 extragalactic jets located south of -30 degrees declination at 8.4GHz and 22GHz since 2007. All aspects of the program are discussed. First epoch results at 8.4GHz are presented along with physical parameters derived therefrom.Methods. These observations were made during 2007/2008 using the telescopes of the Australian Long Baseline Array in conjunction with Hartebeesthoek in South Africa. These data were correlated at the Swinburne University correlator.Results. We present first epoch images for 43 sources, some observed for the first time at milliarcsecond resolution. Parameters of these images as well as physical parameters derived from them are also presented and discussed. These and subsequent images from the TANAMI survey are available at http://pulsar.sternwarte.uni-erlangen.de/tanami/.Conclusions. We obtain reliable, high dynamic range images of the southern hemisphere AGN. All the quasars and BL Lac objects in the sample have a single-sided radio morphology. Galaxies are either double-sided, single-sided or irregular. About 28% of the TANAMI sample has been detected by LAT during its first three months of operations. Initial analysis suggests that when galaxies are excluded, sources detected by LAT have larger opening angles than those not detected by LAT. Brightness temperatures of LAT detections and non-detections seem to have similar distributions. The redshift distributions of the TANAMI sample and sub-samples are similar to those seen for the bright gamma-ray AGN seen by LAT and EGRET but none of the sources with a redshift above 1.8 have been detected by LAT.
Keywords: galaxies: active; galaxies: jets; galaxies: nuclei; gamma rays: observations; quasars: general

Targeting ultra-high energy neutrinos with the ARIANNA experiment - Anker, A.; Barwick, S. W.; Bernhoff, H.; Besson, D. Z.; Bingefors, N.; Gaswint, G.; Glaser, C.; Hallgren, A.; Hanson, J. C.; Lahmann, Robert; Latif, U.; Nam, J.; et al. (Advances in Space Research, 2019)
The measurement of ultra-high energy (UHE) neutrinos (E > 1016 eV) opens a new field of astronomy with the potential to reveal the sources of ultra-high energy cosmic rays especially if combined with observations in the electromagnetic spectrum and gravitational waves. The ARIANNA pilot detector explores the detection of UHE neutrinos with a surface array of independent radio detector stations in Antarctica which allows for a cost-effective instrumentation of large volumes. Twelve stations are currently operating successfully at the Moore's Bay site (Ross Ice Shelf) in Antarctica and at the South Pole. We will review the current state of ARIANNA and its main results. We report on a newly developed wind generator that successfully operates in the harsh Antarctic conditions and powers the station for a substantial time during the dark winter months. The robust ARIANNA surface architecture, combined with environmentally friendly solar and wind power generators, can be installed at any deep ice location on the planet and operated autonomously. We report on the detector capabilities to determine the neutrino direction by reconstructing the signal arrival direction of a 800 m deep calibration pulser, and the reconstruction of the signal polarization using the more abundant cosmic-ray air showers. Finally, we describe a large-scale design – ARIA – that capitalizes on the successful experience of the ARIANNA operation and is designed sensitive enough to discover the first UHE neutrino.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Antarctica; ARIANNA; Askaryan radiation; Cosmic ray; Neutrino; Radio

TAROGE-M: radio antenna array on antarctic high mountain for detecting near-horizontal ultra-high energy air showers - Wang, Shih-Hao; Nam, Jiwoo; Chen, Pisin; Chen, Yaocheng; Choi, Taejin; Ham, Young-Bae; Hsu, Shih-Ying; Huang, Jian-Jung; Huang, Ming-Huey A.; Jee, Geonhwa; Jung, Jongil; Kim, Jieun; et al. (Journal of Cosmology and Astroparticle Physics, 2022)
The TAROGE-M radio observatory is a self-triggered antenna array on top of the similar to 2700m high Mt. Melbourne in Antarctica, designed to detect impulsive geomagnetic emission from extensive air showers induced by ultra-high energy (UHE) particles beyond 1017 eV, including cosmic rays, Earth-skimming tau neutrinos, and particularly, the "ANITA anomalous events" (AAE) from near and below the horizon. The six AAE discovered by the ANITA experiment have signal features similar to tau neutrinos but that hypothesis is in tension either with the interaction length predicted by Standard Model or with the flux limits set by other experiments. Their origin remains uncertain, requiring more experimental inputs for clarification. The detection concept of TAROGE-M takes advantage of a high altitude with synoptic view toward the horizon as an efficient signal collector, and the radio quietness as well as strong and near vertical geomagnetic field in Antarctica, enhancing the relative radio signal strength. This approach has a low energy threshold, high duty cycle, and is easy to extend for quickly enlarging statistics. Here we report experimental results from the first TAROGEM station deployed in January 2020, corresponding to approximately one month of livetime. The station consists of six receiving antennas operating at 180-450 MHz, and can reconstruct source directions of impulsive events with an angular resolution of similar to 0.3 ffi, calibrated in situ with a drone-borne pulser system. To demonstrate TAROGE-M's ability to detect UHE air showers, a search for cosmic ray signals in 25.3-days of data together with the detection simulation were conducted, resulting in seven identified candidates. The detected events have a mean reconstructed energy of 0.95+0.46 -0.31 EeV and zenith angles ranging from 25 ffi to 82 ffi, with both distributions agreeing with the simulations, indicating an energy threshold at about 0.3 EeV. The estimated cosmic ray flux at that energy is 1.2+0.7 -0.9x10(-16) eV(-1) km(-2) yr(-1) sr(-1), also consistent with results of other experiments. The TAROGE-M sensitivity to AAEs is approximated by the tau neutrino exposure with simulations, which suggests comparable sensitivity as ANITA's at around 1 EeV energy with a few station-years of operation. These first results verified the station design and performance in a polar and high-altitude environment, and are promising for further discovery of tau neutrinos and AAEs after an extension in the near future.
CRIS-Team WoS Importer:2023-05-26

TAROGE-M: Radio Observatory on Antarctic High Mountain for Detecting Near-Horizon Ultra-High Energy Air Showers - Wang, Shih Hao; Chen, Pisin; Chen, Yaocheng; Huang, Jian Jung; Huang, Ming Huey Alfred; Kuo, Chung Yun; Leung, Chung Hei; Liu, Tsung Che; Nam, Jiwoo; Shiao, Yu Shao Jerry; Wang, Min Zu; Wang, Shih Hao; et al. (Proceedings of Science, 2022)
The TAROGE-M observatory is an autonomous antenna array on the top of Mt. Melbourne (∼2700 m altitude) in Antarctica, designed to detect radio pulses from ultra-high energy (over 1017 eV) air showers coming from near-horizon directions. The targeted sources include cosmic rays, Earth-skimming tau neutrinos, and most of all, the anomalous near-horizon upward-going events of yet unknown origin discovered by ANITA experiments. The detection concept follows that of ANITA: monitoring large area of ice from high-altitude and taking advantage of strong geomagnetic field and quiet radio background in Antarctica, whereas having significantly greater livetime and scalability. The TAROGE-M station, upgraded from its prototype built in 2019, was deployed in January 2020, and consists of 6 log-periodic dipole antennas pointing horizontally with bandwidth of 180-450 MHz. The station is then calibrated with drone-borne transmitter, with which the event reconstruction obtained ∼0.3° angular resolution. The station was then smoothly operating in the following month, with the live time of ∼ 30 days, before interrupted by a power problem, and its online filtering has identified several candidate cosmic-ray events and sent out via satellite communication. In this paper, the instrumentation of the station for polar and high-altitude environment, its radio-locating performance, the preliminary result on cosmic-ray detection, and the future extension plan are presented.
CRIS-Team Scopus Importer:2023-08-15

TeV Emission of Galactic Plane Sources with HAWC and HESS - Abdalla, H.; Mitchell, Alison; Aharonian, Felix; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cherenkov (HAWC) observatory and the High Energy Stereoscopic System (H.E.S.S.) are two leading instruments in the ground-based very-high-energy gamma-ray domain. HAWC employs the water Cherenkov detection (WCD) technique, while H.E.S.S. is an array of Imaging Atmospheric Cherenkov Telescopes (IACTs). The two facilities therefore differ in multiple aspects, including their observation strategy, the size of their field of view, and their angular resolution, leading to different analysis approaches. Until now, it has been unclear if the results of observations by both types of instruments are consistent: several of the recently discovered HAWC sources have been followed up by IACTs, resulting in a confirmed detection only in a minority of cases. With this paper, we go further and try to resolve the tensions between previous results by performing a new analysis of the H.E.S.S. Galactic plane survey data, applying an analysis technique comparable between H.E.S.S. and HAWC. Events above 1 TeV are selected for both data sets, the point-spread function of H.E.S.S. is broadened to approach that of HAWC, and a similar background estimation method is used. This is the first detailed comparison of the Galactic plane observed by both instruments. H.E.S.S. can confirm the gamma-ray emission of four HAWC sources among seven previously undetected by IACTs, while the three others have measured fluxes below the sensitivity of the H.E.S.S. data set. Remaining differences in the overall gamma-ray flux can be explained by the systematic uncertainties. Therefore, we confirm a consistent view of the gamma-ray sky between WCD and IACT techniques.
CRIS-Team WoS Importer:2021-08-20

TeV Gamma-Ray Observations of the Binary Neutron Star Merger GW170817 with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; Becherini, Y.; et al. (Astrophysical Journal Letters, 2017)
We search for high-energy gamma-ray emission from the binary neutron star merger GW170817 with the H.E.S.S. Imaging Air Cherenkov Telescopes. The observations presented here have been obtained starting only 5.3 hr after GW170817. The H.E.S.S. target selection identified regions of high probability to find a counterpart of the gravitational-wave event. The first of these regions contained the counterpart SSS17a that has been identified in the optical range several hours after our observations. We can therefore present the first data obtained by a ground-based pointing instrument on this object. A subsequent monitoring campaign with the H.E.S.S. telescopes extended over several days, covering timescales from 0.22 to 5.2 days and energy ranges between 270 GeV to 8.55 TeV. No significant gamma-ray emission has been found. The derived upper limits on the very-high-energy gamma-ray flux for the first time constrain non-thermal, high-energy emission following the merger of a confirmed binary neutron star system.
CRIS-Team WoS Importer:2020-01-15

TeV γ-ray observations of the young synchrotron-dominated SNRs G1.9+0.3 and G330.2+1.0 with H.E.S.S. - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
The non-thermal nature of the X-ray emission from the shell-type supernova remnants (SNRs) G1.9+0.3 and G330.2+1.0 is an indication of intense particle acceleration in the shock fronts of both objects. This suggests that the SNRs are prime candidates for very-high-energy (VHE; E > 0.1 TeV) γ -ray observations. G1.9+0.3, recently established as the youngest known SNR in the Galaxy, also offers a unique opportunity to study the earliest stages of SNR evolution in the VHE domain. The purpose of this work is to probe the level of VHE γ -ray emission from both SNRs and use this to constrain their physical properties. Observations were conducted with the H.E.S.S. (High Energy Stereoscopic System) Cherenkov Telescope Array over a more than six-year period spanning 2004-2010. The obtained data have effective livetimes of 67 h for G1.9+0.3 and 16 h for G330.2+1.0. The data are analysed in the context of the multiwavelength observations currently available and in the framework of both leptonic and hadronic particle acceleration scenarios. No significant γ -ray signal from G1.9+0.3 or G330.2+1.0 was detected. Upper limits (99 per cent confidence level) to the TeV flux from G1.9+0.3 and G330.2+1.0 for the assumed spectral index Γ = 2.5 were set at 5.6 × 10 cm s above 0.26 TeV and 3.2 × 10 cm s above 0.38 TeV, respectively. In a one-zone leptonic scenario, these upper limits imply lower limits on the interior magnetic field to B ≳ 12 μG for G1.9+0.3 and to B ≳ 8 μG for G330.2+1.0. In a hadronic scenario, the low ambient densities and the large distances to the SNRs result in very low predicted fluxes, for which the H.E.S.S. upper limits are not constraining. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Gamma-rays: ISM; ISM: magnetic fields; ISM: supernova remnants; Radiation mechanisms: non-thermal

The 2012 flare of PG 1553+113 seen with H.E.S.S. and Fermi-lat - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, Anna; Becherini, Y.; Tjus, J. Becker; Berge, D.; et al. (Astrophysical Journal, 2015)
Very high energy (VHE, E > 100 GeV) γ-ray flaring activity of the high-frequency peaked BL Lac object PG 1553+113 has been detected by the H.E.S.S. telescopes. The flux of the source increased by a factor of 3 during the nights of 2012 April 26 and 27 with respect to the archival measurements with a hint of intra-night variability. No counterpart of this event has been detected in the Fermi-Large Area Telescope data. This pattern is consistent with VHE γ-ray flaring being caused by the injection of ultrarelativistic particles, emitting γ-rays at the highest energies. The dataset offers a unique opportunity to constrain the redshift of this source at z = 0.49 ± 0.04 using a novel method based on Bayesian statistics. The indication of intra-night variability is used to introduce a novel method to probe for a possible Lorentz invariance violation (LIV), and to set limits on the energy scale at which Quantum Gravity (QG) effects causing LIV may arise. For the subluminal case, the derived limits are E,1 > 4.10 × 10 GeV and E,2 > 2.10 × 10 GeV for linear and quadratic LIV effects, respectively.
Keywords: BL Lacertae objects: individual (PG 1553+113); galaxies: active; galaxies: distances and redshifts; gamma-rays: galaxies

The 2014 TeV γ-Ray Flare of Mrk 501 Seen with H.E.S.S.: Temporal and Spectral Constraints on Lorentz Invariance Violation - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astrophysical Journal, 2019)
The blazar Mrk 501 (z = 0.034) was observed at very-high-energy (VHE, E ≳ 100 GeV) gamma-ray wavelengths during a bright flare on the night of 2014 June 23-24 (MJD 56832) with the H.E.S.S. phase-II array of Cherenkov telescopes. Data taken that night by H.E.S.S. at large zenith angle reveal an exceptional number of gamma-ray photons at multi-TeV energies, with rapid flux variability and an energy coverage extending significantly up to 20 TeV. This data set is used to constrain Lorentz invariance violation (LIV) using two independent channels: a temporal approach considers the possibility of an energy dependence in the arrival time of gamma-rays, whereas a spectral approach considers the possibility of modifications to the interaction of VHE gamma-rays with extragalactic background light (EBL) photons. The non-detection of energy-dependent time delays and the non-observation of deviations between the measured spectrum and that of a supposed power-law intrinsic spectrum with standard EBL attenuation are used independently to derive strong constraints on the energy scale of LIV (E QG ) in the subluminal scenario for linear and quadratic perturbations in the dispersion relation of photons. For the case of linear perturbations, the 95% confidence level limits obtained are E QG,1 > 3.6 ×10 17 GeV using the temporal approach and E QG,1 > 2.6 ×10 19 GeV using the spectral approach. For the case of quadratic perturbations, the limits obtained are E QG,2 > 8.5 ×10 10 GeV using the temporal approach and E QG,2 > 7.8 ×10 11 GeV using the spectral approach.
CRIS-Team Scopus Importer:2019-05-14
Keywords: astroparticle physics; BL Lacertae objects: individual (Mrk 501); gamma rays: galaxies

The ANTARES telescope neutrino alert system - Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope has the capability to detect neutrinos produced in astrophysical transient sources. Potential sources include gamma-ray bursts, core collapse supernovae, and flaring active galactic nuclei. To enhance the sensitivity of ANTARES to such sources, a new detection method based on coincident observations of neutrinos and optical signals has been developed. A fast online muon track reconstruction is used to trigger a network of small automatic optical telescopes. Such alerts are generated for special events, such as two or more neutrinos, coincident in time and direction, or single neutrinos of very high energy. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Transient sources; Optical follow-up

The calibration units of KM3NeT - Le Breton, R.; Billault, M.; Boutonnet, C.; Champion, C.; Colonges, S.; Cosquer, A.; Creusot, A.; Henry, S.; Ilioni, A.; Keller, P.; Lagier, P.; Lahmann, Robert; et al. (Journal of Instrumentation, 2021)
KM3NeT is a deep-sea infrastructure composed of two neutrino telescopes being deployed in the Mediterranean Sea: ARCA, near Sicily in Italy, designed for neutrino astronomy, and ORCA, near Toulon in France, designed for neutrino oscillation physics. To achieve the best performance, the exact location of the optical modules, affected by sea current, must be known at any time and the timing resolution between optical modules must reach the nanosecond. Moreover, the properties of the environment in which the telescopes are deployed must be continuously monitored because they affect the timing and positioning calibration. KM3NeT is going to deploy several dedicated Calibration Units to meet these calibration goals. Because of the difference in size between ARCA and ORCA, the design of the Calibration Unit is not the same for the two sites. This proceeding describes all the devices, features and purposes of the Calibration Units with a focus on the ORCA Calibration Unit.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Cherenkov detectors; Detector alignment and calibration methods (lasers; sources; particle-beams); Instrument optimization; Neutrino detectors

The Cherenkov Telescope Array potential for the study of young supernova remnants - Acharya, B. S.; Aramo, Carla; Babic, Ana; Barrio, J. A.; Baushev, A.; Tjus, J. Becker; Berge, D.; Bohacova, M.; Bonardi, A.; Brown, A.; Bugaev, V.; Bulik, T.; et al. (Astroparticle Physics, 2014)
Supernova remnants (SNRs) are among the most important targets for γ-ray observatories. Being prominent non-thermal sources, they are very likely responsible for the acceleration of the bulk of Galactic cosmic rays (CRs). To firmly establish the SNR paradigm for the origin of cosmic rays, it should be confirmed that protons are indeed accelerated in, and released from, SNRs with the appropriate flux and spectrum. This can be done by detailed theoretical models which account for microphysics of acceleration and various radiation processes of hadrons and leptons. The current generation of Cherenkov telescopes has insufficient sensitivity to constrain theoretical models. A new facility, the Cherenkov Telescope Array (CTA), will have superior capabilities and may finally resolve this long standing issue of high-energy astrophysics. We want to assess the capabilities of CTA to reveal the physics of various types of SNRs in the initial 2000 years of their evolution. During this time, the efficiency to accelerate cosmic rays is highest. We perform time-dependent simulations of the hydrodynamics, the magnetic fields, the cosmic-ray acceleration, and the non-thermal emission for type Ia, Ic and IIP SNRs. We calculate the CTA response to the γ-ray emission from these SNRs for various ages and distances, and we perform a realistic analysis of the simulated data. We derive distance limits for the detectability and resolvability of these SNR types at several ages. We test the ability of CTA to reconstruct their morphological and spectral parameters as a function of their distance. Finally, we estimate how well CTA data will constrain the theoretical models.
Keywords: Acceleration of particles; Gamma rays: General; ISM: Supernova remnants; Radiation mechanisms: Non-termal

The Control Unit of the KM3NeT Data Acquisition System - Aiello, S.; Ameli, F.; Domi, Alba; Kalekin, Oleg; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, G.; Ardid, M.; Aublin, J.; Bagatelas, C.; Barbarino, G.; et al. (Computer Physics Communications, 2020)
The KM3NeT Collaboration runs a multi-site neutrino observatory in the Mediterranean Sea. Water Cherenkov particle detectors, deep in the sea and far off the coasts of France and Italy, are already taking data while incremental construction progresses. Data Acquisition Control software is operating off-shore detectors as well as testing and qualification stations for their components. The software, named Control Unit, is highly modular. It can undergo upgrades and reconfiguration with the acquisition running. Interplay with the central database of the Collaboration is obtained in a way that allows for data taking even if Internet links fail. In order to simplify the management of computing resources in the long term, and to cope with possible hardware failures of one or more computers, the KM3NeT Control Unit software features a custom dynamic resource provisioning and failover technology, which is especially important for ensuring continuity in case of rare transient events in multi-messenger astronomy. The software architecture relies on ubiquitous tools and broadly adopted technologies and has been successfully tested on several operating systems.
CRIS-Team Scopus Importer:2020-06-23
Keywords: 07.05.Hd; 29.85.Ca; Astroparticle detector; Data acquisition control; KM3NeT; Neutrino detector

The cosmic ray shadow of the Moon observed with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martit, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
One of the main objectives of the ANTARES telescope is the search for point- like neutrino sources. Both the pointing accuracy and the angular resolution of the detector are important in this context and a reliableway to evaluate this performance is needed. In order to measure the pointing accuracy of the detector, one possibility is to study the shadow of the Moon, i. e. the deficit of the atmospheric muon flux from the direction of the Moon induced by the absorption of cosmic rays. Analysing the data taken between 2007 and 2016, theMoon shadow is observed with 3.5s statistical significance. The detector angular resolution for downwardgoing muons is 0.73. +/- 0.14.. The resulting pointing performance is consistent with the expectations. An independent check of the telescope pointing accuracy is realised with the data collected by a shower array detector onboard of a ship temporarily moving around the ANTARES location.

The ESCAPE Open-source Software and Service Repository - Vuillaume, Thomas; Al-Turany, Mohammad; Füßling, Matthias; Gál, Tamás; Garcia, Enrique; Graf, Kay; Hughes, Gareth; Kettenis, Mark; Kresan, Dmytro; Schnabel, Jutta; Tacke, Christian; Verkouter, Marjolein (2023)

The exceptionally powerful TeV γ-ray emitters in the Large Magellanic Cloud - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Backes, M.; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Becker-Tjus, J.; Berge, D.; et al. (Science, 2015)
The Large Magellanic Cloud, a satellite galaxy of the Milky Way, has been observed with the High Energy Stereoscopic System (H.E.S.S.) above an energy of 100 billion electron volts for a deep exposure of 210 hours. Three sources of different types were detected: the pulsar wind nebula of the most energetic pulsar known, N 157B; the radio-loud supernova remnant N 132D; and the largest nonthermal x-ray shell, the superbubble 30 Dor C. The unique object SN 1987A is, unexpectedly, not detected, which constrains the theoretical framework of particle acceleration in very young supernova remnants. These detections reveal the most energetic tip of a γ-ray source population in an external galaxy and provide via 30 Dor C the unambiguous detection of γ-ray emission from a superbubble.

THE FIRST COMBINED SEARCH for NEUTRINO POINT-SOURCES in the SOUTHERN HEMISPHERE with the ANTARES and ICECUBE NEUTRINO TELESCOPES - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Astrophysical Journal, 2016)
We present the results of searches for point-like sources of neutrinos based on the first combined analysis of data from both the ANTARES and IceCube neutrino telescopes. The combination of both detectors, which differ in size and location, forms a window in the southern sky where the sensitivity to point sources improves by up to a factor of 2 compared with individual analyses. Using data recorded by ANTARES from 2007 to 2012, and by IceCube from 2008 to 2011, we search for sources of neutrino emission both across the southern sky and from a preselected list of candidate objects. No significant excess over background has been found in these searches, and flux upper limits for the candidate sources are presented for E and E power-law spectra with different energy cut-offs.
Keywords: astroparticle physics; neutrinos

The gamma-ray spectrum of the core of Centaurus A as observed with HESS and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, Michael; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Centaurus A (Cen A) is the nearest radio galaxy discovered as a very-high-energy (VHE; 100 GeV-100 TeV) gamma-ray source by the High Energy Stereoscopic System (H.E.S.S.). It is a faint VHE gamma-ray emitter, though its VHE flux exceeds both the extrapolation from early Fermi-LAT observations as well as expectations from a (misaligned) single-zone synchrotron-self Compton (SSC) description. The latter satisfactorily reproduces the emission from Cen A at lower energies up to a few GeV. New observations with H.E.S.S., comparable in exposure time to those previously reported, were performed and eight years of Fermi-LAT data were accumulated to clarify the spectral characteristics of the gamma-ray emission from the core of Cen A. The results allow us for the first time to achieve the goal of constructing a representative, contemporaneous gamma-ray core spectrum of Cen A over almost five orders of magnitude in energy. Advanced analysis methods, including the template fitting method, allow detection in the VHE range of the core with a statistical significance of 12 sigma on the basis of 213 hours of total exposure time. The spectrum in the energy range of 250 GeV-6 TeV is compatible with a power-law function with a photon index Gamma = 2.52 +/- 0.13(stat) +/- 0.20(sys). An updated Fermi-LAT analysis provides evidence for spectral hardening by Delta Gamma similar or equal to 0.4 +/- 0.1 at gamma-ray energies above 2.8(-0.6)(+1.0) GeV at a level of 4.0 sigma. The fact that the spectrum hardens at GeV energies and extends into the VHE regime disfavour a single-zone SSC interpretation for the overall spectral energy distribution (SED) of the core and is suggestive of a new gamma-ray emitting component connecting the high-energy emission above the break energy to the one observed at VHE energies. The absence of significant variability at both GeV and TeV energies does not yet allow disentanglement of the physical nature of this component, though a jet-related origin is possible and a simple two-zone SED model fit is provided to this end.
CRIS-Team WoS Importer:2020-01-15
Keywords: Radiation mechanisms: non-thermal; Gamma rays: galaxies

The HESS Galactic plane survey - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
We present the results of the most comprehensive survey of the Galactic plane in very high-energy (VHE) gamma-rays, including a public release of Galactic sky maps, a catalog of VHE sources, and the discovery of 16 new sources of VHE gamma-rays. The High Energy Spectroscopic System (H.E.S.S.) Galactic plane survey (HGPS) was a decade-long observation program carried out by the H.E.S.S. I array of Cherenkov telescopes in Namibia from 2004 to 2013. The observations amount to nearly 2700 h of quality-selected data, covering the Galactic plane at longitudes from l = 250 degrees to 65 degrees and latitudes vertical bar b vertical bar <= 3 degrees. In addition to the unprecedented spatial coverage, the HGPS also features a relatively high angular resolution (0.08 degrees approximate to 5 arcmin mean point spread function 68% containment radius), sensitivity (less than or similar to 1.5% Crab flux for point-like sources), and energy range (0.2-100 TeV). We constructed a catalog of VHE gamma-ray sources from the HGPS data set with a systematic procedure for both source detection and characterization of morphology and spectrum. We present this likelihood-based method in detail, including the introduction of a model component to account for unresolved, large-scale emission along the Galactic plane. In total, the resulting HGPS catalog contains 78 VHE sources, of which 14 are not reanalyzed here, for example, due to their complex morphology, namely shell-like sources and the Galactic center region. Where possible, we provide a firm identification of the VHE source or plausible associations with sources in other astronomical catalogs. We also studied the characteristics of the VHE sources with source parameter distributions. 16 new sources were previously unknown or unpublished, and we individually discuss their identifications or possible associations. We firmly identified 31 sources as pulsar wind nebulae (PWNe), supernova remnants (SNRs), composite SNRs, or gamma-ray binaries. Among the 47 sources not yet identified, most of them (36) have possible associations with cataloged objects, notably PWNe and energetic pulsars that could power VHE PWNe.
Keywords: gamma rays: general; surveys; Galaxy: general

The H.E.S.S. view of the Galactic Centre region - van Eldik, Christopher (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2008)
Measurements by High Energy Stereoscopic System (H.E.S.S.) provide the first sensitive map of very-high-energy (VHE) γ-ray emission from the central few hundred parsecs of our galaxy. These observations are a valuable tool to understand the acceleration and propagation of energetic particles near the Galactic Centre (GC). The data reveal the existence of three discrete VHE γ-ray sources and the presence of diffuse γ-ray emission correlated with dense molecular clouds. The H.E.S.S. view of the GC region is reviewed, and possible counterparts of H.E.S.S. sources are discussed. © 2008 Elsevier B.V. All rights reserved.
Keywords: Galactic Centre; Gamma rays

The high-energy γ-ray emission of AP Librae - Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Anton, Gisela; Backes, Michael; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2015)
The γ-ray spectrum of the low-frequency-peaked BL Lac (LBL) object AP Librae is studied, following the discovery of very-high-energy (VHE; E > 100 GeV) γ-ray emission up to the TeV range by the H.E.S.S. experiment. This makes AP Librae one of the few VHE emitters of the LBL type. The measured spectrum yields a flux of (8.8 ± 1.5stat ± 1.8sys) × 10-12 cm-2 s-1 above 130 GeV and a spectral index of Γ = 2.65 ± 0.19stat ± 0.20sys. This study also makes use of Fermi-LAT observations in the high energy (HE, E> 100 MeV) range, providing the longest continuous light curve (5 years) ever published on this source. The source underwent a flaring event between MJD 56 306-56 376 in the HE range, with a flux increase of a factor of 3.5 in the 14 day bin light curve and no significant variation in spectral shape with respect to the low-flux state. While the H.E.S.S. and (low state) Fermi-LAT fluxes are in good agreement where they overlap, a spectral curvature between the steep VHE spectrum and the Fermi-LAT spectrum is observed. The maximum of the γ-ray emission in the spectral energy distribution is located below the GeV energy range.
Keywords: BL Lacertae objects: individual: AP Librae; Galaxies: active; Gamma rays: galaxies

The KM3NeT Open Science System - Schnabel, Jutta; Gál, Tamás; Aly, Zineb (2022)

The KM3NeT potential for the next core-collapse supernova observation with neutrinos: KM3NeT Collaboration - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ambrosone, A.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (European Physical Journal C: Particles and Fields, 2021)
The KM3NeT research infrastructure is under construction in the Mediterranean Sea. It consists of two water Cherenkov neutrino detectors, ARCA and ORCA, aimed at neutrino astrophysics and oscillation research, respectively. Instrumenting a large volume of sea water with ∼ 6200 optical modules comprising a total of ∼ 200 , 000 photomultiplier tubes, KM3NeT will achieve sensitivity to ∼10MeV neutrinos from Galactic and near-Galactic core-collapse supernovae through the observation of coincident hits in photomultipliers above the background. In this paper, the sensitivity of KM3NeT to a supernova explosion is estimated from detailed analyses of background data from the first KM3NeT detection units and simulations of the neutrino signal. The KM3NeT observational horizon (for a 5σ discovery) covers essentially the Milky-Way and for the most optimistic model, extends to the Small Magellanic Cloud (∼60kpc). Detailed studies of the time profile of the neutrino signal allow assessment of the KM3NeT capability to determine the arrival time of the neutrino burst with a few milliseconds precision for sources up to 5–8 kpc away, and detecting the peculiar signature of the standing accretion shock instability if the core-collapse supernova explosion happens closer than 3–5 kpc, depending on the progenitor mass. KM3NeT’s capability to measure the neutrino flux spectral parameters is also presented.
CRIS-Team Scopus Importer:2021-06-11

The KM3NeT Project: A km3-scale Mediterranean Neutrino Telescope - Kalekin, Oleg (Locating PeV Cosmic-Ray Accelerators: Future Detectors in Multi-TeV Gamma-Ray Astronomy, 2006)

The mDOM - A multi-PMT optical module for IceCube-Gen2 - Classen, Lew; Kappes, Alexander; Karg, Timo; Kretzschmann, Axel; Kölpin, Alexander; Lindner, Stefan; Röber, Jürgen (DPG-Verhandlungen, 2016)
Following the discovery of an astrophysical neutrino flux by IceCube in 2013, planning is under way for the next generation neutrino telescope at the South Pole, IceCube-Gen2, which will significantly enhance and expand IceCube’s sensitivity both towards high neutrino energies as well as in the low-energy regime. In the scope of these efforts, a novel multi-PMT optical sensor is being developed which, following the KM3NeT design, consists of an array of several small PMTs inside a transparent pressure vessel. This design provides some significant advantages compared to the conventional single-PMT module design, such as an increased effective area, homogeneous coverage of the full solid angle, and intrinsic angular sensitivity. The talk presents an overview of the project and its current status, featuring hardware development, testing, and simulation efforts.

The positioning system of the ANTARES Neutrino Telescope - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; et al. (Journal of Instrumentation, 2012)
The ANTARES neutrino telescope, located 40km off the coast of Toulon in the Mediterranean Sea at a mooring depth of about 2475m, consists of twelve detection lines equipped typically with 25 storeys. Every storey carries three optical modules that detect Cherenkov light induced by charged secondary particles (typically muons) coming from neutrino interactions. As these lines are flexible structures fixed to the sea bed and held taut by a buoy, sea currents cause the lines to move and the storeys to rotate. The knowledge of the position of the optical modules with a precision better than 10cm is essential for a good reconstruction of particle tracks. In this paper the ANTARES positioning system is described. It consists of an acoustic positioning system, for distance triangulation, and a compass-tiltmeter system, for the measurement of the orientation and inclination of the storeys. Necessary corrections are discussed and the results of the detector alignment procedure are described.
Keywords: Timing detectors; Detector modelling and simulations II (electric fields; charge transport; multiplication and induction; pulse formation; electron emission; etc); Detector alignment and calibration methods (lasers; sources; particle-beams); Detector control systems (detector and experiment monitoring and slow-control systems; architecture; hardware; algorithms; databases)

The prototype detection unit of the KM3NeT detector: KM3NeT Collaboration - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Androulakis, G. C.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, M.; et al. (European Physical Journal C: Particles and Fields, 2016)
A prototype detection unit of the KM3NeT deep-sea neutrino telescope has been installed at 3500m depth 80 km offshore the Italian coast. KM3NeT in its final configuration will contain several hundreds of detection units. Each detection unit is a mechanical structure anchored to the sea floor, held vertical by a submerged buoy and supporting optical modules for the detection of Cherenkov light emitted by charged secondary particles emerging from neutrino interactions. This prototype string implements three optical modules with 31 photomultiplier tubes each. These optical modules were developed by the KM3NeT Collaboration to enhance the detection capability of neutrino interactions. The prototype detection unit was operated since its deployment in May 2014 until its decommissioning in July 2015. Reconstruction of the particle trajectories from the data requires a nanosecond accuracy in the time calibration. A procedure for relative time calibration of the photomultiplier tubes contained in each optical module is described. This procedure is based on the measured coincidences produced in the sea by the ^4040K background light and can easily be expanded to a detector with several thousands of optical modules. The time offsets between the different optical modules are obtained using LED nanobeacons mounted inside them. A set of data corresponding to 600 h of livetime was analysed. The results show good agreement with Monte Carlo simulations of the expected optical background and the signal from atmospheric muons. An almost background-free sample of muons was selected by filtering the time correlated signals on all the three optical modules. The zenith angle of the selected muons was reconstructed with a precision of about 3^° ∘.

Thermo-acoustic sound generation in the interaction of pulsed proton and laser beams with a water target - Lahmann, Robert; Anton, Gisela; Graf, Kay; Hossl, J.; Kappes, Alexander; Katz, Uli; Mecke, Klaus; Schwemmer, S. (Astroparticle Physics, 2015)
The generation of hydrodynamic radiation in interactions of pulsed proton and laser beams with matter is explored. The beams were directed into a water target and the resulting acoustic signals were recorded with pressure sensitive sensors. Measurements were performed with varying pulse energies, sensor positions, beam diameters and temperatures. The obtained data are matched by simulation results based on the thermo-acoustic model with uncertainties at a level of 10%. The results imply that the primary mechanism for sound generation by the energy deposition of particles propagating in water is the local heating of the medium. The heating results in a fast expansion or contraction and a pressure pulse of bipolar shape is emitted into the surrounding medium. An interesting, widely discussed application of this effect could be the detection of ultra-high energetic cosmic neutrinos in future large-scale acoustic neutrino detectors. For this application a validation of the sound generation mechanism to high accuracy, as achieved with the experiments discussed in this article, is of high importance.
Keywords: Acoustic neutrino detection; Beam interaction; Cosmic neutrinos; Thermo-acoustic model; Ultra-high energy cosmic rays

The search for high-energy neutrinos coincident with fast radio bursts with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
In the past decade, a new class of bright transient radio sources with millisecond duration has been discovered. The origin of these so-called fast radio bursts (FRBs) is still a mystery, despite the growing observational efforts made by various multiwavelength and multimessenger facilities. To date, many models have been proposed to explain FRBs, but neither the progenitors nor the radiative and the particle acceleration processes at work have been clearly identified. In this paper, we assess whether hadronic processes may occur in the vicinity of the FRB source. If they do, FRBs may contribute to the high-energy cosmic-ray and neutrino fluxes. A search for these hadronic signatures was carried out using the ANTARES neutrino telescope. The analysis consists in looking for high-energy neutrinos, in the TeV-PeV regime, that are spatially and temporally coincident with the detected FRBs. Most of the FRBs discovered in the period 2013-2017 were in the field of view of the ANTARES detector, which is sensitive mostly to events originating from the Southern hemisphere. From this period, 12 FRBs were selected and no coincident neutrino candidate was observed. Upper limits on the per-burst neutrino fluence were derived using a power-law spectrum, dN/DE nu proportional to E-nu(-gamma), for the incoming neutrino flux, assuming spectral indexes gamma = 1.0, 2.0, 2.5. Finally, the neutrino energy was constrained by computing the total energy radiated in neutrinos, assuming different distances for the FRBs. Constraints on the neutrino fluence and on the energy released were derived from the associated null results.
Keywords: acceleration of particles; neutrinos; astroparticle physics; radio continuum: transients; methods: data analysis

The Search for Neutrinos from TXS 0506+056 with the ANTARES Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The results of three different searches for neutrino candidates, associated with the IceCube-170922A event or from the direction of TXS 0506+056, by the ANTARES neutrino telescope, are presented. The first search refers to the online follow-up of the IceCube alert; the second is based on the standard time-integrated method employed by the Collaboration to search for point-like neutrino sources; the third uses information from the IceCube time-dependent analysis that reported bursting activity centered on 2014 December 13, as input for an ANTARES time-dependent analysis. The online follow-up and the time-dependent analysis yield no events related to the source. The time-integrated study performed over a period from 2007 to 2017 fits 1.03 signal events, which corresponds to a p-value of 3.4% (not considering trial factors). Only for two other astrophysical objects in our candidate list has a smaller p-value been found. When considering that 107 sources have been investigated, the post-trial p-value for TXS 0506+056 corresponds to 87%.
Keywords: astroparticle physics; elementary particles; galaxies: active

The starburst galaxy NGC 253 revisited by H.E.S.S. and Fermi-LAT - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Context. NGC 253 is one of only two starburst galaxies found to emit gamma-rays from hundreds of MeV to multi-TeV energies. Accurate measurements of the very-high-energy (VHE; E> 100 GeV) and high-energy (HE; E > 60 MeV) spectra are crucial to study the underlying particle accelerators, probe the dominant emission mechanism(s) and to study cosmic-ray interaction and transport.
CRIS-Team WoS Importer:2020-01-15
Keywords: Astroparticle physics; Galaxies: starburst; Gamma rays: galaxies

The supernova remnant W49B as seen with HESS and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, O.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; et al. (Astronomy & Astrophysics, 2018)
The supernova remnant (SNR) W49B originated from a core-collapse supernova that occurred between one and four thousand years ago, and subsequently evolved into a mixed-morphology remnant, which is interacting with molecular clouds (MC). Gamma-ray observations of SNR-MC associations are a powerful tool to constrain the origin of Galactic cosmic rays, as they can probe the acceleration of hadrons through their interaction with the surrounding medium and subsequent emission of non-thermal photons. We report the detection of a gamma-ray source coincident with W49B at very high energies (VHE; E > 100 GeV) with the H.E.S.S. Cherenkov telescopes together with a study of the source with five years of Fermi-LAT high-energy gamma-ray (0.06-300 GeV) data. The smoothly connected, combined source spectrum, measured from 60 MeV to multi-TeV energies, shows two significant spectral breaks at 304 +/- 20 MeV and 8.4(-2.5)(+2.5) GeV; the latter is constrained by the joint fit from the two instruments. The detected spectral features are similar to those observed in several other SNR-MC associations and are found to be indicative of gamma-ray emission produced through neutral-pion decay.
Keywords: gamma rays: general; ISM: supernova remnants; ISM: clouds

The Surface Array planned for IceCube-Gen2 - Schroeder, Frank G.; Abbasi, R.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Allison, P.; Alves, A. A.; Amin, N. M.; An, R.; et al. (Proceedings of Science, 2022)
IceCube-Gen2, the extension of the IceCube Neutrino Observatory, will feature three main components: an optical array in the deep ice, a large-scale radio array in the shallow ice and firn, and a surface detector above the optical array. Thus, IceCube-Gen2 will not only be an excellent detector for PeV neutrinos, but also constitutes a unique setup for the measurement of cosmic-ray air showers, where the electromagnetic component and low-energy muons are measured at the surface and high-energy muons are measured in the ice. As for ongoing enhancement of IceCube's current surface array, IceTop, we foresee a combination of elevated scintillation and radio detectors for the Gen2 surface array, aiming at high measurement accuracy for air showers. The science goals are manifold: The in-situ measurement of the cosmic-ray flux and mass composition, as well as more thorough tests of hadronic interaction models, will improve the understanding of muons and atmospheric neutrinos detected in the ice, in particular, regarding prompt muons. Moreover, the surface array provides a cosmic-ray veto for the in-ice detector and contributes to the calibration of the optical and radio arrays. Last but not least, the surface array will make major contributions to cosmic-ray science in the energy range of the transition from Galactic to extragalactic sources. The increased sensitivities for photons and for cosmic-ray anisotropies at multi-PeV energies provide a chance to solve the puzzle of the origin of the most energetic Galactic cosmic rays and will serve IceCube's multimessenger mission.
CRIS-Team Scopus Importer:2023-08-15

The SUrvey for Pulsars and Extragalactic Radio Bursts - II. New FRB discoveries and their follow-up - Bhandari, S.; Keane, E. F.; Barr, E. D.; Jameson, A.; Petroff, E.; Johnston, Simon; Bailes, Matthew; Bhat, N. D. R.; Burgay, M.; Burke-Spolaor, S.; Caleb, M.; Eatough, R. P.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
We report the discovery of four Fast Radio Bursts (FRBs) in the ongoing SUrvey for Pulsars and Extragalactic Radio Bursts at the Parkes Radio Telescope: FRBs 150610, 151206, 151230 and 160102. Our real-time discoveries have enabled us to conduct extensive, rapid multimessenger follow-up at 12 major facilities sensitive to radio, optical, X-ray, gamma-ray photons and neutrinos on time-scales ranging from an hour to a few months post-burst. No counterparts to the FRBs were found and we provide upper limits on afterglow luminosities. None of the FRBs were seen to repeat. Formal fits to all FRBs show hints of scattering while their intrinsic widths are unresolved in time. FRB 151206 is at low Galactic latitude, FRB 151230 shows a sharp spectral cut-off, and FRB 160102 has the highest dispersion measure (DM = 2596.1 +/- 0.3 pc cm(-3)) detected to date. Three of the FRBs have high dispersion measures (DM > 1500 pc cm(-3)), favouring a scenario where the DMis dominated by contributions from the intergalactic medium. The slope of the Parkes FRB source counts distribution with fluences > 2 Jy ms is alpha = - 2.2(-1.2)(+0.6) and still consistent with a Euclidean distribution (alpha = -3/2). We also find that the all-sky rate is 1.7(-0.9)(+1.5) x 10(3)FRBs/(4 pi sr)/day above similar to 2 Jy ms and there is currently no strong evidence for a latitude- dependent FRB sky rate.
Keywords: radiation mechanisms: general; methods: data analysis; methods: observational; surveys; intergalactic medium; radio continuum: general

The Very-high-energy Open Data Format: towards a shared, open data format in very-high-energy astronomy - Khelefi, Bruno; Zanin, Roberta; Kosack, Karl; Olivera-Nieto, Laura; Schnabel, Jutta (2023)

Time calibration with atmospheric muon tracks in the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Baret, B.; Barrios-Marti, Javier; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astroparticle Physics, 2016)
The ANTARES experiment consists of an array of photomultipliers distributed along 12 lines and located deep underwater in the Mediterranean Sea. It searches for astrophysical neutrinos collecting the Cherenkov light induced by the charged particles, mainly muons, produced in neutrino interactions around the detector. Since at energies of ∼10 TeV the muon and the incident neutrino are almost collinear, it is possible to use the ANTARES detector as a neutrino telescope and identify a source of neutrinos in the sky starting from a precise reconstruction of the muon trajectory. To get this result, the arrival times of the Cherenkov photons must be accurately measured. A to perform time calibrations with the precision required to have optimal performances of the instrument is described. The reconstructed tracks of the atmospheric muons in the ANTARES detector are used to determine the relative time offsets between photomultipliers. Currently, this method is used to obtain the time calibration constants for photomultipliers on different lines at a precision level of 0.5 ns. It has also been validated for calibrating photomultipliers on the same line, using a system of LEDs and laser light devices.
Keywords: ANTARES; Atmospheric muon tracks; Neutrino Telescopes; Time calibration

Time-delay estimation in unresolved lensed quasars - Domi, Alba; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
Keywords: gravitational lensing: strong; methods: statistical; distance scale

Time-dependent absorption of very high-energy gamma-rays from the Galactic center by pair-production - Abramowski, Attila; Horns, Dieter; Gillessen, Stefan; Ripken, Joachim; van Eldik, Christopher (4th International Meeting on High Energy Gamma-Ray Astronomy, 2009)
Very high energy (VHE) gamma-rays have been detected from the direction of the Galactic center. The H.E.S.S. Cherenkov telescopes have located this γ-ray source with a preliminary position uncertainty of 8.5" per axis (6" statistic + 6" sytematic per axis). Within the uncertainty region several possible counterpart candidates exist: the Super Massive Black Hole Sgr A , the Pulsar Wind Nebula candidate G359.95-0.04, the Low Mass X-Ray Binary-system J174540.0-290031, the stellar cluster IRS 13, as well as self-annihilating dark matter. It is experimentally very challenging to further improve the positional accuracy in this energy range and therefore, it may not be possible to clearly associate one of the counterpart candidates with the VHE-source. Here, we present a new method to investigate a possible link of the VHE-source with the near environment of Sgr A (within approximately 1000 Schwarzschild radii). This method uses the time- and energy-dependent effect of absorption of VHE γ-rays by pair-production (in the following named pair-eclipse) with low-energy photons of stars closely orbiting the SMBH Sgr A . © 2009 American Institute of Physics.
Keywords: γ-rays; Absorption by pair-production; Galactic center; S-stars

Time-dependent search for neutrino emission from X-ray binaries with the ANTARES telescope - Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Journal of Cosmology and Astroparticle Physics, 2017)
ANTARES is currently the largest neutrino telescope operating in the Northern Hemisphere, aiming at the detection of high-energy neutrinos from astrophysical sources. Neutrino telescopes constantly monitor at least one complete hemisphere of the sky, and are thus well-suited to detect neutrinos produced in transient astrophysical sources. A time-dependent search has been applied to a list of 33 X-ray binaries undergoing high flaring activities in satellite data (RXTE/ASM, MAXI and Swift/BAT) and during hardness transition states in the 2008-2012 period. The background originating from interactions of charged cosmic rays in the Earth's atmosphere is drastically reduced by requiring a directional and temporal coincidence with astrophysical phenomena. The results of this search are presented together with comparisons between the neutrino flux upper limits and the neutrino flux predictions from astrophysical models. The neutrino flux upper limits resulting from this search limit the jet parameter space for some astrophysical models.
Keywords: neutrino astronomy; X-ray binaries; X-ray telescopes

Time-Integrated Neutrino Source Searches with 10 Years of IceCube Data - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Arguelles, C.; et al. (Physical Review Letters, 2020)
This Letter presents the results from pointlike neutrino source searches using ten years of IceCube data collected between April 6, 2008 and July 10, 2018. We evaluate the significance of an astrophysical signal from a pointlike source looking for an excess of clustered neutrino events with energies typically above similar to 1 TeV among the background of atmospheric muons and neutrinos. We perform a full-sky scan, a search within a selected source catalog, a catalog population study, and three stacked Galactic catalog searches.
CRIS-Team WoS Importer:2020-02-21

Time-resolved hadronic particle acceleration in the recurrent nova RS Ophiuchi - Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernloehr, K.; Bi, B.; et al. (Science, 2022)
Recurrent novae are repeating thermonuclear explosions in the outer layers of white dwarfs, due to the accretion of fresh material from a binary companion. The shock generated when ejected material slams into the companion star's wind can accelerate particles. We report very-high-energy [VHE: greater than or similar to 100 giga-electron volts] gamma rays from the recurrent nova RS Ophiuchi, up to 1 month after its 2021 outburst, observed using the High Energy Stereoscopic System (H.E.S.S.). The temporal profile of VHE emission is similar to that of lower-energy giga-electron volt emission, indicating a common origin, with a 2-day delay in peak flux. These observations constrain models of time-dependent particle energization, favoring a hadronic emission scenario over the leptonic alternative. Shocks in dense winds provide favorable environments for efficient acceleration of cosmic rays to very high energies.
CRIS-Team WoS Importer:2022-06-03

Towards a 3D likelihood analysis in very-high-energy γ-ray astronomy: The case of H.E.S.S. - Mohrmann, Lars; Nakashima, Kaori; Specovius, Andreas; Tiziani, Domenico; Funk, Stefan; van Eldik, Christopher; Ohm, Stefan (Proceedings of Science, 2019)
The estimation of the residual background due to cosmic ray-induced air showers represents a key element of every analysis of Imaging Atmospheric Cherenkov Telescope (IACT) data. In the past, most techniques have relied on a measurement of the background in supposedly source-free regions within the observed field of view. However, this approach is problematic in regions with many (potentially overlapping) γ-ray sources or large-scale diffuse γ-ray emission, like e.g. the Galactic Plane. For these cases, a template-based 3D likelihood analysis might be superior. In this approach, a spectro-morphological model template, consisting of one or multiple source components and a background component, is fit to the data, resulting in a complete spectral and spatial description of the field of view. In this contribution, we present our efforts to establish a 3D likelihood analysis for data taken with the H.E.S.S. system of IACTs, using the open-source analysis packages ctools and Gammapy. In particular, we focus on the development of a template model for the cosmic ray-induced background - a major challenge in such an approach - from archival H.E.S.S. data. We characterise the obtained model and demonstrate its application using publicly available H.E.S.S. data. The validation of this analysis approach on experimental data also constitutes an important step towards the analysis of data from the upcoming Cherenkov Telescope Array (CTA).
CRIS-Team Scopus Importer:2021-04-20

Trigger performance verification of the FlashCam prototype camera - Sailer, S.; Werner, F.; Hermann, G.; Barcelo, M.; Bauer, C.; Bernhard, S.; Biegger, M.; Canelli, F.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
FlashCam is a camera proposed for the medium-sized telescopes of the Cherenkov Telescope Array (CTA). We compare camera trigger rates obtained from measurements with the camera prototype in the laboratory and Monte Carlo simulations, when scanning the parameter space of the fully-digital trigger logic and the intensity of a continuous light source mimicking the night sky background (NSB) during on-site operation. The comparisons of the measured data results to the Monte Carlo simulations are used to verify the FlashCam trigger logic and the expected trigger performance.
CRIS-Team Scopus Importer:2019-06-25
Keywords: CTA; DAQ; Data management; FlashCam; Front end; Trigger

Ultimate precision in cosmic-ray radio detection - The SKA - Huege, Tim; Bray, Justin D.; Buitink, Stijn; Butler, David; Dallier, Richard; Ekers, Ron D.; Enßlin, Torsten; Falcke, Heino; Haungs, Andreas; James, Clancy; Martin, Lilian; Mitra, Pragati; et al. (EPJ Web of Conferences, 2017)
As of 2023, the low-frequency part of the Square Kilometre Array will go online in Australia. It will constitute the largest and most powerful low-frequency radio-astronomical observatory to date, and will facilitate a rich science programme in astronomy and astrophysics. With modest engineering changes, it will also be able to measure cosmic rays via the radio emission from extensive air showers. The extreme antenna density and the homogeneous coverage provided by more than 60,000 antennas within an area of one km2 will push radio detection of cosmic rays in the energy range around 1017 eV to ultimate precision, with superior capabilities in the reconstruction of arrival direction, energy, and an expected depth-of-shower-maximum resolution of < 10 g/cm2.
CRIS-Team Scopus Importer:2023-08-15

Understanding gravitationally induced decoherence parameters in neutrino oscillations using a microscopic quantum mechanical model - Domi, Alba; et al. (2024)
https://cris.fau.de/converis/publicweb/Publication/319602930

Upper limits from HESS active galactic nuclei observations in 2005-2007 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, Wystan; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
Aims: Very high energy (VHE; E > 100 GeV) γ-ray studies were performed for 18 active galactic nuclei (AGN) from a variety of AGN classes. Methods: VHE observations of a sample of 14 AGN, considered candidate VHE emitters, were made with the High Energy Stereoscopic System (HESS) between January 2005 and July 2007. Large-zenith-angle observations of three northern AGN (Mkn 421, Mkn 501, 1ES 1218+304), known to emit VHE γ-rays, were also performed in order to sample their spectral energy distributions (SEDs) above 1 TeV In addition, the VHE flux from 1ES 1101-232, previously detected by HESS in 2004-2005, was monitored during 2006 and 2007. Results: As significant detections from the HESS observation program are reported elsewhere, the results reported here are primarily integral flux upper limits. The average exposure for each of the 14 VHE-candidate AGN is ∼7 h live time, and the observations have an average energy threshold between 230 GeV and 590 GeV. Upper limits for these 14 AGN range from <0.9% to <4.9% of the Crab Nebula flux, and eight of these are the most constraining ever reported for the object. The brief (<2.2 h each) large-zenith-angle observations yield upper limits for Mkn 501 (<20% Crab above 2.5 TeV) and 1ES 1218+304 (<17% Crab above 1.0 TeV), and a marginal detection (3.5σ) of Mkn 421 (50% Crab above 2.1 TeV). 1ES 1101-232 was marginally detected (3.6σ, 1.7% Crab above 260 GeV) during the 2006 (13.7 h live time) observations, but not in the 2007 (4.6 h live time) data. The upper limit in 2007 (<1.9% Crab above 260 GeV) is below the average flux measured by HESS from 2004-2006. © ESO 2008.
Keywords: Galaxies: active; Gamma rays: observations

Upper limits on very-high-energy gamma-ray emission from core-collapse supernovae observed with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, Michael; Martins, V. Barbosa; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2019)
Young core-collapse supernovae with dense-wind progenitors may be able to accelerate cosmic-ray hadrons beyond the knee of the cosmic-ray spectrum, and this may result in measurable gamma-ray emission. We searched for gamma-ray emission from ten super- novae observed with the High Energy Stereoscopic System (H.E.S.S.) within a year of the supernova event. Nine supernovae were observed serendipitously in the H.E.S.S. data collected between December 2003 and December 2014, with exposure times ranging from 1.4 to 53 h. In addition we observed SN 2016adj as a target of opportunity in February 2016 for 13 h. No significant gamma-ray emission has been detected for any of the objects, and upper limits on the >1 TeV gamma-ray flux of the order of similar to 10(-13) cm(-)(2)s(-1) are established, corresponding to upper limits on the luminosities in the range similar to 2 x 10(39) to similar to 1 x 10(42) erg s(-1). These values are used to place model-dependent constraints on the mass-loss rates of the progenitor stars, implying upper limits between similar to 2 x 10(-5) and similar to 2 x 10(-3) M-circle dot yr(-1) under reasonable assumptions on the particle acceleration parameters.
CRIS-Team WoS Importer:2019-06-28

Validation of open-source science tools and background model construction in gamma-ray astronomy - Mohrmann, Lars; Specovius, Andreas; Tiziani, Domenico; Funk, Stefan; Malyshev, Dmitry; Nakashima, Kaori; van Eldik, Christopher (Astronomy & Astrophysics, 2019)
In classical analyses of gamma-ray data from imaging atmospheric Cherenkov telescopes (IACTs), such as the High Energy Stereoscopic System (H.E.S.S.), aperture photometry, or photon counting, is applied in a (typically circular) region of interest (RoI) encompassing the source. A key element in the analysis is to estimate the amount of background in the RoI due to residual cosmic ray-induced air showers in the data. Various standard background estimation techniques have been developed in the last decades, most of them rely on a measurement of the background from source-free regions within the observed field of view. However, in particular in the Galactic plane, source analysis and background estimation are hampered by the large number of, sometimes overlapping, gamma-ray sources and large-scale di ffuse gamma-ray emission. For complicated fields of view, a three-dimensional (3D) likelihood analysis shows the potential to be superior to classical analysis. In this analysis technique, a spectromorphological model, consisting of one or multiple source components and a background component, is fitted to the data, resulting in a complete spectral and spatial description of the field of view. For the application to IACT data, the major challenge of such an approach is the construction of a robust background model. In this work, we apply the 3D likelihood analysis to various test data recently made public by the H.E.S.S. collaboration, using the open analysis frameworks ctools and Gammapy. First, we show that, when using these tools in a classical analysis approach and comparing to the proprietary H.E.S.S. analysis framework, virtually identical high-level analysis results, such as field-of-view maps and spectra, are obtained. We then describe the construction of a generic background model from data of H.E.S.S. observations, and demonstrate that a 3D likelihood analysis using this background model yields high-level analysis results that are highly compatible with those obtained from the classical analyses. This validation of the 3D likelihood analysis approach on experimental data is an important step towards using this method for IACT data analysis, and in particular for the analysis of data from the upcoming Cherenkov Telescope Array (CTA).
CRIS-Team WoS Importer:2020-01-17

Velocity independent constraints on spin-dependent DM-nucleon interactions from IceCube and PICO - Aartsen, M. G.; Ackermann, M.; Adams, J.; Aguilar, J. A.; Ahlers, M.; Ahrens, M.; Alispach, C.; Andeen, K.; Anderson, T.; Ansseau, I.; Anton, Gisela; Argüelles, C.; et al. (European Physical Journal C: Particles and Fields, 2020)
Adopting the Standard Halo Model (SHM) of an isotropic Maxwellian velocity distribution for dark matter (DM) particles in the Galaxy, the most stringent current constraints on their spin-dependent scattering cross-section with nucleons come from the IceCube neutrino observatory and the PICO-60 C 3F 8 superheated bubble chamber experiments. The former is sensitive to high energy neutrinos from the self-annihilation of DM particles captured in the Sun, while the latter looks for nuclear recoil events from DM scattering off nucleons. Although slower DM particles are more likely to be captured by the Sun, the faster ones are more likely to be detected by PICO. Recent N-body simulations suggest significant deviations from the SHM for the smooth halo component of the DM, while observations hint at a dominant fraction of the local DM being in substructures. We use the method of Ferrer et al. (JCAP 1509: 052, 2015) to exploit the complementarity between the two approaches and derive conservative constraints on DM-nucleon scattering. Our results constrain σSD≲ 3 × 10 - 39cm 2 (6 × 10 - 38cm 2) at ≳ 90 % C.L. for a DM particle of mass 1 TeV annihilating into τ+τ- (bb¯) with a local density of ρDM=0.3GeV/cm3. The constraints scale inversely with ρDM and are independent of the DM velocity distribution.
CRIS-Team Scopus Importer:2020-09-18

Very High Energy γ-ray Observations of the Galactic Centre Region - van Eldik, Christopher (American Institute of Physics Conference Series, 2008)
Keywords: gamma-ray; Galactic center bar circumnuclear matter and bulge; Magnetohydrodynamics and plasmas

Very high energy gamma-ray emission from two blazars of unknown redshift and upper limits on their distance - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
We report on the detection of very high energy (VHE; E > 100 GeV) gamma-ray emission from the BL Lac objects KUV 00311-1938 and PKS 1440-389 with the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observations were accompanied or preceded by multiwavelength observations with Fermi/LAT, XRT and UVOT onboard the Swift satellite, and ATOM. Based on an extrapolation of the Fermi/LAT spectrum towards the VHE gamma-ray regime, we deduce a 95 per cent confidence level upper limit on the unknown redshift of KUV 00311-1938 of z < 0.98 and of PKS 1440-389 of z < 0.53. When combined with previous spectroscopy results, the redshift of KUV 00311-1938 is constrained to 0.51 <= z < 0.98 and of PKS 1440-389 to 0.14 (sic) z < 0.53.
CRIS-Team WoS Importer:2020-06-26

Very high energy gamma-ray observations of the galaxy clusters Abell 496 and Abell 85 with HESS - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2009)
Aims. The nearby galaxy clusters Abell 496 and Abell 85 are studied in the very high-energy (VHE, 100]]> GeV) band to investigate VHE cosmic rays (CRs) in this class of objects which are the largest gravitationally bound systems in the Universe.Methods. HESS, an array of four imaging atmospheric cherenkov telescopes (IACT), was used to observe the targets in the range of VHE gamma rays.Results. No significant gamma-ray signal is found at the respective position of the two clusters with several different source size assumptions for each target. In particular, emission regions corresponding to the high-density core, to the extension of the entire X-ray emission in these clusters, and to the very extended region where the accretion shock is expected are investigated. Upper limits are derived for the gamma-ray flux at energies 570]]> GeV for Abell 496 and 460]]> GeV for Abell 85.Conclusions. From the non-detection in VHE gamma rays, upper limits on the total energy of hadronic CRs in the clusters are calculated. If the cosmic-ray energy density follows the large-scale gas density profile, the limit on the fraction of energy in these non-thermal particles with respect to the total thermal energy of the intra-cluster medium (ICM) is 51% for Abell 496 and only 8% for Abell 85 due to its higher mass and higher gas density. These upper limits are compared with theoretical estimates. They predict about ∼10% of the thermal energy of the ICM in non-thermal particles. The observations presented here can constrain these predictions especially for the case of the Abell 85 cluster. © 2009 ESO.
Keywords: Galaxies: clusters: individual: Abell 496; Galaxies: clusters: individual: Abell 85; Gamma rays: observations

Very high energy γ-ray observations of the binary PSR B1259-63/SS2883 around the 2007 Periastron - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Bernloehr, K.; Bochow, A.; Boisson, C.; Bolmont, J.; et al. (Astronomy & Astrophysics, 2009)
Aims. This article presents very-high-energy (VHE; E > 100 GeV) data from the-ray binary PSRB1259-63 as taken during the years 2005, 2006 and before as well as shortly after the 2007 periastron passage. These data extend the knowledge of the lightcurve of this object to all phases of the 3.4 year binary orbit. The lightcurve constrains physical mechanisms present in this TeV source. Methods. Observations of VHE-rays with the HESS telescope array using the Imaging Atmospheric Cherenkov Technique were performed. The HESS instrument features an angular resolution of <0.1° and an energy resolution of <20%. Gamma-ray events in an energy range of 0.5-70 TeV were recorded. From these data, energy spectra and lightcurve with a monthly time sampling were extracted. Results. VHE-ray emission from PSRB1259-63 was detected with an overall significance of 9.5 standard deviations using 55 h of exposure, obtained from April to August 2007. The monthly flux of-rays during the observation period was measured, yielding VHE lightcurve data for the early pre-periastron phase of the system for the first time. No spectral variability was found on timescales of months. The spectrum is described by a power law with a photon index of G = 2.8 ± 0.2stat ± 0.2sys and flux normalisation F0 = (1.1 ± 0.1stat ± 0.2sys) × 10-12 TeV-1 cm-2 s-1. PSRB1259-63 was also monitored in 2005 and 2006, far from periastron passage, comprising 8.9 h and 7.5 h of exposure, respectively. No significant excess of-rays is seen in those observations. Conclusions.PSRB1259-63 has been re-confirmed as a variable TeV-ray emitter. The firm detection of VHE photons emitted at a true anomaly ? ≈-0.35 of the pulsar orbit, i.e. already 50 days prior to the periastron passage, disfavors the stellar disc target scenario as a primary emission mechanism, based on current knowledge about the companion star's disc inclination, extension, and density profile. © 2009 ESO.
Keywords: radiation mechanisms: non-thermal; methods: observational; stars: binaries: general; stars: neutron; gamma rays: observations; telescopes

VHE gamma-ray discovery and multiwavelength study of the blazar 1ES 2322-409 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
A hotspot at a position compatible with the BL. Lac object 1ES 2322-409 was serendipitously detected with H.E.S.S. during observations performed in 2004 and 2006 on the blazar PKS 2316-423. Additional data on 1ES 2322-409 were taken in 2011 and 2012, leading to a total live-time of 22.3 h. Point-like very-high-energy (VHE; E > 100 GeV) gamma-ray emission is detected from a source centred on the IFS 2322-409 position, with an excess of 116.7 events at a significance of 6.0 sigma. The average VHE gamma-ray spectrum is well described with a power law with a photon index Gamma = 3.40 +/- 0.66(stat) +/- 0.20(sys) and an integral flux Phi(E > 200 GeV) = (3.11 +/- 0.71(stat) 0.62(sys)) x 10(-2)cm(-2)s(-1), which corresponds to 1.1 per cent of the Crab nebula flux above 200 GeV. Multiwavelength data obtained with Fermi LAT, Swift XRT and UVOT, RXTE PCA, ATOM, and additional data from WISE, GROND, and Catalina are also used to characterize the broad-band non-thermal emission of lES 2322-409. The multiwavelength behaviour indicates day-scale variability. Swift UVOT and XRT data show strong variability at longer scales. A spectral energy distribution (SED) is built from contemporaneous observations obtained around a high state identified in Swift data. A modelling of the SED is performed with a stationary homogeneous one-zone synchrotronself-Compton leptonic model. The redshift of the source being unknown, two plausible values were tested for the modelling. A systematic scan of the model parameters space is performed, resulting in a well-constrained combination of values providing a good description of the broad-band behaviour of 1ES 2322-409.
CRIS-Team WoS Importer:2019-04-09
Keywords: BL Lacertae objects: individual: 1ES 2322-409; galaxies: active; gamma-rays: galaxies; Radiation mechanisms: non-thermal

VHE γ-ray emission of PKS2155-304: Spectral and temporal variability - van Eldik, Christopher; Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, W.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2010)
Context. Observations of very high-energy γ-rays from blazars provide information about acceleration mechanisms occurring in their innermost regions. Studies of variability in these objects lead to a better understanding of the mechanisms in play. Aims. To investigate the spectral and temporal variability of VHE (>100 GeV) γ-rays of the well-known high-frequency-peaked BL Lac object PKS 2155-304 with the HESS imaging atmospheric Cherenkov telescopes over a wide range of flux states. Methods. Data collected from 2005 to 2007 were analyzed. Spectra were derived on time scales ranging from 3 years to 4 min. Light curve variability was studied through doubling timescales and structure functions and compared with red noise process simulations. Results. The source was found to be in a low state from 2005 to 2007, except for a set of exceptional flares that occurred in July 2006. The quiescent state of the source is characterized by an associated mean flux level of (4.32 ± 0.09 ± 0.86) × 10 cm s above 200 GeV, or approximately 15% of the Crab Nebula, and a power-law photon index of Γ = 3.53 ± 0.06 ± 0.10. During the flares of July 2006, doubling timescales of ∼2 min are found. The spectral index variation is examined over two orders of magnitude in flux, yielding different behavior at low and high fluxes, which is a new phenomenon in VHE γ-ray emitting blazars. The variability amplitude characterized by the fractional rms F is strongly energy-dependent and is E. The light curve rms correlates with the flux. This is the signature of a multiplicative process that can be accounted for as a red noise with a Fourier index of ∼2. Conclusions. This unique data set shows evidence of a low-level γ-ray emission state from PKS 2155-304 that possibly has a different origin than the outbursts. The discovery of the light curve lognormal behavior might be an indicator of the origin of aperiodic variability in blazars. © ESO, 2010.
Keywords: BL Lacertae objects: individual: PKS 2155-304; galaxies: active; galaxies: jets; gamma rays: general

Viscoelastic properties of suspended cells measured with shear flow deformation cytometry - Gerum, Richard; Mirzahossein, Elham; Eroles, Mar; Elsterer, Jennifer; Mainka, Astrid; Bauer, Andreas; Sonntag, Selina; Winterl, Alexander; Bartl, Johannes; Fischer, Lena; Abuhattum, Shada; Goswami, Ruchi; et al. (eLife, 2022)
Numerous cell functions are accompanied by phenotypic changes in viscoelastic prop-erties, and measuring them can help elucidate higher level cellular functions in health and disease. We present a high-throughput, simple and low-cost microfluidic method for quantitatively measuring the elastic (storage) and viscous (loss) modulus of individual cells. Cells are suspended in a high-viscosity fluid and are pumped with high pressure through a 5.8 cm long and 200 µm wide microflu-idic channel. The fluid shear stress induces large, ear ellipsoidal cell deformations. In addition, the flow profile in the channel causes the cells to rotate in a tank-treading manner. From the cell deformation and tank treading frequency, we extract the frequency-dependent viscoelastic cell properties based on a theoretical framework developed by R. Roscoe [1] that describes the deformation of a viscoelastic sphere in a viscous fluid under steady laminar flow. We confirm the accuracy of the method using atomic force microscopy-calibrated polyacrylamide beads and cells. Our measurements demonstrate that suspended cells exhibit power-law, soft glassy rheological behavior that is cell-cycle-dependent and mediated by the physical interplay between the actin filament and intermediate filament networks.
CRIS-Team Scopus Importer:2022-10-28

γ/hadron separation in very-high-energy γ-ray astronomy using a multivariate analysis method - Ohm, S.; van Eldik, Christopher; Egberts, K. (Astroparticle Physics, 2009)
In recent years, Imaging Atmospheric Cherenkov Telescopes (IACTs) have discovered a rich diversity of very high energy (VHE, >100 GeV) γ-ray emitters in the sky. These instruments image Cherenkov light emitted by γ-ray induced particle cascades in the atmosphere. Background from the much more numerous cosmic-ray cascades is efficiently reduced by considering the shape of the shower images, and the capability to reduce this background is one of the key aspects that determine the sensitivity of a IACT. In this work we apply a tree classification method to data from the High Energy Stereoscopic System (H.E.S.S.). We show the stability of the method and its capabilities to yield an improved background reduction compared to the H.E.S.S. Standard Analysis. © 2009 Elsevier B.V. All rights reserve
Keywords: γ-ray astronomy; Cherenkov technique; Classification; Decision tree; Separation